Assessing orchid diversity and conservation needs in the southern Pacific of Costa Rica - Leonardo Álvarez-Alcázar; Charlotte Watteyn; María José Mata-Quirós; Adam P. Karremans; Franco Pupulin; Diego Bogarín (Journal for Nature Conservation, 2026)

Towards robust predictions of salmon lice infestation pressure in Scottish Lochs: Developing a multi-biophysical model ensemble - Meadhbh Moriarty; Soizic Garnier; Thomas P. Adams; Philip A. Gillibrand; Stevie Brain; Rory O’Hara Murray; Tim M. Szewczyk; Alejandro Gallego; Alexander G. Murray (Ecological Modelling, 2026)

Angucyclinones and N-acetyltyramine from marine Streptomyces mutabilis and their chemotaxonomic significance - Julius Adam V. Lopez; Kimberlyn F. Feguro; Shyra Marie E. Supetran; Romel Leo B. Alojado; Alecks Megxel S. Abordo; Mark B. Carascal; Roland Remenyi; Doralyn S. Dalisay; Jonel P. Saludes (Biochemical Systematics and Ecology, 2026)

Crystallization conditions of oxy-dravite and magnesio-lucchesiite tourmaline in amphibolite-hosted quartz veins at Budniki, SW Poland - Mateusz P. Sęk; Robert B. Trumbull; Adam Włodek; Michaela Vašinová Galiová; Adam Pieczka (Lithos, 2026)

Mind over distance: the food proximity effect on candy taking in a field setting and moderation by trait mindfulness in a hypothetical setting - Brian P. Meier; Adam K. Fetterman (Food Quality and Preference, 2026)

Including a perennial hay crop in a maize-soybean-wheat rotation led to increased production in subsequent grain crops - Adam P. Schreiner-McGraw; Jeffrey D. Wood; Curtis J. Ransom (Field Crops Research, 2026)

Towards robust predictions of salmon lice infestation pressure in Scottish Lochs: Biophysical model parameter sensitivity testing - Meadhbh Moriarty; Thomas P. Adams; Philip A. Gillibrand; Stevie Brain; Soizic Garnier; Rory O’Hara Murray; Tim M Szewczyk; Alexander G. Murray; Alejandro Gallego (Ecological Modelling, 2026)

Metamorphic record of the Niemcza Shear Zone, NE Bohemian Massif (SW Poland): constraints from multiple geothermobarometers and tourmaline chemistry - Dominika Wicher-Jarząb; Jacek Szczepański; Grzegorz P. Lis; Iwona Korybska-Sadło; Beata Marciniak-Maliszewska; Adam Szuszkiewicz (International Journal of Earth Sciences, 2026)

Isolating Effects of Temperature and Light on Nutrient Acquisition by Biofilm and Bryophyte Communities in Arctic Spring-Stream Ecosystems - Tori A. Hebert; Adam C. Hensley; Carla L. Atkinson; Jonathan P. Benstead; Alexander D. Huryn (Ecosystems, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Objective-specific pollen count thresholds for robust and relevant assemblages in boreal and northern temperate forests of eastern Canada - Jonathan A. Lesven; Dorian M. Gaboriau; Pierre J.H. Richard; Adam A. Ali; Hugo Asselin; Marion Blache; Martin P. Girardin; Mathis Jean-Sépet; Noé Moroy; Yves Bergeron (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Towards a Refined Definition of “tidal Influence” for the Coastal Wetland Sciences - Ken W. Krauss; Laura S. Brophy; Judith Z. Drexler; Jeffrey A. Kelleway; Janine B. Adams; Havalend E. Steinmuller; Gregory B. Noe; Michael J. Osland; Jamie A. Duberstein; Kurt P. Kowalski; Amanda L. McCutcheon; Kaileʻa M. Annandale; et al. (Wetlands, 2026)

Toward more meaningful “top–bottom” paleolimnological assessments: evaluation of a Canada-wide lacustrine sedimentation rate map using LakePulse data - Neal Michelutti; Alexandre Baud; Carsten Meyer-Jacob; Adam Jeziorski; Irene Gregory-Eaves; John P. Smol (Journal of Paleolimnology, 2026)

Carbon stocks and yields in smallholder cocoa agroforestry systems along a climatic gradient in Ghana - Raphael Manu; Munir Hoffmann; Obed Alegyisu Manu; Winston Adams Asante; Reimund P. Rötter; Issaka Abdulai (Agroforestry Systems, 2026)
Cocoa agroforestry systems are recognized for their potential to reconcile agricultural production with climate change mitigation, yet the mechanisms governing carbon storage across environmental gradients remain poorly understood. Here, we examined above- and belowground carbon stocks of cocoa and shade trees as well as soil organic carbon (SOC) in smallholder cocoa agroforestry systems across dry, intermediate (mid), and wet climatic zones in Ghana. Despite pronounced differences in shade tree density, size, and species richness, shade-tree aboveground carbon stocks (108–147 Mg C ha −1 ) as well as total farm-level carbon stocks were comparable across the climatic gradient (from dry to wet), with no negative effect on cocoa yield, signifying trade-offs in the structural characteristics of shade trees driven by management. Cocoa tree carbon and SOC stocks varied across the climatic zones but individually contributed less to ecosystem carbon stocks. Cocoa tree carbon stocks were highest in the mid climatic zone (41 Mg C ha −1 ) compared to 22 Mg C ha −1 for the dry and 27 Mg C ha −1 for the wet zone, reflecting the older cocoa tree stands and larger stem diameters of the mid zone. SOC was lower in the dry zone than in the mid and wet zones, by 23 and 27%, respectively, and mirrored the combined effects of climatic conditions and soil properties. The ratio of cocoa yield to total plant carbon increased from the dry to wet climatic zone, indicating a shift in carbon allocation toward productivity under wetter climatic conditions. Our results highlight the capacity of cocoa agroforestry systems to provide climate-mitigation benefits independent of climatic variations but with greater synergies of achieving high cocoa productivity and ecosystem carbon storage under wetter climatic conditions. Overall, these findings underscore the need for climate-specific management strategies that optimizes both carbon sequestration and cocoa productivity in West African agroforestry systems.

Systemic and hepatic responses of early-stage broilers fed diets incorporating spray-dried, extruded or pancreatin-supplemented extruded Chlorella vulgaris - Ana R. Mendes; Farimah Mohammadsadeghi; Maria P. Spínola; Daniela F.P. Carvalho; Obete Madacussengua; Cátia F. Martins; Joana I. Ferreira; Ana M. Fontes; Rui M.A. Pinto; Miguel P. Mourato; Adam J. Davis; Mohsen Afsharmanesh; et al. (Livestock Science, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Framing of ultra-processed foods in UK news media (2022–2023) and associations with quoted actors’ interests: a mixed-methods study - Jennie C Parnham; Kiara Chang; Michael Essman; Deb Smith; Mike P Etkind; Maisie McKenzie; Prisha Shah; Milica Vasiljevic; Mark Petticrew; Martin White; Anthony A Laverty; Emma Boyland; et al. (Food Policy, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Co-Producing Coastal Bird Research on the Gulf Coast through Structured Decision Making (SDM) and Constructed Value of Information (CVoI) - Jennifer L. Fuller; Nicole L. Michel; Kerry E. Grimm; Ashley A. Dayer; Evan M. Adams; Abigail J. Darrah; Auriel M. V. Fournier; Jeffrey S. Gleason; Jacquelyn K. Grace; Erik I. Johnson; Terri J. Maness; Mary Ann Ottinger; et al. (Estuaries and Coasts, 2026)
Conservation practitioners face the complex challenge of addressing global biodiversity threats within social-ecological systems with multiple jurisdictions, numerous interest groups, and changing environmental conditions. Bridging the research-to-implementation gap between scientists and managers, which integrates diverse perspectives that represent the variety of considerations impacting management outcomes can help to inform efficient and effective conservation. Avian conservation programs along the U.S. Gulf Coast exemplify these challenges, as management decisions must address diverse threats to declining coastal bird populations across large breeding, wintering, and migratory ranges while facing uncertainty surrounding the efficacy of large-scale strategies. This provides opportunities for improving management through co-produced research with structured decision making (SDM). We present a case study that demonstrates the application of co-production principles and SDM to collaboratively develop high-priority research questions informing effective avian conservation and management. Additionally, we applied a constructed value of information (CVoI) framework to identify and prioritize which uncertainties to reduce and better understand how research questions impact management actions. The integration of SDM’s five-step decision making framework ensured key principles of co-production were met, while co-production enhanced SDM outcomes by incorporating diverse perspectives and knowledge bases. CVoI further allowed participants to collectively determine final high-priority research questions in the face of complexity and uncertainty. Together, these approaches supported co-produced knowledge-generation, strategic hypothesis prioritization, and identification of research questions most likely to improve conservation decisions. This case study from the U.S. Gulf Coast demonstrates how co-produced research through SDM offers a broadly applicable approach for navigating ecological complexity and bridging the research-to-implementation gap in avian conservation.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Intensity of constructed waterbodies and commonly stocked fishes are associated with fish community changes across a river basin in the southeastern United States - Grace Davenport; Ginny L. Adams; Daniel P. Morrill; Calvin Rezac; George Gavrielides; Jennifer Main; S. Reid Adams (Hydrobiologia, 2026)

Chlorophyll-based canopy photosynthesis model: Development and global synergy analysis - Dong Li; Anatoly A. Gitelson; Adam P. Schreiner-McGraw; Ankur R. Desai; Yan Zhu; Weixing Cao; Kang Yu (Remote Sensing of Environment, 2026)

Successful treatment of low sulfate concentration metalliferous drainage using bacterial sulfate reduction in duplicate short residence time vertical flow wetlands - Adam P. Jarvis; Nick J. Cox; Hugh A.B. Potter; Catherine J. Gandy (Ecological Engineering, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Developing a GTseq panel for individual identification and evaluating application for native and transplanted Sitka black-tailed deer populations - Elise M. Stacy; Jennifer R. Adams; Tessa Hasbrouck; Stacey A. Nerkowski; Nathan R. Campbell; Anthony Crupi; Lisette P. Waits (Conservation Genetics, 2026)
Population size estimation is critical for determining sustainable harvest levels of hunted species. Spatial capture-recapture via non-invasive genetic sampling is one method employed to estimate population size and is especially useful in habitats where aerial surveys are not possible. Developments in DNA sequencing technologies have led to the application of amplicon-based genotyping-in-thousands by sequencing (GTseq) for genotyping tissue and non-invasive genetic samples. Here we developed and assessed the power of a GTseq single nucleotide polymorphism (SNP) panel for individual identification. We performed population structure and diversity analysis of Sitka black-tailed deer ( Odocoileus hemionus sitkensis ) tissue samples from native and transplanted populations in Alaska and British Columbia. We then demonstrated that we could perform individual matching on fecal pellet samples from central Southeast Alaska (CSEAK). Our panel contains 248 SNPs and has enough power for individual identification with as few as 30 loci across all sampled populations. We identified population structure aligned with island geography and translocation histories. To select panel SNPs, we sampled our initial genomic data from one island in CSEAK, resulting in ascertainment bias when applying the panel outside of CSEAK. We highlight that this ascertainment bias led to lower locus variability in populations other than CSEAK. For individual identification outside of CSEAK, we recommend subsetting the panel to only use loci that are variable for the population being studied. If intending to estimate patterns of diversity and differentiation across populations outside of CSEAK, we recommend re-designing the panel with additional range wide genomic data.

Correction to: Genetic structure in a previously extirpated population of gray wolves following reintroduction and natural recolonization - Heather R. Clendenin; David E. Ausband; Jennifer R. Adams; Paul A. Hohenlohe; Lisette P. Waits (Conservation Genetics, 2026)

Sequence analysis of a viral strain isolated for the first time in the UK, clarifies the identity of a novel species of fabavirus - Naomi Beddoe; Sam McGreig; Adrian Fox; Ian P. Adams; Alec Forsyth (Archives of Virology, 2026)
For the first time sequence data of a fabavirus was identified in dahlia from the UK, which was similar to virus sequence reported from dahlia in China. Initial sequences were determined by high-throughput sequencing (HTS) using the Illumina MiSeq platform, and were verified by Sanger sequencing and 5’ and 3’ rapid amplification of cDNA ends (RACE) polymerase chain reaction (PCR). The genome comprised two RNAs that were 5,851 nucleotide (nt) and 3,468 nt long, excluding the 3’-end poly-A tails, each RNA coded for a single polyprotein. The amino acid (aa) sequence identity percentages shared with recognised Fabavirus members over the protease-polymerase (Pro-Pol), Large Coat Protein (LCP) and combined Coat protein (CP) regions were in range with current demarcation thresholds for a distinct Secoviridae species. These sequence data analyses indicate that the fabavirus sequences identified in dahlia in both China and the UK represent a novel species in the family Secoviridae , genus Fabavirus . The name dahlia fabavirus (DFV) is proposed for this putative novel species tentatively named “ Fabavirus dahliae ”.

The AuScope National Virtual Core Library infrastructure program—from vision to implementation - C. Laukamp; S. Mulè; I. C. Lau; B. Pejcic; J. Stromberg; P. Warren; C. Adams; V. Fazio; N. Francis; A. Hunt; L. Jiang; M. LeGras; et al. (Australian Journal of Earth Sciences, 2026)

A new cetrorelix-based estrogen-free ovarian synchronization protocol for fixed-time artificial insemination in beef cattle - Getúlio M. da Silveira; Marcelo S. Fernandes; Gilson A. Pessoa; Jaswant Singh; Gregg P. Adams; Carlos E.P. Leonardi (Theriogenology, 2026)

Buffelgrass (Pennisetum ciliare) invasion is associated with reduced plant diversity and changes in carbon storage in the Sonoran Desert - R. Chelsea Nagy; Emily J. Fusco; Adam L. Mahood; Dylan P. Murphy; Jennifer K. Balch; Kimberly Franklin; Bethany A. Bradley (Journal of Arid Environments, 2026)

Pac-rophage: Teaching Macrophage Phagocytosis Through Game Play - Caroline Cvetkovic; Madison C Fanning; Ali Ansari; Trisha Patnaik; Shreya Gustafson; Divya Bendigeri; Adam P Williamson; Elise A Corbin (Biomedical Engineering Education, 2026)

Geochemical, mineralogical and particle-size controls on origin, transport and storage of sediment-associated metal(loid)s in an acid mine drainage-affected river - Elin Jennings; Patrizia Onnis; Rich Crane; William M. Mayes; Adam P. Jarvis; Karen A. Hudson-Edwards (Applied Geochemistry, 2026)

Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

A comprehensive assessment of Australia’s terrestrial invertebrate pet trade across physical and online marketplaces - Charlotte R. Lassaline; Adam Toomes; Erinn P. Fagan-Jeffries; Thomas Swearingen; Phillip Cassey (Biodiversity and Conservation, 2026)
The terrestrial invertebrate trade in Australia is both poorly researched and largely exempt from regulation, despite numerous conservation and biosecurity risks. To determine the extent and implications of this trade, we conducted systematic monitoring of domestic invertebrate sales between 2019 and 2025, spanning online and physical marketplaces. Platforms surveyed included social media groups, pet store websites, public classifieds, insect trading expositions, and pet stores across all Australian state and territory capital cities. Using a combination of automated web-scraping and manual field surveys, we recorded 12,839 advertisements involving at least 568 invertebrate species from 410 genera and 138 families, as well as 121 undescribed ‘pseudo-taxa’. Of the described species, 537 were native and 33 were non-native. Comparison with a previous Australian snapshot study revealed substantial species turnover, including new emerging taxa and species no longer observed in trade since 2020. Thirty-five advertised species are listed under the IUCN Red List, CITES, or Australia’s EPBC Act, including one Critically Endangered species ( Thersites mitchellae ) for which trade is strictly prohibited. We document a substantial diversity of species not previously reported in wildlife trade and provide the first survey to concurrently monitor trade within expositions, pet stores, the surface web, and social media. Our findings highlight the scale, diversity, and conservation significance of Australia’s terrestrial invertebrate trade, and demonstrate the need for improved monitoring and regulation to mitigate conservation and biosecurity risks.

Eddy Covariance Theory: A Review - Jeffrey D. Wood; Lianhong Gu; Adam P. Schreiner‐McGraw (Global Change Biology, 2026)
Eddy covariance (EC), the gold standard for measuring ecosystem scale gas and heat exchanges, has transformed our understanding of the breathing of the biosphere, and thus global change biology. Despite numerous methodological improvements and insights gained from the technique, the community faces persistent challenges that have been present since the first EC measurements. Here, we review the theoretical developments underpinning EC. We present theoretical developments in four important areas that have relevance to EC measurements of the net ecosystem exchanges (NEE) of gases and heat from a single tower: (i) measuring the total vertical flux density, (ii) flux attenuation, (iii) coordinate rotations, and (iv) energy balance closure. Persistent problems with EC measurements, such as the inability to close the energy budget, led us to identify two priorities for revisiting the theory underlying: (i) sensible heat flux calculations, and (ii) constraining the mean vertical wind velocity. We present a framework for improved calculation of sensible heat flux derived from first principles of fluid mechanics and thermodynamics that considers coupled heat and mass transfer so that conservation of both is obeyed. These refinements are motivated by the need for unbiased measurements of energy and mass transfer between the land surface and atmosphere for ecosystem research and to validate satellite observations and land surface models.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Target isolation and anti-proliferative potency of furocoumarin derivative from Aegle marmelos fruit pulp - Dhruv M. Barot; Dipti B. Upadhyay; Disha P. Vala; Mehul P. Parmar; Aday González-Bakker; Adam N. Khan; José M. Padrón; Hitendra M. Patel (Natural Product Research, 2026)

Sustainable phosphorus capture with PZsorb: Reducing pollution and enabling circular nutrient management - Mariam Darestani; Bijan P. Markhali; Adam Farahani; Matheus C. Duarte; Atefeh Ahmadbeigi; Deshveen Chandran; Ricky-John Spencer; David E.J. Garman; Pooja Kaur Chaggar; Kazem Javan (Journal of Water Process Engineering, 2026)

Integrated machine learning segmentation and 3D change detection for a scalable coastal cliff monitoring workflow - Connor J. Mack; Matthew Maclay; Raphael Krier-Mariani; Adam P. Young (Computers & Geosciences, 2026)

Monitoring evapotranspiration to link agricultural water use with crop yield at sub-field scales - Adam P. Schreiner-McGraw; Martha C. Anderson; Kenneth A. Sudduth; Curtis J. Ransom; Jisung G. Chang; Feng Gao (Precision Agriculture, 2026)
Purpose Scientists and producers have pursued precision agriculture to increase yields and limit environmental impacts. Applying precision agriculture concepts has not been straightforward, however, because complex interactions between soil and weather govern crop growth. We hypothesize that evapotranspiration (ET) is a single metric that captures interactions between plant status, soil, topography, and weather and can be used to predict spatial patterns in crop yield. Methods We used remotely sensed estimates of ET to calculate a normalized ET metric describing the ratio of actual to reference ET (f RET ) at a research farm located in the U.S. Corn Belt. Using the resulting 30-m resolution maps of f RET , we estimated the within-field variability in crop water stress and used machine learning techniques to relate f RET , soil, and topographic properties to crop yield. Results We show that total growing season ET is not a strong predictor of yield spatial variability ( r < 0.3), but when used to train a random forest model, f RET estimates are stronger predictors (mean R 2 = 0.6). In fact, f RET alone is better at predicting yield than any other combination of soil, topographic, and hydrologic data tested with machine learning methods. We also show that end of season yield can be predicted with just 9 weeks of f RET data which provides the opportunity to use remotely sensed ET to guide in-season site-specific management decisions. Conclusion This novel combination of earth observations and machine learning algorithms can guide sustainable intensification of agricultural systems within the context of increasing water stress.

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

The past is prologue: contemporary and historical genetic variation in a bighorn sheep metapopulation - E. Frances Cassirer; Soraia Barbosa; Kimberly R. Andrews; Nathan Borg; Jennifer R. Adams; Hollie Miyasaki; Michael S. Mitchell; Lisette P. Waits (Conservation Genetics, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

A mindfulness-based intervention to reduce altered brain reward function in cannabis use disorder: a double-blind, active and passive, randomised controlled fMRI trial - Emillie Beyer; Martine Skumlien; Govinda Poudel; Arush Honnedevasthana Arun; Eugene McTavish; Hannah Thomson; Hannah Sehl; Rebecca Segrave; Adam Clemente; Izelle Labuschagne; Peter Rendell; Gill Terrett; et al. (Psychopharmacology, 2026)
Cannabis Use Disorder (CUD) affects ~ 50 million individuals worldwide and is associated with alterations in brain reward pathways. Mindfulness-based interventions (MBIs) show promise in reducing substance use and aberrant brain function in substance use disorders (SUD), but the effects on CUD or brain reward function have not been investigated. To examine whether a 2-week MBI vs. active control (i.e., closely matched relaxation) and passive control (i.e., no intervention) affected brain reward function in CUD using the Monetary Incentive Delay fMRI task, 49 individuals with moderate-to-severe CUD were randomised to: a 2-week MBI ( n = 18), active control condition ( n = 15), or passive control condition ( n = 16), and assessed before and after the intervention. The effect of intervention-by-time was analysed using an exploratory whole-brain approach and a priori regions-of-interest approach (ROIs; ventral striatum, dorsal caudate, putamen, insula, cingulate, and orbitofrontal cortices). Whole-brain results revealed significant intervention-by-time effects. Post-MBI, there was: decreased cerebellum activity while anticipating monetary cues, increased parietal activity while receiving monetary wins, and decreased fusiform/superior frontal gyri (SFG) activity while receiving monetary wins. Post-relaxation, activity increased in several regions (i.e., hippocampus, insula, parietal cortex, fusiform, and SFG) during the receipt of monetary wins. Post-no intervention, activity increased in the cerebellum while anticipating monetary cues, and decreased in other areas (i.e., parietal cortex, hippocampus, and insula) while receiving monetary wins. There were no significant intervention-by-time effects using the ROI approach. Overall, MBI, matched relaxation, and no intervention may share changes in partially overlapping brain regions in distinct directions.

Screen time: Forward-facing sonar changes angler behavior and increases fish capture length, but decreases catch rates for smallmouth bass in a randomized controlled experiment - Maxwel V. Wilkinson; Kaden D. Ball; John D. Duvall; Adam O. Pickhardt; Bridger J. Wilson; Zachary S. Feiner; Olaf P. Jensen; Greg G. Sass (Fisheries Research, 2026)

¡Mi Vida Saludable!: Results of a Randomized, Controlled, 2 × 2 Factorial Trial of an In-Person and eHealth Diet and Physical Activity Intervention in Latina Breast Cancer Survivors - Heather Greenlee; Margarita Santiago-Torres; Isobel Contento; Pamela A. Koch; Eileen Rillamas-Sun; Heewon L. Gray; Adam M. Brickman; Ann Ogden Gaffney; Cynthia A. Thomson; Tracy E. Crane; Naxielly Dominguez; Jhack Sepulveda; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

PFAS released from the metals recovery process of the lithium-ion battery black mass - Phong H.N. Vo; Christian Vogel; Simon M. Clark; David P. Bishop; Morten Droas; Ewa Partyka-Jankowska; Michael W. Förster; Christian Adam; Vladimir Strezov; Hong T.M. Nguyen (Journal of Hazardous Materials, 2026)

Combined brine concentration and crystallization using air gap diffusion distillation for high-salinity desalination - Walter P. Parker; Jordan D. Kocher; Michael J. Adams; Taekyu Kim; Akanksha K. Menon (Desalination, 2026)

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pressures on coastal biodiversity in South Africa: a cross-realm review - LR Harris; L van Niekerk; KJ Sink; AL Skowno; SP Kirkman; JB Adams; NC James; S Lamberth; DA Lemley; P Majiedt; CF MacKay; B Newman; et al. (African Journal of Marine Science, 2026)

Sedimentation across a coastal plain to deep-water system: Insights from a Carboniferous succession, northern England - Sheng Chen; Adam D. McArthur; Luca Colombera; Nigel P. Mountney (Sedimentary Geology, 2026)

Phylogenomics of poachers (Agonidae) and the evolution of armor in cottoid fishes (Perciformes: Cottoidei) - Megan L. Vandenberg; Zach Heiple; Matthew A. Kolmann; Thaddaeus Buser; Adam P. Summers; Fernando Meléndez-Vazquez; Dahiana Arcila; Katherine P. Maslenikov; Luke Tornabene (Molecular Phylogenetics and Evolution, 2026)

Occurrence, patterns and previously overlooked sources of three veterinary ectoparasiticides in rural and urban Welsh rivers - Molly Hadley; Laura Rodwell; Matt Stewart; Daniel Crowther; Jasper Linley-Adams; Sian Craig; Suzanne Thomas; Anthony Gravell; Isabelle Durance; Ian P. Vaughan; S.J. Ormerod (Environmental Pollution, 2026)

Zebrafish parental co-exposure to environmentally relevant levels of inorganic arsenic + methylmercury impacts neurobehavior in parents and progeny - Sarah E. Rothenberg; Eric Johnson; Jane LaDu; Lindsey St. Mary; Jay C. Adams; Kate Rice; Brian P. Jackson; Robyn L. Tanguay; Lisa Truong (Environmental Toxicology and Pharmacology, 2026)

Genetic structure in a previously extirpated population of gray wolves following reintroduction and natural recolonization - Heather R. Clendenin; David E. Ausband; Jennifer R. Adams; Paul A. Hohenlohe; Lisette P. Waits (Conservation Genetics, 2026)
Genetic structuring in wildlife populations is driven by barriers that restrict gene flow as well as the history of population demography. Mechanisms driving genetic structuring can be nuanced in group-living species, such as gray wolves ( Canis lupus ). Behavioral factors, such as social affiliation and resistance, natal habitat imprinting, and trade-offs between dispersal from natal packs and territorial biding, affect habitat selection of wolves despite landscape barriers providing little resistance to their extensive dispersal capabilities. Wolves were previously extirpated from Idaho, USA, and current populations are the result of both reintroductions in 1995 and 1996 and natural dispersal from Canada. In this context we examined genetic structure of wolves in Idaho using 101 individuals genotyped at 18 nuclear DNA microsatellite loci and a subset of 38 individuals genotyped at 1019 single nucleotide polymorphism markers. We hypothesized panmictic (i.e., random mating) genetic structure in Idaho due to the long-distance dispersal abilities of gray wolves. Contrary to our hypothesis, we found three genetic clusters of gray wolves in Idaho, primarily supported by SNP markers. Microsatellite data suggested similar patterns, but permutation tests indicated these differences were not statistically significant. The extent of differentiation and evidence of gene flow, however, suggests that the three genetic clusters are not wholly isolated from one another. The distinctions between clusters spatially align with areas of reintroduction into central Idaho and Yellowstone National Park, as well ongoing natural recolonization from adjacent populations in Canada and Montana. Wolves at the periphery of analysis areas showed more admixture than those in the core, consistent with territoriality and mating behaviors contributing to genetic structuring. We demonstrate how management history, including reintroduction efforts, and animal behavior may interact and contribute to patterns of genetic structure in wild populations.

Genetic diversity and genetic structure near the range periphery of a reintroduced endemic grassland ungulate - Jeff W. Rue; Jennifer R. Adams; Jon P. Beckmann; Lisette P. Waits (Conservation Genetics, 2026)

Genome‐Wide DNA Methylation Patterns Predict Age in the Zebra Shark ( Stegostoma tigrinum ) and Provide Insight Into the Evolution of Vertebrate Aging - Samantha L. Bock; Kady Lyons; Lei Yang; Jennifer Wyffels; Lance Adams; Nienke Klerks; Aaron Jeskie; Ellen Leever; Taylor Hartl; Javier Almunia; Dan Peterson; Ana Ferreira; et al. (Molecular Ecology, 2026)
Epigenomic changes are a hallmark of aging, and DNA methylation (DNAm) has emerged as the most reliable molecular marker of an individual's age. Genome‐wide patterns of age‐associated hypo‐ and hypermethylation have been applied to generate predictive models (i.e., “epigenetic clocks”) capable of estimating chronological age in an increasingly diverse set of species including many mammals, a few birds, a reptile, and several bony fishes. Elasmobranchs (sharks, skates, and rays) are underrepresented in comparative investigations of epigenetic aging despite exhibiting exceptional life history variation, occupying a key basal position in the vertebrate phylogeny, and encompassing a large proportion of threatened species lacking accurate, non‐lethal age determination methods. Here, we characterize epigenome‐wide aging signals in the zebra shark ( Stegostoma tigrinum ), a long‐lived elasmobranch of conservation concern, from whole‐genome enzymatic methyl‐sequencing of whole blood. Using a cohort of 51 known‐age aquarium‐bred individuals, we develop several epigenetic clock models capable of predicting chronological age with a median absolute error of 1.03–1.99 years (3.32%–6.42% of lifespan) based on the methylation status of as few as ten cytosines. We further apply our models to 19 individuals of unknown age originating from the wild. By profiling the broader age‐associated methylome we demonstrate that these patterns not only predict age with high accuracy but also exhibit striking similarities in their genomic distributions to those observed in mammals pointing to conservation of the processes underlying epigenetic aging across vertebrates.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Forest structure and microclimate predict nesting activity and reproductive success of cavity-nesting Hymenoptera - Emily P. Tudor; Adam T. Cross; Sean Tomlinson (Forest Ecology and Management, 2026)

Pre- and postnatal exposure to PM2.5 and NO2 and blood pressure in children: Results from the ECHO Cohort - Yu Ni; Andrew Law; Xingyu Gao; Adam A. Szpiro; Christine T. Loftus; Miranda Jones; Logan C. Dearborn; Marnie F. Hazlehurst; Allison R. Sherris; Sindana Ilango; Kaja Z. LeWinn; Nicole R. Bush; et al. (Environmental Research, 2026)

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

A framework for designing multi-objective landscapes for conservation - Alienor L.M. Chauvenet; Anna R. Renwick; Hugh P. Possingham; Vanessa M. Adams; Jennifer McGowan; Vesna Gagić; Nancy A. Schellhorn (Biological Conservation, 2026)

Sand Source and Fertilizer Addition Effects on the Growth of Two Foundational Dune Grasses: Implications for Restoration - Teagan A. Frazier; Christine Angelini; Mary A. Schneider; Carrie R. Adams; Andrew H. Altieri; Joseph P. Morton (Estuaries and Coasts, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effect of a GnRH antagonist on the fate of the dominant ovarian follicle and the emergence of the next follicular wave in alpacas - Jaswant Singh; Miruna Munteanu; Muhammad A. Shakeel; Gregg P. Adams (Theriogenology, 2026)

Experimental survey of L-SHADE and SHADE-based adaptive differential evolution algorithms - Adam P. Piotrowski; Agnieszka E. Piotrowska; Jaroslaw J. Napiorkowski (Swarm and Evolutionary Computation, 2026)

Multivariate calibration of the agricultural policy/environmental eXtender model for field scale simulation of hydrologic and agronomic outcomes - Quinn J. Pallardy; Claire Baffaut; Adam P. Schreiner-McGraw; Kenneth A. Sudduth; Curtis J. Ransom; Lori J. Abendroth; Kristen S. Veum (Science of The Total Environment, 2026)

Uncovering UK coastal legacy wastes and their potential contaminant release risks through mineralogy and geochemistry - Patrizia Onnis; Elin Jennings; Violeta Ramos; Alex L. Riley; Catherine J. Gandy; Rich A. Crane; Ian T. Burke; Gavyn K. Rollinson; Patrick Byrne; Bryan M. Spears; Justyna P. Olszewska; Will M. Mayes; et al. (Journal of Hazardous Materials, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Patient Advocate–Trainee Engagement in Oncology Education: Insights from a Short Pilot Survey - Christina A. Simone-Soule; Sara E. Burke; Dema Abul-Enin; Charita Kunta; Adeseye Adekeye; Phuoc Tran; Amy Leader; Adam P. Dicker; Nicole L. Simone (Journal of Cancer Education, 2026)
Patient advocates represent the voice of the patient community and bring a unique perspective to research. We hypothesized that including patient advocates in research training would increase trainees ability to communicate their science, understand the impact of their work and increase their empathy for patients. An IRB-approved survey was administered to assess the impact of patient advocate feedback on trainees who presented their research via posters at our Radiation Oncology Research Symposium. Trainees reported demographics and self-assessed their use of lay language, changes in empathy, understanding the impact of their research, and potential future implications. The binomial proportion test and Fisher’s exact test were used to determine significance. The survey was completed by 80% (28/35) of trainees who participated in the poster session and interacted with patient advocates. Trainees were predominantly younger (60.7% under 30yo) and people of color (60.7%). Almost all trainees (96.4%) were comfortable talking to advocates but only 89.29% were comfortable using lay language. Trainees agreed (75%) that interacting with advocates increased their empathy. Most trainees (71.4%) believed patient advocates helped them understand the significance of their research and 64.3% believed advocates helped them develop new research ideas. Most trainees would like advocates at future poster presentations (85.7%), but did not want them to participate in study design or analysis. Gender and training level did not affect trainees’ ability to communicate in lay language, their empathy for patients, or understanding of their work’s clinical relevance. Including patient advocates in poster sessions may improve trainees ability to present their research in lay language, increase their empathy and understand the clinical impact of their research. Future radiation oncology training should consider including the patient advocate voice to improve the tangible connection between research and real-world impact.

Crude protein requirements of tropical rock lobster (Palinurus ornatus Fabricius, 1798): A factorial model - Adam Yeap; Chris G. Carter; Basseer Codabaccus; Andrea Williamson; Quinn P. Fitzgibbon; Gregory G. Smith (Aquaculture, 2026)

Exploring the fluorinome of PFAS-impacted groundwater using 21 tesla FT-ICR mass spectrometry - Wenchao Lu; Lydia Babcock-Adams; Hamidreza Sharifan; John J. Kornuc; Shilai Hao; Christopher P. Higgins; Robert B. Young; Amy M. McKenna; Jens Blotevogel (Water Research, 2026)

Pollen transport to deep-marine environments: Considerations for reconstructing past vegetation from marine sediment cores - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Anthony E. Shorrock; Martin P. Crundwell; Katharina Pank; Madison Clarke; Adam Woodhouse; Davide Gamboa; Jenni L. Hopkins; Matt S. McGlone; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A new model for quantitative analysis of kinematic properties of faults: Examples from the Jiyang Depression, NE China - Qiwei Gou; Shuping Chen; Yifan Du; Adam D. McArthur; Nigel P. Mountney; Haowei Yuan; Xi Li; Huaibo Zhao (Journal of Asian Earth Sciences, 2026)

Current and Future Approaches to Determining Amino Acid Requirements in Crustaceans - Adam Yeap; Chris G. Carter; Basseer Codabaccus; Quinn P. Fitzgibbon; Gregory G. Smith (Reviews in Aquaculture, 2026)
Nutrition is crucial in aquaculture, with feed ingredients and manufacturing being one of the largest expenditures. The effectiveness of a feed in promoting animal growth and health is dependent on ingredients with appropriate nutritional profiles. Proteins are a costly component of aquaculture feeds; moreover, dietary crude protein requirements for crustaceans can be high, sometimes exceeding 50% of the diet. As proteins are composed of amino acids, understanding species‐specific amino acid requirements is essential for developing cost‐effective, customised commercial feeds. Several methods have been used to determine crustacean amino acid requirements, each with advantages and limitations. Given the varied feeding behaviours between crustacean species, some methods may only be appropriate for certain species. In this review, we propose the Requirements by Ration Level approach as the most suitable method for developing factorial models for feed formulation. This method considers amino acid intake, retention, and loss, whilst integrating digestibility, growth, and chemical composition. It is reliable, accurate, and addresses concerns of amino acid balance changes previously raised in the literature. By using a broken convex curve model instead of a broken line model, more realistic predictions are produced, reflecting dynamic conditions and transitions towards the plateau where the amino acid requirement is met. Additionally, technological advancements have allowed complementary studies in omics, nutritional physiology, and true protein. This review highlights various methods for determining amino acid requirements and demonstrates how the Requirement by Ration Level approach can produce consistent results across experiments, reducing experimental repetition and advancing our understanding of amino acid requirements.

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Risky business: consistent breeding migration in a benthic shark despite environmental variability - Loéva Martin-Podevin; Juliette Tariel-Adam; Andrew P. Allen; Nathan Bass; Tristan Guttridge; Culum Brown (Animal Behaviour, 2025)

Stakeholders' perspectives on seagrass ecosystem services and their threats vary across Zanzibar archipelago, Tanzania - Baraka P. Nyangoko; Leonard J. Chauka; Lukas Meysick; Sven Rohde; Janine Adams; Peter J. Schupp (Regional Studies in Marine Science, 2025)

Assessing the effects of thermo-oxidation and naturally-occurring trace metal ions on the peroxidative susceptibilities of unrefined and refined sunflower oils: An 1H NMR-coupled chemometrics study - Gilbert Ampem; Adam Le Gresley; Martin Grootveld; Simon De Mars; Declan P. Naughton (Food Research International, 2025)

The effects of cadmium and high fructose diet on metabolic and reproductive health in female CD-1 mice - Victoria R. Adams; Janice A. Dye; Micheal G. Narotsky; Makala L. Moore; Helen H. Nguyen; Aubrey L. Sasser; Kaberi P. Das; Lillian F. Strader; Joseph P. Pancras; Donna Hill; Chloe Davis; Wanda C. Williams; et al. (Food and Chemical Toxicology, 2025)

First record of acid sulfate soils in a southern African Ramsar estuarine lake - Janine B. Adams; Julia Penaluna; Chuene P. Lakane; Taryn Riddin; Gavin M. Rishworth; David Turner; Lara Van Niekerk; Daniel A. Lemley (Wetlands Ecology and Management, 2025)

Rock Mass Classification and Block Volume Distribution Using the RMi Method: Masigit Cliff Rockfall Mitigation Case Study - Hasan T. Atmojo; Antonina P. Martireni; Khori Sugianti; Adam R. Ekasara; Susilowati Susilowati; Daniel Radityo; Thema Arrisaldi (Geotechnical and Geological Engineering, 2025)

A quasi-differential measurement of neutron scattering from tantalum between 0.65 MeV and 20 MeV - Gregory J. Siemers; Yaron Danon; Sukhjinder Singh; Katelyn C. Keparutis; Peter J. Brain; Benjamin H. Wang; Adam M. Daskalakis; Devin P. Barry; Michael J. Rapp; Robert C. Block (Annals of Nuclear Energy, 2025)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Assessing recovery and conservation of Australian freshwater fishes with the IUCN Green Status of Species and structured expert elicitation - Maiko L. Lutz; David G. Chapple; Molly K. Grace; Luciano B. Beheregaray; Chris J. Brauer; Iain Ellis; Adam Kerezsy; John D. Koehn; Mark Lintermans; Jarod P. Lyon; Matthew McLellan; Luke Pearce; et al. (Conservation Biology, 2025)
The International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), introduced in 2021, is a global standard of measurement used to assess the level to which a species has recovered (i.e., is viable and providing its ecological function across its entire range). It is also used to evaluate how a species has responded to past conservation actions and the expected conservation gains and recovery potential it would receive in the short‐ and long‐term future. Preliminary application of the GSS method has relied on expert knowledge from individuals or small groups of specialists. However, more accurate and reliable results are likely to be produced by formally eliciting individual judgments from a diverse range of experts, followed by discussion, reevaluation, and synthesis of these judgments. We developed a method in which 2 structured expert elicitation workshops are used to conduct GSS assessments and applied this method to 8 Australian freshwater fish species from the Murray–Darling Basin. We integrated the investigate, discuss, evaluate, aggregate protocol into the GSS methods; experts assessed the species’ IUCN Green Score (percent recovery) in the current state and for 5 other scenarios in the past and future with and without conservation. Four GSS conservation impact metrics were calculated based on the averages of expert judgments. Experts forecasted that impact in the short‐term would be minimal (i.e., conservation gain metric = zero or low) for 5 of the 8 species because targeted and maintained conservation actions are often lacking. In contrast, experts indicated long‐term recovery potential would be considerably higher if implementation of appropriate recovery activities could be sustained (all 8 species had medium or high recovery potential). We concluded that the GSS is well suited to a modified workshop approach because it aims to reduce biases associated with expert judgments and encourages valuable knowledge sharing among experts.

Chemical components of electric vehicle and internal combustion engine vehicle fire smoke and their mutagenic effects - Yong Ho Kim; Adam Nored; Gavin P. Horn; Richard M. Kesler; Adam Barowy; Alex Schraiber; Benjamin Gaudet; Alexander C. Mayer; Micah Niemeier-Walsh; Kenneth W. Fent; Kasey Kovalcik; Joseph Patrick Pancras; et al. (Environmental Science and Pollution Research, 2025)

Stable carbon isotope fractionation during the transformation of amorphous CaCO3 at low water–solid ratios: impact of humidity and temperature - Maria P. Asta; Sarah Bonilla-Correa; Aurélie Pace; Martin Dietzel; Antonio García-Alix; Torsten Vennemann; Anders Meibom; Arthur Adams (Geochimica et Cosmochimica Acta, 2025)

Shifts in suitability of pinyon-juniper communities: A climate adaptation framework for range-wide management of arid woodland resources - Adam Noel; Daniel R. Schlaepfer; Ian P. Barrett; Michael C. Duniway; Jodi Norris; Chris T. Domschke; Brad J. Butterfield; Megan C. Swan; Kim Hartwig; Michele R. Crist; John B. Bradford (Forest Ecology and Management, 2025)

Multi-physics simulation–driven assessment of environmental and cost performance in ultra-high performance concrete (UHPC) bridge deck under local climate effects - Jin Fan; Wei Huang; Hao Wang; Matthew P. Adams; Matthew J. Bandelt (Engineering Structures, 2025)

Gut microbiome signatures predict cognitive impairment in older cancer survivors - Brandi C. Miller; Jayden A. Haggler; Diptaraj S. Chaudhari; Rohit Shukla; Vivek Kumar; Sidharth P. Mishra; Michal M. Masternak; Peter Holland; Corinne Labyak; Adam Golden; Mariana Dangiolo; Andrea Y. Arikawa; et al. (GeroScience, 2025)
Cancer treatments are improving, and the population of cancer survivors is steadily increasing. However, many survivors experience long-term side effects, including chemobrain and other age-related geriatric disorders like cognitive impairment (CI), severely impacting their quality of life. Emerging studies suggest that the gut microbiome plays a central role in cognitive health. However, the long-term effects of cancer treatments on the microbiome, and how these changes impact cognitive health in survivors, remain largely unknown. Shotgun metagenomic data from 150 older adults (≥ 60 years old, including 49 cancer survivors and 101 controls) from the Microbiome in Aging Gut and Brain (MiaGB) consortium revealed that Tyzzerella , Eggerthella lenta , and Bacteroides vulgatus were specific markers of the cancer survivor gut and could differentiate cancer survivorship in this cohort. Microbiome signatures were distinct in cancer survivors with CI compared to those without and differed from those seen in non-cancer individuals with CI. Bacterial taxa including Streptococcus thermophilus and Firmicutes bacterium CAG 114 were significantly reduced in cancer survivors and strongly associated with CI. Importantly, metabolic pathway analysis revealed that microbial neurotransmitter synthesis was significantly depleted in the gut of cancer survivors, suggesting a mechanistic link to CI. Our results suggest that microbiome signatures predict cancer survivorship and the risk of CI in older adults, potentially by depleting neurotransmitter synthesis in the gut. These findings aid in establishing the role of the microbiome in predicting cancer survivorship and CI risk, which is valuable in the development of novel therapies to support the growing population of cancer survivors. Graphical Abstract

Fate of synthetic fertilizer nitrogen in a maize system depends on dairy manure type: insights from an isotopic tracing field study - Joshua P Mirabella; Adam von Haden; Gregg Sanford; Matthew Ruark; Xia Zhu-Barker (Biology and Fertility of Soils, 2025)
Understanding the fate of fertilizer nitrogen (N) in cropping systems is critical to improving agricultural sustainability and minimizing environmental losses. However, efforts to trace fertilizer N are often complicated by manure application in dairy cropping systems. We used a stable isotope tracing approach to investigate how different manure products influence the fate of synthetic fertilizer N in a Midwestern maize silage system by tracking 15 N-labled ammonium sulfate into crop biomass, soil organic matter fractions (particulate (POM) and mineral associated (MAOM)), and gaseous loss as nitrous oxide (N 2 O). Treatments included unprocessed liquid manure (LM), solid manure derived through chemical (CS) or physical (PS) separation, and a no-manure control (NM), combined with fertilizer rates of 90, 180, and 270 kg N ha −1 . Cumulative N 2 O emissions increased significantly with both manure application and higher fertilizer rates, with PS having lower emissions than LM following fertilizer application. Fertilizer contributed similar proportions to cumulative N 2 O emissions regardless of manure treatment. Total fertilizer N uptake by crops did not differ among manure treatments, but crops took up more fertilizer N at higher fertilizer application rates. Notably, application of CS and PS enhanced fertilizer N retention in the 0–15 cm soil MAOM pool compared to LM and NM. These findings highlight that although manure type does not significantly affect fertilizer N uptake by crops or fertilizer-derived N 2 O emissions, solid manures (i.e., CS and PS) can significantly increase fertilizer N retention in soils, offering potential benefits for long-term soil fertility and reduced N losses.

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Grazing halos reveal differential ecosystem vulnerabilities in vegetated habitats - Mario Minguito‐Frutos; Rohan Arthur; Jordi Boada; Candela Marco‐Méndez; Matthew P. Adams; Jordi F. Pagès; Xavier Buñuel; Albert Pessarrodona; Xavier Turon; Enric Ballesteros; Laura Tamburello; Simone Farina; et al. (Ecology, 2025)
The dynamic balance between primary production and herbivory is key to the resilience of plant‐dominated ecosystems across the world. However, many vegetated ecosystems are becoming increasingly susceptible to herbivore‐triggered collapses, as this balance is disrupted due to predator declines, increasing nutrients, and other interacting impacts of global change. Yet without accessible, cost‐effective tools to evaluate the production‐consumption relationship, it is difficult to know how close an ecosystem is to imminent overgrazing collapse. Here, we explore the effectiveness of individually formed sea urchin grazing halos as robust indicators of marine habitat vulnerability to overgrazing. Halos are grazed patches of bare rock on macrophyte‐dominated substrates that represent the balance between macrophyte production and per capita herbivore consumption. We measured 1211 halos in 31 locations across the Mediterranean Sea to characterize how plant‐herbivore interactions are mediated by endogenous (i.e., species identity, habitat type, and sea urchin size) and exogenous factors (i.e., environmental factors influencing biotic and abiotic contexts: depth, nutrients, temperature, or protection level). Our results show that halo size was effective in detecting differences in the effect of endogenous and exogenous factors on these interactions. Across locations, halo size was sensitive to differences in (i) species identity, with some species being more impactful than others; (ii) the type of habitat, with some habitats being more vulnerable than others; (iii) protection level, with halo size consistently lower inside marine protected areas; (iv) urchin size, with halo size increasing consistently with herbivore size; (v) nutrient conditions, with halo size increasing as nutrient availability decreased; as well as (vi) depth, with halo size increasing consistently with depth. These results indicate that overgrazing vulnerability is highly contingent on local ecological contexts, which strongly mediate plant‐herbivore interactions. While drivers of ecosystem collapse may be global, the ability of ecosystems to cope is often inherently local. We need locally responsive measures and contextually meaningful solutions to manage ecological integrity in the face of global change. In this context, individually measured grazing halos can be a powerful tool in assessing and managing the resilience of macrophyte ecosystems.

A triaxial in-situ stress measurement system for investigating radial variability of the vertical-to-lateral pressure ratio in grain silos - George Dyck; Adam Rogers; Michael D. Montross; Kurt Hildebrand; Aaron P. Turner; Jitendra Paliwal; Barry Farmer; Carlos A. Jarro (Computers and Electronics in Agriculture, 2025)

Speciation and leaching behaviour of inorganic contaminants in actively eroding historical coastal municipal solid waste landfills - Ian T. Burke; Patrizia Onnis; Alex L. Riley; Catherine J. Gandy; Violeta Ramos; Gavyn K. Rollinson; Patrick Byrne; Richard A. Crane; Karen A. Hudson-Edwards; Elin Jennings; William M. Mayes; J. Frederick W. Mosselmans; et al. (Marine Pollution Bulletin, 2025)

Global retrieval of canopy chlorophyll content from Sentinel-3 OLCI TOA data using a two-step upscaling method integrating physical and machine learning models - Dong Li; Holly Croft; Gregory Duveiller; Adam P. Schreiner-McGraw; Anirudh Belwalkar; Tao Cheng; Yan Zhu; Weixing Cao; Kang Yu (Remote Sensing of Environment, 2025)

Using low levels of antimicrobials and antiseptics as elicitors for environmental isolates to activate or re-activate antimicrobial producing biosynthetic gene clusters - Amy McLeman; Emma Murphy; Adam P. Roberts (Phytochemistry Letters, 2025)

Holocene environmental change in Singapore: Insights from sedimentary and foraminifera records - Yu Ting Yan; Adam D. Switzer; Stephen Chua; Kyle Morgan; Christophe Fontanier; Stephen J. Culver; Abang M.S. Nugraha; Chris Gouramanis; Yama Dixit; Benjamin P. Horton (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Dietetics and Nursing Students Affirmatively Report the Likelihood of Recommending Predominantly Plant-based Diets for Non-communicable Disease Management - P. Dyett; L. Foster-Nicholas; C. Mitchell; V. Jones-Oyefeso; V. Sealey-Tobias; A. Adams-Robinson; P. Valley-Thom; D. Balfour (Journal of the Academy of Nutrition and Dietetics, 2025)

How the choice of model calibration procedure affects projections of lake surface water temperatures for future climatic conditions - Jaroslaw J. Napiorkowski; Adam P. Piotrowski; Marzena Osuch; Senlin Zhu; Emilia Karamuz (Journal of Hydrology, 2025)

Mercury isotope constraints on artisanal and small-scale gold mining source contributions and redox cycling in the Yanomami Indigenous Territory - J. Garnier; L.A. Martin; J.E. Sonke; J. Souza; J. Quintarelli; V. Kutter; H. Roig; M.-P. Bonnet; L. Maurice; E.A.M. Adam; P. Seyler (Journal of Hazardous Materials, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

CRISPR-Cas systems in combating antimicrobial resistance: which system to choose? A systematic review - Hannay Crystynah Almeida de Souza; Pedro Panzenhagen; Ana Beatriz Portes; Anamaria M. P. dos Santos; Juliana Fidelis; Carlos Adam Conte Junior (World Journal of Microbiology and Biotechnology, 2025)

Describing Stem and Branch Morphology of Five-Year Old Sonderegger Pine - Kelsey D. Shoemaker; D. Paul Jackson; Joshua P. Adams (Forest Science, 2025)

LIBS as a tool for Li-pegmatite exploration and prospect evaluation: Soil mica and soil analysis from the Carolina Tin-Spodumene Belt - Russell S. Harmon; P. Louis Lu; Adam C. Curry; Russell M. Murray; Daniel D. Richter (Applied Geochemistry, 2025)

Genetic Assessment of the Spinner Dolphin ( Stenella longirostris ) in the Largest Offshore Sedimentary Basin in Brazil - Thaís Leal; Ana Lúcia Cypriano‐Souza; Paulo C. Simões‐Lopes; Sandro L. Bonatto; Jeremy J. Kiszka; Ruth Y. Ewing; Adam Lache; Maria C. Cartolano; Ana P. B. Costa (Marine Mammal Science, 2025)
Assessing the genetic diversity of a population is critical to evaluate its resilience in the face of anthropogenic impacts. This study aimed to assess the genetic diversity and structure of the spinner dolphins ( Stenella longirostris ) that inhabit the Santos Basin (SB), south and southeast Brazil. Analyses were conducted using seven microsatellite loci and a 686 bp fragment of the mitochondrial DNA (mtDNA) control region. The genetic relationship between SB spinner dolphins with the island‐associated spinner dolphins of Fernando de Noronha and spinner dolphins distributed in the western North Atlantic, including the Wider Caribbean region, was also investigated through a 324 bp fragment of the mtDNA control region. Results indicate that the offshore group of spinner dolphins in the SB has high genetic diversity for both mtDNA and nuclear markers. Based on mtDNA, the SB group has moderate genetic connectivity to the western North Atlantic/Wider Caribbean region spinner dolphins, but high genetic differentiation from their closest neighbors (Fernando de Noronha). These findings indicate that although SB spinner dolphins occur in an area of strong anthropogenic impacts, they present a high level of neutral genetic variation, with subtle matrilineally derived structure in the offshore (not island‐associated) waters of the western Atlantic.

Familiarity preferences in zebrafish ( Danio rerio ) depend on shoal proximity - William T. Swaney; Caitlyn Ellwood; Joshua P. Davis; Adam R. Reddon (Journal of Fish Biology, 2025)
Individuals of many species prefer to associate with familiar conspecifics from their established social group over unfamiliar conspecifics. Such familiarity preferences are thought to be adaptive and have been documented widely in many social fishes. Zebrafish ( Danio rerio ) are extensively studied, highly social fish that form stable shoals in the wild, however there is only mixed evidence for familiarity preferences in this species. Here, we test how a small variation in experimental design can influence preferences for familiar conspecifics in D. rerio by varying the distance between two stimulus shoals of fish in a shoaling choice paradigm. Individual subjects tested for their preference to shoal with familiar or unfamiliar groups of conspecifics showed a preference for familiar fish when the two shoals were 30 cm apart, but not when they were 45 or 60 cm apart. Thus, choice tests can be used to detect familiarity preferences in D. rerio , but only when alternate shoals are close together, as increased intershoal distances seemingly prevent subjects from displaying their preference. Longer distances may inhibit preference behavior due to the higher risk of crossing between shoals, alternatively subjects may be unable to reliably discern distinguishing cues of familiarity when the shoals are further apart. Our results demonstrate that while familiarity preferences exist in D. rerio , experimental test design is critical for detecting and measuring these successfully.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Variation in patterns of production and water-use efficiency among agroecosystems - Olivia L. Hajek; Nicole E. Kaplan; Shefali Azad; Philip A. Fay; Makki Khorchani; Amanda M. Nelson; Adam P. Schreiner-McGraw; Lori J. Abendroth; Claire Baffaut; John Baker; Brandon T. Bestelmeyer; Elizabeth H. Boughton; et al. (Science of The Total Environment, 2025)

Porosity and hydrous alteration of the Martian crust from InSight seismic data - Brigitte Knapmeyer-Endrun; Ludmila Adam; Sebastian Carrasco; Matthew P. Golombek; Doyeon Kim; Martin Knapmeyer; Katarina Miljković; Ana-Catalina Plesa; Nicholas H. Warner; Mark Wieczorek (Physics of the Earth and Planetary Interiors, 2025)

The development and future direction of renewable energy in Ethiopia, Kenya, Uganda, and Botswana - N. Girgibo; P. Haapalainen; L. Karita; P. Peura; G. Adam; T. Sissay; A. Worku; M. Girma; M. Einax; P. Maphane; A. Cleophas; A. Kiprop; et al. (Next Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Comparative Phylogeography of West African Rainforest Frogs Reveals Regional Variation in Refugia Dynamics - Mario Ernst; Daniel M. Portik; Gabriel H. Segniagbeto; Caleb Ofori‐Boateng; Joseph Doumbia; Johannes Penner; N'Goran G. Kouamé; Matthew K. Fujita; Adam D. Leaché; Mozes P. K. Blom; Mark‐Oliver Rödel (Molecular Ecology, 2025)
Understanding how species responded to climatic change in the past can help predict the long‐term implications of contemporary climate change. The Upper Guinean rainforests of West Africa are a global biodiversity hotspot, and it is well documented that climatic fluctuations in the Pleistocene drove the expansion and contraction of rainforest cover in this region. West African slippery frogs, genus Conraua , are rainforest specialists and present an excellent opportunity to study the effects of climate‐driven landscape changes on contemporary phylogeographic patterns and population dynamics. They exclusively inhabit rainforest streams and show little morphological or ecological disparity. We generated a population‐level dataset of genome‐wide restriction site‐associated DNA (RAD) loci for four species spread across Upper Guinea. The observed phylogeographic structure is consistent with previously postulated macro‐ and micro‐refugia. Building on these results, we used demographic modelling to trace demographic trends over time and infer population connectivity patterns. Overall, populations in topographically complex regions, like the Fouta Djallon, showed signatures of long‐term local persistence and milder changes in population size. In contrast, we found more dynamic histories of contraction and expansion in the main Upper Guinean rainforest block. Our findings provide insights into regional biodiversity patterns and show large variation in population responses to climatic fluctuations. This suggests that local environmental factors have played a key role in shaping population dynamics. Such insights are particularly relevant in relatively understudied biodiversity hotspots, such as the Upper Guinean rainforests of West Africa. Our results have implications for conservation management and prioritisation at the species, site, and ecosystem level.

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Synthesising Support for the Entrainment Hypothesis Through Spatially Explicit Life Cycles, Vagrancy and Collapse of Atlantic Tarpon ( Megalops atlanticus ) - Lucas P. Griffin; Aaron J. Adams; Jacob W. Brownscombe; Steven J. Cooke; Michael A. Dance; Susan K. Lowerre‐Barbieri; Eric S. Orbesen; Derke Snodgrass; Andy J. Danylchuk (Fish and Fisheries, 2025)
Understanding spatial dynamics and migratory behaviours of fish populations is essential for effective fisheries management. We focus on the migratory Atlantic tarpon ( Megalops atlanticus ) to explore how movement strategies and spatial life cycle patterns shape stock dynamics, contingent structure and mechanisms for collapse and recovery. The entrainment hypothesis posits that migratory routes are socially transmitted from experienced repeat spawners to younger conspecifics, resulting in distinct contingents within a population. Using a combination of literature review, life history data, mark‐and‐recapture records and electronic tagging, we evaluated five biological hypotheses related to entrainment mechanisms, habitat conservatism and phenotypic plasticity within Atlantic tarpon populations. Our findings provide evidence for migratory connectivity and the role of entrainment in shaping Atlantic tarpon contingent structure across the Western Atlantic. Movement and mark‐and‐recapture data revealed spatially discrete contingents with some intermixing, highlighting behavioural conservatism and phenotypic plasticity. Examples of vagrancy showed Atlantic tarpon caught far from their capture contingent, suggesting vagrant movements may contribute to colonising new habitats under suitable conditions. Straying by a subset of individuals may also increase the recovery and resilience of Atlantic tarpon stocks following collective memory loss in migratory routes. Research on contingent structure, larval recruitment patterns and abundance trends is needed to inform management measures to ensure the maintenance of migratory knowledge. This approach provides a framework for understanding Atlantic tarpon and other migratory marine fish stock dynamics, while underscoring the importance of coordinated management and conservation efforts across contingent boundaries.

Tree species diversity and population dynamics along the forest fragment gradient in Langol Reserve Forest, Manipur - Khumanthem Babina Devi; C. Lalruatkimi; Ahmed Abdallah Adam Mohamed; Lalthawmmawii Khawlhring; O. P. Tripathi (Vegetos, 2025)

Identifying insulinemic responses of ID horses offered varying levels of NSC and meal-sizes - B.S. Kerley; P. Harris; E. Jacquay; M. Askins; M. McClendon; A.A. Adams (Journal of Equine Veterinary Science, 2025)

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Community-based mangrove restoration following a catastrophic hurricane in The Bahamas - Justin P. Lewis; Sean T. Giery; Keith A. Rossin; Kyle A. Rossin; Jordan R. Cissell; Michael K. Steinberg; Nina L. Sanchez; Aaron J. Adams; Craig A. Layman (Wetlands Ecology and Management, 2025)
Restoration of damaged coastal ecosystems is a component of broader conservation strategies. Hurricane Dorian (September 2019) was the worst natural disaster in the history of The Bahamas. This caused widespread societal and ecological damage, including destroying mangrove ecosystems—systems that provide numerous ecosystem services for the country. We first used satellite mapping to document mangrove destruction caused by Dorian. Second, several local, national, and international partners organized to spearhead community-based mangrove planting initiatives that resulted in more than 101,560 trees planted as of December 2024. We carried out a field experiment with the plantings to examine the effects of tree age (propagule vs. seedling), spacing design (clumped vs. spaced), and plant source (The Bahamas vs. Florida). Seedling survival was 4.5 × that of propagules—but at a greater time and financial cost—indicating that a combination of planting propagules and seedlings may be a preferred restoration approach. No effect of clumped vs. spaced distribution was found. This suggests other factors, e.g., nutrient limitation or hydroperiod, drive the success of plantings. Source effects (whether propagules were collected from, and grown to seedlings in, The Bahamas or Florida) influenced seedling survival and growth and had an influence similar in magnitude to local patch-scale environmental variation. The need for ecosystem restoration following Hurricane Dorian and the willingness of more than 2,000 community individuals to contribute made possible the scale and scope of this project. These findings will help guide this community-based initiative and it will inform similar restoration efforts in other regions.

Occurrence and movement patterns of juvenile Atlantic tarpon (Megalops atlanticus) in the Península de Guanahacabibes Biosphere Reserve, Cuba - Zenaida María Navarro-Martínez; Dorka Cobián-Rojas; Lucas P. Griffin; Alejandro Camejo-Vergara; Aaron J. Adams; Andy J. Danylchuk; Jorge Angulo-Valdés (Environmental Biology of Fishes, 2025)

Effects of recreational disturbance history on female Trinidadian guppies’ responses to chemical predation cues - Alix J. P. Brusseau; Félixe Dumaresq-Synnott; Jade Morris; Abigail C. Nagl; Adam L. Crane; Grant E. Brown (Environmental Biology of Fishes, 2025)

Resting Supine for 45 Minutes Yields Consistent Baseline Lumbar Intervertebral Disc Height in Asymptomatic Participants - Nicole E. Zimmer; James A. Coppock; Andrzej S. Kosinski; Charles E. Spritzer; Adam P. Goode; Louis E. DeFrate (Annals of Biomedical Engineering, 2025)

Prairie stream nutrient stoichiometry across space and time: Influence of discharge, season, and crop type - Amy B. White; Robert B. Brua; Kristin J. Painter; Helen P. Jarvie; Adam G. Yates (Limnology and Oceanography, 2025)
Stream water nutrient ratios are often influenced by flow variation and landscape characteristics. However, the influence of these drivers on total and dissolved nutrient ratios remains understudied, especially in prairie ecosystems where hydrologic connectivity between soils and streams exhibits substantial spatial and seasonal variability. Here, we ask how hydrology and land cover drive patterns of nitrogen (N), phosphorus (P), and N : P ratios across streams and rivers draining northern prairie ecosystems. To answer this, we compiled nutrient concentration data for tributaries of the Red River, Manitoba, Canada, to assess seasonal and annual variation in nutrient ratios, as well as the relationship between crop cover, discharge, and ratios, over 1‐yr, 10‐yr, and 30‐yr time spans. Total nitrogen : total phosphorus ratios were near the Redfield mass ratio (N/P = 7.23) across 24 streams in the Red River Valley. By comparison, dissolved inorganic nitrogen : total dissolved phosphorus ratios in these streams were N depleted and generally declined from spring through to autumn. The types of crops grown did not appear to be a consistent influence on nutrient ratios in streams throughout the region. In contrast, stream flows strongly influenced spring and summer nutrient ratios in four tributaries over a 30‐yr period. Specifically, increasing stream flow tended to decrease TN : TP and DIN : TDP in the two eastern tributaries but increase DIN : TDP in the western tributaries. Our findings that nutrient ratios in prairie streams are impacted by seasonality and fluctuating hydrologic conditions suggest that nutrient ratios in Red River tributaries may be impacted by future climate change.

Multi-omics reveal microbial succession and metabolomic adaptations to flood in a hypersaline coastal lagoon - Christopher Keneally; Daniel Chilton; Tyler N. Dornan; Stephen P. Kidd; Virginie Gaget; Adam Toomes; Charlotte Lassaline; Reuben Petrovski; Lisa Wood; Justin D. Brookes (Water Research, 2025)

Fish consumption advice is depriving children of neurolipids and other nutrients essential to brain and eye development - Philip Spiller; J. Thomas Brenna; Susan E. Carlson; Jean Golding; Michael A. Crawford; Joseph R. Hibbeln; Berthold V. Koletzko; John Columbo; Penny Kris-Etherton; Sonja L. Connor; Clark Carrington; P. Michael Bolger; et al. (NeuroToxicology, 2025)

Hazard of coastal cliff top failure through time - Zuzanna M. Swirad; Adam P. Young (Geomorphology, 2025)

Exploring the influence of seed bacteria and fungi on seed germination and seedling traits in Brachypodium congeners - Alicia J. Foxx; Sveinn V. Einarsson; Karla P. Franco Meléndez; Adam R. Rivers (Symbiosis, 2025)
Seed microbiomes represent the first colonization of the plant by microbes and influence community assembly of subsequent microbes. The role that parental genotype and species of origin play in structuring and sourcing the seed microbiome is crucial to understanding the seed microbiome and patterns in microbiome variation. Seed-borne microbes become part of the seedling microbiome and have the potential to influence seedling traits and whether variation in seedling traits can be explained by seed fungal and bacterial microbiome characteristics is important to improving our ability to predict seedling-microbiome trait responses a priori for application. Unfortunately, the relationship between seedling traits or germination response and seed microbiome characteristics have only been quantitatively linked in one study to our knowledge. So, here we grew individuals of a wild collection of the annual grass, Brachypodium distachyon and inbred lines of a congener, Brachypodium hybridum . We grew plants in a greenhouse for seed production and used high throughput amplicon sequencing to characterize offspring seed microbiome. We also characterized the growth of sibling seedlings to those sequenced. We found that for only one of the eight traits evaluated, seed germination during cold stratification, the abundance of the most prevalent microbial families had a marginal positive influence on whether germination happened during cold stratification ( R 2 = 0.29, p = 0.07). These results critically show that seed microbiomes are strongly influenced by parental genotype and species and seed microbiomes may have diminishing influences on seed and seedling traits. Thus, more work is needed to realize the goal of microbiome-trait prediction.

Isolation and characterisation of a native cyanobacteria for a microalgal consortium producing PHAs in agrifood residues - Sergio Serrano-Blanco; Marc-Antoine Cimon; Thi Thanh Ha Pham; Adam P. Harvey; Simon Barnabé; Sharon B. Velasquez-Orta (Algal Research, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Rapid Ocean Warming Drives Sexually Divergent Habitat Use in a Threatened Predatory Marine Ectotherm - Lucy R. Mead; Adam Piper; David Jiménez Alvarado; Eva Meyers; Joanna Barker; Hector Toledo‐Padilla; Edy Herraiz; Alberto F. Campoamor; Michael Sealey; Maria Belén Caro; Tomàs Bañeras; Charlotte Pike; et al. (Global Change Biology, 2025)
Climate change poses one of the greatest threats to marine ecosystems worldwide, altering physical, chemical, and biological processes at unprecedented rates. Severe impacts on marine species and habitats have been extensively documented, with shifts in phenology, spatial distribution, and migratory behaviour increasingly pervasive. However, there is a lack of species‐specific data examining responses and adaptation to rapid warming and environmental extremes, especially for marine ectotherms. In this study, we investigate the broad‐scale environmental drivers of distribution in a Critically Endangered ectothermic marine predator, the angelshark Squatina squatina , and report on a behavioural anomaly observed in 2022. Between 2018 and 2023, 112 adult S. squatina were tracked using acoustic telemetry in La Graciosa Marine Reserve in the Canary Islands. Relationships between seasonal presence of S. squatina and remotely sensed environmental parameters were examined with Boosted Regression Tree and Generalised Additive Modelling. Major sex differences were found, with female sharks strongly influenced by environmental conditions and particularly sensitive to temperature, with a possible upper thermal threshold close to 22.5°C. Peak sea surface temperature in the study area increased from 22.99°C to 23.81°C, and the number of days above 22.5°C nearly tripled. Absence of females during the 2022 breeding season coincided with widespread thermal anomalies across the Northeast Atlantic Ocean, with unusually high temperatures persisting later into the year. We conclude that this potentially disrupted seasonal thermal cues for S. squatina movement, leading to sexually divergent habitat use. Given the warming projected for this region, thermal thresholds may increasingly be exceeded, and key areas may become inhospitable for female S. squatina , which is of huge concern for this already highly threatened species. These findings highlight the urgency of identifying species‐specific environmental tolerances and incorporating these into conservation so that management remains ecologically relevant in a rapidly warming ocean.

Decoupling of temperature and growth of white spruce at western treeline, Alaska, is unrelated to intrinsic water stress - Amy E. Miller; Adam Z. Csank; Michael P. Hannam; Rosemary L. Sherriff; Steven W. Leavitt (Ecology, 2025)
Late 20th century warming has weakened the relationship between temperature and growth in northern forests. This loss of sensitivity to temperature, often attributed to drought stress in warmer regions of the boreal forest, has also been observed in cool, mesic environments, where warming‐related growth declines are poorly understood. We used annually resolved ring‐width and carbon stable isotope (δ 13 C) chronologies from white spruce forest and woodland stands in southwest Alaska to examine tree responses to climate during a recent warming period (1970–2011). Trends in ring‐width index (RWI) varied by stand type: RWI increased in forests and woodlands in the first half of the record (1970–1990), but only woodlands continued that trend in the latter half (1991–2011). Warmer spring temperatures predicted increased RWI in both stand types, and warmer summer temperatures predicted decreased RWI in forests, but these relationships weakened through time. Carbon isotope discrimination (Δ 13 C), a frequent indicator of stomatal regulation of water loss, showed no coherent trend in either stand type but was positively associated with summer precipitation in forests, suggesting the potential for intermittent water limitation. Our results indicate that RWI and Δ 13 C have responded differently to climate through time and that these responses have been mediated by stand type.

Rapid repetitive syllable sounds associate with episodic memory, executive function, and working memory in cognitively healthy and subjectively impaired older adults - Julia Giffard; Renjie Li; Eddy Roccati; Adam P. Vogel; Aidan D. Bindoff; Lynette R. Goldberg; Quan Bai; Jane Alty (GeroScience, 2025)
Non-invasive screening tools for Alzheimer’s disease (AD) risk are needed. Decline in episodic memory and subjective cognitive impairment (SCI) are both associated with elevated AD risk. We investigated associations between three cognitive domains (episodic memory, executive function, and working memory) and motor speech performance in older adults with healthy cognition (HC) or SCI. In total, 1014 community-dwelling participants (cross-sectional sample: 843 HC, mean 66.9 years, 72.8% female; 171 SCI, mean 66.3 years, 70.8% female) remotely completed cognitive tests (Paired Associates Learning and Spatial Working Memory from the Cambridge Neuropsychological Test Automated Battery) and motor speech tests (Tasmanian [TAS] Test). We evaluated whether acoustic motor speech features extracted from 10-s tests of “pa,” “ta,” or “ka” syllable repetition improved episodic memory, executive function, and working memory regression models over age, sex, education, anxiety, and depression (ΔAIC > 2). Motor speech features improved estimation of cognitive scores over fixed demographic and clinical variables in each group and cognitive domain. In summary, we found associations between motor speech performance and cognition in older adults. Short motor speech tests demonstrate potential for non-invasive, cost-effective AD risk screening. Longitudinal research is needed to investigate relationships between individual motor speech features and cognitive changes confirmed to result from the progression of AD.

Proteoglycan-4 (PRG4) serum concentration is lower in aged mice, and genetic deficiency impacts survival probability, blood parameters, and bone during aging - Adam P. Tanguay; Nikhil G. Menon; Emma Slavin; Mikayla Moody; Erin McEwen; Gregory D. Jay; Joseph Lorenzo; Jenna M. Bartley; Vanessa M. Scanlon; Alix C. Deymier; Tannin A. Schmidt (GeroScience, 2025)

Cryptic species, biogeography, and patterns of introgression in the fish genus Mogurnda (Eleotridae) from the Australian wet tropics: A purple patch for purple-spots - Samuel R. Amini; Mark Adams; Michael P. Hammer; Glenn Briggs; James A. Donaldson; Brendan C. Ebner; Peter J. Unmack (Molecular Phylogenetics and Evolution, 2025)

Altered cytokine release of airway epithelial cells in vitro by combinations of respiratory syncytial virus, Streptococcus pneumoniae, Printex 90 and diesel exhaust particles - Marcia M. Oldenburger; Raiza Hasrat; Axel A. Bonacic Marinovic; Eric R. Gremmer; Edwin P. Zwart; Gabriel Goderski; Geraly Duijm; Debby Bogaert; Adam Meijer; Arno Swart; Flemming R. Cassee; Gerco den Hartog; et al. (Environmental Research, 2025)

Acidifying surface water and water level management promote Sphagnum health for peatland restoration and paludiculture - Adam H.W. Koks; Sannimari A. Käärmelahti; Ralph J.M. Temmink; Alfons J.P. Smolders; Bas P. van de Riet; Leon P.M. Lamers; Roy C.J.H. Peters; Christian Fritz; Gijs van Dijk (Ecological Engineering, 2025)

Complementarity and integration of animal and in vitro non-animal pre-clinical model systems– an Australian perspective - Ruth M. Arkell; Ernst J. Wolvetang; Twishi Gulati; James E. Hennessy; Adam P. Hill; Thierry Jardé; Andrew J. Kueh; Paul Q. Thomas; Louise N. Winteringham; Michael S. Dobbie (Mammalian Genome, 2025)

Tree swallow (Tachycineta bicolor) demographics and metal(loid) concentrations in egg contents from the Kootenai River basin, Montana nest box colonies - Brian C. Balmer; Joseph P. Skorupa; Katherine B. Adams; Bridger M. Creel; Gregory C. Hoffman; Megan A. Fylling; Stephanie Le; Jacob M. Martin; Theresa L. McBride; Jacob T. Williams; Travis S. Schmidt (Environmental Monitoring and Assessment, 2025)

Pathogenicity and molecular characterization of bacteria isolates at postharvest storage of Ibadan sweet, Valencia, and Washington navel citrus fruits - Adams Abdul-Rahaman; Simon V. Irtwange; Kortse P. Aloho; Ajar Nath Yadav; Bashir Barau (Vegetos, 2025)

Staying hooked: effective science engagement and communication in recreational fisheries - Pablo Pita; Sean Tracey; Robert Arlinghaus; Eneko Bachiller; Filipa Pinho-Duarte; Keno Ferter; Filipe Henriques; Samantha Hook; Kieran Hyder; Alejo Irigoyen; María P. Jiménez; Martín Laporta; et al. (Frontiers in Marine Science, 2025)
● This abstract summarizes the results of two expert consultations conducted to gather insights into effective communication and engagement strategies in recreational fisheries. ● Effective science communication fosters knowledge, understanding, and trust in both science and management decisions. ● Public involvement and stakeholder engagement are essential for effective management. ● Simplifying complex research findings and using diverse communication tools enhance awareness and understanding. ● Strong communication strategies are necessary to implement sustainable recreational fisheries management frameworks. ● Funding for communication efforts is often insufficient but remains crucial for success. ● Participatory workshops and data-sharing arrangements enhance collaboration and involvement. ● Multi-stakeholder consortiums and tailored communication strategies strengthen stakeholder engagement and promote adaptive governance. Interdisciplinary outreach and strategic social media use play vital roles in raising environmental awareness.

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

Influence of extended photoperiod using blue light masks on hypertrichosis, coat condition, and general health parameters in horses with pituitary pars intermedia dysfunction - S. Parmantier; P. Kyriazopoulou; M. McClendon; A. Adams; B.A. Murphy (Journal of Equine Veterinary Science, 2025)

Insulinemic responses to long-stem forage hay in horses with insulin dysregulation (ID) - M. Askins; P. Harris; M. McClendon; A. Adams (Journal of Equine Veterinary Science, 2025)

What acoustic telemetry can and cannot tell us about fish biology - David M. P. Jacoby; Adam T. Piper (Journal of Fish Biology, 2025)
Acoustic telemetry (AT) has become ubiquitous in aquatic monitoring and fish biology, conservation, and management. Since the early use of active ultrasonic tracking that required researchers to follow at a distance their species of interest, the field has diversified considerably, with exciting advances in both hydrophone and transmitter technology. Once a highly specialized methodology, however, AT is fast becoming a generalist tool for those wishing to study or conserve fishes, leading to diversifying application by non‐specialists. With this transition in mind, we evaluate exactly what AT has become useful for, discussing how the technological and analytical advances around AT can address important questions within fish biology. In doing so, we highlight the key ecological and applied research areas where AT continues to reveal crucial new insights and, in particular, when combined with complimentary research approaches. We provide a comprehensive breakdown of the state of the art for applications of AT, discussing the ongoing challenges, where its strengths lie, and how future developments may revolutionize fisheries management, behavioral ecology and species protection. Through selected papers we illustrate specific applications across the broad spectrum of fish biology. By bringing together the recent and future developments in this field under categories designed to broadly capture many aspects of fish biology, we hope to offer a useful guide for the non‐specialist practitioner as they attempt to navigate the dizzying array of considerations and ongoing developments within this diverse toolkit.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Role of Forest Carbon Change in Shaping Future Land Use and Land Cover Change - Meng Luo; Xin Zhao; Dalei Hao; Ben Bond‐Lamberty; Adam Daigneault; Pralit L. Patel; Sian Kou‐Giesbrecht; Christopher P. O. Reyer; Hamid Dashti; Min Chen (Global Change Biology, 2025)
Global change, particularly the changes in atmospheric CO 2 concentration, climatic variables, and nitrogen deposition, has been widely recognized and examined to have worldwide impacts on forest carbon. However, its influence on forest area required to meet the demand for timber and carbon storage and subsequent land use and land cover change (LULCC) is rarely studied. This study explores the role of global change‐driven forest carbon change in shaping future global LULCC projections and investigates underlying drivers. We incorporated the global change impacts on forest carbon from the Canadian Land Surface Scheme Including Biogeochemical Cycles model simulations (driven by meteorological forcing projections from two Earth system models [ESMs]) into the Global Change Analysis Model, under three combinations of shared socioeconomic pathways and representative concentration pathways (SSP126, SSP370, and SSP585). Including forest carbon change decreases the projected expansion of managed forest and managed pasture, reduces the loss of unmanaged pastures and forests, and provides more cropland. The relative change in managed forest by 2100 is −4.0%, −21.7%, and −31.9%, under SSP126, SSP370, and SSP585, respectively, when forest carbon change is considered. CO 2 fertilization is the dominant driver, increasing forest vegetation and soil carbon by 37% and 4.1%, and leading to 78.6% of the total area with a change in land use types by 2100 under SSP585. In comparison, climate change reduces forest vegetation and soil carbon by −3.5% and −0.8%, influencing 23.9% of the total area with a change in land use types by 2100 under SSP585, while nitrogen deposition has minor impacts. Using meteorological forcing data from two ESMs leads to similar impacts of forest carbon change on LULCC in terms of sign and trend but different magnitudes. This study highlights the large impact of forest carbon change on shaping future LULCC dynamics and the critical role of CO 2 fertilization.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Phytoplankton responses to reduced freshwater inflow and acid conditions in a Ramsar estuarine lake - Chuene P. Lakane; Janine B. Adams; Daniel A. Lemley (Marine Environmental Research, 2025)

Where giants roam: The importance of remote islands and seamount corridors to adult tiger sharks in the South Pacific Ocean - Jordan K. Matley; Lauren Meyer; Adam Barnett; Mark Scott; Elizabeth A. Dinsdale; Michael P. Doane; David Harasti; Lisa A. Hoopes; Charlie Huveneers (Marine Environmental Research, 2025)

First application of high-resolution X-ray computed tomography to quantify the fossil record of foraminifera: The Nicola bed, Monte San Nicola, Sicily; type area for the Quaternary System - Wiesława Radmacher; Martin J. Head; Grzegorz P. Kaczmarczyk; Mateusz Mikołajczak; Adam Włodek; Anna Spadło; Daniel Wałach; Alfred Uchman; Antonio Caruso (Marine and Petroleum Geology, 2025)

A generalised sigmoid population growth model with energy dependence: Application to quantify the tipping point for Antarctic shallow seabed algae - Elise Mills; Graeme F. Clark; Matthew J. Simpson; Mark Baird; Matthew P. Adams (Environmental Modelling & Software, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Spatial variability of metal(loid) leaching from coastal colliery wastes under freshwater and saline water conditions - Catherine J. Gandy; Ian T. Burke; Patrick Byrne; Nick Cooper; Richard A. Crane; Karen A. Hudson-Edwards; William M. Mayes; Patrizia Onnis; Alex L. Riley; Adam P. Jarvis (Journal of Environmental Management, 2025)

Groundwater storage loss in the central valley analysis using a novel method based on in situ data compared to GRACE-derived data - Michael D. Stevens; Saul G. Ramirez; Eva-Marie H. Martin; Norman L. Jones; Gustavious P. Williams; Kyra H. Adams; Daniel P. Ames; Sarva T. Pulla (Environmental Modelling & Software, 2025)

Metaheuristics should be tested on large benchmark set with various numbers of function evaluations - Adam P. Piotrowski; Jaroslaw J. Napiorkowski; Agnieszka E. Piotrowska (Swarm and Evolutionary Computation, 2025)

Spatial and temporal (annual and decadal) trends of metal(loid) concentrations and loads in an acid mine drainage-affected river - Elin Jennings; Patrizia Onnis; Rich Crane; Sean D.W. Comber; Patrick Byrne; Alex L. Riley; William M. Mayes; Adam P. Jarvis; Karen A. Hudson-Edwards (Science of The Total Environment, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Creek System and Regional Patterns of Juncus roemerianus Stress and Links to Salt Marsh Loss on the Florida Gulf Coast - Stephanie A. Verhulst; Matthew P. Conlin; Peter N. Adams; Carrie Reinhardt Adams (Wetlands, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Synchrotron X-ray Fluorescence Microscopy Reveals Trace Elemental Indicators of Life History in Marsupial Teeth - William M. G. Parker; Justin W. Adams; David P. Hocking; Erich M. G. Fitzgerald; Geoff Shaw; Marilyn B. Renfree; Alistair R. Evans (Biological Trace Element Research, 2025)
As teeth develop, their mineralised composition is a bio-recorder of diet, environment, and growth. High-resolution elemental mapping provides a tool to reveal records of life history within teeth. The relative concentrations of a range of trace elements change between in utero development, birth, and weaning in eutherian mammals. Marsupials, however, have a different mode of development: altricial birth and growth within the pouch facilitated by compositional transitions in milk. How these differences alter patterns of elemental mineralisation and become recorded in marsupial teeth is previously unknown. This study analyses the distribution of calcium (major element), zinc (actively incorporated trace element), and strontium (passively incorporated trace element) in the teeth of five species of diprotodontian marsupial using synchrotron X-ray fluorescence microscopy. We find that the diprotodontian lower incisor concatenates elemental variation from across the molariform dentition, preserving a prolonged record of life history in four of the five species. Patterns of elemental incorporation in enamel, dentine, and cementum are presented, with Ca, Zn, and Sr having differing distributions. Zn accretion indicates a role in mineralisation and/or prevention of tooth degradation. Zn also demarcates incremental cementum lines. Sr is shown to be passively incorporated into marsupial teeth, with increasing Sr concentration in milk recorded in dental tissues formed contemporaneously. Older individuals have oscillatory signals in Sr that appear linked to seasonality. These findings highlight some similarities between eutherian and marsupial trace element incorporation, particularly in the distribution of Zn. Sr signals in marsupial teeth record key aspects of life history.

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

Evolution of rimmed carbonate platform architecture controlled by sea-level change: Insights from the Lower-Middle Cambrian of the Northern Tarim Basin, China - Qing He; Kaibo Shi; Yongsheng Ma; Bo Liu; Jun Han; Jun Li; Xiangyu Bai; Chun Wu; Adam D. McArthur; Nigel P. Mountney (Marine and Petroleum Geology, 2025)

Exploring environmental and managerial impacts of crude oil volatility on QUAD financial markets: Insights into dynamic connectedness - Miklesh Prasad Yadav; Neha Puri; Parul Bhatia; Adam P. Shore (Journal of Environmental Management, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

A non‐monophyly of ‘crowned’ Daphnia ( Ctenodaphnia ) Dybowski et Grochowski, 1895 (Cladocera: Daphniidae): From genomes to morphology - Dmitry D. Pereboev; Petr G. Garibian; Dmitry P. Karabanov; Boris D. Efeykin; Yan R. Galimov; Adam Petrusek; Alexey A. Kotov (Zoologica Scripta, 2025)
Daphnia (Crustacea: Cladocera) has been frequently used as a model taxon for studying prey antipredator defences. Among numerous representatives of this genus, there are several taxa within the subgenus Daphnia ( Ctenodaphnia ) with a morphological innovation unique for these cladocerans, a head plate. In some populations, the margin of this anterior projection of carapace into the head shield is adorned with a remarkable ‘crown of thorns’, which has been shown to be an antipredator adaptation against tadpole shrimps (Notostraca). This structure is phenotypically plastic, dependent on the presence of these omnivorous crustaceans in the respective water bodies. We aimed to evaluate the monophyly of Eurasian ‘crowned’ Daphnia species (i.e., those forming the ‘crown of thorns’ under some circumstance) based on genomic phylogenies and morphology. For this study, we have individually sequenced the genomes of five daphniids, four representing taxa able to form ‘crowns’ (two specimens of different clades of the D . ( C .) atkinsoni complex and two specimens of D . ( C .) triquetra from distant populations), and D . ( C .) mediterranea distantly related to D . ( C .) atkinsoni that lacks the head plate. We analysed them along with genomes obtained from GenBank, focusing on either full mitochondrial or partial nuclear datasets (BUSCO). Our main hypothesis on a monophyly of all ‘crowned’ daphnids was rejected. Genomic analyses confirmed existence of two independent lineages able to express this phenotypic trait in the Palaearctic: (1) a monophyletic D . ( C .) atkinsoni s. lat. and (2) D . ( C .) triquetra , formally redescribed here. These lineages form a well‐supported clade together with several other species lacking a head plate (including D . ( C .) mediterranea ). Genomic analyses indicate that D . ( C .) atkinsoni s. lat. is closely related to D . ( C .) tibetana ; mitochondrial markers also suggest a close relationship of D . ( D .) triquetra with D . ( C .) studeri , both D . ( C .) tibetana and D . ( C .) studeri , are lacking this morphological feature. Molecular clock estimated the time of the differentiation of the major clade containing both ‘crowned Daphnia ’ to the Late Mesozoic, confirming an antiquity of the head plate as antipredator defence.

Foliar N Content Parallels Increasing Aridity in a Mediterranean‐Saharan Transition Zone: Evidence From Regional and Global Trends - Tomasz P. Wyka; Piotr Robakowski; Angel Romo; Adam Boratyński; Roma Żytkowiak; Jacek Oleksyn (Journal of Biogeography, 2025)
Aim Warm deserts are characterised by water shortages and high temperature extremes. A commonly reported adaptive strategy in such environments is maximisation of photosynthetic capacity, which allows plants to achieve positive carbon budgets by taking advantage of short periods of water availability and non‐inhibitory temperatures. Considering the well‐supported interspecific covariation between photosynthetic capacity and leaf N concentration, we tested the hypothesis that environmental aridity is related to an elevated leaf nitrogen content. Location 53 locations in the transitional zone spanning the Mediterranean and the Sahara Desert in Morocco. The mean maximal temperature ( T max ) within the area varied between 35.7°C and 43.5°C, and the mean annual precipitation (MAP) was between 12 and 246 mm. Taxon 225 vascular species representative of local vegetation. Methods Leaf samples were collected along a regional aridity gradient and preserved in herbarium presses. The leaf mass per area (LMA) and N concentrations expressed on leaf mass ( N mass ) and area ( N area ) basis were determined. We also obtained LMA and N mass values for 6711 species from a worldwide database for comparative analysis. Results Significant increases in mean LMA, N mass and N area accompanied the increase in T max and the decrease in MAP in woody species and in non‐graminoid herbs, but not in graminoids. Considering the overall aridity of our sampling area, we compared the N mass values of Moroccan plants with those from a worldwide database. We found that at a common LMA, the Moroccan plants showed on average elevated N mass relative to global values. Main Conclusions These two lines of evidence: regional gradient and global comparison confirm that hot deserts select for high leaf N content. This result suggests the direction of natural selection that will accompany future climate warming and habitat aridification.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Forest structure and tree diversity along an altitudinal gradient in Sikkim Himalaya - Mamta Chettri; Uttam Kumar Sahoo; Devendra Kumar; Faisal Ismail Musa; Ahmed Abdallah Adam Mohamed; Lalrempuii Hrahsel; P. C. Vanlalhluna (Vegetos, 2024)

A comparison of visual and molecular methods for inferring biological communities in aquaculture enriched sediments - Impact assessment and cost-benefit analysis - Alexander Coutts; Danielle Zimmermann; Adam Davey; John P. Bowman; Donald J. Ross; Elisabeth M.A. Strain (Marine Pollution Bulletin, 2024)

High-precision 40Ar/39Ar dating of Australasian tektites associated with bifacial tools in the Bose Basin (Xiaomei and Fengshudao sites), South China and in Vietnam (Go Da and Roc Tung 1 sites) - Véronique Michel; Fred Jourdan; Marie-Hélène Moncel; Bernard Gratuze; Guanjun Shen; Wei Wang; Celia Mayers; Adam Frew; Dominique Cauche; Patricia Valensi; Sylvain Gallet; Anatoly P. Derevianko; et al. (Quaternary Science Reviews, 2024)

Long-term coastal dynamics: The evolution of a mixed sediment mega-nourishment consisting of colliery spoil - Sebastian J. Pitman; Ian T. Burke; Helen Jay; Nick Cooper; William M. Mayes; Adam P. Jarvis (Journal of Environmental Management, 2024)

Oxygen isotope fractionation during amorphous to crystalline calcium carbonate transformation at varying relative humidity and temperature - Maria P. Asta; Sarah Bonilla-Correa; Aurélie Pace; Martin Dietzel; Antonio García-Alix; Torsten Vennemann; Anders Meibom; Arthur Adams (Geochimica et Cosmochimica Acta, 2024)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

PLMC: Language Model of Protein Sequences Enhances Protein Crystallization Prediction - Dapeng Xiong; Kaicheng U; Jianfeng Sun; Adam P. Cribbs (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Climate Change and the Emergence of No‐Analog Forest Assemblages in North America - Andrew V. Gougherty; Anantha M. Prasad; Matthew P. Peters; Stephen N. Matthews; Bryce T. Adams (Global Change Biology, 2024)
Future climate change is expected to result in tree species shifting their geographic distributions in ways that could reorganize species into assemblages with no contemporary analog. These projected no‐analog forests raise concern as their ecological function could similarly shift, which may challenge established conservation and management efforts. Here, we implement a community‐level modelling approach to identify the key climatic and topographic drivers of forest composition in North America, and then use these models to predict the distribution of “disappearing” and “novel” forest assemblages in future climate. We applied this modelling technique to both the taxonomic and phylogenetic composition of forest trees, to identify where species turnover may be greatest, and whether species are likely to be replaced with close relatives. Our work shows that approximately 11.9% of contemporary North American forests have low predicted similarity to future forests, and 26.2% of future forests could be compositionally novel compared with contemporary forests, but there was substantial geographic variability in the magnitude of these metrics across the continent. High‐elevation regions in the west tend to be nearest to their closest compositional analog, suggesting these regions may be most likely to realize the future predicted composition. This work provides a new approach to understanding how forest composition may shift in future climates in a way that avoids the need for individual species predictions and extends climate‐matching approaches with meaningful biological data.

Tide–surge interaction observed at Singapore and the east coast of Peninsular Malaysia using a semi-empirical model - Zhi Yang Koh; Benjamin S. Grandey; Dhrubajyoti Samanta; Adam D. Switzer; Benjamin P. Horton; Justin Dauwels; Lock Yue Chew (Ocean Science, 2024)
Tide–surge interaction plays a substantial role in determining the characteristics of coastal water levels over shallow regions. We study the tide–surge interaction observed at seven tide gauges along Singapore and the east coast of Peninsular Malaysia, focusing on the timing of extreme non-tidal residuals relative to tidal high water. We propose a modified statistical framework using a no-tide–surge interaction (no-TSI) null distribution that accounts for asymmetry and variation in the duration of tidal cycles. We find that our modified framework can mitigate false-positive signals of tide–surge interaction in this region. We find evidence of tide–surge interaction at all seven locations, with characteristics varying smoothly along the coastline: the highest non-tidal residuals are found to occur most frequently before tidal high water in the south, both before and after tidal high water in the central region, and after tidal high water in the north. We also propose a semi-empirical model to investigate the effects of tidal-phase alteration, which is one mechanism of tide–surge interaction. Results of our semi-empirical model reveal that tidal-phase alteration caused by storm surges is substantial enough to generate significant change in the timing of extreme non-tidal residuals. To mitigate the effect of tidal-phase alteration on return level estimation, skew surge can be used. We conclude that (1) tide–surge interaction influences coastal water levels in this region, (2) our semi-empirical model provides insight into the mechanism of tidal-phase alteration, and (3) our no-TSI distribution should be used for similar studies globally.

Effects of storage-handling methods on nutrient analysis of fresh-forage samples - B.S. Kerley; P. Harris; K. Lea; M. McClendon; A.A. Adams (Journal of Equine Veterinary Science, 2024)

Intensified microalgae production and development of microbial communities on suspended carriers and municipal wastewater - Sergio Serrano-Blanco; Rixia Zan; Adam P. Harvey; Sharon B. Velasquez-Orta (Journal of Environmental Management, 2024)

The Current State of Biotransformation Science – Industry Survey of In Vitro and In Vivo Practices, Clinical Translation, and Future Trends - John P. Savaryn; Kevin Coe; Matthew A. Cerny; Kevin Colizza; Patricia Moliner; Lloyd King; Bin Ma; Jim Atherton; Adam Auclair; Mark T. Cancilla; Marsha Eno; Ulrik Jurva; et al. (Pharmaceutical Research, 2024)

Activity patterns of Octopus tetricus (Mollusca: Cephalopoda) and their behavioural responses to fisheries trap and bait combinations - Adam A. Vrandich; Brendan P. Kelaher; Karina C. Hall (Marine Biology, 2024)
An understanding of octopus behaviour and their capture by fishing gears is required to inform efficient, sustainable, and ethical octopus fisheries. Here, the behaviour of Octopus tetricus was assessed in response to different bait and trap combinations in an outdoor mesocosm experiment. Eight wild octopuses were collected, maintained in individual tanks with flow-through seawater and aeration, and monitored with a 24-h video surveillance system. Six different traps and four different baits were presented to each octopus in various combinations during four sequential trials. Fine-mesh crab traps were the most successful in capturing octopus, accounting for 23 of the total 30 captures across all trials. Whereas solid trigger traps produced the greatest number of other interactions (e.g., octopus sitting on trap/in the entrance), averaging 43 interactions per trial, but were rarely triggered. Bait type did not influence octopus capture, trap interaction frequency, or octopus activity; however, only artificial bait types were trialled, and fresh natural baits may elicit a stronger response and should be investigated in future research. Generally, octopus were inactive, dedicating only 9.5% of their total time to active behaviours. Octopus activity varied with time of day, with peak activity during morning daylight (0800–1200) and the lowest activity during the dark hours of the very early morning (0000–0400). Additionally, capture numbers, trap interactions, and activity varied among individuals, with bolder personalities in some octopus. This natural variation among individual octopuses may lead to fishery-induced selection associated with the elevated capture frequency of bold or more active individuals.

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Neurocognitive correlates of cerebral mitochondrial function and energy metabolism using phosphorus magnetic resonance spectroscopy in older adults - Francesca V. Lopez; Andrew O’Shea; Zhiguang Huo; Steven T. DeKosky; Theodore P. Trouard; Gene E. Alexander; Adam J. Woods; Dawn Bowers (GeroScience, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Enhancing resilience: Integrating future flood modeling and socio-economic analysis in the face of climate change impacts - Natalie P. Memarsadeghi; Sebastian Rowan; Adam W. Sisco; Ahmad A. Tavakoly (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evolutionary relationships and fine-scale geographic structuring in the temperate percichthyid genus Gadopsis (blackfishes) to support fisheries and conservation management - Matthew A. Campbell; Michael P. Hammer; Mark Adams; Tarmo A. Raadik; Peter J. Unmack (Molecular Phylogenetics and Evolution, 2024)

Production of high velocity micron-sized ice particles using the NASA Ames Vertical Gun Range for application to missions to icy moons. - R. Bonaccorsi; D. Willson; R. Gold; E. Adams; A. Ricca; C.J. Cornelison; J.-P. Wiens; D. Zheng; A.J. Perez; C.P. McKay (Icarus, 2024)

Sustainable reinforced concrete design: The role of ultra-high performance concrete (UHPC) in life-cycle structural performance and environmental impacts - Jin Fan; Yi Shao; Matthew J. Bandelt; Matthew P. Adams; Claudia P. Ostertag (Engineering Structures, 2024)

A new Neu—a syngeneic model of spontaneously metastatic HER2-positive breast cancer - Aaron G. Baugh; Edgar Gonzalez; Valerie H. Narumi; Jesse Kreger; Yingtong Liu; Christine Rafie; Sofi Castanon; Julie Jang; Luciane T. Kagohara; Dimitra P. Anastasiadou; James Leatherman; Todd Armstrong; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic disease results from the dissemination of tumor cells beyond their organ of origin to grow in distant organs and is the primary cause of death in patients with advanced breast cancer. Preclinical murine models in which primary tumors spontaneously metastasize are valuable tools for studying metastatic progression and novel cancer treatment combinations. Here, we characterize a novel syngeneic murine breast tumor cell line that provides a model of spontaneously metastatic neu-expressing breast cancer with quicker onset of widespread metastases after orthotopic mammary implantation in immune-competent NeuN mice. The NT2.5-lung metastasis (-LM) cell line was derived from serial passaging of tumor cells that were macro-dissected from spontaneous lung metastases after orthotopic mammary implantation of parental NT2.5 cells. Within one week of NT2.5-LM implantation, metastases are observed in the lungs. Within four weeks, metastases are also observed in the bones, spleen, colon, and liver. We demonstrate that NT2.5-LM metastases are positive for NeuN—the murine equivalent of human epidermal growth factor 2 (HER2). We further demonstrate altered expression of markers of epithelial-to-mesenchymal transition (EMT), suggestive of their enhanced metastatic potential. Genomic analyses support these findings and reveal enrichment in EMT-regulating pathways. In addition, the metastases are rapidly growing, proliferative, and responsive to HER2-directed therapy. The new NT2.5-LM model provides certain advantages over the parental NT2/NT2.5 model, given its more rapid and spontaneous development of metastases. Besides investigating mechanisms of metastatic progression, this new model may be used for the rationalized development of novel therapeutic interventions and assessment of therapeutic responses.

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Functional correlation tensors in brain white matter and the effects of normal aging - Lyuan Xu; Yurui Gao; Muwei Li; Richard Lawless; Yu Zhao; Kurt G. Schilling; Baxter P. Rogers; Adam W. Anderson; Zhaohua Ding; Bennett A. Landman; John C. Gore (Brain Imaging and Behavior, 2024)
Resting state correlations between blood oxygenation level dependent (BOLD) MRI signals from voxels in white matter (WM) are demonstrably anisotropic, so that functional correlation tensors (FCT) may be used to quantify the underlying microstructure of BOLD effects in WM tracts. However, the overall spatial distribution of FCTs and their metrics in specific populations has not yet been established, and the factors that affect their precise arrangements remain unclear. Changes in WM occur with normal aging, and these may be expected to affect FCTs. We hypothesized that FCTs exhibit a characteristic spatial pattern and may show systematic changes with aging or other factors. Here we report our analyses of the FCT characteristics of fMRI images of a large cohort of 461 cognitively normal subjects (190 females, 271 males) sourced from the Open Access Series of Imaging Studies (OASIS), with age distributions of 42 y/o – 95 y/o. Group averages and statistics of FCT indices, including axial functional correlations, radial functional correlations, mean functional correlations and fractional anisotropy, were quantified in WM bundles defined by the JHU ICBM-DTI-81 WM atlas. In addition, their variations with normal aging were examined. The results revealed a dimorphic distribution of changes in FCT metrics with age, with decreases of the functional correlations in some regions and increases in others. Supplementary analysis revealed that females exhibited significant age effects on a greater number of WM areas, but the interaction between age and sex was not significant. The findings demonstrate the reproducibility of the spatial distribution of FCT metrics and reveal subtle regional changes with age.

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Drivers of seasonal water hyacinth dynamics in permanently eutrophic estuarine waters - Chuene P. Lakane; Janine B. Adams; Daniel A. Lemley (Biological Invasions, 2024)
Anthropogenic nutrient enrichment is one of the key global change pressures threatening the health of estuaries. This is evident at the persistently eutrophic Swartkops Estuary located along the warm temperate coast of South Africa. Augmented nutrient-rich baseflows (e.g., stormwater runoff, wastewater treatment work discharges) have resulted in the persistent growth of invasive alien aquatic plants (IAAPs), particularly water hyacinth ( Pontederia crassipes ), in the upper estuarine reaches. As such, the objective of this study was to investigate the temporal population dynamics of water hyacinth in the Swartkops Estuary to inform management options. Methods included five-weekly sampling campaigns in winter, spring, and summer, interspersed with monthly sampling over a year-long period. Physico-chemical variables and river inflow were measured in situ, while samples were collected for inorganic nutrients, phytoplankton biomass, and IAAP measurements (cover, biomass, and tissue nutrients). Model results indicated that increased water temperature and inorganic nitrogen (ammonium and NO x ) levels promoted increased coverage of water hyacinth, while seasonal analysis highlighted reduced ( p

First report of carnation Italian ringspot virus in Gypsophila in the United Kingdom - G. Webster; L. Frew; R. Ward; A. R. Fowkes; A. Skelton; V. Harju; I. P. Adams; S. McGreig; H. Pufal; C. Conyers; A. Fox (Journal of Plant Pathology, 2024)

Meta‐analytical evidence for frequency‐dependent selection across the tree of life - Miguel Gómez‐Llano; Ronald D. Bassar; Erik I. Svensson; Simon P. Tye; Adam M. Siepielski (Ecology Letters, 2024)
Explaining the maintenance of genetic variation in fitness‐related traits within populations is a fundamental challenge in ecology and evolutionary biology. Frequency‐dependent selection (FDS) is one mechanism that can maintain such variation, especially when selection favours rare variants (negative FDS). However, our general knowledge about the occurrence of FDS, its strength and direction remain fragmented, limiting general inferences about this important evolutionary process. We systematically reviewed the published literature on FDS and assembled a database of 747 effect sizes from 101 studies to analyse the occurrence, strength, and direction of FDS, and the factors that could explain heterogeneity in FDS. Using a meta‐analysis, we found that overall, FDS is more commonly negative, although not significantly when accounting for phylogeny. An analysis of absolute values of effect sizes, however, revealed the widespread occurrence of modest FDS. However, negative FDS was only significant in laboratory experiments and non‐significant in mesocosms and field‐based studies. Moreover, negative FDS was stronger in studies measuring fecundity and involving resource competition over studies using other fitness components or focused on other ecological interactions. Our study unveils key general patterns of FDS and points in future promising research directions that can help us understand a long‐standing fundamental problem in evolutionary biology and its consequences for demography and ecological dynamics.

No association between markers of systemic inflammation and endothelial dysfunction with Alzheimer’s disease progression: a longitudinal study - Arne van Setten; Jeroen F. Uleman; René J. F. Melis; Brian Lawlor; Niels P. Riksen; Jurgen A. H. R. Claassen; Rianne A. A. de Heus; Ricardo Segurado; Sean Kennelly; Marcel G. M. Olde Rikkert; Robert Howard; Florence Pasquier; et al. (GeroScience, 2024)
Introduction Systemic inflammation and endothelial dysfunction are potentially modifiable factors implicated in Alzheimer’s disease (AD), which offer potential therapeutic targets to slow disease progression. Methods We investigated the relationship between baseline circulating levels of inflammatory (TNF-α, IL-1ß) and endothelial cell markers (VCAM-1, ICAM-1, E-selectin) and 18-month cognitive decline (ADAS-cog12) in 266 mild-to-moderate AD patients from the NILVAD study. We employed individual growth models to examine associations, potential mediation, and interaction effects while adjusting for confounders. Results The average increase in ADAS-cog12 scores over all patients was 8.1 points in 18 months. No significant association was found between the markers and the rate of cognitive decline. Mediation analysis revealed no mediating role for endothelial cell markers, and interaction effects were not observed. Discussion Our results do not support the role of systemic inflammation or endothelial dysfunction in progression in persons with AD.

Coding genome of a novel potyvirus, hogweed virus Y (HogVY) - Daisy Furrokh; Sam McGreig; Ian P. Adams; Ben Barrett; Aimee Fowkes; Anna Skelton; Adrian Fox; Ines Vazquez-Iglesias (Journal of Plant Pathology, 2024)

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Milk production in pottery. Evidence for various exploited resources used by the first farmers in Central Pyrenees using the morphological, chemical and stable carbon isotopic composition of organic residues from ceramic vessels - Nàdia Tarifa-Mateo; R. Laborda; A. Sierra; L. Montes; P. Utrilla; M. Saña; E. Motsch; P. Schaeffer; P. Adam (Archaeological and Anthropological Sciences, 2024)

A novel virus of the family Secoviridae detected in lettuce in the United Kingdom and in dandelion in Slovakia - Ian P. Adams; Giuseppe Micali; Ummey Hany; Anna Skelton; Val Harju; Adam Buxton-Kirk; Lukáš Predajňa; Katarína Šoltys; Michaela Mrkvová; Miroslav Glasa; Adrian Fox (Journal of Plant Pathology, 2024)

Environmental behaviour of iron and steel slags in coastal settings - Alex L. Riley; James Cameron; Ian T. Burke; Patrizia Onnis; John M. MacDonald; Catherine J. Gandy; Richard A. Crane; Patrick Byrne; Sean Comber; Adam P. Jarvis; Karen A. Hudson-Edwards; William M. Mayes (Environmental Science and Pollution Research, 2024)
Iron and steel slags have a long history of both disposal and beneficial use in the coastal zone. Despite the large volumes of slag deposited, comprehensive assessments of potential risks associated with metal(loid) leaching from iron and steel by-products are rare for coastal systems. This study provides a national-scale overview of the 14 known slag deposits in the coastal environment of Great Britain (those within 100 m of the mean high-water mark), comprising geochemical characterisation and leaching test data (using both low and high ionic strength waters) to assess potential leaching risks. The seaward facing length of slag deposits totalled at least 76 km, and are predominantly composed of blast furnace (iron-making) slags from the early to mid-20th Century. Some of these form tidal barriers and formal coastal defence structures, but larger deposits are associated with historical coastal disposal in many former areas of iron and steel production, notably the Cumbrian coast of England. Slag deposits are dominated by melilite phases (e.g. gehlenite), with evidence of secondary mineral formation (e.g. gypsum, calcite) indicative of weathering. Leaching tests typically show lower element (e.g. Ba, V, Cr, Fe) release under seawater leaching scenarios compared to deionised water, largely ascribable to the pH buffering provided by the former. Only Mn and Mo showed elevated leaching concentrations in seawater treatments, though at modest levels (<3 mg/L and 0.01 mg/L, respectively). No significant leaching of potentially ecotoxic elements such as Cr and V (mean leachate concentrations <0.006 mg/L for both) were apparent in seawater, which micro-X-Ray Absorption Near Edge Structure (μXANES) analysis show are both present in slags in low valence (and low toxicity) forms. Although there may be physical hazards posed by extensive erosion of deposits in high-energy coastlines, the data suggest seawater leaching of coastal iron and steel slags in the UK is likely to pose minimal environmental risk.

Investigation of near-rectilinear halo orbit search and rescue using staging L 1 / L 2 Lyapunov and distant retrograde orbit families - Thomas J. Fay; Adam P. Wilmer; Robert A. Bettinger (Journal of Space Safety Engineering, 2024)

HBM4EU E-waste study: Assessing persistent organic pollutants in blood, silicone wristbands, and settled dust among E-waste recycling workers in Europe - Adam Cseresznye; Emilie M. Hardy; Yu Ait Bamai; Paulien Cleys; Giulia Poma; Govindan Malarvannan; Paul T.J. Scheepers; Susana Viegas; Carla Martins; Simo P. Porras; Tiina Santonen; Lode Godderis; et al. (Environmental Research, 2024)

Correction: Revisiting conservation units for the endangered mountain yellow-legged frog species complex (Rana muscosa, Rana sierrae) using multiple genomic methods - Allison Q. Byrne; Andrew P. Rothstein; Lydia L. Smith; Hannah Kania; Roland A. Knapp; Daniel M. Boiano; Cheryl J. Briggs; Adam R. Backlin; Robert N. Fisher; Erica Bree Rosenblum (Conservation Genetics, 2024)

Revisiting conservation units for the endangered mountain yellow-legged frog species complex (Rana muscosa, Rana sierrae) using multiple genomic methods - Allison Q. Byrne; Andrew P. Rothstein; Lydia L. Smith; Hannah Kania; Roland A. Knapp; Daniel M. Boiano; Cheryl J. Briggs; Adam R. Backlin; Robert N. Fisher; Erica Bree Rosenblum (Conservation Genetics, 2024)
Insights from conservation genomics have dramatically improved recovery plans for numerous endangered species. However, most taxa have yet to benefit from the full application of genomic technologies. The mountain yellow-legged frog species complex, Rana muscosa and Rana sierrae, inhabits the Sierra Nevada mountains and Transverse/Peninsular Ranges of California and Nevada. Both species have declined precipitously throughout their historical distributions. Conservation management plans outline extensive ongoing recovery efforts but are still based on the genetic structure determined primarily using a single mitochondrial sequence. Our study used two different sequencing strategies – amplicon sequencing and exome capture – to refine our understanding of the population genetics of these imperiled amphibians. We used buccal swabs, museum tissue samples, and archived skin swabs to genotype frog populations across their range. Using the amplicon sequencing and exome capture datasets separately and combined, we document five major genetic clusters. Notably, we found evidence supporting previous species boundaries within Kings Canyon National Park with some exceptions at individual sites. Though we see evidence of genetic clustering, especially in the R. muscosa clade, we also found evidence of some admixture across cluster boundaries in the R. sierrae clade, suggesting a stepping-stone model of population structure. We also find that the southern R. muscosa cluster had large runs of homozygosity and the lowest overall heterozygosity of any of the clusters, consistent with previous reports of marked declines in this area. Overall, our results clarify management unit designations across the range of an endangered species and highlight the importance of sampling the entire range of a species, even when collecting genome-scale data.

Distinct orchid mycorrhizal fungal communities among co-occurring Vanilla species in Costa Rica: root substrate and population-based segregation - Shan Wong; Jaspreet Kaur; Pankaj Kumar; Adam P. Karremans; Jyotsna Sharma (Mycorrhiza, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Sub-lethal effects of the insecticide, imidacloprid, on the responses of damselfly larvae to chemosensory cues indicating predation risk - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Douglas P. Chivers; Maud C.O. Ferrari (Chemosphere, 2024)

Parsing the toxicity paradox: Composition and duration of exposure alter predicted oil spill effects by orders of magnitude - Deborah P. French-McCay; Hilary J. Robinson; Julie E. Adams; Matthew A. Frediani; Matthew J. Murphy; Cheryl Morse; Melissa Gloekler; Thomas F. Parkerton (Marine Pollution Bulletin, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Role of Eating Behavior and Stress in Maintenance of Dietary Changes During the PREVIEW Intervention - Elli Jalo; Mikael Fogelholm; Margriet Westerterp-Plantenga; Tanja C. Adam; Mathijs Drummen; Maija Huttunen-Lenz; Louise Kjølbæk; José Alfredo Martinez; Teodora Handjieva-Darlenska; Moira A. Taylor; Jennie Brand-Miller; Sally Poppitt; et al. (Journal of Nutrition Education and Behavior, 2024)

A rapid and automated computational approach to the design of multistable soft actuators - Mehran Mirramezani; Deniz Oktay; Ryan P. Adams (Computer Physics Communications, 2024)

A rice GT61 glycosyltransferase possesses dual activities mediating 2-O-xylosyl and 2-O-arabinosyl substitutions of xylan - Ruiqin Zhong; Dayong Zhou; Dennis R. Phillips; Earle R. Adams; Lirong Chen; John P. Rose; Bi-Cheng Wang; Zheng-Hua Ye (Planta, 2024)

Carotenoid skin ornaments as flexible indicators of male foraging behavior in a marine predator: Variation among Mexican colonies of brown booby (Sula leucogaster) - Nathan P. Michael; Roxana Torres; Andreanna J. Welch; Jonathan Felis; Josh Adams; Mario Erandi Bonillas-Monge; Samantha Hodgson; Laura Lopez-Marquez; Alejandro Martínez-Flores; Gala Enidh Castro-Mejias; Anne E. Wiley (Marine Biology, 2024)
Carotenoid-dependent ornaments can reflect animals’ diet and foraging behaviors. However, this association should be spatially flexible and variable among populations to account for geographic variation in optimal foraging behaviors. We tested this hypothesis using populations of a marine predator (the brown booby, Sula leucogaster ) that forage across a gradient in ocean depth in and near the Gulf of California. Specifically, we quantified green chroma for two skin traits (foot and gular color) and their relationship to foraging location and diet of males, as measured via global positioning system tracking and stable carbon isotope analysis of blood plasma. Our three focal colonies varied in which foraging attributes were linked to carotenoid-rich ornaments. For gular skin, our data showed a shift from a benthic prey-green skin association in the shallow waters in the north to a pelagic prey-green skin association in the deepest waters to the south. Mean foraging trip duration and distance of foraging site from coast also predicted skin coloration in some colonies. Finally, brown booby colonies varied in which trait (foot versus gular skin color) was associated with foraging metrics. Overall, our results indicate that male ornaments reflect quality of diet and foraging–information that may help females select mates who are adapted to local foraging conditions and therefore, are likely to provide better parental care. More broadly, our results stress that diet-dependent ornaments are closely linked to animals’ environments and that we cannot assume ornaments or ornament signal content are ubiquitous within species, even when ornaments appear similar among populations.

The Role of Verbal Fluency in the Cerebellar Cognitive Affective Syndrome Scale in Friedreich Ataxia - Louise A. Corben; Eliza Blomfield; Geneieve Tai; Hiba Bilal; Ian H. Harding; Nellie Georgiou-Karistianis; Martin B. Delatycki; Adam P. Vogel (The Cerebellum, 2024)
Cerebellar pathology engenders the disturbance of movement that characterizes Friedreich ataxia (FRDA), yet the impact of cerebellar pathology on cognition in FRDA remains unclear. Numerous studies have unequivocally demonstrated the role of the cerebellar pathology in disturbed cognitive, language and affective regulation, referred to as Cerebellar Cognitive Affective Syndrome (CCAS), and quantified by the CCAS-Scale (CCAS-S). The presence of dysarthria in many individuals with ataxia, particularly FRDA, may confound results on some items of the CCAS-S resulting in false-positive scores. This study explored the relationship between performance on the CCAS-S and clinical metrics of disease severity in 57 adults with FRDA. In addition, this study explored the relationship between measures of intelligibility and naturalness of speech and scores on the CCAS-S in a subgroup of 39 individuals with FRDA. We demonstrated a significant relationship between clinical metrics and performance on the CCAS-S. In addition, we confirmed the items that returned the greatest rate of failure were based on Verbal Fluency Tasks, revealing a significant relationship between these items and measures of speech. Measures of speech explained over half of the variance in the CCAS-S score suggesting the role of dysarthria in the performance on the CCAS-S is not clear. Further work is required prior to adopting the CCAS-S as a cognitive screening tool for individuals with FRDA.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Capturing uncertainty when modelling environmental drivers of fish populations, with an illustrative application to Pacific Cod in the eastern Bering Sea - André E. Punt; Michael G. Dalton; Grant D. Adams; Steven J. Barbeaux; Wei Cheng; Albert J. Hermann; Kirstin K. Holsman; Peter-John F. Hulson; Thomas P. Hurst; Alberto Rovellini (Fisheries Research, 2024)

Glyphosate-based restoration of a degraded grassland threatens soil health and the diversity of nematode communities - J. Parr McQueen; Eli M.S. Gendron; Adam J. Solon; Clifton P. Bueno de Mesquita; Rebecca A. Hufft; Nancy Shackelford; Katharine N. Suding; Steven K. Schmidt; Dorota L. Porazinska (Soil Biology and Biochemistry, 2024)

Investigation of mixing miscible liquids with high viscosity contrasts in turbulently stirred vessels using electrical resistance tomography - Sorosh Mirfasihi; Wrichik Basu; Philip Martin; Adam Kowalski; Claudio P. Fonte; Amir Keshmiri (Chemical Engineering Journal, 2024)

Analysis of flux footprints in fragmented, heterogeneous croplands - Shweta Kumari; B. V. N. P. Kambhammettu; Mark. A. Adams; Dev Niyogi (Meteorology and Atmospheric Physics, 2024)
An accurate quantification of fluxes from heterogeneous sites and further bifurcation into contributing homogeneous fluxes is an active field of research. Among such sites, fragmented croplands with varying surface roughness characteristics pose formidable challenges for footprint analysis. We conducted two flux monitoring experiments in fragmented croplands characterized by two dissimilar surfaces with objectives to: (i) evaluate the performance of two analytical footprint models in heterogeneous canopy considering aggregated roughness parameters and (ii) analyze the contribution of fluxes from individual surfaces under changing wind speed. A set of three eddy covariance (EC) towers (one each capturing the homogenous fluxes from individual surfaces and a third, high tower capturing the heterogeneous mixed fluxes) was used for method validation. High-quality EC fluxes that fulfill stationarity and internal turbulence tests were analyzed considering daytime, unstable conditions. In the first experiment, source area contribution from a surface is gradually reduced by progressive cut, and its effect on high-tower flux measurements is analyzed. Two footprint models (Kormann and Meixner ‘KM’; analytical solution to Lagrangian model ‘FFP’) with modified surface roughness parameters were applied under changing source area contributions. FFP model has consistently over predicted the footprints (RMSE FFP = 0.31 m −1 , PBIAS FFP = 19.00), whereas KM model prediction was gradually changed from over prediction to under prediction towards higher upwind distances (RMSE KM = 0.02 m −1 , PBIAS KM = 8.50). Sensitivity analysis revealed that the models are more sensitive to turbulent conditions than surface characteristics. This motivated to conduct the second experiment, where the fractional contribution of individual surfaces ( α and β ) to the heterogeneous fluxes measured by the high tower (T3) was estimated using the principle of superposition (FT3 = α FT1 + β FT2). Results showed that α and β are dynamic during daylight hours and strongly depend on mean wind speed ( U ) and friction velocity ( u *). The contribution of fluxes from adjoining fields [1 − ( α + β )] is significant beyond 80% isopleth. Our findings provide guidelines for future analysis of fluxes in heterogeneous, fragmented croplands.

3D printed microfluidic devices for integrated solid-phase extraction and microchip electrophoresis of preterm birth biomarkers - Joule E. Esene; Addalyn J. Burningham; Anum Tahir; Gregory P. Nordin; Adam T. Woolley (Analytica Chimica Acta, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Optimizing Communication in Ataxia: A Multifaceted Approach to Alternative and Augmentative Communication (AAC) - Adam P. Vogel; Caroline Spencer; Katie Burke; Daniella de Bruyn; Peter Gibilisco; Scott Blackman; Jennifer M. Vojtech; Thayabaran Kathiresan (The Cerebellum, 2024)
The progression of multisystem neurodegenerative diseases such as ataxia significantly impacts speech and communication, necessitating adaptive clinical care strategies. With the deterioration of speech, Alternative and Augmentative Communication (AAC) can play an ever increasing role in daily life for individuals with ataxia. This review describes the spectrum of AAC resources available, ranging from unaided gestures and sign language to high-tech solutions like speech-generating devices (SGDs) and eye-tracking technology. Despite the availability of various AAC tools, their efficacy is often compromised by the physical limitations inherent in ataxia, including upper limb ataxia and visual disturbances. Traditional speech-to-text algorithms and eye gaze technology face challenges in accuracy and efficiency due to the atypical speech and movement patterns associated with the disease. In addressing these challenges, maintaining existing speech abilities through rehabilitation is prioritized, complemented by advances in digital therapeutics to provide home-based treatments. Simultaneously, projects incorporating AI driven solutions aim to enhance the intelligibility of dysarthric speech through improved speech-to-text accuracy. This review discusses the complex needs assessment for AAC in ataxia, emphasizing the dynamic nature of the disease and the importance of regular reassessment to tailor communication strategies to the changing abilities of the individual. It also highlights the necessity of multidisciplinary involvement for effective AAC assessment and intervention. The future of AAC looks promising with developments in brain-computer interfaces and the potential of voice banking, although their application in ataxia requires further exploration.

An explanation for the accuracy of sensor-based measures of energy intake: Amount of food consumed matters more than dietary composition - Tommy Chou; Adam W. Hoover; Stephanie P. Goldstein; Dante Greco-Henderson; Corby K. Martin; Hollie A. Raynor; Eric R. Muth; J. Graham Thomas (Appetite, 2024)

Community perspectives on heat and health in Baltimore City - Idiatou Diallo; Linchen He; Kirsten Koehler; Adam P. Spira; Rasika Kale; Jierui Ou; Genee Smith; Sabriya L. Linton; Jura Augustinavicius (Urban Climate, 2024)

Electrochemical and scanning transmission X-ray microscopy studies of MnO2 and Mn3O4 for supercapacitor cathodes: Influence of fabrication method and electrochemical activation on charge storage - Wenjuan Yang; Haytham Eraky; Chunyang Zhang; Adam P. Hitchcock; Igor Zhitomirsky (Chemical Engineering Journal, 2024)

Are threatened seabird colonies of the pacific ocean genetically vulnerable? The case of the red-tailed tropicbird, Phaethon rubricauda, as a model species - Andrea I Varela; Katherina Brokordt; Juliana A Vianna; María José Frugone; Stefanie MH Ismar-Rebitz; Chris P Gaskin; Nicholas Carlile; Terence O’Dwyer; Josh Adams; Eric A VanderWerf; Guillermo Luna-Jorquera (Biodiversity and Conservation, 2024)

Wave, light, and dissolved oxygen exposures drive novel coastal eelgrass (Zostera pacifica) transplant performance - Rilee D. Sanders; Adam K. Obaza; Benjamin C. Grime; Mathilde Lindhart; Luke P. Miller; Kristen E. Elsmore; Olivia C. Carmack; Tom K. Ford; James J. Leichter (Frontiers in Marine Science, 2024)
The high ecological and economic value of seagrass has been long recognized, with these foundational habitats providing myriad ecosystem services. Yet through cumulative anthropogenic impacts, seagrasses are exhibiting extensive declines globally. A litany of studies and active restoration trials have demonstrated practical methodologies to restore seagrass habitats and effectively return critical habitat functions to degraded coastal zone systems worldwide. Seagrass loss along the U.S. West Coast has precipitated decades of seagrass protection, conservation, and restoration efforts. Yet, mitigation transplanting efforts have prioritized Zostera marina (narrow-leaved eelgrass) in shallow, protected environments, while a dearth of information is available on species inhabiting offshore islands and exposed mainland coasts. In this study, we conducted a novel transplant of Zostera pacifica , a wide-leaved species found in depths of 7 – 20 m along the offshore islands and mainland coast of California. Transplants were conducted at three geographically distinct sites in Santa Monica Bay, coupled with continuous monitoring of biophysical parameters providing insight into physical drivers at transplant and donor sites. Utilizing in situ data, and environmental thresholds adapted from the literature for Z. marina , we performed exposure analyses to evaluate factors influencing Z. pacifica transplant performance. Exceedances of threshold values for environmental parameters, specifically, wave exposure and near-bed flow speeds ( H rms > 0.59 m and U rms > 0.1 m s -1 ), photosynthetically active radiation (< 3 and > 5 mol m -2 day -1 ) and dissolved oxygen (< 3 mg O 2 L -1 ) exposure impacted transplant survivorship. These results suggest Z. pacifica persist in biophysically dynamic conditions and are sensitive to exceedances of thresholds, underlining the importance of pre-transplant site-selection processes to this species. These data represent the first holistic study of Z. pacifica transplanting on an exposed mainland coast, which provides a view into the baseline environmental envelopes within existing Z. pacifica habitat, and further, may serve as a model for investigating scalable open coast seagrass restoration for temperate regions.

Exposure to the insecticide, imidacloprid, impairs predator-recognition learning in damselfly larvae - Prashani D. Wickramasingha; Christy A. Morrissey; Iain D. Phillips; Adam L. Crane; Maud C.O. Ferrari; Douglas P. Chivers (Environmental Pollution, 2024)

Estimating reductions in the risk of vessels striking whales achieved by management strategies - Jessica V. Redfern; Brooke C. Hodge; Daniel E. Pendleton; Amy R. Knowlton; Jeffrey Adams; Eric M. Patterson; Caroline P. Good; Jason J. Roberts (Biological Conservation, 2024)

Trace element chemistry and strontium isotope ratios of atmospheric particulate matter reveal air quality impacts from mineral dust, urban pollution, and fireworks in the Wasatch Front, Utah, USA - Micah J. Marcy; Gregory T. Carling; Alyssa N. Thompson; Barry R. Bickmore; Stephen T. Nelson; Kevin A. Rey; Diego P. Fernandez; Matthew Heiner; Bradley R. Adams (Applied Geochemistry, 2024)

Wetscapes provide the physical basis to sustainable peatland livelihoods - Ralph J. M. Temmink; Bjorn J. M. Robroek; Gijs van Dijk; Adam H. W. Koks; Sannimari A. Käärmelahti; Alexandra Barthelmes; Martin J. Wassen; Rafael Ziegler; Magdalena N. Steele; Wim Giesen; Hans Joosten; Christian Fritz; et al. (Ambio, 2024)

Frontal–temporal regional differences in brain energy metabolism and mitochondrial function using 31P MRS in older adults - Francesca V. Lopez; Andrew O’Shea; Zhiguang Huo; Steven T. DeKosky; Theodore P. Trouard; Gene E. Alexander; Adam J. Woods; Dawn Bowers (GeroScience, 2024)

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Effect of temperature on the degradation of glyphosate by Mn-oxide: Products and pathways of degradation - Spencer R. Moller; Adam F. Wallace; Rumana Zahir; Abrar Quadery; Deb P. Jaisi (Journal of Hazardous Materials, 2024)

HBM4EU e-waste study: Occupational exposure of electronic waste workers to phthalates and DINCH in Europe - Paulien Cleys; Emilie Hardy; Yu Ait Bamai; Giulia Poma; Adam Cseresznye; Govindan Malarvannan; Paul T.J. Scheepers; Susana Viegas; Simo P. Porras; Tiina Santonen; Lode Godderis; Jelle Verdonck; et al. (International Journal of Hygiene and Environmental Health, 2024)

Quantifying the impact of climate smart agricultural practices on soil carbon storage relative to conventional management - Adam P. Schreiner-McGraw; Curtis J. Ransom; Kristen S. Veum; Jeffrey D. Wood; Kenneth A. Sudduth; Lori J. Abendroth (Agricultural and Forest Meteorology, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Un‘covering’ blanket bonds: Assessing the adoption of blanket bonds across the states - Nurun Naher; Adam P. Mayer; Jonathan M. Fisk; John C. Morris (The Extractive Industries and Society, 2023)

Choice of benchmark optimization problems does matter - Adam P. Piotrowski; Jaroslaw J. Napiorkowski; Agnieszka E. Piotrowska (Swarm and Evolutionary Computation, 2023)

Net effects explains the benefits to children from maternal fish consumption despite methylmercury in fish - Philip Spiller; Edwin van Wijngaarden; Heather R. Adams; J.J. Strain; Emeir M. McSorley; Maria S. Mulhern; Marie C. Conway; Allison J. Yeates; Clark Carrington; P. Michael Bolger; Kara M. Morgan; Caroline M. Taylor; et al. (NeuroToxicology, 2023)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Mixed nitrate and metal contamination influences operational speciation of toxic and essential elements - Michael P. Thorgersen; Jennifer L. Goff; Farris L. Poole; Kathleen F. Walker; Andrew D. Putt; Lauren M. Lui; Terry C. Hazen; Adam P. Arkin; Michael W.W. Adams (Environmental Pollution, 2023)

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

Application of VirCapSeq-VERT and BacCapSeq in the diagnosis of presumed and definitive neuroinfectious diseases - Abhilasha P. Boruah; Adam Kroopnick; Riddhi Thakkar; Anne E. Wapniarski; Carla Kim; Rachelle Dugue; Eileen Harrigan; W. Ian Lipkin; Nischay Mishra; Kiran T. Thakur (Journal of NeuroVirology, 2023)

Using Smartphone Sensors for Ataxia Trials: Consensus Guidance by the Ataxia Global Initiative Working Group on Digital-Motor Biomarkers - Andrea H. Németh; Chrystalina A. Antoniades; Juergen Dukart; Martina Minnerop; Clara Rentz; Bart-Jan Schuman; Bart van de Warrenburg; Ilse Willemse; Enrico Bertini; Anoopum S. Gupta; Carlos Bandeira de Mello Monteiro; Hajar Almoajil; et al. (The Cerebellum, 2023)
Smartphone sensors are used increasingly in the assessment of ataxias. To date, there is no specific consensus guidance regarding a priority set of smartphone sensor measurements, or standard assessment criteria that are appropriate for clinical trials. As part of the Ataxia Global Initiative Digital-Motor Biomarkers Working Group (AGI WG4), aimed at evaluating key ataxia clinical domains (gait/posture, upper limb, speech and oculomotor assessments), we provide consensus guidance for use of internal smartphone sensors to assess key domains. Guidance was developed by means of a literature review and a two stage Delphi study conducted by an Expert panel, which surveyed members of AGI WG4, representing clinical, research, industry and patient-led experts, and consensus meetings by the Expert panel to agree on standard criteria and map current literature to these criteria. Seven publications were identified that investigated ataxias using internal smartphone sensors. The Delphi 1 survey ascertained current practice, and systems in use or under development. Wide variations in smartphones sensor use for assessing ataxia were identified. The Delphi 2 survey identified seven measures that were strongly endorsed as priorities in assessing 3/4 domains, namely gait/posture, upper limb, and speech performance. The Expert panel recommended 15 standard criteria to be fulfilled in studies. Evaluation of current literature revealed that none of the studies met all criteria, with most being early-phase validation studies. Our guidance highlights the importance of consensus, identifies priority measures and standard criteria, and will encourage further research into the use of internal smartphone sensors to measure ataxia digital-motor biomarkers.

Dinuclear gold(I) complexes based on carbene and diphosphane ligands: bis[2-(dicyclohexylphosphano)ethyl]amine complex inhibits the proteasome activity, decreases stem cell markers and spheroid viability in lung cancer cells - Naike Casagrande; Cinzia Borghese; Giuseppe Corona; Donatella Aldinucci; Muhammad Altaf; Adam A. A. Sulaiman; Anvarhusein A. Isab; Saeed Ahmad; Abdul Malik P. Peedikakkal (JBIC Journal of Biological Inorganic Chemistry, 2023)

Glacial Isostatic Adjustment modelling of the mid-Holocene sea-level highstand of Singapore and Southeast Asia - Tanghua Li; Stephen Chua; Fangyi Tan; Nicole S. Khan; Timothy A. Shaw; Jedrzej Majewski; Aron J. Meltzner; Adam D. Switzer; Patrick Wu; Benjamin P. Horton (Quaternary Science Reviews, 2023)

Coastal response to Holocene Sea-level change: A case study from Singapore - Stephen Chua; Adam D. Switzer; Chris Gouramanis; Yama Dixit; Michael I. Bird; Benjamin P. Horton (Marine Geology, 2023)

Living mulches reduce natural enemies when combined with frequent pesticide applications - T. Blake Hudson; Adam M. Alford; Tom R. Bilbo; Sean C. Boyle; Helene B. Doughty; Thomas P. Kuhar; Lorena Lopez; Kelly C. McIntyre; Allison K. Stawara; James F. Walgenbach; Courtney Walls; Carmen K. Blubaugh (Agriculture, Ecosystems & Environment, 2023)

Nerine potexvirus 1: a new Potexvirus species detected from Nerine in the United Kingdom - Naomi Beddoe; Sam McGreig; John Walsh; Adrian Fox; Ian P. Adams; Alec Forsyth (Journal of Plant Pathology, 2023)

Quantitative Speech Assessment in Ataxia—Consensus Recommendations by the Ataxia Global Initiative Working Group on Digital-Motor Markers - Adam P. Vogel; Anna Sobanska; Anoopum Gupta; Gessica Vasco; Marcus Grobe-Einsler; Susanna Summa; Stephanie Borel (The Cerebellum, 2023)
Dysarthria is a common and debilitating symptom of many neurodegenerative diseases, including those resulting in ataxia. Changes to speech lead to significant reductions in quality of life, impacting the speaker in most daily activities. Recognition of its importance as an objective outcome measure in clinical trials for ataxia is growing. Its viability as an endpoint across the disease spectrum (i.e. pre-symptomatic onwards) means that trials can recruit ambulant individuals and later-stage individuals who are often excluded because of difficulty completing lower limb tasks. Here we discuss the key considerations for speech testing in clinical trials including hardware selection, suitability of tasks and their role in protocols for trials and propose a core set of tasks for speech testing in clinical trials. Test batteries could include forms suitable for remote short, sensitive and easy to use, with norms available in several languages. The use of artificial intelligence also could improve accuracy and automaticity of analytical pipelines in clinic and trials.

Total water level controls on the trajectory of dune toe retreat - Matthew P. Conlin; Nicholas Cohn; Peter N. Adams (Geomorphology, 2023)

High temperature flow synthesis of iron oxide nanoparticles: Size tuning via reactor engineering - Maximilian O. Besenhard; Liudmyla Storozhuk; Alec. P. LaGrow; Luca Panariello; Adam Maney; Sayan Pal; Céline Kiefer; Damien Mertz; Le Duc Tung; Martin R. Lees; Nguyen Thi Kim Thanh; Asterios Gavriilidis (Chemical Engineering Journal, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Antimicrobial activity of thermophilin 110 against the opportunistic pathogen Cutibacterium acnes - John A. Renye; Mayra A. Mendez-Encinas; Andre K. White; Amanda L. Miller; Michael J. McAnulty; Madhav P. Yadav; Arland T. Hotchkiss; Giselle K. P. Guron; Adam M. Oest; Karla G. Martinez-Robinson; Elizabeth Carvajal-Millan (Biotechnology Letters, 2023)

Changes in oral health during aging in a novel non-human primate model - Parveez Ahamed Abdul-Azees; Hanzhou Wang; Yong-Hee P. Chun; Jason Pizzini; David D. Dean; Kelly R. Reveles; Milos Marinkovic; Xiao-Dong Chen; Adam B. Salmon; Chih-Ko Yeh (GeroScience, 2023)

A DNA-barcode biodiversity standard analysis method (DNA-BSAM) reveals a large variance in the effect of a range of biological, chemical and physical soil management interventions at different sites, but location is one of the most important aspects determining the nature of agricultural soil microbiology - Matías Fernández-Huarte; John G. Elphinstone; Ian P. Adams; Joana G. Vicente; Anne Bhogal; Christine A. Watson; Francois Dussart; Elizabeth A. Stockdale; John Walshaw; Sam McGreig; Robert W. Simmons; Lucie Mašková; et al. (Soil Biology and Biochemistry, 2023)

Diversification of the sleepers (Gobiiformes: Gobioidei: Eleotridae) and evolution of the root gobioid families - Christine E. Thacker; W. Tyler McCraney; Richard C. Harrington; Thomas J. Near; James J. Shelley; Mark Adams; Michael P. Hammer; Peter J. Unmack (Molecular Phylogenetics and Evolution, 2023)

Cultivation potential of Vanilla crop wild relatives in two contrasting land use systems - Charlotte Watteyn; Bert Reubens; José Bernal Azofeifa Bolaños; Frank Solano Campos; Araceli Pérez Silva; Adam P. Karremans; Bart Muys (European Journal of Agronomy, 2023)

Correction: Wetscapes: Restoring and maintaining peatland landscapes for sustainable futures - Ralph J. M. Temmink; Bjorn J. M. Robroek; Gijs van Dijk; Adam H. W. Koks; Sannimari A. Käärmelahti; Alexandra Barthelmes; Martin J. Wassen; Rafael Ziegler; Magdalena N. Steele; Wim Giesen; Hans Joosten; Christian Fritz; et al. (Ambio, 2023)

Wetscapes: Restoring and maintaining peatland landscapes for sustainable futures - Ralph J. M. Temmink; Bjorn J. M. Robroek; Gijs van Dijk; Adam H. W. Koks; Sannimari A. Käärmelahti; Alexandra Barthelmes; Martin J. Wassen; Rafael Ziegler; Magdalena N. Steele; Wim Giesen; Hans Joosten; Christian Fritz; et al. (Ambio, 2023)
Peatlands are among the world’s most carbon-dense ecosystems and hotspots of carbon storage. Although peatland drainage causes strong carbon emissions, land subsidence, fires and biodiversity loss, drainage-based agriculture and forestry on peatland is still expanding on a global scale. To maintain and restore their vital carbon sequestration and storage function and to reach the goals of the Paris Agreement, rewetting and restoration of all drained and degraded peatlands is urgently required. However, socio-economic conditions and hydrological constraints hitherto prevent rewetting and restoration on large scale, which calls for rethinking landscape use. We here argue that creating integrated wetscapes (wet peatland landscapes), including nature preserve cores, buffer zones and paludiculture areas (for wet productive land use), will enable sustainable and complementary land-use functions on the landscape level. As such, transforming landscapes into wetscapes presents an inevitable, novel, ecologically and socio-economically sound alternative for drainage-based peatland use.

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Evidence of population-level impacts and resiliency for Gulf of Mexico shelf taxa following the Deepwater Horizon oil spill - William F. Patterson; Kelly Lynn Robinson; Beverly K. Barnett; Matthew D. Campbell; David C. Chagaris; Jeffrey P. Chanton; Kendra L. Daly; David S. Hanisko; Frank J. Hernandez; Steven A. Murawski; Adam G. Pollack; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The goal of this paper was to review the evidence of population-level impacts of the Deepwater Horizon Oil Spill (DWH) on Gulf of Mexico (GOM) continental shelf taxa, as well as evidence of resiliency following the DWH. There is considerable environmental and biological evidence that GOM shelf taxa were exposed to and suffered direct and indirect impacts of the DWH. Numerous assessments, from mesocosm studies to analysis of biopsied tissue or tissue samples from necropsied animals, revealed a constellation of physiological effects related to DWH impacts on GOM biota, some of which clearly or likely resulted in mortality. While the estimated concentrations of hydrocarbons in shelf waters and sediments were orders of magnitude lower than measured in inshore or deep GOM environments, the level of mortality observed or predicted was substantial for many shelf taxa. In some cases, such as for zooplankton, community shifts following the spill were ephemeral, likely reflecting high rates of population turnover and productivity. In other taxa, such as GOM reef fishes, impacts of the spill are confounded with other stressors, such as fishing mortality or the appearance and rapid population growth of invasive lionfish ( Pterois spp.). In yet others, such as cetaceans, modeling efforts to predict population-level effects of the DWH made conservative assumptions given the species’ protected status, which post-DWH population assessments either failed to detect or population increases were estimated. A persistent theme that emerged was the lack of precise population-level data or assessments prior to the DWH for many taxa, but even when data or assessments did exist, examining evidence of population resiliency was confounded by other stressors impacting GOM biota. Unless efforts are made to increase the resolution of the data or precision of population assessments, difficulties will likely remain in estimating the scale of population-level effects or resiliency in the case of future large-scale environmental catastrophes.

Genetic structure of pike (Esox lucius Linnaeus, 1758) populations along the Polish coast of the southern Baltic Sea: Comparison to Danish brackish population - Anna Wąs-Barcz; Rafał Bernaś; Martyna Greszkiewicz; Adam M. Lejk; Dariusz P. Fey (Fisheries Research, 2023)

Sediment provenance and dispersal in the early Eocene Dongying Depression, Bohai Bay Basin, Eastern China: Evidence from detrital zircon geochronology, geochemistry and petrology - Ke Yang; Xiaomin Zhu; Luca Colombera; Adam McArthur; Nigel P. Mountney; Shifa Zhu; Lei Jin; Tingting Shen; Huaiyu Yang; Hongkui Chen; Shuanghui Xie; Xuling Jin (Sedimentary Geology, 2023)

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Evidence of a thoracic crop in workers, soldiers, and queens of Carebara perpusilla ants (Formicidae: Myrmicinae) - Adam Khalife; Johan Billen; Evan P. Economo (The Science of Nature, 2023)

Antibody Fc-binding profiles and ACE2 affinity to SARS-CoV-2 RBD variants - Ebene R. Haycroft; Samantha K. Davis; Pradhipa Ramanathan; Ester Lopez; Ruth A. Purcell; Li Lynn Tan; Phillip Pymm; Bruce D. Wines; P. Mark Hogarth; Adam K. Wheatley; Jennifer A. Juno; Samuel J. Redmond; et al. (Medical Microbiology and Immunology, 2023)
Emerging SARS-CoV-2 variants, notably Omicron, continue to remain a formidable challenge to worldwide public health. The SARS-CoV-2 receptor-binding domain (RBD) is a hotspot for mutations, reflecting its critical role at the ACE2 interface during viral entry. Here, we comprehensively investigated the impact of RBD mutations, including 5 variants of concern (VOC) or interest—including Omicron (BA.2)—and 33 common point mutations, both on IgG recognition and ACE2-binding inhibition, as well as FcγRIIa- and FcγRIIIa-binding antibodies, in plasma from two-dose BNT162b2-vaccine recipients and mild-COVID-19 convalescent subjects obtained during the first wave using a custom-designed bead-based 39-plex array. IgG-recognition and FcγR-binding antibodies were decreased against the RBD of Beta and Omicron, as well as point mutation G446S, found in several Omicron sub-variants as compared to wild type. Notably, while there was a profound decrease in ACE2 inhibition against Omicron, FcγR-binding antibodies were less affected, suggesting that Fc functional antibody responses may be better retained against the RBD of Omicron in comparison to neutralization. Furthermore, while measurement of RBD–ACE2-binding affinity via biolayer interferometry showed that all VOC RBDs have enhanced affinity to human ACE2, we demonstrate that human ACE2 polymorphisms, E35K (rs1348114695) has reduced affinity to VOCs, while K26R (rs4646116) and S19P (rs73635825) have increased binding kinetics to the RBD of VOCs, potentially affecting virus–host interaction and, thereby, host susceptibility. Collectively, our findings provide in-depth coverage of the impact of RBD mutations on key facets of host–virus interactions.

Public recognition of climate change inequities within the United States - Jonathon P. Schuldt; Adam R. Pearson (Climatic Change, 2023)

Evaluation of approaches to recruitment of racially and ethnically diverse breast cancer patients from an integrated health care setting for collection of observational social network data - Candyce H. Kroenke; Elaine Kurtovich; Rhonda Aoki; Veronica C. Shim; Tracy D. Chan; Leslie Manace Brenman; Jane Bethard-Tracy; Alyce S. Adams; David P. Kennedy (Cancer Causes & Control, 2023)

Severe Zinc Deficiency Impairs Accrual of Bone in Rapidly Growing Rats That Is Partially Corrected Following Short-term Zinc Repletion - Laura M. Beaver; Yang Song; Kenneth A. Philbrick; Carmen P. Wong; Dawn A. Olson; Adam J. Branscum; Russell T. Turner; Emily Ho; Urszula T. Iwaniec (Biological Trace Element Research, 2023)

The road towards effective governance and management of marine protected areas in South Africa: evolving policies, paradigms and processes - SP Kirkman; P Kowalski; BQ Mann; GM Branch; MG van der Bank; KJ Sink; P Fielding; JB Mann-Lang; MC Pfaff; D Kotsedi; R Adams; S Dlulisa; et al. (African Journal of Marine Science, 2023)

Microscale pollen release and dispersal patterns in flowering grass populations - Carl A. Frisk; Godfrey P. Apangu; Geoffrey M. Petch; Simon Creer; Mary Hanson; Beverley Adams-Groom; Carsten A. Skjøth (Science of The Total Environment, 2023)

Herbaceous vegetation responses to experimental fire in savannas and forests depend on biome and climate - Zachary J. Gold; Adam F. A. Pellegrini; Tyler K. Refsland; Romina J. Andrioli; Marlin L. Bowles; Dale G. Brockway; Neil Burrows; Augusto C. Franco; Steve W. Hallgren; Sarah E. Hobbie; William A. Hoffmann; Kevin P. Kirkman; et al. (Ecology Letters, 2023)
Fire–vegetation feedbacks potentially maintain global savanna and forest distributions. Accordingly, vegetation in savanna and forest ecosystems should have differential responses to fire, but fire response data for herbaceous vegetation have yet to be synthesized across biomes. Here, we examined herbaceous vegetation responses to experimental fire at 30 sites spanning four continents. Across a variety of metrics, herbaceous vegetation increased in abundance where fire was applied, with larger responses to fire in wetter and in cooler and/or less seasonal systems. Compared to forests, savannas were associated with a 4.8 (±0.4) times larger difference in herbaceous vegetation abundance for burned versus unburned plots. In particular, grass cover decreased with fire exclusion in savannas, largely via decreases in C 4 grass cover, whereas changes in fire frequency had a relatively weak effect on grass cover in forests. These differential responses underscore the importance of fire for maintaining the vegetation structure of savannas and forests.

Bladder Cancer Prevention: Potential Molecular Targets and Their Clinically Relevant Agents - Surya P. Singh; Adam S. Asch; Chinthalapally V. Rao; Venkateshwar Madka (Current Pharmacology Reports, 2023)

Sweet as Vanilla hartii: Evidence for a nectar-rewarding pollination mechanism in Vanilla (Orchidaceae) flowers - Charlotte Watteyn; Daniela Scaccabarozzi; Bart Muys; Bert Reubens; James D. Ackerman; Mauricio Fernández Otárola; Maria Fernanda Guizar Amador; Adam P. Karremans (Flora, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Remote monitoring of cognition in cirrhosis and encephalopathy: future opportunity and challenge - Adam P. Buckholz; Russell Rosenblatt (Metabolic Brain Disease, 2023)

Implementation During a Pandemic: Findings, Successes, and Lessons Learned from Community Grantees - Wilhelmenia Mathias; Karen A. Nichols; Jewel Golden-Wright; Ciaran M. Fairman; Tisha M. Felder; Lauren Workman; Karen E. Wickersham; Kimberly J. Flicker; Jingxi Sheng; Samuel B. Noblet; Swann Arp Adams; Jan M. Eberth; et al. (Journal of Cancer Education, 2023)

Species‐specific acclimatization capacity of key traits explains global vertical distribution of seagrass species - Mario Minguito‐Frutos; Jordi Boada; Jordi F. Pagès; Candela Marco‐Méndez; Rohan Arthur; Matthew P. Adams; Teresa Alcoverro (Global Ecology and Biogeography, 2023)
Aim The global vertical depth distribution of seagrass species remains poorly understood. Locally, the abundance and distribution of seagrasses is determined by light penetration, but at global levels each seagrass species has very distinct maximum distributional depth ranges, indicating that plant‐associated traits must also influence their specific depth ranges. Seagrass‐specific attributes, such as plant size or architecture, growth or reproductive strategy and their physiological and/or morphological acclimatization potential, have been suggested to be responsible for this variety of vertical distributions. We investigate here whether these species‐specific traits drive differences in the global maximum vertical distribution of seagrasses. Location Global. Time period Publications between 1982 and 2020. Major taxa studied Seagrasses (order Alismatales). Methods We tested whether the species‐specific maximum vertical distribution of seagrasses can be predicted by (1) their rhizome diameter (a proxy for plant size); (2) their functional resilience (growth/reproductive strategy); or (3) their acclimatization capacity. For the last aspect, we used a systematic review followed by meta‐analytical approaches to select key seagrass traits that could potentially acclimatize to extreme light ranges across different seagrasses. Results We found that vertical distribution is best explained by the species‐specific acclimatization capacity of various seagrass traits, including saturation irradiance (physiological trait), leaves per shoot (morphological trait) and above‐ground biomass (structural trait). In contrast, our results indicate no predictive power of seagrass size or growth/reproductive strategy on the vertical distribution of seagrasses. Main conclusions Across the globe, the ability of seagrass species to thrive at a wide range of depths is strongly linked to the species‐specific acclimatization capacity of key traits at different organizational levels.

Unique trans-kingdom microbiome structural and functional signatures predict cognitive decline in older adults - Diptaraj S. Chaudhari; Shalini Jain; Vinod K. Yata; Sidharth P. Mishra; Ambuj Kumar; Amoy Fraser; Judyta Kociolek; Mariana Dangiolo; Amanda Smith; Adam Golden; Michal M. Masternak; Peter Holland; et al. (GeroScience, 2023)
The prevalence of age-related cognitive disorders/dementia is increasing, and effective prevention and treatment interventions are lacking due to an incomplete understanding of aging neuropathophysiology. Emerging evidence suggests that abnormalities in gut microbiome are linked with age-related cognitive decline and getting acceptance as one of the pillars of the Geroscience hypothesis. However, the potential clinical importance of gut microbiome abnormalities in predicting the risk of cognitive decline in older adults is unclear. Till now the majority of clinical studies were done using 16S rRNA sequencing which only accounts for analyzing bacterial abundance, while lacking an understanding of other crucial microbial kingdoms, such as viruses, fungi, archaea, and the functional profiling of the microbiome community. Utilizing data and samples of older adults with mild cognitive impairment (MCI; n = 23) and cognitively healthy controls ( n = 25). Our whole-genome metagenomic sequencing revealed that the gut of older adults with MCI harbors a less diverse microbiome with a specific increase in total viruses and a decrease in bacterial abundance compared with controls. The virome, bacteriome, and microbial metabolic signatures were significantly distinct in subjects with MCI versus controls. Selected bacteriome signatures show high predictive potential of cognitive dysfunction than virome signatures while combining virome and metabolic signatures with bacteriome boosts the prediction power. Altogether, the results from our pilot study indicate that trans-kingdom microbiome signatures are significantly distinct in MCI gut compared with controls and may have utility for predicting the risk of developing cognitive decline and dementia- debilitating public health problems in older adults.

Angler and guide perceptions provide insights into the status and threats of the Atlantic tarpon (Megalops atlanticus) fishery - Lucas P. Griffin; Grace A. Casselberry; Ezra M. Markowitz; Jacob W. Brownscombe; Aaron J. Adams; Bill Horn; Steven J. Cooke; Andy J. Danylchuk (Marine Policy, 2023)

Phylogenomics and biogeography of arid-adapted Chlamydogobius goby fishes - Krystina D. Mossop; Alan R. Lemmon; Emily Moriarty Lemmon; Ron Eytan; Mark Adams; Peter J. Unmack; Katie Smith Date; Hernán E. Morales; Michael P. Hammer; Bob B.M. Wong; David G. Chapple (Molecular Phylogenetics and Evolution, 2023)

TALKS: A systematic framework for resolving model-data discrepancies - Maria P. Vilas; Felix Egger; Matthew P. Adams; Holger R. Maier; Barbara Robson; Jonathan Ferrer Mestres; Lachlan Stewart; Paul Maxwell; Katherine R. O'Brien (Environmental Modelling & Software, 2023)

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

Adverse impacts of Roundup on soil bacteria, soil chemistry and mycorrhizal fungi during restoration of a Colorado grassland - Clifton P. Bueno de Mesquita; Adam J. Solon; Amy Barfield; Claire F. Mastrangelo; Abigail J. Tubman; Kim Vincent; Dorota L. Porazinska; Rebecca A. Hufft; Nancy Shackelford; Katharine N. Suding; Steven K. Schmidt (Applied Soil Ecology, 2023)

A pan-Baltic assessment of temporal trends in coastal pike populations - Jens Olsson; Matilda L. Andersson; Ulf Bergström; Robert Arlinghaus; Asta Audzijonyte; Soren Berg; Laura Briekmane; Justas Dainys; Henrik Dalby Ravn; Jan Droll; Łukasz Dziemian; Dariusz P. Fey; et al. (Fisheries Research, 2023)

Laboratory safety evaluation of lokivetmab, a canine anti-interleukin-31 monoclonal antibody, in dogs - Matthew Krautmann; Rodney R. Walters; Vickie L. King; Kevin Esch; Sean P. Mahabir; Andrea Gonzales; Paul J. Dominowski; Laurel Sly; Duncan Mwangi; Dennis L. Foss; Sharath Rai; James E. Messamore; et al. (Veterinary Immunology and Immunopathology, 2023)

Finite element model of female thermoregulation with geometry based on medical images - Michael P. Castellani; Timothy P. Rioux; John W. Castellani; Adam W. Potter; Sean R. Notley; Xiaojiang Xu (Journal of Thermal Biology, 2023)

Validation and Comparison of Nutrient Intakes from Two Dietary Questionnaires Developed for the Multiethnic Cohort Study - Lynne R. Wilkens; Minji Kang; Song-Yi Park; Adam Sawyer; Carol J. Boushey; Donna Lyn M. Au; Hee-Young Paik; Loïc Le Marchand; Christopher A. Haiman; Laurence N. Kolonel; Suzanne P. Murphy (Journal of the Academy of Nutrition and Dietetics, 2023)

Tracing widespread Early Miocene ignimbrite eruptions and petrogenesis at the onset of the Carpathian-Pannonian Region silicic volcanism - Mihovil Brlek; Simon Richard Tapster; Julie Schindlbeck-Belo; Sean P. Gaynor; Steffen Kutterolf; Folkmar Hauff; Svetoslav V. Georgiev; Nina Trinajstić; Sanja Šuica; Vlatko Brčić; Kuo-Lung Wang; Hao-Yang Lee; et al. (Gondwana Research, 2023)

Hydrodynamics of an integrated fish and periphyton recirculating aquaculture system - Adam N. Bell; Lior Guttman; Kevan L. Main; Michael Nystrom; Nathan P. Brennan; Sarina J. Ergas (Algal Research, 2023)

Agriculture accentuates interannual variability in water fluxes but not carbon fluxes, relative to native prairie, in the U.S. Corn Belt - Adam P. Schreiner-McGraw; Jeffrey D. Wood; Megan E. Metz; E. John Sadler; Kenneth A. Sudduth (Agricultural and Forest Meteorology, 2023)

A foam column system harvesting freshwater algae for biodiesel production: An experiment and process model evaluations - Shurooq T. Al-Humairi; Jonathan G.M. Lee; Adam P. Harvey; Ali Dawood Salman; Tatjána Juzsakova; B. Van; Phuoc–Cuong Le; D. Duong La; Arvind Kumar Mungray; Pau Loke Show; D. Duc Nguyen (Science of The Total Environment, 2023)

Investigating geological records of tsunamis in Western Thailand with environmental DNA - Wenshu Yap; Adam D. Switzer; Chris Gouramanis; Benjamin P. Horton; Ezequiel M. Marzinelli; Winona Wijaya; Yu Ting Yan; Dale Dominey-Howes; Maurizio Labbate; Kruawun Jankaew; Federico M. Lauro (Marine Geology, 2023)

Silicone passive sampling used to identify novel dermal chemical exposures of firefighters and assess PPE innovations - Emily M. Bonner; Gavin P. Horn; Denise L. Smith; Steve Kerber; Kenneth W. Fent; Lane G. Tidwell; Richard P. Scott; Kaley T. Adams; Kim A. Anderson (International Journal of Hygiene and Environmental Health, 2023)

Exploring the benefits and dis-benefits of climate migration as an adaptive strategy along the rural-peri-urban continuum in Namibia - Jessica P. R. Thorn; Penelao Nangolo; Rebeca Aleu Biancardi; Sheona Shackleton; Robert A. Marchant; Olayinka Ajala; Guillermo Delgado; John K. E. Mfune; Steve Cinderby; Adam P. Hejnowicz (Regional Environmental Change, 2023)
The scale of climate migration across the Global South is expected to increase during this century. By 2050, millions of Africans are likely to consider, or be pushed into, migration because of climate hazards contributing to agricultural disruption, water and food scarcity, desertification, flooding, drought, coastal erosion, and heat waves. However, the migration-climate nexus is complex, as is the question of whether migration can be considered a climate change adaptation strategy across both the rural and urban space. Combining data from household surveys, key informant interviews, and secondary sources related to regional disaster, demographic, resource, and economic trends between 1990 and 2020 from north central and central dryland Namibia, we investigate (i) human migration flows and the influence of climate hazards on these flows and (ii) the benefits and dis-benefits of migration in supporting climate change adaptation, from the perspective of migrants (personal factors and intervening obstacles), areas of origin, and areas of destination. Our analysis suggests an increase in climate-related push factors that could be driving rural out-migration from the north central region to peri-urban settlements in the central region of the country. While push factors play a role in rural-urban migration, there are also several pull factors (many of which have been long-term drivers of urban migration) such as perceived higher wages, diversity of livelihoods, water, health and energy provisioning, remittances, better education opportunities, and the exchange of non-marketed products. Migration to peri-urban settlements can reduce some risks (e.g. loss of crops and income due to climate extremes) but amplify others (e.g. heat stress and insecure land tenure). Adaptation at both ends of the rural–urban continuum is supported by deeply embedded linkages in a model of circular rural–urban-rural migration and interdependencies. Results empirically inform current and future policy debates around climate mobilities in Namibia, with wider implications across Africa. Graphical abstract

Do nurse plant effects strengthen over time? Results from 12 years of desert habitat restoration - Scott R. Abella; Lindsay P. Chiquoine; Mary A. Balogh; Adam J. Taylor; Seth M. Munson (Plant Ecology, 2023)

Tree Mortality may Drive Landscape Formation: Comparative Study from Ten Temperate Forests - P. Šamonil; P. Daněk; J. A. Lutz; K. J. Anderson-Teixeira; J. Jaroš; J. D. Phillips; A. Rousová; D. Adam; A. J. Larson; J. Kašpar; D. Janik; I. Vašíčková; et al. (Ecosystems, 2023)

Food safety concerns on polycyclic aromatic hydrocarbon contamination in fish products from estuarine bays throughout the American continent - Júlia Vianna de Pinho; Amanda P. Lopes; Paloma de Almeida Rodrigues; Rafaela Gomes Ferrari; Rachel Ann Hauser-Davis; Carlos Adam Conte-Junior (Science of The Total Environment, 2023)

Use of propionic acid additions to enhance zinc removal from mine drainage in short residence time, flow-through sulfate-reducing bioreactors - Catherine J. Gandy; Neil D. Gray; Obioma K. Mejeha; Angela Sherry; Adam P. Jarvis (Journal of Environmental Management, 2023)

Consistent responses to moisture stress despite diverse growth forms within mountain fynbos communities - Robert P. Skelton; Adam G. West; Daniel Buttner; Todd E. Dawson (Oecologia, 2023)
Understanding climate change impacts on the Cape Floristic Region requires improved knowledge of plant physiological responses to the environment. Studies examining physiological responses of mountain fynbos have consisted of campaign-based measurements, capturing snapshots of plant water relations and photosynthesis. We examine conclusions drawn from prior studies by tracking in situ physiological responses of three species, representing dominant growth forms (proteoid, ericoid, restioid), over 2 years using miniature continuous sap flow technology, long-term observations of leaf/culm water potential and gas exchange, and xylem vulnerability to embolism. We observed considerable inter-specific variation in the timing and extent of seasonal declines in productivity. Shallow-rooted Erica monsoniana exhibited steep within-season declines in sap flow and water potentials, and pronounced inter-annual variability in total daily sap flux ( J s ). Protea repens showed steady reductions in J s across both years, despite deeper roots and less negative water potentials. Cannomois congesta —a shallow-rooted restioid—was least negatively impacted. Following rehydrating rain at the end of summer, gas exchange recovery was lower in the drier year compared with the normal year, but did not differ between species. Loss of function in the drier year was partially accounted for by loss of xylem transport capacity in Erica and Cannomois , but not Protea. Hitherto unseen water use patterns, including inter-annual variability of gas exchange associated with contrasting water uptake properties, reveal that species use different mechanisms to cope with summer dry periods. Revealing physiological responses of key growth forms enhances predictions of plant function within mountain fynbos under future conditions.

Crown Lifting of Low-Density Loblolly Pine ( Pinus taeda ) Plantations on Nonindustrial Private Forest Lands - Darcey Collins; Joshua J Granger; Stephen Dicke; Krishna P Poudel; Adam Polinko; John L Willis (Forest Science, 2023)
Pruning or the physical removal of lower branches, in combination with wider tree spacing, offers an alternative management scheme for small nonindustrial private forest landowners in areas lacking markets for small diameter wood. A 5-year-old loblolly pine (Pinus taeda) plantation was thinned to 495 trees/ha (200 trees/ac). Four crown-lifting treatments of 35%, 40%, 45%, and 50% live crown ratio (LCR) were then implemented. An additional unmanaged plot was established in an unthinned, unpruned area. Two replications were established for all pruning treatments. The target LCR was maintained throughout the study with the additional crown-lifting activities in 2003, 2004, and 2008. At age 8, the average diameter of the unmanaged plot was 13.5 cm (5.3 in), and the diameter of the 50% LCR treatment, which had the greatest diameter growth of all the treatments, was 20.8 cm (8.2 in). The highest mortality rate (22%) was observed in the unmanaged plot, but it was not significantly greater than the other treatments. Low density plantings maintained with pruning could allow small nonindustrial private landowners to obtain a high value sawtimber product while eliminating the need for thinning practices commonly used in traditional pine plantation management.

Reliability of active robotic neuro-navigated transcranial magnetic stimulation motor maps - Cynthia K. Kahl; Adrianna Giuffre; James G. Wrightson; Ephrem Zewdie; Elizabeth G. Condliffe; Frank P. MacMaster; Adam Kirton (Experimental Brain Research, 2023)

A common measure of prey immune function is not constrained by the cascading effects of predators - Adam Z. Hasik; Simon P. Tye; Taylor Ping; Adam M. Siepielski (Evolutionary Ecology, 2023)

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Spatial-temporal patterns of Permit (Trachinotus falcatus) habitat residency in the Florida Keys, USA - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; Ross Boucek; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Correction to: Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos‑Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre‑Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos-Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre-Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

Perceptual and Acoustic Analysis of Speech in Spinocerebellar ataxia Type 1 - Teije van Prooije; Simone Knuijt; Judith Oostveen; Kirsten Kapteijns; Adam P. Vogel; Bart van de Warrenburg (The Cerebellum, 2023)
This study characterizes the speech phenotype of spinocerebellar ataxia type 1 (SCA1) using both perceptual and objective acoustic analysis of speech in a cohort of SCA1 patients. Twenty-seven symptomatic SCA1 patients in various disease stages (SARA score range: 3–32 points) and 18 sex and age matched healthy controls underwent a clinical assessment addressing ataxia severity, non-ataxia signs, cognitive functioning, and speech. Speech samples were perceptually rated by trained speech therapists, and acoustic metrics representing speech timing, vocal control, and voice quality were extracted. Perceptual analysis revealed reduced intelligibility and naturalness in speech samples of SCA1 patients. Acoustically, SCA1 patients presented with slower speech rate and diadochokinetic rate as well as longer syllable duration compared to healthy controls. No distinct abnormalities in voice quality in the acoustic analysis were detected at group level. Both the affected perceptual and acoustic variables correlated with ataxia severity. Longitudinal assessment of speech is needed to place changes in speech in the context of disease progression and potential response to treatment.

The drivers of anguillid eel movement in lentic water bodies: a systematic map - Michael J. Williamson; David M. P. Jacoby; Adam T. Piper (Reviews in Fish Biology and Fisheries, 2023)
Anguillid eels are near globally distributed catadromous fishes with marine spawning areas and inshore and inland growth areas in both lotic (rivers, estuaries) and lentic (lakes, ponds, lagoons) water bodies. As predators, anguillid eels play an important ecological role in both marine and freshwater systems, and several species are harvested commercially for food. However, some of the more widely distributed species have undergone severe declines in recruitment and their population status is now of significant concern. Given the multiple and lengthy migrations undertaken by anguillid eels, understanding of the drivers of movement is fundamental for species conservation and management. Yet, despite the importance of lentic systems to their ecology, most studies on anguillid eel movement have been conducted in lotic systems. Given that key influences on eel migration in lotic water bodies, such as fluctuations in flow and water temperature, may be minimised in lentic environments, the transferability of findings between lotic and lentic systems cannot be assumed. A systematic map was constructed to synthesise current knowledge on the extrinsic and intrinsic drivers of anguillid eel movement in lentic systems. The current state of knowledge of the drivers of eel movement in lentic systems is presented and compared to the relatively well-understood drivers of movement in lotic systems. We also discuss current knowledge gaps and limitations, and identify key future research requirements to inform the management and conservation of anguillid eels in understudied lentic systems. Graphical abstract

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Leaching composition and associated microbial community of recycled concrete aggregate (RCA) - Maedeh Soleimanifar; Anuruddha Jayasuriya; Matthew P. Adams; Lucia Rodriguez-Freire (Journal of Hazardous Materials, 2023)

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

Strategic model reduction by analysing model sloppiness: A case study in coral calcification - Sarah A. Vollert; Christopher Drovandi; Gloria M. Monsalve-Bravo; Matthew P. Adams (Environmental Modelling & Software, 2023)

Reconstructing the dynamics of managed populations to estimate the impact of citizen surveillance - Daniel Spring; Thao P. Le; Samuel Adam Bloom; Jonathan M. Keith; Tom Kompas (Ecological Modelling, 2023)

Fermentative conversion of unpretreated plant biomass: A thermophilic threshold for indigenous microbial growth - Ryan G. Bing; Morgan J. Carey; Tunyaboon Laemthong; Daniel J. Willard; James R. Crosby; Daniel B. Sulis; Jack P. Wang; Michael W.W. Adams; Robert M. Kelly (Bioresource Technology, 2023)

Low population genetic structure is consistent with high habitat connectivity in a commercially important fish species (Lutjanus jocu) - Julia Tovar Verba; Adam Stow; Bernhard Bein; Maria Grazia Pennino; Priscila F. M. Lopes; Beatrice P. Ferreira; Meghana Mortier; Sergio Maia Queiroz Lima; Ricardo J. Pereira (Marine Biology, 2023)
The level of habitat availability influences genetic divergence among populations and the genetic diversity within populations. In the marine environment, near-shore species are among the most sensitive to habitat changes. Knowledge of how historical environmental change affected habitat availability and genetic variation can be applied to the development of proactive management strategies of exploited species. Here, we modeled the contemporary and historical distribution of Lutjanus jocu in Brazil. We describe patterns of genomic diversity to better understand how climatic cycles might correlate with the species demographic history and current genetic structure. We show that during the Last Glacial Maximum, there were ecological barriers that are absent today, possibly dividing the range of the species into three geographically separated areas of suitable habitat. Consistent with a historical reduction in habitat area, our analysis of demographic changes shows that L. jocu experienced a severe bottleneck followed by a population size expansion. We also found an absence of genetic structure and similar levels of genetic diversity throughout the sampled range of the species. Collectively, our results suggest that habitat availability changes have not obviously influenced contemporary levels of genetic divergence between populations. However, our demographic analyses suggest that the high sensitivity of this species to environmental change should be taken into consideration for management strategies. Furthermore, the general low levels of genetic structure and inference of high gene flow suggest that L. jocu likely constitutes a single stock in Brazilian waters and, therefore, requires coordinated legislation and management across its distribution.

Diversity in financing and implementation pathways for industrial symbiosis across the globe - Zhe Liu; Weslynne S. Ashton; Michelle Adams; Qing Wang; Raymond P. Cote; Tony R. Walker; Lu Sun; Peter Lowitt (Environment, Development and Sustainability, 2023)

Tree Foliage is a Methane Sink in Upland Temperate Forests - Adam S. Gorgolewski; John P. Caspersen; Juliana Vantellingen; Sean C. Thomas (Ecosystems, 2023)

Calibration of conceptual rainfall-runoff models by selected differential evolution and particle swarm optimization variants - Jaroslaw J. Napiorkowski; Adam P. Piotrowski; Emilia Karamuz; Tesfaye B. Senbeta (Acta Geophysica, 2022)
The performance of conceptual catchment runoff models may highly depend on the specific choice of calibration methods made by the user. Particle Swarm Optimization (PSO) and Differential Evolution (DE) are two well-known families of Evolutionary Algorithms that are widely used for calibration of hydrological and environmental models. In the present paper, five DE and five PSO optimization algorithms are compared regarding calibration of two conceptual models, namely the Swedish HBV model (Hydrologiska Byrans Vattenavdelning model) and the French GR4J model (modèle du Génie Rural à 4 paramètres Journalier) of the Kamienna catchment runoff. This catchment is located in the middle part of Poland. The main goal of the study was to find out whether DE or PSO algorithms would be better suited for calibration of conceptual rainfall-runoff models. In general, four out of five DE algorithms perform better than four out of five PSO methods, at least for the calibration data. However, one DE algorithm constantly performs very poorly, while one PSO algorithm is among the best optimizers. Large differences are observed between results obtained for calibration and validation data sets. Differences between optimization algorithms are lower for the GR4J than for the HBV model, probably because GR4J has fewer parameters to optimize than HBV.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Conceptualizing a probabilistic risk and loss assessment framework for wildfires - Negar Elhami-Khorasani; Hamed Ebrahimian; Lawrence Buja; Susan L. Cutter; Branko Kosovic; Neil Lareau; Brian J. Meacham; Eric Rowell; Ertugrul Taciroglu; Matthew P. Thompson; Adam C. Watts (Natural Hazards, 2022)

Rediagnosis of the monotypic genus Lepadicyathus Prokofiev 2005 (Gobiesocidae: Diademichthyinae) and redescription of Lepadicyathus minor (Briggs 1955), new combination - Kyoji Fujiwara; Kevin W. Conway; Adam P. Summers; Hiroyuki Motomura (Ichthyological Research, 2022)

Association Between Head Impact Biomechanics and Physical Load in College Football - Bradley J. Lauck; Aaron M. Sinnott; Adam W. Kiefer; Darin A. Padua; Jacob R. Powell; Haley R. Sledge; Jason P. Mihalik (Annals of Biomedical Engineering, 2022)

Immersion challenge model for Flavobacterium psychrophilum infection of Atlantic salmon ( Salmo salar L.) fry - Valeria Macchia; Makoto Inami; Anne Ramstad; Fabian Grammes; Andrew Reeve; Thomas Moen; Jacob Seilø Torgersen; Alexandra Adams; Andrew P. Desbois; Rowena Hoare (Journal of Fish Diseases, 2022)
Flavobacterium psychrophilum is the causative agent of bacterial cold‐water disease (CWBD) and rainbow trout fry syndrome (RTFS), which affect salmonids. To better understand this pathogen and its interaction with the host during infection, including to support the development of resistant breeds and new vaccines and treatments, there is a pressing need for reliable and reproducible immersion challenge models that more closely mimic natural routes of infection. The aim of this present study was to evaluate a challenge model developed previously for rainbow trout for use in Atlantic salmon. First, preliminary challenges were conducted in Atlantic salmon ( n = 120) and rainbow trout ( n = 80) fry using two F. psychrophilum isolates collected from each fish species, respectively; fish had been pretreated with 200 mg/L hydrogen peroxide for 1 h. Thereafter, the main challenge was performed for just one F. psychrophilum isolate for each species (at 2 × 10 7 CFU/mL) but using larger cohorts (Atlantic salmon: n = 1187; rainbow trout: n = 2701). Survival in the main challenge was 81.2% in Atlantic salmon (21 days post‐challenge) and 45.3% in rainbow trout (31 days post‐challenge). Mortalities progressed similarly during the preliminary and main challenges for both species, demonstrating the reproducibility of this model. This is the first immersion challenge model of F. psychrophilum to be developed successfully for Atlantic salmon.

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Comparisons between sequenced and re-sequenced genomes of historical subterranean clover mottle virus isolates - John Fosu-Nyarko; Ian P. Adams; Michael G. K. Jones; Adrian Fox; Roger A. C. Jones (Journal of Plant Pathology, 2022)
We report comparisons between the complete genomic sequences of five historical Western Australian isolates of subterranean clover mottle virus (SCMoV) from 1989–2000, and an infectious clone of its 1989 isolate. Sanger Sequencing (SS) and High Throughput Sequencing (HTS), or both, were used to obtain these genomes. Four of the SCMoV isolates were sequenced by SS in 1999–2002, but re-sequenced again by HTS in 2020. The pairs of sequences obtained from these four isolates differed by only 18–59 nucleotides. This small difference resulted from the different sequencing methods, the < 1–5 years each isolate was host passaged before freeze-drying prior to HTS sequencing, or a combination of both. Since SCMoV has not been reported outside Australia, this similarity suggests the population sequenced represents the progeny of either an indigenous virus that spread from a native legume to subterranean clover after its introduction or a recent seed-borne incursion from elsewhere. The ORF1 was the most variable, and the phylogenetic tree constructed with ORF1s showed the isolates grouped according to their symptom severity in subterranean clover, indicating the probability that ORF1-encoded P1 protein is a symptom determinant. A satellite RNA was associated with all SCMoV genomes obtained by HTS but none derived by SS.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Eruptive history of Mason Spur, a Miocene—Pleistocene polygenetic volcanic complex in southern Victoria Land, West Antarctic Rift System, Antarctica - John L. Smellie; Adam P. Martin; Gianfranco Di Vincenzo; Dougal B. Townsend; Matthew T. Heizler; Dawn C. S. Ruth (Bulletin of Volcanology, 2022)
Mason Spur is a deeply eroded Middle Miocene to Pleistocene (c. 13 to 0.37 Ma) volcanic complex in southern Victoria Land, within the West Antarctic Rift System (WARS). The oldest rocks include a large volume of trachyte ignimbrites that provided abundant volcanic detritus recovered in McMurdo Sound drill cores. The ignimbrites together with early-formed intrusions were strongly deformed during a substantial caldera collapse at c. 13 Ma. Intense erosion modified the volcanic landscape, creating a paleo-relief of several hundred metres. Deep ravines were cut and filled by deposits of multiple lahars probably linked to gravitational collapses of trachyte dome(s). Small-volume trachytic magmas were also erupted, forming lavas and at least one tuff cone. The youngest trachytic activity comprises a lava dome and related block-and-ash-flow deposits, erupted at 6 Ma. Basanite erupted throughout the history of the complex and eruptions younger than 12 Ma are almost exclusively basanite, forming scoria cones, water-cooled lavas, and tuff cones. Three peripheral outcrops are composed of basanitic ‘a‘ā lava-fed deltas, probably erupted from vents on neighbouring volcanoes at Mount Discovery and Mount Morning. Abundant ignimbrite deposits at Mason Spur differentiate this volcanic complex from others in the WARS. Eruptions were triggered by rift extension initially, yielding the voluminous trachytes sourced from a magma chamber on the margin of the WARS. Later mafic eruptions were associated with deep crustal faults related to residual intraplate deformation. These results add important details to the eruptive history of the intracontinental WARS.

Predictive biophysical models of bivalve larvae dispersal in Scotland - Ana Corrochano-Fraile; Thomas P. Adams; Dmitry Aleynik; Michaël Bekaert; Stefano Carboni (Frontiers in Marine Science, 2022)
In Scotland, bivalves are widely distributed. However, their larvae dispersion is still largely unknown and difficult to assess in situ . And, while Mytilus spp. dominate shellfish production, it is mostly dependent on natural spat recruitment from wild populations. Understanding the larval distribution pattern would safeguard natural resources while also ensuring sustainable farming practises. The feasibility of a model that simulates biophysical interactions between larval behaviour and ocean motions was investigated. We employed an unstructured tri-dimensional hydrodynamic model (finite volume coastal ocean model) to drive a particle tracking model, where prediction of larval movement and dispersal at defined locations might aid in population monitoring and spat recruitment. Our findings reveal a strong link between larval distribution and meteorological factors such as wind forces and currents velocity. The model, also, depicts a fast and considerable larval movement, resulting in a substantial mix of plankton and bivalve larvae, forming a large connection between the southern and northern regions of Scotland’s West coast. This enables us to forecast the breeding grounds of any area of interest, potentially charting connectivity between cultivated and wild populations. These results have significant implications for the dynamics of ecologically and economically important species, such as population growth and loss, harvesting and agricultural management in the context of climate change, and sustainable shellfish fisheries management. Furthermore, the observations on Scottish water flow suggest that tracking particles with similar behaviour to bivalve larvae, such as other pelagic larval stages of keystone species and potential pathogens such as sea lice, may have policy and farming implications, as well as disease control amid global warming issues.

Correction to: The Impact of Right Temporal Lobe Epilepsy on Nonverbal Memory: Meta-regression of Stimulus- and Task-related Moderators - Adam C. Bentvelzen; Roy P. C. Kessels; Nicholas A. Badcock; Greg Savage (Neuropsychology Review, 2022)

The Impact of Right Temporal Lobe Epilepsy On Nonverbal Memory: Meta-regression of Stimulus- and Task-related Moderators - Adam C. Bentvelzen; Roy P. C. Kessels; Nicholas A. Badcock; Greg Savage (Neuropsychology Review, 2022)

Integrating blue: How do we make nationally determined contributions work for both blue carbon and local coastal communities? - Amrit Melissa Dencer-Brown; Robyn Shilland; Daniel Friess; Dorothée Herr; Lisa Benson; Nicholas J. Berry; Miguel Cifuentes-Jara; Patrick Colas; Ellyn Damayanti; Elisa López García; Marina Gavaldão; Gabriel Grimsditch; et al. (Ambio, 2022)
Blue Carbon Ecosystems (BCEs) help mitigate and adapt to climate change but their integration into policy, such as Nationally Determined Contributions (NDCs), remains underdeveloped. Most BCE conservation requires community engagement, hence community-scale projects must be nested within the implementation of NDCs without compromising livelihoods or social justice. Thirty-three experts, drawn from academia, project development and policy, each developed ten key questions for consideration on how to achieve this. These questions were distilled into ten themes, ranked in order of importance, giving three broad categories of people , policy & finance , and science & technology . Critical considerations for success include the need for genuine participation by communities, inclusive project governance, integration of local work into national policies and practices, sustaining livelihoods and income (for example through the voluntary carbon market and/or national Payment for Ecosystem Services and other types of financial compensation schemes) and simplification of carbon accounting and verification methodologies to lower barriers to entry.

Barriers in European spiny lobster ( Palinurus elephas ) aquaculture: What we know so far? - Adam L. K. Yeap; Cecília de Souza Valente; Finnian Hartnett; Ellie‐Ann Conneely; Majbritt Bolton‐Warberg; Simon J. Davies; Mark P. Johnson; Alex H. L. Wan (Reviews in Aquaculture, 2022)
Palinurids, also known as spiny lobsters, are high‐value seafood, which is economically important for many European and Asian seafood trades. However, the reduction of wild European spiny lobster populations produces a need for developing alternative renewable strategies to meet current and future demands. Aquaculture of spiny lobsters has the potential to become of major economic importance in the coming years with growing markets in Asia, Europe, and America, with Palinurus elephas being a promising candidate species for use in the commercial culture and stock enhancement of natural fisheries. This is due to its shorter larval periods and rapid growth to the critical puerulus stage compared with other spiny lobster species. While we have a basic understanding of the lifecycle and biology of P. elephas , much of this is based on work undertaken on similar species globally. There are many gaps in our knowledge that need to be addressed to make its aquaculture viable with appropriate feeds being an immediate issue as well as many other husbandry‐related factors. Previous studies act as a platform providing a baseline for further research and highlighting constraints. Developments in the use of P. elephas are promising due to realistically bridgeable knowledge gaps, the likelihood of producing sustainable food and the high commercial value of spiny lobsters. This review identifies our present state of knowledge and outlines the scope for further research and necessary technological developments to make it a viable contribution towards crustacean aquaculture in Europe.

Forty-year-old beet ringspot virus isolate: tests for potato true seed transmission, genome sequencing, recombination analysis and phylogenetic placement - Roger A. C. Jones; Aimee R. Fowkes; Sam McGreig; Adrian Fox; Ian P. Adams (Journal of Plant Pathology, 2022)
Summary Beet ringspot virus (BRSV) isolate IF came from a 1980 bait test on a Scottish soil sample. Between 1982 and 1984, it was used to study possible BRSV seed transmission in potato ( Solanum tuberosum ). To encourage flowering, potato scions were graft-inoculated onto tomato plants and these grafted plants were inoculated with IF. Flowers on BRSV-infected potato shoots were self-pollinated and their seeds collected. BRSV was found readily in pollen from these potato flowers, but never detected in any seedlings that grew from their seeds. Thus, although BRSV was present in pollen, no evidence of potato true seed transmission was obtained. In 1985, IF was preserved by freeze-drying and kept thereafter in a historical virus isolate collection. In 2020, it was subjected to high throughput sequencing and a complete genomic sequence was obtained. No recombination was detected in the IF sequence but its RNA1 and RNA2 were major parents of three, and a minor parent of one, recombinant BRSV isolates, respectively. Phylogenetic analysis of the P1 and P2 components of the coat protein gene encoded on its RNA2 placed the isolate IF sequence within the BRSV lineage. However, too few other BRSV sequences from different countries were present to provide information on its geographical associations.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Mapping risk to plant populations from short fire intervals via relationships between maturation period and environmental productivity - Carl R. Gosper; Ben P. Miller; Rachael V. Gallagher; Janine Kinloch; Richard van Dongen; Emma Adams; Sarah Barrett; Anne Cochrane; Sarah Comer; Lachlan McCaw; Russell G. Miller; Suzanne M. Prober; et al. (Plant Ecology, 2022)

The effect of salinity on the development of freshwater pike (Esox lucius) eggs in the context of drastic pike population decline in Puck Lagoon, Baltic Sea - Martyna Greszkiewicz; Dariusz P. Fey; Adam M. Lejk; Michał Zimak (Hydrobiologia, 2022)

Fibroadenoma in vulval ectopic breast tissue in a patient with PTEN Hamartoma Tumour Syndrome - Hannah Dawson; Alannah Smrke; Peter M. Ellery; Nafisa Wilkinson; Adam N. Rosenthal; Terri P. McVeigh (Familial Cancer, 2022)

An Update on the Measurement of Motor Cerebellar Dysfunction in Multiple Sclerosis - Katherine Hope Kenyon; Frederique Boonstra; Gustavo Noffs; Helmut Butzkueven; Adam P. Vogel; Scott Kolbe; Anneke van der Walt (The Cerebellum, 2022)
Multiple sclerosis (MS) is a progressive disease that often affects the cerebellum. It is characterised by demyelination, inflammation, and neurodegeneration within the central nervous system. Damage to the cerebellum in MS is associated with increased disability and decreased quality of life. Symptoms include gait and balance problems, motor speech disorder, upper limb dysfunction, and oculomotor difficulties. Monitoring symptoms is crucial for effective management of MS. A combination of clinical, neuroimaging, and task-based measures is generally used to diagnose and monitor MS. This paper reviews the present and new tools used by clinicians and researchers to assess cerebellar impairment in people with MS (pwMS). It also describes recent advances in digital and home-based monitoring for people with MS.

Enhancing plant N uptake with biochar-based fertilizers: limitation of sorption and prospects - Daniel P. Rasse; Simon Weldon; Erik J. Joner; Stephen Joseph; Claudia I. Kammann; Xiaoyu Liu; Adam O’Toole; Genxing Pan; N. Pelin Kocatürk-Schumacher (Plant and Soil, 2022)
Background Biochar-based fertilizer products (BCF) have been reported to increase both crop yield and N-use efficiency. Such positive effects are often assumed to result from the slow-release of N adsorbed on BCF structures. However, a careful review of the literature suggests that actual mechanisms remain uncertain, which hampers the development of efficient BCF products. Scope Here, we aim at reviewing BCF mechanisms responsible for enhanced N uptake by plants, and evaluate the potential for further improvement. We review the capacity of biochar structures to adsorb and release N forms, the biochar properties supporting this effect, and the methods that have been proposed to enhance this effect. Conclusions Current biochar products show insufficient sorption capacity for the retention of N forms to support the production of slow-release BCFs of high enough N concentration. Substantial slow-release effects appear to require conventional coating technology. Sorption capacity can be improved through activation and additives, but currently not to the extent needed for concentrated BCFs. Positive effects of commercial BCFs containing small amount of biochar appear to result from pyrolysis-derived biostimulants. Our review highlights three prospects for improving N retention: 1) sorption of NH 3 gas on specifically activated biochar, 2) synergies between biochar and clay porosities, which might provide economical sorption enhancement, and 3) physical loading of solid N forms within biochar. Beyond proof of concept, quantitative nutrient studies are needed to ascertain that potential future BCFs deliver expected effects on both slow-release and N use efficiency.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Corrigendum: Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2022)

Clinical withdrawal symptom profile of synthetic cannabinoid receptor agonists and comparison of effects with high potency cannabis - Sam Craft; Jason A. Ferris; Monica J. Barratt; Larissa J. Maier; Michael T. Lynskey; Adam R. Winstock; Tom P. Freeman (Psychopharmacology, 2022)
Synthetic cannabinoid receptor agonists (SCRAs) may be used as an alternative to natural cannabis; however, they may carry a greater risk of problematic use and withdrawal. This study aimed to characterise the withdrawal symptom profile of SCRAs and compare their profile of effect with high-potency herbal cannabis. Global Drug Survey data (2015 and 2016) were used to access a clinically relevant sample of people reporting use of SCRAs >10 times in the past 12-months, a previous SCRA quit attempt, and lifetime use of high-potency herbal cannabis. Participants completed an 11-item SCRA withdrawal symptom checklist and compared SCRAs and high-potency herbal cannabis on their onset and duration of effects, speed of the development of tolerance, severity of withdrawal, and difficulty with dose titration. Participants ( n = 284) reported experiencing a mean of 4.4 (95% CI: 4.1, 4.8) withdrawal symptoms after not using SCRAs for >1 day; most frequently reported were sleep issues (59.2%), irritability (55.6%), and low mood (54.2%). Withdrawal symptoms were significantly associated with frequency (>51 vs. 11–50 times per year: IRR = 1.43, 95% CI: 1.16, 1.77, p = 0.005) and quantity (grams per session: IRR = 1.13, 95% CI: 1.05, 1.22, p = 0.001) of SCRA use. Compared to high-potency herbal cannabis, SCRAs were rated as having a faster onset and shorter duration of effects, faster development of tolerance, and more severe withdrawal ( p ’s < 0.001). In conclusion, SCRA withdrawal symptoms are more likely to occur after greater SCRA exposure. The effects of SCRA indicate a more severe withdrawal syndrome and a greater risk of problematic use than natural cannabis.

High throughput sequencing of a 42 year-old isolate of hogweed virus 4 (HV4) reveals that is a member of the genus Chordovirus - Adrian Fox; Aimee Fowkes; Ines Vazquez-Iglesias; Christine Conyers; Ben Barrett; Sam McGreig; Ian P. Adams (Journal of Plant Pathology, 2022)

Greenhouse gases and green roofs: carbon dioxide and methane fluxes in relation to substrate characteristics - Md Abdul Halim; Juliana Vantellingen; Adam S. Gorgolewski; William K. Rose; Jennifer A. P. Drake; Liat Margolis; Sean C. Thomas (Urban Ecosystems, 2022)

Dark heterochromia in adult masked lapwings is universal, asymmetrical and possibly slightly sexually dimorphic - Adam P. A. Cardilini; Daniel Lees; Dylan Roche; Peter Dann; Michael A. Weston (Journal of Ornithology, 2022)
Variations in eye colour in birds are poorly documented. We measured and characterised eyes of 25 birds in the hand (16° × 22.5° segments per eye), using standardised and scaled images, and examined observations of 1 marked individual through time. We describe universal and extensive dark heterochromia (non-uniform colouration of the eye) in adult masked lapwings Vanellus miles novaehollandiae in our study population . Asymmetrical within-eye heterochromia has not previously been recorded for Charadridae, but in a review of images of eyes in the genus Vanellus , we found 45% of the 22 species had detectable heterochromia. There was a tendency ( p = 0.051 after false discovery rate correction) for males to have slightly less black in the upper posterior part of the eye, a difference not distinguishable enough to aid sexing in the hand. We suggest standardised images of captured birds would underpin a more nuanced understanding of the occurrence of subtle heterochromia among birds, which may permit phylogenetic analyses directed at exploring possible evolution or function of such eye pigmentation.

An opinion piece: the evolutionary and ecological consequences of changing selection pressures on marine migration in Atlantic salmon - Colin E. Adams; Louise Chavarie; Jessica R. Rodger; Hannele M. Honkanen; Davide Thambithurai; Matthew P. Newton (Journal of Fish Biology, 2022)
There are strong signals that the selection forces favouring the expression of long‐distance sea migration by Atlantic salmon ( Salmo salar ) are changing. Unlike many other behavioural traits, the costs of migration are incurred before any fitness benefits become apparent to the migrant. The expression of this behaviour has thus been shaped by selection forces over multiple generations and cannot respond to short interval (within a single generation) environmental change as many other behavioural traits can. Here we provide a framework to examine the evolutionary and ecological consequences of a sustained increase in migration cost. We argue that Atlantic salmon may have entered an evolutionary trap , where long‐distance sea migration has become maladaptive because of shifting environmental conditions. We predict that if higher migration costs (affecting survivorship and ultimately fitness) persist, then shifting selection pressures will result in continuing declines in population size. We suggest, however, that in some populations there is demonstrable capacity for evolutionary rescue responses within the species which is to be found in the variation in the expression of migration. Under a scenario of low to moderate change in the selection forces that previously promoted migration, we argue that disruptive, sex‐based selection would result in partial migration, where females retain sea migration but with anadromy loss predominantly in males. With more acute selection forces, anadromy may be strongly selected against, under these conditions both sexes may become freshwater resident. We suggest that as the migration costs appear to be higher in catchments with standing waters, then this outcome is more likely in such systems. We also speculate that as a result of the genetic structuring in this species, not all populations may have the capacity to respond adequately to change. The consequences of this for the species and its management are discussed.

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Effects of continuous cycling training on motor unit firing rates, input excitation, and myosin heavy chain of the vastus lateralis in sedentary females - Michael A. Trevino; Hannah L. Dimmick; Mandy E. Parra; Adam J. Sterczala; Jonathan D. Miller; Jake A. Deckert; Philip M. Gallagher; Andrew C. Fry; Joseph P. Weir; Trent J. Herda (Experimental Brain Research, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Offshore aquaculture of finfish: Big expectations at sea - Bernat Morro; Keith Davidson; Thomas P. Adams; Lynne Falconer; Max Holloway; Andrew Dale; Dmitry Aleynik; Philipp R. Thies; Faryal Khalid; Jon Hardwick; Helen Smith; Philip A. Gillibrand; et al. (Reviews in Aquaculture, 2022)
Offshore aquaculture has gained momentum in recent years, and the production of an increasing number of marine fish species is being relocated offshore. Initially, predictions of the advantages that offshore aquaculture would present over nearshore farming were made without enough science‐based evidence. Now, with more scientific knowledge, this review revisits past predictions and expectations of offshore aquaculture. We analysed and explained the oceanographic features that define offshore and nearshore sites. Using Atlantic salmon ( Salmo salar ) as a case study, we focussed on sea lice, amoebic gill disease, and the risk of harmful algal blooms, as well as the direct effects of the oceanography on the health and physiology of fish. The operational and licencing challenges and advantages of offshore aquaculture are also considered. The lack of space in increasingly saturated sheltered areas will push new farms out to offshore locations and, if appropriate steps are followed, offshore aquaculture can be successful. Firstly, the physical capabilities of the farmed fish species and infrastructure must be fully understood. Secondly, the oceanography of potential sites must be carefully studied to confirm that they are compatible with the species‐specific capabilities. And, thirdly, an economic plan considering the operational costs and licencing limitations of the site must be developed. This review will serve as a guide and a compilation of information for researchers and stakeholders.

New Opportunities and Untapped Scientific Potential in the Abyssal Ocean - Jeffrey J. Marlow; Rika E. Anderson; Anna-Louise Reysenbach; Jeffrey S. Seewald; Timothy M. Shank; Andreas P. Teske; V. Dorsey Wanless; S. Adam Soule (Frontiers in Marine Science, 2022)
The abyssal ocean covers more than half of the Earth’s surface, yet remains understudied and underappreciated. In this Perspectives article, we mark the occasion of the Deep Submergence Vehicle Alvin’s increased depth range (from 4500 to 6500 m) to highlight the scientific potential of the abyssal seafloor. From a geologic perspective, ultra-slow spreading mid-ocean ridges, Petit Spot volcanism, transform faults, and subduction zones put the full life cycle of oceanic crust on display in the abyss, revealing constructive and destructive forces over wide ranges in time and space. Geochemically, the abyssal pressure regime influences the solubility of constituents such as silica and carbonate, and extremely high-temperature fluid-rock reactions in the shallow subsurface lead to distinctive and potentially unique geochemical profiles. Microbial residents range from low-abundance, low-energy communities on the abyssal plains to fast growing thermophiles at hydrothermal vents. Given its spatial extent and position as an intermediate zone between coastal and deep hadal settings, the abyss represents a lynchpin in global-scale processes such as nutrient and energy flux, population structure, and biogeographic diversity. Taken together, the abyssal ocean contributes critical ecosystem services while facing acute and diffuse anthropogenic threats from deep-sea mining, pollution, and climate change.

A natural history account of Megalomyrmex ayri Brandão, 1990 (Hymenoptera: Formicidae: Myrmicinae) - L. P. Prado; R. R. Silva; C. R. F. Brandão; M. S. C. Morini; R. M. M. Adams (Insectes Sociaux, 2022)

Early onset of aging phenotype in vascular repair by Mas receptor deficiency - Goutham Vasam; Shrinidh Joshi S; Su Yamin Miyat; Hashim Adam; Yagna P. Jarajapu (GeroScience, 2022)

Mechanisms of breast cancer metastasis - S. David Nathanson; Michael Detmar; Timothy P. Padera; Lucy R. Yates; Danny R. Welch; Thomas C. Beadnell; Adam D. Scheid; Emma D. Wrenn; Kevin Cheung (Clinical & Experimental Metastasis, 2022)
Invasive breast cancer tends to metastasize to lymph nodes and systemic sites. The management of metastasis has evolved by focusing on controlling the growth of the disease in the breast/chest wall, and at metastatic sites, initially by surgery alone, then by a combination of surgery with radiation, and later by adding systemic treatments in the form of chemotherapy, hormone manipulation, targeted therapy, immunotherapy and other treatments aimed at inhibiting the proliferation of cancer cells. It would be valuable for us to know how breast cancer metastasizes; such knowledge would likely encourage the development of therapies that focus on mechanisms of metastasis and might even allow us to avoid toxic therapies that are currently used for this disease. For example, if we had a drug that targeted a gene that is critical for metastasis, we might even be able to cure a vast majority of patients with breast cancer. By bringing together scientists with expertise in molecular aspects of breast cancer metastasis, and those with expertise in the mechanical aspects of metastasis, this paper probes interesting aspects of the metastasis cascade, further enlightening us in our efforts to improve the outcome from breast cancer treatments.

Biophysics in the time of COVID - Adam P. Hill (Biophysical Reviews, 2022)

Metabolic and electrolyte abnormalities as risk factors in drug-induced long QT syndrome - Clifford TeBay; Adam P. Hill; Monique J. Windley (Biophysical Reviews, 2022)
Drug-induced long QT syndrome (diLQTS) is the phenomenon by which the administration of drugs causes prolongation of cardiac repolarisation and leads to an increased risk of the ventricular tachycardia known as torsades de pointes (TdP). In most cases of diLQTS, the primary molecular target is the human ether-à-go-go-related gene protein (hERG) potassium channel, which carries the rapid delayed rectifier current (I Kr ) in the heart. However, the proarrhythmic risk associated with drugs that block hERG can be modified in patients by a range of environmental- and disease-related factors, such as febrile temperatures, alterations in pH, dyselectrolytaemias such as hypokalaemia and hypomagnesemia and coadministration with other drugs. In this review, we will discuss the clinical occurrence of drug-induced LQTS in the context of these modifying factors as well as the mechanisms by which they contribute to altered hERG potency and proarrhythmic risk.

An introduction to decision science for conservation - Victoria Hemming; Abbey E. Camaclang; Megan S. Adams; Mark Burgman; Katherine Carbeck; Josie Carwardine; Iadine Chadès; Lia Chalifour; Sarah J. Converse; Lindsay N. K. Davidson; Georgia E. Garrard; Riley Finn; et al. (Conservation Biology, 2022)
Biodiversity conservation decisions are difficult, especially when they involve differing values, complex multidimensional objectives, scarce resources, urgency, and considerable uncertainty. Decision science embodies a theory about how to make difficult decisions and an extensive array of frameworks and tools that make that theory practical. We sought to improve conceptual clarity and practical application of decision science to help decision makers apply decision science to conservation problems. We addressed barriers to the uptake of decision science, including a lack of training and awareness of decision science; confusion over common terminology and which tools and frameworks to apply; and the mistaken impression that applying decision science must be time consuming, expensive, and complex. To aid in navigating the extensive and disparate decision science literature, we clarify meaning of common terms: decision science , decision theory , decision analysis , structured decision‐making , and decision‐support tools . Applying decision science does not have to be complex or time consuming; rather, it begins with knowing how to think through the components of a decision utilizing decision analysis (i.e., define the problem, elicit objectives, develop alternatives, estimate consequences, and perform trade‐offs). This is best achieved by applying a rapid‐prototyping approach. At each step, decision‐support tools can provide additional insight and clarity, whereas decision‐support frameworks (e.g., priority threat management and systematic conservation planning) can aid navigation of multiple steps of a decision analysis for particular contexts. We summarize key decision‐support frameworks and tools and describe to which step of a decision analysis, and to which contexts, each is most useful to apply. Our introduction to decision science will aid in contextualizing current approaches and new developments, and help decision makers begin to apply decision science to conservation problems.

A critical review of the compassionate conservation debate - Simon Coghlan; Adam P. A. Cardilini (Conservation Biology, 2022)
Compassionate conservation holds that compassion should transform conservation. It has prompted heated debate and has been criticized strongly. We reviewed the debate to characterize compassionate conservation and to philosophically analyze critiques that are recurring and that warrant further critical attention. The necessary elements of compassionate conservation relate to the moral value of sentient animals and conservation and to science and conservation practice. Although compassionate conservation has several nontraditional necessary conditions, it also importantly allows a degree of pluralism in values and scientific judgment regarding animals and conservation practice. We identified 52 specific criticisms from 11 articles that directly critique compassionate conservation. We closely examined 33 of these because they recurred regularly or included substantial questions that required further response. Critics criticized compassionate conservation's ethical foundations, scientific credentials, clarity of application, understanding of compassion , its alleged threat to conservation and biodiversity. Some criticisms, we found, are question begging, confused, or overlook conceptual complexity. These criticisms raise questions for critics and proponents, regarding, for example, equal versus differential intrinsic moral value of different sentient animals (including humans), problems of natural and human‐caused suffering of wild animals and predation, and the acceptability of specific conservation practices within compassionate conservation. By addressing recurring and faulty critiques of compassionate conservation and identifying issues for compassionate conservation to address, this review provides a clearer basis for crucial ongoing interdisciplinary dialogue about ethics, values, and conservation.

Bioconstruction and Bioerosion in the Northern Adriatic Coralligenous Reefs Quantified by X-Ray Computed Tomography - Eva Turicchia; Marco Abbiati; Matteo Bettuzzi; Barbara Calcinai; Maria Pia Morigi; Adam P. Summers; Massimo Ponti (Frontiers in Marine Science, 2022)
The northern Adriatic continental shelf hosts several coralligenous reefs rising from the sedimentary bottom and characterized by three main benthic assemblages, respectively, dominated by algal turfs, encrusting calcareous rhodophyte (ECRs) or erect sponges. Bioconstruction and bioerosion processes have been investigated using recruitment travertine limestone tiles deployed in a random site for each main benthic assemblages off Chioggia, 6.1–14.4 km offshore and 20.2–25.4 m depth. Tiles were retrieved after 3 and 12 years and analyzed by X-ray computed tomography (CT), allowing for non-destructively identifying and quantifying deposited and eroded limestone. The main builders were ECRs, serpulids, bryozoans, barnacles, and the bivalves Anomia ephippium , while the most effective borers were sponges from the genus Cliona and the bivalve Rocellaria dubia . The deposition of limestone after 12 years was greater at the site MR08 dominated by ECRs (12.52 ± 2.22 kg m –2 ), intermediate at the site P213 dominated by erect sponges (4.20 ± 1.24 kg m –2 ), and lower in the site P204 dominated by algal turfs (2.20 ± 0.72 kg m –2 ). At MR08, the deposition rate did not vary much over time (from 1.295 ± 0.270 to 1.080 ± 0.198 kg m –2 a –1 ), while in the other two sites, it significantly slowed down after the first survey period: from 0.952 ± 0.199 to 0.350 ± 0.103 kg m –2 a –1 at P213, and from 1.470 ± 0.462 to 0.203 ± 0.058 kg m –2 a –1 at P204. The amount of eroded limestone increased with the exposure time, with no significant differences among sites, from 1.13 ± 0.29 to 10.39 ± 1.14 kg m –2 on average at 3 and 12 years, respectively. The bioerosion rate also increased with the exposure time and was slightly higher at MR08 (from 0.682 ± 0.208 to 1.105 ± 0.088 kg m –2 a –1 ), mostly eroded by Cliona rhodensis in addition to C. viridis , compared to P204 (from 0.267 ± 0.078 to 0.676 ± 0.172 kg m –2 a –1 ) and P213 (from 0.179 ± 0.065 to 0.816 ± 0.171 kg m –2 a –1 ). Overall, bioconstruction has overcome the bioerosion processes in 3 years. In 12 years, the estimated net balance was essentially nil at all sites. Combining field experiment and CT analysis, this study provides the first quantification of the bioerosion and bioconstruction processes in the northern Adriatic coralligenous reefs, a fundamental step toward their conservation.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Response of Antarctic soil fauna to climate‐driven changes since the Last Glacial Maximum - André L. C. Franco; Byron J. Adams; Melisa A. Diaz; Nathan P. Lemoine; Nicholas B. Dragone; Noah Fierer; W. Berry Lyons; Ian Hogg; Diana H. Wall (Global Change Biology, 2022)
Understanding how terrestrial biotic communities have responded to glacial recession since the Last Glacial Maximum (LGM) can inform present and future responses of biota to climate change. In Antarctica, the Transantarctic Mountains (TAM) have experienced massive environmental changes associated with glacial retreat since the LGM, yet we have few clues as to how its soil invertebrate‐dominated animal communities have responded. Here, we surveyed soil invertebrate fauna from above and below proposed LGM elevations along transects located at 12 features across the Shackleton Glacier region. Our transects captured gradients of surface ages possibly up to 4.5 million years and the soils have been free from human disturbance for their entire history. Our data support the hypothesis that soils exposed during the LGM are now less suitable habitats for invertebrates than those that have been exposed by deglaciation following the LGM. Our results show that faunal abundance, community composition, and diversity were all strongly affected by climate‐driven changes since the LGM. Soils more recently exposed by the glacial recession (as indicated by distances from present ice surfaces) had higher faunal abundances and species richness than older exposed soils. Higher abundances of the dominant nematode Scottnema were found in older exposed soils, while Eudorylaimus , Plectus , tardigrades, and rotifers preferentially occurred in more recently exposed soils. Approximately 30% of the soils from which invertebrates could be extracted had only Scottnema , and these single‐taxon communities occurred more frequently in soils exposed for longer periods of time. Our structural equation modeling of abiotic drivers highlighted soil salinity as a key mediator of Scottnema responses to soil exposure age. These changes in soil habitat suitability and biotic communities since the LGM indicate that Antarctic terrestrial biodiversity throughout the TAM will be highly altered by climate warming.

Tracking deepwater oxygen recovery using sedimentary chironomid assemblages: Peninsula Lake revisited - Adam Jeziorski; Clare Nelligan; Dara Corrigan; Carsten Meyer-Jacob; Andrew M. Paterson; John P. Smol (Journal of Paleolimnology, 2021)

Timescales and thermal evolution of large silicic magma reservoirs during an ignimbrite flare-up: perspectives from zircon - Adam Curry; Sean P. Gaynor; J. H. F. L. Davies; Maria Ovtcharova; Guy Simpson; Luca Caricchi (Contributions to Mineralogy and Petrology, 2021)
Four voluminous ignimbrites (150–500 km 3 ) erupted in rapid succession at 27 Ma in the central San Juan caldera cluster, Colorado. To reconstruct the timescales and thermal evolution of these magma reservoirs, we used zircon ID-TIMS U–Pb geochronology, zircon LA-ICP-MS geochemistry, thermal modeling, and zircon age and crystallization modeling. Zircon geochronology reveals dispersed zircon age spectra in all ignimbrites, with decreasing age dispersion through time that we term a ‘chimney sweeping’ event. Zircon whole-grain age modeling suggests that 2σ zircon age spans represent approximately one-quarter of total zircon crystallization timescales due to the averaging effect of whole-grain, individual zircon ages, resulting in zircon crystallization timescales of 0.8–2.7 m.y. Thermal and zircon crystallization modeling combined with Ti-in-zircon temperatures indicates that magma reservoirs were built over millions of years at relatively low magmatic vertical accretion rates (VARs) of 2–5 × 10 –3 m y −1 (2–5 × 10 –6 km 3 y −1 km −2 ), and we suggest that such low VARs were characteristic of the assembly of the greater San Juan magmatic body. Though we cannot unequivocally discern between dispersed zircon age spectra caused by inheritance (xenocrystic or antecrystic) versus prolonged crystallization from the same magma reservoir (autocrystic), our findings suggest that long-term magma input at relatively low VARs produced thermally mature upper crustal magma reservoirs resulting in protracted zircon crystallization timescales. Compiling all U–Pb ID-TIMS zircon ages of large ignimbrites, we interpret the longer timescales of subduction-related ignimbrites as a result of longer term, lower flux magmatism, and the shorter timescales of Snake River Plain ignimbrites as a result of shorter term, higher flux magmatism.

Genetic structure of endangered species Adenophora liliifolia and footprints of postglacial recolonisation in Central Europe - Lucie Vaculná; Ľuboš Majeský; Tahir Ali; Alexey P. Seregin; Romana Prausová; Adam Kapler; Dmytro Iakushenko; Marco Thines; Miloslav Kitner (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Using Predicted Patterns of 3D Prey Distribution to Map King Penguin Foraging Habitat - Roland Proud; Camille Le Guen; Richard B. Sherley; Akiko Kato; Yan Ropert-Coudert; Norman Ratcliffe; Simon Jarman; Adam Wyness; John P. Y. Arnould; Ryan A. Saunders; Paul G. Fernandes; Lars Boehme; et al. (Frontiers in Marine Science, 2021)
King penguins ( Aptenodytes patagonicus ) are an iconic Southern Ocean species, but the prey distributions that underpin their at-sea foraging tracks and diving behaviour remain unclear. We conducted simultaneous acoustic surveys off South Georgia and tracking of king penguins breeding ashore there in Austral summer 2017 to gain insight into habitat use and foraging behaviour. Acoustic surveys revealed ubiquitous deep scattering layers (DSLs; acoustically detected layers of fish and other micronekton that inhabit the mesopelagic zone) at c. 500 m and shallower ephemeral fish schools. Based on DNA extracted from penguin faecal samples, these schools were likely comprised of lanternfish (an important component of king penguin diets), icefish ( Channichthyidae spp.) and painted noties ( Lepidonotothen larseni ). Penguins did not dive as deep as DSLs, but their prey-encounter depth-distributions, as revealed by biologging, overlapped at fine scale (10s of m) with depths of acoustically detected fish schools. We used neural networks to predict local scale (10 km) fish echo intensity and depth distribution at penguin dive locations based on environmental correlates, and developed models of habitat use. Habitat modelling revealed that king penguins preferentially foraged at locations predicted to have shallow and dense (high acoustic energy) fish schools associated with shallow and dense DSLs. These associations could be used to predict the distribution of king penguins from other colonies at South Georgia for which no tracking data are available, and to identify areas of potential ecological significance within the South Georgia and the South Sandwich Islands marine protected area.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Large Vessel Activity and Low-Frequency Underwater Sound Benchmarks in United States Waters - Samara M. Haver; Jeffrey D. Adams; Leila T. Hatch; Sofie M. Van Parijs; Robert P. Dziak; Joseph Haxel; Scott A. Heppell; Megan F. McKenna; David K. Mellinger; Jason Gedamke (Frontiers in Marine Science, 2021)
Chronic low-frequency noise from commercial shipping is a worldwide threat to marine animals that rely on sound for essential life functions. Although the U.S. National Oceanic and Atmospheric Administration recognizes the potential negative impacts of shipping noise in marine environments, there are currently no standard metrics to monitor and quantify shipping noise in U.S. marine waters. However, one-third octave band acoustic measurements centered at 63 and 125 Hz are used as international (European Union Marine Strategy Framework Directive) indicators for underwater ambient noise levels driven by shipping activity. We apply these metrics to passive acoustic monitoring data collected over 20 months in 2016–2017 at five dispersed sites throughout the U.S. Exclusive Economic Zone: Alaskan Arctic, Hawaii, Gulf of Mexico, Northeast Canyons and Seamounts Marine National Monument (Northwest Atlantic), and Cordell Bank National Marine Sanctuary (Northeast Pacific). To verify the relationship between shipping activity and underwater sound levels, vessel movement data from the Automatic Identification System (AIS) were paired to each passive acoustic monitoring site. Daily average sound levels were consistently near to or higher than 100 dB re 1 μPa in both the 63 and 125 Hz one-third octave bands at sites with high levels of shipping traffic (Gulf of Mexico, Northeast Canyons and Seamounts, and Cordell Bank). Where cargo vessels were less common (the Arctic and Hawaii), daily average sound levels were comparatively lower. Specifically, sound levels were ∼20 dB lower year-round in Hawaii and ∼10-20 dB lower in the Alaskan Arctic, depending on the season. Although these band-level measurements can only generally facilitate differentiation of sound sources, these results demonstrate that international acoustic indicators of commercial shipping can be applied to data collected in U.S. waters as a unified metric to approximate the influence of shipping as a driver of ambient noise levels, provide critical information to managers and policy makers about the status of marine environments, and to identify places and times for more detailed investigation regarding environmental impacts.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

The Hammer and the Nail: Biomechanics of Striking and Struck Canadian University Football Players - Jeffrey S. Brooks; Adam Redgrift; Allen A. Champagne; James P. Dickey (Annals of Biomedical Engineering, 2021)
This study sought to evaluate head accelerations in both players involved in a football collision. Players on two opposing Canadian university teams were equipped with helmet mounted sensors during one game per season, for two consecutive seasons. A total of 276 collisions between 58 instrumented players were identified via video and cross-referenced with sensor timestamps. Player involvement (striking and struck), impact type (block or tackle), head impact location (front, back, left and right), and play type were recorded from video footage. While struck players did not experience significantly different linear or rotational accelerations between any play types, striking players had the highest linear and rotational head accelerations during kickoff plays ( p ≤ .03). Striking players also experienced greater linear and rotational head accelerations than struck players during kickoff plays ( p = .001). However, struck players experienced greater linear and rotational accelerations than striking players during kick return plays ( p ≤ .008). Other studies have established that the more severe the head impact, the greater risk for injury to the brain. This paper’s results highlight that kickoff play rule changes, as implemented in American college football, would decrease head impact exposure of Canadian university football athletes and make the game safer.

Toxicity Assays of Commercial Chlorpyrifos Under UV/H2O2 and UVC Photolysis Treatments - Suelen Angeli; Eliane Adams; Gabriella P. Masceno; Rúbia M. Lima; Larisa M. Utzig; Fernando Rodrigues-Silva; Liziê D. T. Prola; Adriane M. Freitas; Marcus V. Liz (Water, Air, & Soil Pollution, 2021)

An early warning system for wave-driven coastal flooding at Imperial Beach, CA - Mark A. Merrifield; Mele Johnson; R. T. Guza; Julia W. Fiedler; Adam P. Young; Cassandra S. Henderson; Athina M. Z. Lange; William C. O’Reilly; Bonnie C. Ludka; Michele Okihiro; Timu Gallien; Kyle Pappas; et al. (Natural Hazards, 2021)
Waves overtop berms and seawalls along the shoreline of Imperial Beach (IB), CA when energetic winter swell and high tide coincide. These intermittent, few-hour long events flood low-lying areas and pose a growing inundation risk as sea levels rise. To support city flood response and management, an IB flood warning system was developed. Total water level (TWL) forecasts combine predictions of tides and sea-level anomalies with wave runup estimates based on incident wave forecasts and the nonlinear wave model SWASH. In contrast to widely used empirical runup formulas that rely on significant wave height and peak period, and use only a foreshore slope for bathymetry, the SWASH model incorporates spectral incident wave forcing and uses the cross-shore depth profile. TWL forecasts using a SWASH emulator demonstrate skill several days in advance. Observations set TWL thresholds for minor and moderate flooding. The specific wave and water level conditions that lead to flooding, and key contributors to TWL uncertainty, are identified. TWL forecast skill is reduced by errors in the incident wave forecast and the one-dimensional runup model, and lack of information of variable beach morphology (e.g., protective sand berms can erode during storms). Model errors are largest for the most extreme events. Without mitigation, projected sea-level rise will substantially increase the duration and severity of street flooding. Application of the warning system approach to other locations requires incident wave hindcasts and forecasts, numerical simulation of the runup associated with local storms and beach morphology, and model calibration with flood observations.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Correction to: Field evaluation of seven products to control cyanobacterial blooms in aquaculture - Riley P. Buley; Catie Adams; Angelea P. Belfiore; Edna G. Fernandez-Figueroa; Matthew F. Gladfelter; Brynne Garner; David L. Straus; Alan E. Wilson (Environmental Science and Pollution Research, 2021)

Invasion and Extirpation Potential of Native and Invasive Spartina Species Under Climate Change - Francisco O. Borges; Catarina P. Santos; José R. Paula; Enrique Mateos-Naranjo; Susana Redondo-Gomez; Janine Barbara Adams; Isabel Caçador; Vanessa F. Fonseca; Patrick Reis-Santos; Bernardo Duarte; Rui Rosa (Frontiers in Marine Science, 2021)
Coastal areas host some of the planet’s most productive ecosystems, providing life-sustaining ecological services and several benefits to humankind, while also being some of the most threatened areas (e.g., by globalization, climate change, and biological invasion). Salt marshes are coastal habitats with a key role in food and shelter provisioning, sediment deposition, nutrient cycling and carbon storage. Spartina spp. is a genus of grass halophytes which occurs in salt marshes worldwide, and includes species with different invasive potential. We evaluated the effect of climate change in the distribution and invasion potential of five Spartina species ( S. anglica , S. alterniflora , S. densiflora , S. patens , and S. maritima ) at a global scale. Species distribution models (SDMs) were applied on species occurrence data and atmospheric environmental predictors (WorldClim 2.1) to project potential changes in habitat suitability and associated changes in distribution and species co-occurrence until the end of the century, across four Shared Socioeconomic Pathway scenarios (i.e., SSP1-2.6 to SSP5-8.5). Projections showed a global trend for increasing species co-occurrence, with a general range expansion potentiated by increasing pathway severity. This study suggests that Spartina species can potentially benefit from climate change, predicting poleward expansions in the Northern Hemisphere for most species, with results pointing at increased conflict and invasion potential in Northern Europe and East Asian shorelines, already under strong invasive pressure. S. anglica is projected to remain a successful invader, with more severe scenarios likely favoring greater expansions. S. alterniflora exhibits very low expansion comparatively, despite exhibiting the same northward distribution shift. SSP1-2.6 produced the smallest change to species co-occurrence, suggesting a smaller potential for invasion-related conflicts, although still registering a potential net expansion for the Genus. Despite their limitations, SDMs can help establish general trends in climate change ecology and inform policymakers and environmental agents to ensure the correct management of these habitats and, ultimately, ecosystems.

A digital tool for prevention and management of cold weather injuries—Cold Weather Ensemble Decision Aid (CoWEDA) - Xiaojiang Xu; Timothy P. Rioux; Julio Gonzalez; Eric O. Hansen; John W. Castellani; William R. Santee; Anthony J. Karis; Adam W. Potter (International Journal of Biometeorology, 2021)
This paper describes a Cold Weather Ensemble Decision Aid (CoWEDA) that provides guidance for cold weather injury prevention, mission planning, and clothing selection. CoWEDA incorporates current science from the disciplines of physiology, meteorology, clothing, and computer modeling. The thermal performance of a cold weather ensemble is defined by endurance times, which are the time intervals from initial exposure until the safety limits are reached. These safety limits correspond to conservative temperature thresholds that provide a warning of the approaching onset of frostbite and/or hypothermia. A validated six-cylinder thermoregulatory model is used to predict human thermal responses to cold while wearing different ensembles. The performance metrics, model, and a database of clothing properties were integrated into a user-friendly software application. CoWEDA is the first tool that allows users to build their own ensembles from the clothing menu (i.e., jackets, footwear, and accessories) for each body region (i.e., head, torso, lower body, hands, feet) and view their selections in the context of physiological strain and the operational consequences. Comparison of predicted values to skin and core temperatures, measured during 17 cold exposures ranging from 0 to −40°C, indicated that the accuracy of CoWEDA prediction is acceptable, and most predictions are within measured mean ± SD. CoWEDA predicts the risk of frostbite and hypothermia and ensures that a selected clothing ensemble is appropriate for expected weather conditions and activities. CoWEDA represents a significant enhancement of required clothing insulation (IREQ, ISO 11079) and wind chill index-based guidance for cold weather safety and survival.

Pathogenic STX3 variants affecting the retinal and intestinal transcripts cause an early-onset severe retinal dystrophy in microvillus inclusion disease subjects - Andreas R. Janecke; Xiaoqin Liu; Rüdiger Adam; Sumanth Punuru; Arne Viestenz; Valeria Strauß; Martin Laass; Elizabeth Sanchez; Roberto Adachi; Martha P. Schatz; Ujwala S. Saboo; Naveen Mittal; et al. (Human Genetics, 2021)
Biallelic STX3 variants were previously reported in five individuals with the severe congenital enteropathy, microvillus inclusion disease (MVID). Here, we provide a significant extension of the phenotypic spectrum caused by STX3 variants. We report ten individuals of diverse geographic origin with biallelic STX3 loss-of-function variants, identified through exome sequencing, single-nucleotide polymorphism array-based homozygosity mapping, and international collaboration. The evaluated individuals all presented with MVID. Eight individuals also displayed early-onset severe retinal dystrophy, i.e., syndromic—intestinal and retinal—disease. These individuals harbored STX3 variants that affected both the retinal and intestinal STX3 transcripts, whereas STX3 variants affected only the intestinal transcript in individuals with solitary MVID. That STX3 is essential for retinal photoreceptor survival was confirmed by the creation of a rod photoreceptor-specific STX3 knockout mouse model which revealed a time-dependent reduction in the number of rod photoreceptors, thinning of the outer nuclear layer, and the eventual loss of both rod and cone photoreceptors. Together, our results provide a link between STX3 loss-of-function variants and a human retinal dystrophy. Depending on the genomic site of a human loss-of-function STX3 variant, it can cause MVID, the novel intestinal-retinal syndrome reported here or, hypothetically, an isolated retinal dystrophy.

Exposure to degraded coral habitat depresses oxygen uptake rate during exercise of a juvenile reef fish - Adam T. Downie; Caroline M. Phelps; Rhondda Jones; Jodie L. Rummer; Douglas P. Chivers; Maud C. O. Ferrari; Mark I. McCormick (Coral Reefs, 2021)

Cultural determinants of climate change opinion: familism predicts climate beliefs and policy support among US Latinos - Adam R. Pearson; Guadalupe A. Bacio; Sarah Naiman; Rainer Romero-Canyas; Jonathon P. Schuldt (Climatic Change, 2021)

Unravelling the taxonomy and identification of a problematic group of benthic fishes from tropical rivers (Gobiidae: Glossogobius ) - Michael P. Hammer; Laura Taillebois; Alison J. King; David A. Crook; Dion Wedd; Mark Adams; Peter J. Unmack; Doug F. Hoese; Terry Bertozzi (Journal of Fish Biology, 2021)
Flathead gobies (genus Glossogobius ) include c . 40 small‐ to medium‐sized benthic fishes found primarily in freshwater habitats across the Indo‐Pacific, having biodiversity value as well as cultural and economic value as food fishes, especially in developing countries. To help resolve considerable confusion regarding the identification of some of the larger‐growing Glossogobius species, a systematic framework was established using nuclear genetic markers, mitochondrial DNA barcoding and phenotypic evidence for a geographically widespread collection of individuals from the waterways of tropical northern Australia. Species boundaries and distribution patterns were discordant with those previously reported, most notably for the tank goby Glossogobius giuris , which included a cryptic species. Genetic divergence was matched with accompanying unique visual characters that aid field identification. Additional taxonomic complexity was also evident, by comparison with DNA barcodes from international locations, suggesting that the specific names applicable for two of the candidate species in Australia remain unresolved due to confusion surrounding type specimens. Although flathead gobies are assumed to be widespread and common, this study demonstrates that unrealised taxonomic and ecological complexity is evident, and this will influence assessments of tropical biodiversity and species conservation. This study supports the need for taxonomic studies of freshwater fishes to underpin management in areas subject to significant environmental change.

Is impaired dopaminergic function associated with mobility capacity in older adults? - Simon Moskowitz; David W. Russ; Leatha A. Clark; Nathan P. Wages; Dustin R. Grooms; Adam J. Woods; Julie Suhr; Janet E. Simon; Andrew O’Shea; Cody R. Criss; Paolo Fadda; Brian C. Clark (GeroScience, 2021)

Field evaluation of seven products to control cyanobacterial blooms in aquaculture - Riley P. Buley; Catie Adams; Angelea P. Belfiore; Edna G. Fernandez-Figueroa; Matthew F. Gladfelter; Brynne Garner; Alan E. Wilson (Environmental Science and Pollution Research, 2021)

Fine-Scale Air Pollution Models for Epidemiologic Research: Insights From Approaches Developed in the Multi-ethnic Study of Atherosclerosis and Air Pollution (MESA Air) - Kipruto Kirwa; Adam A. Szpiro; Lianne Sheppard; Paul D. Sampson; Meng Wang; Joshua P. Keller; Michael T. Young; Sun-Young Kim; Timothy V. Larson; Joel D. Kaufman (Current Environmental Health Reports, 2021)

A Simplified In Silico Model of Left Ventricular Outflow in Patients After Transcatheter Mitral Valve Replacement with Anterior Leaflet Laceration - Keshav Kohli; Zhenglun Alan Wei; Vahid Sadri; Tiffany Netto; John C. Lisko; Adam B. Greenbaum; Vasilis Babaliaros; John N. Oshinski; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Importance of species translocations under rapid climate change - Nathalie Butt; Alienor L.M. Chauvenet; Vanessa M. Adams; Maria Beger; Rachael V. Gallagher; Danielle F. Shanahan; Michelle Ward; James E.M. Watson; Hugh P. Possingham (Conservation Biology, 2021)
Species that cannot adapt or keep pace with a changing climate are likely to need human intervention to shift to more suitable climates. While hundreds of articles mention using translocation as a climate‐change adaptation tool, in practice, assisted migration as a conservation action remains rare, especially for animals. This is likely due to concern over introducing species to places where they may become invasive. However, there are other barriers to consider, such as time‐frame mismatch, sociopolitical, knowledge and uncertainty barriers to conservationists adopting assisted migration as a go‐to strategy. We recommend the following to advance assisted migration as a conservation tool: attempt assisted migrations at small scales, translocate species with little invasion risk, adopt robust monitoring protocols that trigger an active response, and promote political and public support.

Elasmobranch Community Dynamics in Florida’s Southern Indian River Lagoon - Grace Roskar; Michael P. McCallister; Adam M. Schaefer; Matthew J. Ajemian (Estuaries and Coasts, 2021)

Resource Occurrence and Productivity in Existing and Proposed Wind Energy Lease Areas on the Northeast US Shelf - Kevin D. Friedland; Elizabeth T. Methratta; Andrew B. Gill; Sarah K. Gaichas; Tobey H. Curtis; Evan M. Adams; Janelle L. Morano; Daniel P. Crear; M. Conor McManus; Damian C. Brady (Frontiers in Marine Science, 2021)
States in the Northeast United States have the ambitious goal of producing more than 22 GW of offshore wind energy in the coming decades. The infrastructure associated with offshore wind energy development is expected to modify marine habitats and potentially alter the ecosystem services. Species distribution models were constructed for a group of fish and macroinvertebrate taxa resident in the Northeast US Continental Shelf marine ecosystem. These models were analyzed to provide baseline context for impact assessment of lease areas in the Middle Atlantic Bight designated for renewable wind energy installations. Using random forest machine learning, models based on occurrence and biomass were constructed for 93 species providing seasonal depictions of their habitat distributions. We developed a scoring index to characterize lease area habitat use for each species. Subsequently, groups of species were identified that reflect varying levels of lease area habitat use ranging across high, moderate, low, and no reliance on the lease area habitats. Among the species with high to moderate reliance were black sea bass ( Centropristis striata ), summer flounder ( Paralichthys dentatus ), and Atlantic menhaden ( Brevoortia tyrannus ), which are important fisheries species in the region. Potential for impact was characterized by the number of species with habitat dependencies associated with lease areas and these varied with a number of continuous gradients. Habitats that support high biomass were distributed more to the northeast, while high occupancy habitats appeared to be further from the coast. There was no obvious effect of the size of the lease area on the importance of associated habitats. Model results indicated that physical drivers and lower trophic level indicators might strongly control the habitat distribution of ecologically and commercially important species in the wind lease areas. Therefore, physical and biological oceanography on the continental shelf proximate to wind energy infrastructure development should be monitored for changes in water column structure and the productivity of phytoplankton and zooplankton and the effects of these changes on the trophic system.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Lava effusion rate evolution and erupted volume during the 2018 Kīlauea lower East Rift Zone eruption - Hannah R. Dietterich; Angela K. Diefenbach; S. Adam Soule; Michael H. Zoeller; Matthew P. Patrick; Jon J. Major; Paul R. Lundgren (Bulletin of Volcanology, 2021)

The population genomics of repeated freshwater colonizations by Gulf pipefish - Sarah P. Flanagan; Emily Rose; Adam G. Jones (Molecular Ecology, 2021)
How organisms adapt to the novel challenges imposed by the colonization of a new habitat has long been a central question in evolutionary biology. When multiple populations of the same species independently adapt to similar environmental challenges, the question becomes whether the populations have arrived at their adaptations through the same genetic mechanisms. In recent years, genetic techniques have been used to tackle these questions by investigating the genome‐level changes underlying local adaptation. Here, we present a genomic analysis of colonization of freshwater habitats by a primarily marine fish, the Gulf pipefish ( Syngnathus scovelli ). We sample pipefish from four geographically distinct freshwater locations and use double‐digest restriction site associated DNA sequencing to compare them to 12 previously studied saltwater populations. The two most geographically distant and isolated freshwater populations are the most genetically distinct, although demographic analysis suggests that these populations are experiencing ongoing migration with their saltwater neighbours. Additionally, outlier regions were found genome‐wide, showing parallelism across ecotype pairs. We conclude that these multiple freshwater colonizations involve similar genomic regions, despite the large geographical distances and different underlying mechanisms. These similar patterns are probably facilitated by the interacting effects of intrinsic barriers, gene flow among populations and ecological selection in the Gulf pipefish.

Diets of double‐crested cormorants in the Lake Winnebago System, Wisconsin - Ryan P. Koenigs; Daniel J. Dembkowski; Charles D. Lovell; Daniel A. Isermann; Adam D. Nickel (Fisheries Management and Ecology, 2021)
Double‐crested cormorant Phalacrocorox auritus Lesson (cormorant) populations have increased throughout the Great Lakes region of North America causing concern related to the impact of cormorant predation on fish communities. A recent decline in yellow perch Perca flavescens (Mitchill) abundance within the Lake Winnebago System, Wisconsin, USA, prompted an assessment of cormorant diets to evaluate potential effects of cormorant predation on the sportfish community. Diets were collected from 883 cormorants (417 from Lake Winnebago and 466 from Lake Butte des Morts) between 2015 and 2017. Cormorant diets on both waterbodies consisted mostly of freshwater drum Aplodinotus grunniens Rafinesque and gizzard shad Dorosoma cepedianum (Lesueur). Yellow perch and walleye Sander vitreus (Mitchill) observations were infrequent and represented

Evaluating surrogates of genetic diversity for conservation planning - Jeffrey O. Hanson; Ana Veríssimo; Guillermo Velo‐Antón; Adam Marques; Miguel Camacho‐Sanchez; Íñigo Martínez‐Solano; Helena Gonçalves; Fernando Sequeira; Hugh P. Possingham; Silvia B. Carvalho (Conservation Biology, 2021)
Protected‐area systems should conserve intraspecific genetic diversity. Because genetic data require resources to obtain, several approaches have been proposed for generating plans for protected‐area systems (prioritizations) when genetic data are not available. Yet such surrogate‐based approaches remain poorly tested. We evaluated the effectiveness of potential surrogate‐based approaches based on microsatellite genetic data collected across the Iberian Peninsula for 7 amphibian and 3 reptilian species. Long‐term environmental suitability did not effectively represent sites containing high genetic diversity (allelic richness). Prioritizations based on long‐term environmental suitability had similar performance to random prioritizations. Geographic distances and resistance distances based on contemporary environmental suitability were not always effective surrogates for identification of combinations of sites that contain individuals with different genetic compositions. Our results demonstrate that population genetic data based on commonly used neutral markers can inform prioritizations, and we could not find an adequate substitute. Conservation planners need to weigh the potential benefits of genetic data against their acquisition costs.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Signatures of selection in a recent invasion reveal adaptive divergence in a highly vagile invasive species - Katarina C. Stuart; Adam P. A. Cardilini; Phillip Cassey; Mark F. Richardson; William B. Sherwin; Lee A. Rollins; Craig D. H. Sherman (Molecular Ecology, 2021)
A detailed understanding of population genetics in invasive populations helps us to identify drivers of successful alien introductions. Here, we investigate putative signals of selection in Australian populations of invasive common starlings, Sturnus vulgaris , and seek to understand how these have been influenced by introduction history. We used reduced representation sequencing to determine population structure, and identify Single Nucleotide Polymorphisms (SNPs) that are putatively under selection. We found that since their introduction into Australia, starling populations have become genetically differentiated despite the potential for high levels of dispersal, and that starlings have responded to selective pressures imposed by a wide range of environmental conditions across their geographic range. Isolation by distance appears to have played a strong role in determining genetic substructure across the starling's Australian range. Analyses of candidate SNPs that are putatively under selection indicated that aridity, precipitation and temperature may be important factors driving adaptive variation across the starling's invasive range in Australia. However, we also noted that the historic introduction regime may leave footprints on sites flagged as being under adaptive selection, and encourage critical interpretation of selection analyses in non‐native populations.

The Experience of Chemotherapy Teaching and Readability of Chemotherapy Educational Materials for Women with Breast Cancer - Pearman D. Parker; Sue P. Heiney; Daniela B. Friedman; Swann Arp Adams; Robin M. Dawson (Journal of Cancer Education, 2021)

Newly discovered cichlid fish biodiversity threatened by hybridization with non‐native species - Tabitha Blackwell; Antonia G. P. Ford; Adam G. Ciezarek; Stephanie J. Bradbeer; Carlos A. Gracida Juarez; Alan M. Smith; Benjamin P. Ngatunga; Asilatu Shechonge; Rashid Tamatamah; Graham Etherington; Wilfried Haerty; Federica Di Palma; et al. (Molecular Ecology, 2021)
Invasive freshwater fishes are known to readily hybridize with indigenous congeneric species, driving loss of unique and irreplaceable genetic resources. Here we reveal that newly discovered (2013–2016) evolutionarily significant populations of Korogwe tilapia ( Oreochromis korogwe ) from southern Tanzania are threatened by hybridization with the larger invasive Nile tilapia ( Oreochromis niloticus ). We use a combination of morphology, microsatellite allele frequencies and whole genome sequences to show that O. korogwe from southern lakes (Nambawala, Rutamba and Mitupa) are distinct from geographically disjunct populations in northern Tanzania (Zigi River and Mlingano Dam). We also provide genetic evidence of O. korogwe × niloticus hybrids in three southern lakes and demonstrate heterogeneity in the extent of admixture across the genome. Finally, using the least admixed genomic regions we estimate that the northern and southern O. korogwe populations most plausibly diverged ~140,000 years ago, suggesting that the geographical separation of the northern and southern groups is not a result of a recent translocation, and instead these populations represent independent evolutionarily significant units. We conclude that these newly discovered and phenotypically unique cichlid populations are already threatened by hybridization with an invasive species, and propose that these irreplaceable genetic resources would benefit from conservation interventions.

Tropical peatlands and their contribution to the global carbon cycle and climate change - Kelly Ribeiro; Felipe S. Pacheco; José W. Ferreira; Eráclito R. de Sousa‐Neto; Adam Hastie; Guenther C. Krieger Filho; Plínio C. Alvalá; Maria C. Forti; Jean P. Ometto (Global Change Biology, 2021)
Peatlands are carbon‐rich ecosystems that cover 185–423 million hectares (Mha) of the earth's surface. The majority of the world's peatlands are in temperate and boreal zones, whereas tropical ones cover only a total area of 90–170 Mha. However, there are still considerable uncertainties in C stock estimates as well as a lack of information about depth, bulk density and carbon accumulation rates. The incomplete data are notable especially in tropical peatlands located in South America, which are estimated to have the largest area of peatlands in the tropical zone. This paper displays the current state of knowledge surrounding tropical peatlands and their biophysical characteristics, distribution and carbon stock, role in the global climate, the impacts of direct human disturbances on carbon accumulation rates and greenhouse gas (GHG) emissions. Based on the new peat extension and depth data, we estimate that tropical peatlands store 152–288 Gt C, or about half of the global peatland emitted carbon. We discuss the knowledge gaps in research on distribution, depth, C stock and fluxes in these ecosystems which play an important role in the global carbon cycle and risk releasing large quantities of GHGs into the atmosphere (CO 2 and CH 4 ) when subjected to anthropogenic interferences (e.g., drainage and deforestation). Recent studies show that although climate change has an impact on the carbon fluxes of these ecosystems, the direct anthropogenic disturbance may play a greater role. The future of these systems as carbon sinks will depend on advancing current scientific knowledge and incorporating local understanding to support policies geared toward managing and conserving peatlands in vulnerable regions, such as the Amazon where recent records show increased forest fires and deforestation.

Fine-scale foraging effort and efficiency of Macaroni penguins is influenced by prey type, patch density and temporal dynamics - G. J. Sutton; C. A. Bost; A. Z. Kouzani; S. D. Adams; K. Mitchell; J. P. Y. Arnould (Marine Biology, 2021)

Bacterial Communities of Ballan Wrasse (Labrus bergylta) Eggs at a Commercial Marine Hatchery - Aileen Bone; Michaël Bekaert; Athina Papadopoulou; Stuart McMillan; Alexandra Adams; Andrew Davie; Andrew P. Desbois (Current Microbiology, 2021)
Ballan wrasse ( Labrus bergylta , Ascanius 1767) are cleaner fish cultured in northern Europe to remove sea lice from farmed Atlantic salmon ( Salmo salar , Linnaeus 1758). Despite increasing appreciation for the importance of the microbiota on the phenotypes of vertebrates including teleosts, the microbiota of wrasse eggs has yet to be described. Therefore, the aim of this present study was to describe the bacterial component of the microbiota of ballan wrasse eggs shortly after spawning and at 5 days, once the eggs had undergone a routine incubation protocol that included surface disinfection steps in a common holding tank. Triplicate egg samples were collected from each of three spawning tanks and analysis of 16S rRNA gene sequences revealed that 88.6% of reads could be identified to 186 taxonomic families. At Day 0, reads corresponding to members of the Vibrionaceae, Colwelliaceae and Rubritaleaceae families were detected at greatest relative abundances. Bacterial communities of eggs varied more greatly between tanks than between samples deriving from the same tank. At Day 5, there was a consistent reduction in 16S rRNA gene sequence richness across the tanks. Even though the eggs from the different tanks were incubated in a common holding tank, the bacterial communities of the eggs from the different tanks had diverged to become increasingly dissimilar. This suggests that the disinfection and incubation exerted differential effects of the microbiota of the eggs from each tank and that the influence of the tank water on the composition of the egg microbiota was lower than expected. This first comprehensive description of the ballan wrasse egg bacterial community is an initial step to understand the role and function of the microbiota on the phenotype of this fish. In future, mass DNA sequencing methods may be applied in hatcheries to screen for pathogens and as a tool to assess the health status of eggs.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Responses of Intertidal Bacterial Biofilm Communities to Increasing pCO2 - Dorsaf Kerfahi; Ben P. Harvey; Sylvain Agostini; Koetsu Kon; Ruiping Huang; Jonathan M. Adams; Jason M. Hall-Spencer (Marine Biotechnology, 2020)

eDNA metabarcoding bioassessment of endangered fairy shrimp (Branchinecta spp.) - Zachary Gold; Adam R. Wall; Emily E. Curd; Ryan P. Kelly; N. Dean Pentcheff; Lee Ripma; Paul H. Barber; Regina Wetzer (Conservation Genetics Resources, 2020)

Forget the audience: tadpoles release similar disturbance cues regardless of kinship or familiarity - Kevin R. Bairos-Novak; Adam L. Crane; Gabrielle H. Achtymichuk; Jonathan Hsin; Ita A. E. Rivera-Hernández; Olena M. Simko; Theresa E. Wrynn; Douglas P. Chivers; Maud C. O. Ferrari (Behavioral Ecology and Sociobiology, 2020)

Identification and full genomic sequence of nerine yellow stripe virus - Naomi Beddoe; Ian P. Adams; Sam McGreig; Alec Forsyth (Archives of Virology, 2020)

Effects of fungicide chemical class, fungicide application timing, and environment on Fusarium head blight in winter wheat - Carlos Bolanos-Carriel; Stephen N. Wegulo; P. Stephen Baenziger; Deanna Funnell-Harris; Heather E. Hallen-Adams; Kent M. Eskridge (European Journal of Plant Pathology, 2020)

Ultraviolet-assisted oiling assessment improves detection of oiled birds experiencing clinical signs of hemolytic anemia after exposure to the Deepwater Horizon oil spill - Jesse A. Fallon; Eric P. Smith; Nina Schoch; James D. Paruk; Evan M. Adams; David C. Evers; Patrick G. R. Jodice; Marie Perkins; Dustin E. Meattey; William A. Hopkins (Ecotoxicology, 2020)

Characterization of a highly heterogeneous flysch deposit and excavation implications: case study from Auckland, New Zealand - B. Fleetwood; M. S. Brook; G. Brink; N. R. Richards; L. Adam; P. M. Black (Bulletin of Engineering Geology and the Environment, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

Clear as mud: the ecology and conservation of a secretive wetland fish (Neochanna cleaveri:Galaxiidae) in a heavily altered landscape - Nick S. Whiterod; Michael P. Hammer; Thomas C. Barnes; Mel Tucker; Mark Adams; Tarmo A. Raadik (Wetlands Ecology and Management, 2020)

Confirming the Source of High-Sulfate Concentrations in Dead Horse Creek, Winkler, Manitoba, Canada, Using a Dual-Isotope Bayesian Probability Mixing Model - Adam J. Dubinsky; Rebecca P. A. Wilks; William M. Buhay (Water, Air, & Soil Pollution, 2020)

Acoustic Speech Analytics Are Predictive of Cerebellar Dysfunction in Multiple Sclerosis - Gustavo Noffs; Frederique M. C. Boonstra; Thushara Perera; Scott C. Kolbe; Jim Stankovich; Helmut Butzkueven; Andrew Evans; Adam P. Vogel; Anneke van der Walt (The Cerebellum, 2020)

Application of machine learning algorithms to identify cryptic reproductive habitats using diverse information sources - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre-Barbieri; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Oecologia, 2020)

Predicting site-specific storm wave run-up - Julia W. Fiedler; Adam P. Young; Bonnie C. Ludka; William C. O’Reilly; Cassandra Henderson; Mark A. Merrifield; R. T. Guza (Natural Hazards, 2020)
Storm wave run-up causes beach erosion, wave overtopping, and street flooding. Extreme runup estimates may be improved, relative to predictions from general empirical formulae with default parameter values, by using historical storm waves and eroded profiles in numerical runup simulations. A climatology of storm wave run-up at Imperial Beach, California is developed using the numerical model SWASH, and over a decade of hindcast spectral waves and observed depth profiles. For use in a local flood warning system, the relationship between incident wave energy spectra E ( f ) and SWASH-modeled shoreline water levels is approximated with the numerically simple integrated power law approximation (IPA). Broad and multi-peaked E ( f ) are accommodated by characterizing wave forcing with frequency-weighted integrals of E ( f ). This integral approach improves runup estimates compared to the more commonly used bulk parameterization using deep water wave height $$H_0$$ H 0 and deep water wavelength $$L_0$$ L 0 Hunt (Trans Am Soc Civ Eng 126(4):542–570, 1961) and Stockdon et al. (Coast Eng 53(7):573–588, 2006. 10.1016/j.coastaleng.2005.12.005 ). Scaling of energy and frequency contributions in IPA, determined by searching parameter space for the best fit to SWASH, show an $$H_0L_0$$ H 0 L 0 scaling is near optimal. IPA performance is tested with LiDAR observations of storm run-up, which reached 2.5 m above the offshore water level, overtopped backshore riprap, and eroded the foreshore beach slope. Driven with estimates from a regional wave model and observed $$β _f$$ β f , the IPA reproduced observed run-up with $$<30%$$ < 30 % error. However, errors in model physics, depth profile, and incoming wave predictions partially cancelled. IPA (or alternative empirical forms) can be calibrated (using SWASH or similar) for sites where historical waves and eroded bathymetry are available.

Temporally Altered miRNA Expression in a Piglet Model of Hypoxic Ischemic Brain Injury - Sophie Casey; Kate Goasdoue; Stephanie M. Miller; Gary P. Brennan; Gary Cowin; Adam G. O’Mahony; Christopher Burke; Boubou Hallberg; Geraldine B. Boylan; Aideen M. Sullivan; David C. Henshall; Gerard W. O’Keeffe; et al. (Molecular Neurobiology, 2020)

Divergent trends of large carnivore populations within the Bénoué Complex, North Cameroon, shown by long-term fine-scale monitoring - C. E. Bakker; I. E. Kirsten; H. Bauer; B. M. Croes; W. L. M. Tamis; P. N. Tumenta; S. Adam; A. S. Kamgang; H. H. de Iongh (European Journal of Wildlife Research, 2020)

Historical patterns in mercury exposure for North American songbirds - Marie Perkins; Oksana P. Lane; David C. Evers; Amy Sauer; Evan M. Adams; Nelson J. O’Driscoll; Samuel T. Edmunds; Allyson K. Jackson; Julie C. Hagelin; Jeremiah Trimble; Elsie M. Sunderland (Ecotoxicology, 2020)

Geographic hierarchical population genetic structuring in British European whitefish (Coregonus lavaretus) and its implications for conservation - M. Crotti; C. E. Adams; E. C. Etheridge; C. W. Bean; A. R. D. Gowans; R. Knudsen; A. A. Lyle; P. S. Maitland; I. J. Winfield; K. R. Elmer; K. Præbel (Conservation Genetics, 2020)
The European whitefish Coregonus lavaretus complex represents one of the most diverse radiations within salmonids, with extreme morphological and genetic differentiation across its range. Such variation has led to the assignment of many populations to separate species. In Great Britain, the seven native populations of C. lavaretus (two in Scotland, four in England, one in Wales) were previously classified into three species, and recent taxonomic revision resurrected the previous nomenclature. Here we used a dataset of 15 microsatellites to: (1) investigate the genetic diversity of British populations, (2) assess the level of population structure and the relationships between British populations. Genetic diversity was highest in Welsh (H O = 0.50, A R = 5.29), intermediate in English (H O = 0.41–0.50, A R = 2.83–3.88), and lowest in Scottish populations (H O = 0.28–0.35, A R = 2.56–3.04). Population structure analyses indicated high genetic differentiation (global F ST = 0.388) between all populations but for the two Scottish populations (F ST = 0.063) and two English populations (F ST = 0.038). Principal component analysis and molecular ANOVA revealed separation between Scottish, English, and Welsh populations, with the Scottish populations being the most diverged. We argue that the data presented here are not sufficient to support a separation of the British European whitefish populations into three separate species, but support the delineation of different ESUs for these populations.

River/stream water temperature forecasting using artificial intelligence models: a systematic review - Senlin Zhu; Adam P. Piotrowski (Acta Geophysica, 2020)

Recognizing animal personhood in compassionate conservation - Arian D. Wallach; Chelsea Batavia; Marc Bekoff; Shelley Alexander; Liv Baker; Dror Ben‐Ami; Louise Boronyak; Adam P. A. Cardilin; Yohay Carmel; Danielle Celermajer; Simon Coghlan; Yara Dahdal; et al. (Conservation Biology, 2020)
Compassionate conservation is based on the ethical position that actions taken to protect biodiversity should be guided by compassion for all sentient beings. Critics argue that there are 3 core reasons harming animals is acceptable in conservation programs: the primary purpose of conservation is biodiversity protection; conservation is already compassionate to animals; and conservation should prioritize compassion to humans. We used argument analysis to clarify the values and logics underlying the debate around compassionate conservation. We found that objections to compassionate conservation are expressions of human exceptionalism, the view that humans are of a categorically separate and higher moral status than all other species. In contrast, compassionate conservationists believe that conservation should expand its moral community by recognizing all sentient beings as persons. Personhood, in an ethical sense, implies the individual is owed respect and should not be treated merely as a means to other ends. On scientific and ethical grounds, there are good reasons to extend personhood to sentient animals, particularly in conservation. The moral exclusion or subordination of members of other species legitimates the ongoing manipulation and exploitation of the living worlds, the very reason conservation was needed in the first place. Embracing compassion can help dismantle human exceptionalism, recognize nonhuman personhood, and navigate a more expansive moral space.

Four Cultural Narratives for Managing Social-ecological Complexity in Public Natural Resource Management - Nick A. Kirsop-Taylor; Adam P. Hejnowicz; Karen Scott (Environmental Management, 2020)
Public Natural Resource Management (NRM) agencies operate in complex social-ecological domains. These complexities proliferate unpredictably therefore investigating and supporting the ability of public agencies to respond effectively is increasingly important. However, understanding how public NRM agencies innovate and restructure to negotiate the range of particular complexities they face is an under researched field. One particular conceptualisation of the social-ecological complexities facing NRM agencies that is of growing influence is the Water–Energy–Food (WEF) nexus. Yet, as a tool to frame and understand those complexities it has limitations. Specifically, it overlooks how NRMs respond institutionally to these social-ecological complexities in the context of economic and organisational challenges—thus creating a gap in the literature. Current debates in public administration can be brought to bear here. Using an organisational cultures approach, this paper reports on a case study with a national NRM agency to investigate how they are attempting to transform institutionally to respond to complexity in challenging times. The research involved 12 elite interviews with senior leaders from Natural Resources Wales, (NRW) and investigated how cultural narratives are being explicitly and implicitly constructed and mobilised to this end. The research identified four distinct and sequential cultural narratives: collaboration, communication, trust, and empowerment where each narrative supported the delivery of different dimensions of NRW’s social-ecological complexity mandate. Counter to the current managerialist approaches in public administration, these results suggest that the empowerment of expert bureaucrats is important in responding effectively to complexity.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Targeting reactive oxygen species (ROS) to combat the age-related loss of muscle mass and function - Anastasia Thoma; Tania Akter-Miah; Rebecca L. Reade; Adam P. Lightfoot (Biogerontology, 2020)
The loss of muscle mass and function with age, termed sarcopenia, is an inevitable process, which has a significant impact on quality of life. During ageing we observe a progressive loss of total muscle fibres and a reduction in cross-sectional area of the remaining fibres, resulting in a significant reduction in force output. The mechanisms which underpin sarcopenia are complex and poorly understood, ranging from inflammation, dysregulation of protein metabolism and denervation. However, there is significant evidence to demonstrate that modified ROS generation, redox dis-homeostasis and mitochondrial dysfunction may have an important role to play. Based on this, significant interest and research has interrogated potential ROS-targeted therapies, ranging from nutritional-based interventions such as vitamin E/C, polyphenols (resveratrol) and targeted pharmacological compounds, using molecules such as SS-31 and MitoQ. In this review we evaluate these approaches to target aberrant age-related ROS generation and the impact on muscle mass and function.

Plio‐Pleistocene sea‐level changes drive speciation of freshwater fishes in north‐western Australia - James J. Shelley; Stephen E. Swearer; Tim Dempster; Mark Adams; Matthew C. Le Feuvre; Michael P. Hammer; Peter J. Unmack (Journal of Biogeography, 2020)
Aim Despite the influence of sea‐level changes on biogeographic/phylogeographic patterns in freshwater ecosystems being well documented, studies that explicitly link the influence of sea‐level change with speciation are rare. We aim to test the hypothesis that sea‐level changes during the Pliocene and Pleistocene have driven speciation in north‐western Australia's (NWA’s) largest freshwater fish family, Terapontidae, building upon a body of evolutionary literature focussed on the family. Location North‐western Australian rivers including those draining the Kimberley Plateau. Taxon Grunters (Family: Terapontidae, Genera: Hannia , Hephaestus , Leiopotherapon , Syncomistes ). Methods A GIS was used to reconstruct palaeodrainages during lowered sea levels and to delineate regions of high connectivity during low and high (current) sea‐level conditions. For seven species, the degree of phylogenetic divergence among river basins in different regions was evaluated using a maximum likelihood phylogeny and analyses of the proportion of genetic divergence expressed with 601 base pairs of the mtDNA cytochrome b (cytb) gene. Results A low proportion of cytb haplotypes were shared among catchments not connected by the same receiving waters (e.g. estuaries) under current (high) sea levels, indicating that contemporary dispersal is limited over fine spatial scales. Deeper phylogeographic patterns were largely congruent with reconstructed low sea‐level (LSL) drainage arrangements indicating that historic among‐catchment connectivity was far more widespread under LSL conditions. Main Conclusions The NWA landscape represents a geographic template that has shaped patterns of broad dispersal under low sea levels, and fine‐scale isolation under high sea levels. The weight of evidence from recent literature on species boundaries and evolutionary patterns within the terapontids suggests that most NWA species were derived rapidly and recently from a series of spatio‐temporal vicariant events caused by such sea‐level fluctuations during the late Pliocene and Pleistocene. Together, the findings provide a rare, comprehensively tested example of sea‐level change driving speciation in the tropics.

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Dynamic adaptive mesh optimisation for immiscible viscous fingering - A. E. Kampitsis; A. Adam; P. Salinas; C. C. Pain; A. H. Muggeridge; M. D. Jackson (Computational Geosciences, 2020)
Immiscible fingering is challenging to model since it requires a very fine mesh for the numerical method to capture the interaction of the shock front with the capillary pressure. This can result in computationally intensive simulations if a fixed mesh is used. We apply a higher order conservative dynamic adaptive mesh optimisation (DAMO) technique, to model immiscible viscous fingering in porous media. We show that the approach accurately captures the development and growth of the interfacial instability. Convergence is demonstrated under grid refinement with capillary pressure for both a fixed unstructured mesh and with DAMO. Using DAMO leads to significantly reduced computational cost compared to the equivalent fixed mesh simulations. We also present the late-time response of viscous fingers through numerical examples in a 2D rectangular domain and in a 3D cylindrical geometry. Both problems are computationally challenging in the absence of DAMO. The dynamic adaptive problem requires up to 36 times fewer elements than the prohibitively expensive fixed mesh solution, with the computational cost reduced accordingly.

Predators weaken prey intraspecific competition through phenotypic selection - Adam M. Siepielski; Adam Z. Hasik; Taylor Ping; Mabel Serrano; Koby Strayhorn; Simon P. Tye (Ecology Letters, 2020)
Predators have a key role shaping competitor dynamics in food webs. Perhaps the most obvious way this occurs is when predators reduce competitor densities. However, consumption could also generate phenotypic selection on prey that determines the strength of competition, thus coupling consumptive and trait‐based effects of predators. In a mesocosm experiment simulating fish predation on damselflies, we found that selection against high damselfly activity rates – a phenotype mediating predation and competition – weakened the strength of density dependence in damselfly growth rates. A field experiment corroborated this finding and showed that increasing damselfly densities in lakes with high fish densities had limited effects on damselfly growth rates but generated a precipitous growth rate decline where fish densities were lower – a pattern expected because of spatial variation in selection imposed by predation. These results suggest that accounting for both consumption and selection is necessary to determine how predators regulate prey competitive interactions.

Inter-trial phase coherence of visually evoked postural responses in virtual reality - David Engel; Adrian Schütz; Milosz Krala; Jakob C. B. Schwenk; Adam P. Morris; Frank Bremmer (Experimental Brain Research, 2020)
Vision plays a central role in maintaining balance. When humans perceive their body as moving, they trigger counter movements. This results in body sway, which has typically been investigated by measuring the body’s center of pressure (COP). Here, we aimed to induce visually evoked postural responses (VEPR) by simulating self-motion in virtual reality (VR) using a sinusoidally oscillating “moving room” paradigm. Ten healthy subjects participated in the experiment. Stimulation consisted of a 3D-cloud of random dots, presented through a VR headset, which oscillated sinusoidally in the anterior–posterior direction at different frequencies. We used a force platform to measure subjects’ COP over time and quantified the resulting trajectory by wavelet analyses including inter-trial phase coherence (ITPC). Subjects exhibited significant coupling of their COP to the respective stimulus. Even when spectral analysis of postural sway showed only small responses in the expected frequency bands (power), ITPC revealed an almost constant strength of coupling to the stimulus within but also across subjects and presented frequencies. Remarkably, ITPC even revealed a strong phase coupling to stimulation at 1.5 Hz, which exceeds the frequency range that has generally been attributed to the coupling of human postural sway to an oscillatory visual scenery. These findings suggest phase-locking to be an essential feature of visuomotor control.

Correction to: Keeping pace with forestry: Multi-scale conservation in a changing production forest matrix - Adam Felton; Therese Löfroth; Per Angelstam; Lena Gustafsson; Joakim Hjältén; Annika M. Felton; Per Simonsson; Anders Dahlberg; Matts Lindbladh; Johan Svensson; Urban Nilsson; Isak Lodin; et al. (Ambio, 2020)
In the original published article, the sentence “Nevertheless, semi-natural forest remnants continue to be harvested and fragmented (Svensson et al. 2018; Jonsson et al. 2019), and over 2000 forest-associated species (of 15 000 assessed) are listed as threatened on Sweden’s red-list, largely represented by macro-fungi, beetles, lichens and butterflies (Sandström 2015).”under the section Introduction was incorrect. The correct version of the sentence is “Nevertheless, semi-natural forest remnants continue to be harvested and fragmented (Svensson et al. 2018; Jonsson et al. 2019), and approximately 2000 forest-associated species (of 15 000 assessed) are on Sweden’s red-list, largely represented by macro-fungi, beetles, lichens and butterflies (Sandström 2015).”

Keeping pace with forestry: Multi-scale conservation in a changing production forest matrix - Adam Felton; Therese Löfroth; Per Angelstam; Lena Gustafsson; Joakim Hjältén; Annika M. Felton; Per Simonsson; Anders Dahlberg; Matts Lindbladh; Johan Svensson; Urban Nilsson; Isak Lodin; et al. (Ambio, 2020)
The multi-scale approach to conserving forest biodiversity has been used in Sweden since the 1980s, a period defined by increased reserve area and conservation actions within production forests. However, two thousand forest-associated species remain on Sweden’s red-list, and Sweden’s 2020 goals for sustainable forests are not being met. We argue that ongoing changes in the production forest matrix require more consideration, and that multi-scale conservation must be adapted to, and integrated with, production forest development. To make this case, we summarize trends in habitat provision by Sweden’s protected and production forests, and the variety of ways silviculture can affect biodiversity. We discuss how different forestry trajectories affect the type and extent of conservation approaches needed to secure biodiversity, and suggest leverage points for aiding the adoption of diversified silviculture. Sweden’s long-term experience with multi-scale conservation and intensive forestry provides insights for other countries trying to conserve species within production landscapes.

Report on the Thirty-Fifth Southern Forest Tree Improvement Conference (SFTIC 2019) - C. Dana Nelson; Ellen V. Crocker; Laura DeWald; Earl M. Raley; Joshua P. Adams; Barbara S. Crane; Gary F. Peter; Claudio Casola; John M. Davis; Scott A. Merkle (Tree Genetics & Genomes, 2020)

Magnetosome magnetite biomineralization in a flagellated protist: evidence for an early evolutionary origin for magnetoreception in eukaryotes - Pedro Leão; Lucas Le Nagard; Hao Yuan; Jefferson Cypriano; Inácio Da Silva‐Neto; Dennis A. Bazylinski; Daniel Acosta‐Avalos; Henrique L. de Barros; Adam P. Hitchcock; Ulysses Lins; Fernanda Abreu (Environmental Microbiology, 2020)
Summary The most well‐recognized magnetoreception behaviour is that of the magnetotactic bacteria (MTB), which synthesize membrane‐bounded magnetic nanocrystals called magnetosomes via a biologically controlled process. The magnetic minerals identified in prokaryotic magnetosomes are magnetite (Fe 3 O 4 ) and greigite (Fe 3 S 4 ). Magnetosome crystals, regardless of composition, have consistent, species‐specific morphologies and single‐domain size range. Because of these features, magnetosome magnetite crystals possess specific properties in comparison to abiotic, chemically synthesized magnetite. Despite numerous discoveries regarding MTB phylogeny over the last decades, this diversity is still considered underestimated. Characterization of magnetotactic microorganisms is important as it might provide insights into the origin and establishment of magnetoreception in general, including eukaryotes. Here, we describe the magnetotactic behaviour and characterize the magnetosomes from a flagellated protist using culture‐independent methods. Results strongly suggest that, unlike previously described magnetotactic protists, this flagellate is capable of biomineralizing its own anisotropic magnetite magnetosomes, which are aligned in complex aggregations of multiple chains within the cell. This organism has a similar response to magnetic field inversions as MTB. Therefore, this eukaryotic species might represent an early origin of magnetoreception based on magnetite biomineralization. It should add to the definition of parameters and criteria to classify biogenic magnetite in the fossil record.

Informing management decisions for ecological networks, using dynamic models calibrated to noisy time‐series data - Matthew P. Adams; Scott A. Sisson; Kate J. Helmstedt; Christopher M. Baker; Matthew H. Holden; Michaela Plein; Jacinta Holloway; Kerrie L. Mengersen; Eve McDonald‐Madden (Ecology Letters, 2020)
Well‐intentioned environmental management can backfire, causing unforeseen damage. To avoid this, managers and ecologists seek accurate predictions of the ecosystem‐wide impacts of interventions, given small and imprecise datasets, which is an incredibly difficult task. We generated and analysed thousands of ecosystem population time series to investigate whether fitted models can aid decision‐makers to select interventions. Using these time‐series data (sparse and noisy datasets drawn from deterministic Lotka‐Volterra systems with two to nine species, of known network structure), dynamic model forecasts of whether a species’ future population will be positively or negatively affected by rapid eradication of another species were correct > 70% of the time. Although 70% correct classifications is only slightly better than an uninformative prediction (50%), this classification accuracy can be feasibly improved by increasing monitoring accuracy and frequency. Our findings suggest that models may not need to produce well‐constrained predictions before they can inform decisions that improve environmental outcomes.

Heat Waves Are a Major Threat to Turbid Coral Reefs in Brazil - Gustavo A. S. Duarte; Helena D. M. Villela; Matheus Deocleciano; Denise Silva; Adam Barno; Pedro M. Cardoso; Caren L. S. Vilela; Phillipe Rosado; Camila S. M. A. Messias; Maria Alejandra Chacon; Erika P. Santoro; Daniele B. Olmedo; et al. (Frontiers in Marine Science, 2020)

Carbon dioxide supersaturation in high‐elevation oligotrophic lakes and reservoirs in the Sierra Nevada, California - Adam P. Cohen; John M. Melack (Limnology and Oceanography, 2020)
To better understand the contribution of alpine lakes to global CO 2 emissions, carbon dioxide concentrations and fluxes to the atmosphere were measured in five high‐elevation lakes and five reservoirs in the Sierra Nevada, California. Median summer surface concentrations of dissolved CO 2 (reservoirs: 21.1 μ M, lakes: 23.7 μ M) were supersaturated for most of the ice‐free season. Median diffusive flux of CO 2 was low as compared to other inland waters (lakes: 260 mg CO 2 m −2 d −1 , reservoirs: 192 mg CO 2 m −2 d −1 ). Linear mixed modeling demonstrated that the length of ice cover, persisting for 5–9 months and allowing for accumulation of under‐ice CO 2 , was a strong predictor of summer surface CO 2 . During the ice‐free period, surface evasion of CO 2 was highest for the first 40 d after ice‐off when carbon dioxide that had accumulated during winter was released, although supersaturation and evasion continued until fall at most sites despite low rates of ecosystem metabolism. This study suggests that the contribution of high‐elevation, oligotrophic lakes and reservoirs in the Sierra to global CO 2 emissions are small despite persistent supersaturation, and are primarily driven by the duration of ice cover.

Contrasting patterns of genetic connectivity in brooding and spawning corals across a remote atoll system in northwest Australia - Luke Thomas; Jim N. Underwood; Arne A. S. Adam; Zoe T. Richards; Laurence Dugal; Karen J. Miller; James P. Gilmour (Coral Reefs, 2020)

Development of a multi-assay approach for monitoring coral diversity using eDNA metabarcoding - Jason B. Alexander; Michael Bunce; Nicole White; Shaun P. Wilkinson; Arne A. S. Adam; Tina Berry; Michael Stat; Luke Thomas; Stephen J. Newman; Laurence Dugal; Zoe T. Richards (Coral Reefs, 2020)

Seasonal occupancy and connectivity amongst nearshore flats and reef habitats by permit Trachinotus falcatus : considerations for fisheries management - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre‐Barbieri; Glenn T. Crossin; Sara J. Iverson; Ross Boucek; Aaron J. Adams; Steven J. Cooke; Andy J. Danylchuk (Journal of Fish Biology, 2020)
We used acoustic telemetry to quantify permit Trachinotus falcatus habitat use and connectivity in proximity to the Florida Keys, USA, and assessed these patterns relative to current habitat and fisheries management practices. From March 2017 to June 2018, 45 permit tagged within 16 km of the lower Florida Keys were detected at stationary acoustic receivers throughout the south Florida region, the majority of which remained within the Special Permit Zone, where more extensive fisheries harvest regulations are implemented. There was a high level of connectivity between nearshore flats ( i.e. ,

The response of stomatal conductance to seasonal drought in tropical forests - Jin Wu; Shawn P. Serbin; Kim S. Ely; Brett T. Wolfe; L. Turin Dickman; Charlotte Grossiord; Sean T. Michaletz; Adam D. Collins; Matteo Detto; Nate G. McDowell; S. Joseph Wright; Alistair Rogers (Global Change Biology, 2020)
Stomata regulate CO 2 uptake for photosynthesis and water loss through transpiration. The approaches used to represent stomatal conductance ( g s ) in models vary. In particular, current understanding of drivers of the variation in a key parameter in those models, the slope parameter (i.e. a measure of intrinsic plant water‐use‐efficiency), is still limited, particularly in the tropics. Here we collected diurnal measurements of leaf gas exchange and leaf water potential (Ψ leaf ), and a suite of plant traits from the upper canopy of 15 tropical trees in two contrasting Panamanian forests throughout the dry season of the 2016 El Niño. The plant traits included wood density, leaf‐mass‐per‐area (LMA), leaf carboxylation capacity ( V c,max ), leaf water content, the degree of isohydry, and predawn Ψ leaf . We first investigated how the choice of four commonly used leaf‐level g s models with and without the inclusion of Ψ leaf as an additional predictor variable influence the ability to predict g s , and then explored the abiotic (i.e. month, site‐month interaction) and biotic (i.e. tree‐species‐specific characteristics) drivers of slope parameter variation. Our results show that the inclusion of Ψ leaf did not improve model performance and that the models that represent the response of g s to vapor pressure deficit performed better than corresponding models that respond to relative humidity. Within each g s model, we found large variation in the slope parameter, and this variation was attributable to the biotic driver, rather than abiotic drivers. We further investigated potential relationships between the slope parameter and the six available plant traits mentioned above, and found that only one trait, LMA, had a significant correlation with the slope parameter ( R 2 = 0.66, n = 15), highlighting a potential path towards improved model parameterization. This study advances understanding of g s dynamics over seasonal drought, and identifies a practical, trait‐based approach to improve modeling of carbon and water exchange in tropical forests.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Terpenes May Serve as Feeding Deterrents and Foraging Cues for Mammalian Herbivores - Michele M. Skopec; Robert P. Adams; James P. Muir (Journal of Chemical Ecology, 2019)

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Genomic sequence and host range studies reveal considerable variation within the species Arracacha virus B - Roger A. C. Jones; Adrian Fox; Neil Boonham; Ian P. Adams (Archives of Virology, 2019)

Intramuscular fast-flow vascular anomaly contains somatic MAP2K1 and KRAS mutations - Jeremy A. Goss; Dennis J. Konczyk; Patrick J. Smits; Harry P. W. Kozakewich; Ahmad I. Alomari; Alyaa Al-Ibraheemi; Amir H. Taghinia; Belinda H. Dickie; Denise M. Adams; Steven J. Fishman; John B. Mulliken; Matthew L. Warman; et al. (Angiogenesis, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Joint Optimization of Conceptual Rainfall-Runoff Model Parameters and Weights Attributed to Meteorological Stations - Adam P. Piotrowski; Marzena Osuch; Jarosław J. Napiorkowski (Water Resources Management, 2019)
Conceptual lumped rainfall-runoff models are frequently used for various environmental problems. To put them into practice, both the model calibration method and data series of the area-averaged precipitation and air temperature are needed. In the case when data from more than one measurement station are available, first the catchment-averaged meteorological data series are usually obtained by some method, and then they are used for calibration of a lumped rainfall-runoff model. However, various optimization methods could easily be applied to simultaneously calibrate both the aggregation weights attributed to various meteorological stations to obtain a lumped meteorological data series and the rainfall-runoff model parameters. This increases the problem dimensionality but allows the optimization procedure to choose the data that are most important for the rainfall-runoff process in a particular catchment, without a priori assumptions. We test the idea using two conceptual models, HBV and GR4J, and three mutually different, relatively recently proposed Evolutionary Computation and Swarm Intelligence optimization algorithms, that are applied to three catchments located in Poland and northwestern USA. We consider two cases: with and without the model error correction applied to the rainfall-runoff models. It is shown that for the calibration period, joint optimization of the weights used to aggregate the meteorological data and the parameters of the rainfall-runoff model improves the results. However, the results for the validation period are inconclusive and depend on the model, error correction, optimization algorithm, and catchment.

Rare variants and loci for age-related macular degeneration in the Ohio and Indiana Amish - Andrea R. Waksmunski; Robert P. Igo; Yeunjoo E. Song; Jessica N. Cooke Bailey; Renee Laux; Denise Fuzzell; Sarada Fuzzell; Larry D. Adams; Laura Caywood; Michael Prough; Dwight Stambolian; William K. Scott; et al. (Human Genetics, 2019)

Re-emergence of North Atlantic subsurface ocean temperature anomalies in a seasonal forecast system - Jeremy P. Grist; Bablu Sinha; Helene. T. Hewitt; Aurélie Duchez; Craig MacLachlan; Patrick Hyder; Simon A. Josey; Joël J.-M. Hirschi; Adam T. Blaker; Adrian. L. New; Adam A. Scaife; Chris D. Roberts (Climate Dynamics, 2019)

Skill of dynamical and GHACOF consensus seasonal forecasts of East African rainfall - Dean P. Walker; Cathryn E. Birch; John H. Marsham; Adam A. Scaife; Richard J. Graham; Zewdu T. Segele (Climate Dynamics, 2019)

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

Loving the mess: navigating diversity and conflict in social values for sustainability - Jasper O. Kenter; Christopher M. Raymond; Carena J. van Riper; Elaine Azzopardi; Michelle R. Brear; Fulvia Calcagni; Ian Christie; Michael Christie; Anne Fordham; Rachelle K. Gould; Christopher D. Ives; Adam P. Hejnowicz; et al. (Sustainability Science, 2019)

Larval Transport Modeling Support for Identifying Population Sources of European Green Crab in the Salish Sea - Elizabeth Brasseale; Emily W. Grason; P. Sean McDonald; Jeff Adams; Parker MacCready (Estuaries and Coasts, 2019)

Sustainability and the common good: Catholic Social Teaching and ‘Integral Ecology’ as contributions to a framework of social values for sustainability transitions - Ian Christie; Richard M. Gunton; Adam P. Hejnowicz (Sustainability Science, 2019)

Phenotypic Plasticity of Nest-Mate Recognition Cues in Formica exsecta Ants - Stephen J. Martin; Falko P. Drijfhout; Adam G. Hart (Journal of Chemical Ecology, 2019)

Survival, behaviour, and morphology of larval wood frogs, Lithobates sylvaticus, under threat from an exotic crayfish predator, Orconectes virilis - Adam L. Crane; Kevin R. Bairos-Novak; Dale M. Jefferson; Douglas P. Chivers; Maud C. O. Ferrari (Aquatic Ecology, 2019)

Effect of external compression on femoral retrograde shear and microvascular oxygenation in exercise trained and recreationally active young men - Patricia Pagan Lassalle; Adam J. Palamar; Jacob P. DeBlois; Wesley K. Lefferts; Kevin S. Heffernan (European Journal of Applied Physiology, 2019)

Correction to: Mercury accumulation, speciation, and temporal trends in Atlantic Stingrays (Hypanus sabinus) - Brianne K. Soulen; Douglas H. Adams; Aaron P. Roberts (Ecotoxicology, 2019)

Submarine giant pumice: a window into the shallow conduit dynamics of a recent silicic eruption - Samuel J. Mitchell; Bruce F. Houghton; Rebecca J. Carey; Michael Manga; Kristen E. Fauria; Max P. Jones; S. Adam Soule; Chris E. Conway; Zihan Wei; Thomas Giachetti (Bulletin of Volcanology, 2019)
Meter-scale vesicular blocks, termed “giant pumice,” are characteristic primary products of many subaqueous silicic eruptions. The size of giant pumices allows us to describe meter-scale variations in textures and geochemistry with implications for shearing processes, ascent dynamics, and thermal histories within submarine conduits prior to eruption. The submarine eruption of Havre volcano, Kermadec Arc, in 2012, produced at least 0.1 km 3 of rhyolitic giant pumice from a single 900-m-deep vent, with blocks up to 10 m in size transported to at least 6 km from source. We sampled and analyzed 29 giant pumices from the 2012 Havre eruption. Geochemical analyses of whole rock and matrix glass show no evidence for geochemical heterogeneities in parental magma; any textural variations can be attributed to crystallization of phenocrysts and microlites, and degassing. Extensive growth of microlites occurred near conduit walls where magma was then mingled with ascending microlite-poor, low viscosity rhyolite. Meter- to micron-scale textural analyses of giant pumices identify diversity throughout an individual block and between the exteriors of individual blocks. We identify evidence for post-disruption vesicle growth during pumice ascent in the water column above the submarine vent. A 2D cumulative strain model with a flared, shallow conduit may explain observed vesicularity contrasts (elongate tube vesicles vs spherical vesicles). Low vesicle number densities in these pumices from this high-intensity silicic eruption demonstrate the effect of hydrostatic pressure above a deep submarine vent in suppressing rapid late-stage bubble nucleation and inhibiting explosive fragmentation in the shallow conduit.

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting - Daniela B. Friedman; Swann Arp Adams; Heather M. Brandt; Sue P. Heiney; James R. Hébert; John R. Ureda; Jessica S. Seel; Courtney S. Schrock; Wilhelmenia Mathias; Vivian Clark-Armstead; Reverend Vernette Dees; Reverend Perry Oliver (Journal of Cancer Education, 2019)

Introduction to the Australian Society for Biophysics - Adam P. Hill (Biophysical Reviews, 2019)

Aversion learning in response to an invasive venomous prey depends on stimulus strength - Cameron P. Venable; Thomas S. Adams; Tracy Langkilde (Biological Invasions, 2019)

Connectivity explains local ant community structure in a Neotropical forest canopy: a large‐scale experimental approach - Benjamin J. Adams; Stefan A. Schnitzer; Stephen P. Yanoviak (Ecology, 2019)
Understanding how habitat structure and resource availability affect local species distributions is a key goal of community ecology. Where habitats occur as a mosaic, variation in connectivity among patches influences both local species richness and composition, and connectivity is a key conservation concern in fragmented landscapes. Similarly, availability of limiting resources frequently determines species coexistence or exclusion. For primarily cursorial arthropods like ants, gaps between neighboring trees are a significant barrier to movement through the forest canopy. Competition for limited resources such as nest sites also promotes antagonistic interactions. Lianas (woody vines) connect normally isolated neighboring tree crowns and often have hollow stems inhabited by ants. We used two large‐scale liana‐removal experiments to determine how connectivity and nest site availability provided by lianas affect arboreal ant species richness, species composition, and β‐diversity in a lowland tropical forest in Panama. Removing lianas from a tree crown reduced ant species richness up to 35%, and disproportionately affected species that require large foraging areas. Adding artificial connectivity to trees mitigated the effects of liana removal. Ant colonization of artificial nests was higher (73% occupied) in trees without lianas vs. trees with lianas (28% occupied). However, artificial nests typically were colonized by existing polydomous, resident ant species. As a result, nest addition did not affect ant community structure. Collectively, these results indicate that lianas are important to the maintenance of arboreal ant diversity specifically by providing connectivity among neighboring tree crowns. Anticipated increases in liana abundance in this forest could increase the local (tree‐level) species richness of arboreal ants, with a compositional bias toward elevating the density of broad‐ranging specialist predators.

The Cross-Talk Between Sphingolipids and Insulin-Like Growth Factor Signaling: Significance for Aging and Neurodegeneration - Henryk Jęśko; Adam Stępień; Walter J. Lukiw; Robert P. Strosznajder (Molecular Neurobiology, 2019)

Recommendations for cerebrospinal fluid analysis - D. Hepnar; P. Adam; H. Žáková; M. Krušina; P. Kalvach; J. Kasík; I. Karpowicz; J. Nasler; K. Bechyně; T. Fiala; M. Mamiňák; I. Malíková; et al. (Folia Microbiologica, 2019)

Quadriceps muscle function following anterior cruciate ligament reconstruction: systemic differences in neural and morphological characteristics - Adam S. Lepley; Dustin R. Grooms; Julie P. Burland; Steven M. Davi; Jeffrey M. Kinsella-Shaw; Lindsey K. Lepley (Experimental Brain Research, 2019)

Mercury accumulation, speciation, and temporal trends in Atlantic Stingrays (Hypanus sabinus) - Brianne K. Soulen; Douglas H. Adams; Aaron P. Roberts (Ecotoxicology, 2019)

Correction to: Trophic plasticity and the invasion of a renowned piscivore: a diet synthesis of northern pike (Esox lucius) from the native and introduced ranges in Alaska, U.S.A. - C. Nathan Cathcart; Kristine J. Dunker; Thomas P. Quinn; Adam J. Sepulveda; Frank A. von Hippel; Andrew Wizik; Daniel B. Young; Peter A. H. Westley (Biological Invasions, 2019)

Trophic plasticity and the invasion of a renowned piscivore: a diet synthesis of northern pike (Esox lucius) from the native and introduced ranges in Alaska, U.S.A. - C. Nathan Cathcart; Kristine J. Dunker; Thomas P. Quinn; Adam J. Sepulveda; Frank A. von Hippel; Andrew Wizik; Daniel B. Young; Peter A. H. Westley (Biological Invasions, 2019)

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Exercise intensity effects on total sweat electrolyte losses and regional vs. whole-body sweat [Na+], [Cl−], and [K+] - Lindsay B. Baker; Peter John D. De Chavez; Corey T. Ungaro; Bridget C. Sopeña; Ryan P. Nuccio; Adam J. Reimel; Kelly A. Barnes (European Journal of Applied Physiology, 2019)

Measuring site fidelity and homesite-to-pre-spawning site connectivity of bonefish (Albula vulpes): using mark-recapture to inform habitat conservation - R. E. Boucek; J. P. Lewis; B. D. Stewart; Z. R. Jud; E. Carey; A. J. Adams (Environmental Biology of Fishes, 2019)

Identifying pre-spawning aggregation sites for bonefish (Albula vulpes) in the Bahamas to inform habitat protection and species conservation - Aaron J. Adams; Jonathan M. Shenker; Zachary R. Jud; Justin P. Lewis; Eric Carey; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Impacts of laurel wilt disease on arthropod herbivores of North American Lauraceae - John J. Riggins; Adam D. Chupp; John P. Formby; Natalie A. Dearing; Hannah M. Bares; Richard L. Brown; Kelly F. Oten (Biological Invasions, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

The future of parentage analysis: From microsatellites to SNPs and beyond - Sarah P. Flanagan; Adam G. Jones (Molecular Ecology, 2019)
Parentage analysis is a cornerstone of molecular ecology that has delivered fundamental insights into behaviour, ecology and evolution. Microsatellite markers have long been the king of parentage, their hypervariable nature conferring sufficient power to correctly assign offspring to parents. However, microsatellite markers have seen a sharp decline in use with the rise of next‐generation sequencing technologies, especially in the study of population genetics and local adaptation. The time is ripe to review the current state of parentage analysis and see how it stands to be affected by the emergence of next‐generation sequencing approaches. We find that single nucleotide polymorphisms (SNPs), the typical next‐generation sequencing marker, remain underutilized in parentage analysis but are gaining momentum, with 58 SNP‐based parentage analyses published thus far. Many of these papers, particularly the earlier ones, compare the power of SNPs and microsatellites in a parentage context. In virtually every case, SNPs are at least as powerful as microsatellite markers. As few as 100–500 SNPs are sufficient to resolve parentage completely in most situations. We also provide an overview of the analytical programs that are commonly used and compatible with SNP data. As the next‐generation parentage enterprise grows, a reliance on likelihood and Bayesian approaches, as opposed to strict exclusion, will become increasingly important. We discuss some of the caveats surrounding the use of next‐generation sequencing data for parentage analysis and conclude that the future is bright for this important realm of molecular ecology.

Efficacy of a polyvalent injectable vaccine against Flavobacterium psychrophilum administered to rainbow trout ( Oncorhynchus mykiss L.) - Rowena Hoare; Sung‐Ju Jung; Thao P. H. Ngo; Kerry L. Bartie; Kim D. Thompson; Alexandra Adams (Journal of Fish Diseases, 2019)
Flavobacterium psychrophilum is one of the most important pathogens affecting cultured rainbow trout ( Oncorhynchus mykiss ). Recent information from UK salmonid farms showed country‐wide distribution of genetically and serologically divergent clones, which has hampered the development of a vaccine for rainbow trout fry syndrome. The current study assessed the efficacy of an injectable polyvalent vaccine containing formalin‐inactivated F. psychrophilum in rainbow trout. The vaccine was formulated with an oil adjuvant (Montanide ISA 760VG) or formalin‐killed cells alone. Duplicate groups of trout (60 ± 13 g) were given phosphate‐buffered saline or vaccine formulated with Montanide by intra‐peritoneal (i.p.) injection and challenged by intra‐muscular (i.m.) injection with a homologous and a heterologous isolate of F. psychrophilum at 525 degree days post‐vaccination (dd pv). Significant protection was achieved in vaccinated fish ( p = 0.0001, RPS 76% homologous, 88% heterologous). Efficacy of the adjuvanted vaccine was also demonstrated by heterologous challenge at 1155 dd pv resulting in 100% protection, whereas survival in the un‐adjuvanted group was not significantly different from control fish. Levels of specific antibody at 1155 dd pv, as measured by ELISA, were significantly higher in the fish vaccinated with adjuvant when compared with unvaccinated fish.

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Relationship Between Calibration Time and Final Performance of Conceptual Rainfall-Runoff Models - Adam P. Piotrowski; Jaroslaw J. Napiorkowski; Marzena Osuch (Water Resources Management, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Iron‐ and aluminium‐induced depletion of molybdenum in acidic environments impedes the nitrogen cycle - Xiaoxuan Ge; Brian J. Vaccaro; Michael P. Thorgersen; Farris L. Poole; Erica L. Majumder; Grant M. Zane; Kara B. De León; W. Andrew Lancaster; Ji Won Moon; Charles J. Paradis; Frederick von Netzer; David A. Stahl; et al. (Environmental Microbiology, 2019)
Summary Anthropogenic nitrate contamination is a serious problem in many natural environments. Nitrate removal by microbial action is dependent on the metal molybdenum (Mo), which is required by nitrate reductase for denitrification and dissimilatory nitrate reduction to ammonium. The soluble form of Mo, molybdate (MoO 4 2− ), is incorporated into and adsorbed by iron (Fe) and aluminium (Al) (oxy) hydroxide minerals. Herein we used Oak Ridge Reservation (ORR) as a model nitrate‐contaminated acidic environment to investigate whether the formation of Fe‐ and Al‐precipitates could impede microbial nitrate removal by depleting Mo. We demonstrate that Fe and Al mineral formation that occurs as the pH of acidic synthetic groundwater is increased, decreases soluble Mo to low picomolar concentrations, a process proposed to mimic environmental diffusion of acidic contaminated groundwater. Analysis of ORR sediments revealed recalcitrant Mo in the contaminated core that co‐occurred with Fe and Al, consistent with Mo scavenging by Fe/Al precipitates. Nitrate removal by ORR isolate Pseudomonas fluorescens N2A2 is virtually abolished by Fe/Al precipitate‐induced Mo depletion. The depletion of naturally occurring Mo in nitrate‐ and Fe/Al‐contaminated acidic environments like ORR or acid mine drainage sites has the potential to impede microbial‐based nitrate reduction thereby extending the duration of nitrate in the environment.

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

The impact of high throughput sequencing on plant health diagnostics - Ian P. Adams; Adrian Fox; Neil Boonham; Sébastien Massart; Kris De Jonghe (European Journal of Plant Pathology, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

The role of gene flow in rapid and repeated evolution of cave‐related traits in Mexican tetra, Astyanax mexicanus - Adam Herman; Yaniv Brandvain; James Weagley; William R. Jeffery; Alex C. Keene; Thomas J. Y. Kono; Helena Bilandžija; Richard Borowsky; Luis Espinasa; Kelly O'Quin; Claudia P. Ornelas‐García; Masato Yoshizawa; et al. (Molecular Ecology, 2018)
Understanding the molecular basis of repeatedly evolved phenotypes can yield key insights into the evolutionary process. Quantifying gene flow between populations is especially important in interpreting mechanisms of repeated phenotypic evolution, and genomic analyses have revealed that admixture occurs more frequently between diverging lineages than previously thought. In this study, we resequenced 47 whole genomes of the Mexican tetra from three cave populations, two surface populations and outgroup samples. We confirmed that cave populations are polyphyletic and two Astyanax mexicanus lineages are present in our data set. The two lineages likely diverged much more recently than previous mitochondrial estimates of 5–7 mya. Divergence of cave populations from their phylogenetically closest surface population likely occurred between ~161 and 191 k generations ago. The favoured demographic model for most population pairs accounts for divergence with secondary contact and heterogeneous gene flow across the genome, and we rigorously identified gene flow among all lineages sampled. Therefore, the evolution of cave‐related traits occurred more rapidly than previously thought, and trogolomorphic traits are maintained despite gene flow with surface populations. The recency of these estimated divergence events suggests that selection may drive the evolution of cave‐derived traits, as opposed to disuse and drift. Finally, we show that a key trogolomorphic phenotype QTL is enriched for genomic regions with low divergence between caves, suggesting that regions important for cave phenotypes may be transferred between caves via gene flow. Our study shows that gene flow must be considered in studies of independent, repeated trait evolution.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Root and mycorrhizal fungal foraging responses to fruit removal in apple trees - Emily K. Lavely; Jianghong Zhang; Thomas S. Adams; David R. Bryla; Jared L. DeForest; Richard P. Marini; Robert Crassweller; David M. Eissenstat (Plant and Soil, 2018)

The Impact of Federal and State Conservation Programs on Farmer Nitrogen Management - Adam P. Reimer; Riva C. H. Denny; Diana Stuart (Environmental Management, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

A habitat‐based approach to predict impacts of marine protected areas on fishers - João B. Teixeira; Rodrigo L. Moura; Morena Mills; Carissa Klein; Christopher J. Brown; Vanessa M. Adams; Hedley Grantham; Matthew Watts; Deborah Faria; Gilberto M. Amado‐Filho; Alex C. Bastos; Reinaldo Lourival; et al. (Conservation Biology, 2018)
Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation.

Assessing phytoplankton composition and structure within micro-estuaries and micro-outlets: a community analysis approach - Tatenda Dalu; Mandla L. Magoro; Jonathan D. Tonkin; Lucienne R. D. Human; Renzo Perissinotto; Shaun H. P. Deyzel; Janine B. Adams; Alan K. Whitfield (Hydrobiologia, 2018)

Evolutionary Divergence of TNL Disease-Resistant Proteins in Soybean (Glycine max) and Common Bean (Phaseolus vulgaris) - Surendra Neupane; Qin Ma; Febina M. Mathew; Adam J. Varenhorst; Ethan J. Andersen; Madhav P. Nepal (Biochemical Genetics, 2018)

Impairment of Thiamine Transport at the GUT-BBB-AXIS Contributes to Wernicke’s Encephalopathy - P. M. Abdul Muneer; Saleena Alikunju; Heather Schuetz; Adam M. Szlachetka; Xiaotang Ma; James Haorah (Molecular Neurobiology, 2018)

The role of resveratrol on skeletal muscle cell differentiation and myotube hypertrophy during glucose restriction - Hannah F. Dugdale; David C. Hughes; Robert Allan; Colleen S. Deane; Christopher R. Coxon; James P. Morton; Claire E. Stewart; Adam P. Sharples (Molecular and Cellular Biochemistry, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Nanogeochemistry of hydrothermal magnetite - Artur P. Deditius; Martin Reich; Adam C. Simon; Alexandra Suvorova; Jaayke Knipping; Malcolm P. Roberts; Sergey Rubanov; Aaron Dodd; Martin Saunders (Contributions to Mineralogy and Petrology, 2018)

It's Electric: When Technology Gives a Boost to Stem Cell Science - Abraham P. Lee; Mohammad Aghaamoo; Tayloria N. G. Adams; Lisa A. Flanagan (Current Stem Cell Reports, 2018)

The influence of aquaculture unit proximity on the pattern of Lepeophtheirus salmonis infection of anadromous Salmo trutta populations on the isle of Skye, Scotland - I. Moore; J. A. Dodd; M. Newton; C. W. Bean; I. Lindsay; P. Jarosz; C. E. Adams (Journal of Fish Biology, 2018)
A total of 230 anadromous Salmo trutta (brown trout) were sampled in five sheltered coastal fjords (or sea lochs) on the Isle of Skye, Scotland, U.K., in 2016 at varying distances from active Atlantic salmon Salmo salar farms. Statistical models were developed to investigate potential correlations between salmon lice Lepeophtheirus salmonis burdens on S. trutta hosts and their proximity to S. salar farm cages. Significant correlations were found between lice burdens and fish fork length and proximity to the nearest S. salar farm. The probability of the presence of L. salmonis on fish hosts increased with fish host size and with distance from the nearest S. salar farm, but total lice burdens were highest in fish sampled near S. salar farms and decreased with distance. The proportion of different life‐cycle stages of L. salmonis were also dependent on S. salar farm proximity, with higher juvenile lice numbers recorded at sites near S. salar farm cages. These results highlight the complexity of the relationship between S. trutta and L. salmonis infections on wild fish and emphasize the requirement of further research to quantify these effects to better inform conservation and management strategies, particularly in areas of active S. salar farm facilities.

Where are weather-suicide associations valid? An examination of nine US counties with varying seasonality - P. Grady Dixon; Adam J. Kalkstein (International Journal of Biometeorology, 2018)

Illuminating the link between perceived threat and control over climate change: the role of attributions for causation and mitigation - Julie Davydova; Adam R. Pearson; Matthew T. Ballew; Jonathon P. Schuldt (Climatic Change, 2018)

Apex predatory sharks and crocodiles simultaneously scavenge a whale carcass - Austin J. Gallagher; Yannis P. Papastamatiou; Adam Barnett (Journal of Ethology, 2018)

Water guns affect abundance and behavior of bigheaded carp and native fish differently - José M. Rivera; David C. Glover; Patrick M. Kocovsky; James E. Garvey; Mark P. Gaikowski; Nathan R. Jensen; Ryan F. Adams (Biological Invasions, 2018)

Wissensbasierte Werkstoffauswahl für Absaugsysteme in der Stahlindustrie - P. Friesenecker; K. Adam; C. Katsich; E. Badisch (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Combining abundance and performance data reveals how temperature regulates coastal occurrences and activity of a roaming apex predator - Nicholas L. Payne; Carl G. Meyer; James A. Smith; Jonathan D. R. Houghton; Adam Barnett; Bonnie J. Holmes; Itsumi Nakamura; Yannis P. Papastamatiou; Mark A. Royer; Daniel M. Coffey; James M. Anderson; Melanie R. Hutchinson; et al. (Global Change Biology, 2018)
The redistribution of species has emerged as one of the most pervasive impacts of anthropogenic climate warming, and presents many societal challenges. Understanding how temperature regulates species distributions is particularly important for mobile marine fauna such as sharks given their seemingly rapid responses to warming, and the socio‐political implications of human encounters with some dangerous species. The predictability of species distributions can potentially be improved by accounting for temperature's influence on performance, an elusive relationship for most large animals. We combined multi‐decadal catch data and bio‐logging to show that coastal abundance and swimming performance of tiger sharks Galeocerdo cuvier are both highest at ~22°C, suggesting thermal constraints on performance may regulate this species' distribution. Tiger sharks are responsible for a large proportion of shark bites on humans, and a focus of controversial control measures in several countries. The combination of distribution and performance data moves towards a mechanistic understanding of tiger shark's thermal niche, and delivers a simple yet powerful indicator for predicting the location and timing of their occurrences throughout coastlines. For example, tiger sharks are mostly caught at Australia's popular New South Wales beaches (i.e. near Sydney) in the warmest months, but our data suggest similar abundances will occur in winter and summer if annual sea surface temperatures increase by a further 1–2°C.

Non-communicable chronic diseases and timely breast cancer screening among women of the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study - K. H. Wang; T. A. Thompson; D. Galusha; H. Friedman; C. M. Nazario; M. Nunez; R. G. Maharaj; O. P. Adams; M. Nunez-Smith (Cancer Causes & Control, 2018)

Decision Support and Shared Decision Making About Active Surveillance Versus Active Treatment Among Men Diagnosed with Low-Risk Prostate Cancer: a Pilot Study - Ronald E. Myers; Amy E. Leader; Jean Hoffman Censits; Edouard J. Trabulsi; Scott W. Keith; Anett M. Petrich; Anna M. Quinn; Robert B. Den; Mark D. Hurwitz; Costas D. Lallas; Sarah E. Hegarty; Adam P. Dicker; et al. (Journal of Cancer Education, 2018)

In vivo neuroimaging and behavioral correlates in a rat model of chemotherapy-induced cognitive dysfunction - Robert L. Barry; Nellie E. Byun; M. Noor Tantawy; Chase A. Mackey; George H. Wilson; Adam J. Stark; Michael P. Flom; Laura C. Gee; C. Chad Quarles (Brain Imaging and Behavior, 2018)

Antimicrobial susceptibility of Flavobacterium psychrophilum isolates from the United Kingdom - T P H Ngo; P Smith; K L Bartie; K D Thompson; D W Verner‐Jeffreys; R Hoare; A Adams (Journal of Fish Diseases, 2018)
Routine application of antimicrobials is the current treatment of choice for rainbow trout fry syndrome ( RTFS ) or bacterial coldwater disease ( BCWD ) caused by Flavobacterium psychrophilum . In this study, the antimicrobial susceptibilities of 133 F. psychrophilum isolates, 118 of which were from the UK , were evaluated by broth microdilution and disc diffusion methods following VET 04‐A2 and VET 03‐A guidelines of Clinical and Laboratory Standards Institute ( CLSI ), respectively. Isolates were categorized as wild type (fully susceptible, WT ) or non‐wild type ( NWT ) using normalized resistance interpretation ( NRI )‐determined cut‐off values ( CO WT ). Broth microdilution testing showed that only 12% of UK isolates were WT to oxolinic acid ( MIC CO WT ≤ 0.25 mg/L) and 42% were WT for oxytetracycline ( MIC CO WT ≤ 0.25 mg/L). In contrast, all the isolates tested were WT ( MIC CO WT ≤ 2 mg/L) for florfenicol, the main antimicrobial for RTFS control in the UK . Disc diffusion‐based CO WT values were ≥51 mm for 10 μg amoxicillin, ≥44 mm for 30 μg florfenicol, ≥30 mm for 2 μg oxolinic acid and ≥51 mm for 30 μg oxytetracycline. There was a high categorical agreement between the classifications of the isolates by two testing methods for florfenicol (100%), oxytetracycline (93%) and oxolinic acid (99%).

Aquatic Invasive Species in the Great Lakes Region: An Overview - Luis E. Escobar; Sophie Mallez; Michael McCartney; Christine Lee; Daniel P. Zielinski; Ratna Ghosal; Przemyslaw G. Bajer; Carli Wagner; Becca Nash; Megan Tomamichel; Paul Venturelli; Prince P. Mathai; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

The impact of a small-scale riverine obstacle on the upstream migration of Atlantic Salmon - M. Newton; J. A. Dodd; J. Barry; P. Boylan; C. E. Adams (Hydrobiologia, 2018)

Geographically distributed hybrid testing & collaboration between geotechnical centrifuge and structures laboratories - Mobin Ojaghi; Ignacio Lamata Martínez; Matt S. Dietz; Martin S. Williams; Anthony Blakeborough; Adam J. Crewe; Colin A. Taylor; S. P. Gopal Madabhushi; Stuart K. Haigh (Earthquake Engineering and Engineering Vibration, 2018)

Climate change and Saharan dust drive recent cladoceran and primary production changes in remote alpine lakes of Sierra Nevada, Spain - Laura Jiménez; Kathleen M. Rühland; Adam Jeziorski; John P. Smol; Carmen Pérez‐Martínez (Global Change Biology, 2018)
Recent anthropogenic climate change and the exponential increase over the past few decades of Saharan dust deposition, containing ecologically important inputs of phosphorus (P) and calcium (Ca), are potentially affecting remote aquatic ecosystems. In this study, we examine changes in cladoceran assemblage composition and chlorophyll‐ a concentrations over the past ~150 years from high‐resolution, well‐dated sediment cores retrieved from six remote high mountain lakes in the Sierra Nevada Mountains of Southern Spain, a region affected by Saharan dust deposition. In each lake, marked shifts in cladoceran assemblages and chlorophyll‐ a concentrations in recent decades indicate a regional‐scale response to climate and Saharan dust deposition. Chlorophyll‐ a concentrations have increased since the 1970s, consistent with a response to rising air temperatures and the intensification of atmospheric deposition of Saharan P. Similar shifts in cladoceran taxa across lakes began over a century ago, but have intensified over the past ~50 years, concurrent with trends in regional air temperature, precipitation, and increased Saharan dust deposition. An abrupt increase in the relative abundance of the benthic cladoceran Alona quadrangularis at the expense of Chydorus sphaericus , and a significant increase in Daphnia pulex gr. was a common trend in these softwater lakes. Differences in the magnitude and timing of these changes are likely due to catchment and lake‐specific differences. In contrast with other alpine lakes that are often affected by acid deposition, atmospheric Ca deposition appears to be a significant explanatory factor, among others, for the changes in the lake biota of Sierra Nevada that has not been previously considered. The effects observed in Sierra Nevada are likely occurring in other Mediterranean lake districts, especially in softwater, oligotrophic lakes. The predicted increases in global temperature and Saharan dust deposition in the future will further impact the ecological condition of these ecosystems.

Murine myoblast migration: influence of replicative ageing and nutrition - Alexander D. Brown; Graeme L. Close; Adam P. Sharples; Claire E. Stewart (Biogerontology, 2017)

Increased grassland arthropod production with mammalian herbivory and eutrophication: a test of mediation pathways - Eric M. Lind; Kimberly J. La Pierre; Eric W. Seabloom; Juan Alberti; Oscar Iribarne; Jennifer Firn; Daniel S. Gruner; Adam D. Kay; Jesus Pascal; Justin P. Wright; Louie Yang; Elizabeth T. Borer (Ecology, 2017)
Increases in nutrient availability and alterations to mammalian herbivore communities are a hallmark of the Anthropocene, with consequences for the primary producer communities in many ecosystems. While progress has advanced understanding of plant community responses to these perturbations, the consequences for energy flow to higher trophic levels in the form of secondary production are less well understood. We quantified arthropod biomass after manipulating soil nutrient availability and wild mammalian herbivory, using identical methods across 13 temperate grasslands. Of experimental increases in nitrogen, phosphorus, and potassium, only treatments including nitrogen resulted in significantly increased arthropod biomass. Wild mammalian herbivore removal had a marginal, negative effect on arthropod biomass, with no interaction with nutrient availability. Path analysis including all sites implicated nutrient content of the primary producers as a driver of increased arthropod mean size, which we confirmed using 10 sites for which we had foliar nutrient data. Plant biomass and physical structure mediated the increase in arthropod abundance, while the nitrogen treatments accounted for additional variation not explained by our measured plant variables. The mean size of arthropod individuals was 2.5 times more influential on the plot‐level total arthropod biomass than was the number of individuals. The eutrophication of grasslands through human activity, especially nitrogen deposition, thus may contribute to higher production of arthropod consumers through increases in nutrient availability across trophic levels.

Chemical changes in organic matter after fungal colonization in a nitrogen fertilized and unfertilized Norway spruce forest - César Nicolás; Juan P. Almeida; Magnus Ellström; Adam Bahr; Sharon E. Bone; Nicholas P. Rosenstock; John R. Bargar; Anders Tunlid; Per Persson; Håkan Wallander (Plant and Soil, 2017)

Gulf War illness (GWI) as a neuroimmune disease - Apostolos P. Georgopoulos; Lisa M. James; Adam F. Carpenter; Brian E. Engdahl; Arthur C. Leuthold; Scott M. Lewis (Experimental Brain Research, 2017)

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Subcortical brain atrophy in Gulf War Illness - Peka Christova; Lisa M. James; Brian E. Engdahl; Scott M. Lewis; Adam F. Carpenter; Apostolos P. Georgopoulos (Experimental Brain Research, 2017)

Carbon Input and Accumulation in Freshwater to Brackish Marshes on the Barrier Islands of Virginia, USA - Nathan Sedghi; Emily C. Adams; Frank P. Day (Wetlands, 2017)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Quantitative trait loci controlling vegetative propagation traits mapped in European pear (Pyrus communis L.) - Mareike Knäbel; Adam P. Friend; John W. Palmer; Robert Diack; Susan E. Gardiner; Stuart Tustin; Robert Schaffer; Toshi Foster; David Chagné (Tree Genetics & Genomes, 2017)

Evaluating species-specific changes in hydrologic regimes: an iterative approach for salmonids in the Greater Yellowstone Area (USA) - Robert Al-Chokhachy; Adam J. Sepulveda; Andrew M. Ray; David P. Thoma; Michael T. Tercek (Reviews in Fish Biology and Fisheries, 2017)

An eccentric new species of Stelis from Peru (Orchidaceae: Pleurothallidinae) - Benjamin Collantes; Adam P. Karremans (Brittonia, 2017)

Impact of Fiber Structure on the Material Stability and Rupture Mechanisms of Coronary Atherosclerotic Plaques - Graeham R. Douglas; Adam J. Brown; Jonathan H. Gillard; Martin R. Bennett; Michael P. F. Sutcliffe; Zhongzhao Teng (Annals of Biomedical Engineering, 2017)

Wildfire size alters long‐term vegetation trajectories in boreal forests of eastern North America - Cécile C. Remy; Martin Lavoie; Martin P. Girardin; Christelle Hély; Yves Bergeron; Pierre Grondin; France Oris; Hugo Asselin; Adam A. Ali (Journal of Biogeography, 2017)
Aim Wildfire activity is projected to increase under global warming in many parts of the world. Knowledge of the role of these disturbances in shaping the composition of boreal forests is needed to better anticipate their future impacts. Here, we investigate the incidence of wildfire activity (burned biomass, frequency and size) on multi‐millennia vegetation trajectories in two coniferous boreal forest regions that display different types of vegetation composition and relief. We hypothesize that this difference in vegetation results from dissimilar wildfire activity during the Holocene. Location Conifer‐dominated boreal forests in Quebec‐Labrador, eastern North America. Methods Fire and vegetation histories during the last 8000 years were reconstructed and compared through analyses of charcoal and pollen records extracted from nine lacustrine deposits located in two spruce‐moss forests: the western region, co‐dominated by Pinus banksiana, and the eastern region, co‐dominated by Abies balsamea . Results Between 7000 and 2000 cal. yr bp , the western region experienced fewer fires than the eastern region, but they were larger in size. The main species adapted to fire, P. banksiana and Alnus viridis ssp. crispa, progressively co‐dominated with Picea sp.. Conversely, in the eastern region, P. banksiana and A. viridis ssp. crispa were very rare, and Picea sp. co‐dominated with non‐fire‐adapted A. balsamea and Betula sp.. Then, around 2000 cal. yr bp , fires decreased in frequency but were larger in size in the eastern region than in the western one, thus allowing densification of P. banksiana and A. viridis ssp. crispa in these landscapes. Main conclusions In the coniferous boreal forests of eastern North America, fire size was relatively more important in determining the long‐term vegetation trajectories in comparison with fire frequency. Changes in the rate of occurrence of large‐fire episodes will have significant impacts on vegetation dynamics over the next decades under continuing warming.

Setting conservation priorities for migratory networks under uncertainty - Kiran L. Dhanjal‐Adams; Marcel Klaassen; Sam Nicol; Hugh P. Possingham; Iadine Chadès; Richard A. Fuller (Conservation Biology, 2017)
Conserving migratory species requires protecting connected habitat along the pathways they travel. Despite recent improvements in tracking animal movements, migratory connectivity remains poorly resolved at a population level for the vast majority of species, thus conservation prioritization is hampered. To address this data limitation, we developed a novel approach to spatial prioritization based on a model of potential connectivity derived from empirical data on species abundance and distance traveled between sites during migration. We applied the approach to migratory shorebirds of the East Asian‐Australasian Flyway. Conservation strategies that prioritized sites based on connectivity and abundance metrics together maintained larger populations of birds than strategies that prioritized sites based only on abundance metrics. The conservation value of a site therefore depended on both its capacity to support migratory animals and its position within the migratory pathway; the loss of crucial sites led to partial or total population collapse. We suggest that conservation approaches that prioritize sites supporting large populations of migrants should, where possible, also include data on the spatial arrangement of sites.

Thermal constraints on foraging of tropical canopy ants - Michelle Elise Spicer; Alyssa Y. Stark; Benjamin J. Adams; Riley Kneale; Michael Kaspari; Stephen P. Yanoviak (Oecologia, 2017)

Leeches as a source of mammalian viral DNA and RNA—a study in medicinal leeches - Marie-Louise Kampmann; Ida Bærholm Schnell; Randi Holm Jensen; Jan Axtner; Adam F. Sander; Anders J. Hansen; Mads F. Bertelsen; Alex D. Greenwood; M. Thomas P. Gilbert; Andreas Wilting (European Journal of Wildlife Research, 2017)

The evolution of the natural killer complex; a comparison between mammals using new high-quality genome assemblies and targeted annotation - John C. Schwartz; Mark S. Gibson; Dorothea Heimeier; Sergey Koren; Adam M. Phillippy; Derek M. Bickhart; Timothy P. L. Smith; Juan F. Medrano; John A. Hammond (Immunogenetics, 2017)

Are modern metaheuristics successful in calibrating simple conceptual rainfall–runoff models? - Adam P. Piotrowski; Maciej J. Napiorkowski; Jaroslaw J. Napiorkowski; Marzena Osuch; Zbigniew W. Kundzewicz (Hydrological Sciences Journal, 2017)

Spittlebugs as vectors of Xylella fastidiosa in olive orchards in Italy - Daniele Cornara; Maria Saponari; Adam R. Zeilinger; Angelo de Stradis; Donato Boscia; Giuliana Loconsole; Domenico Bosco; Giovanni P. Martelli; Rodrigo P. P. Almeida; Francesco Porcelli (Journal of Pest Science, 2017)

Measured body composition and geometrical data of four “virtual family” members for thermoregulatory modeling - Xiaojiang Xu; Timothy P. Rioux; Tynan MacLeod; Tejash Patel; Maxwell N. Rome; Adam W. Potter (International Journal of Biometeorology, 2017)

Erratum to: Brief exposure to Pope Francis heightens moral beliefs about climate change - Jonathon P. Schuldt; Adam R. Pearson; Rainer Romero-Canyas; Dylan Larson-Konar (Climatic Change, 2017)

Brief exposure to Pope Francis heightens moral beliefs about climate change - Jonathon P. Schuldt; Adam R. Pearson; Rainer Romero-Canyas; Dylan Larson-Konar (Climatic Change, 2017)

Characterisation of neuroprotective efficacy of modified poly-arginine-9 (R9) peptides using a neuronal glutamic acid excitotoxicity model - Adam B. Edwards; Ryan S. Anderton; Neville W. Knuckey; Bruno P. Meloni (Molecular and Cellular Biochemistry, 2017)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

The Neuroprotective Peptide Poly-Arginine-12 (R12) Reduces Cell Surface Levels of NMDA NR2B Receptor Subunit in Cortical Neurons; Investigation into the Involvement of Endocytic Mechanisms - Gabriella MacDougall; Ryan S. Anderton; Adam B. Edwards; Neville W. Knuckey; Bruno P. Meloni (Journal of Molecular Neuroscience, 2017)

Omega-3 fatty acid EPA improves regenerative capacity of mouse skeletal muscle cells exposed to saturated fat and inflammation - Amarjit Saini; Adam P. Sharples; Nasser Al-Shanti; Claire E. Stewart (Biogerontology, 2017)

Interactions between ungulates, forests, and supplementary feeding: the role of nutritional balancing in determining outcomes - Annika M. Felton; Adam Felton; Joris P. G. M. Cromsigt; Lars Edenius; Jonas Malmsten; Hilde Karine Wam (Mammal Research, 2017)

Growth of four tropical tree species in petroleum-contaminated soil and effects of crude oil contamination - I. Pérez-Hernández; S. Ochoa-Gaona; R. H. Adams; M. C. Rivera-Cruz; V. Pérez-Hernández; A. Jarquín-Sánchez; V. Geissen; P. Martínez-Zurimendi (Environmental Science and Pollution Research, 2017)

Autumn olive (Elaeagnus umbellata) presence and proliferation on former surface coal mines in Eastern USA - Adam J. Oliphant; R. H. Wynne; C. E. Zipper; W. M. Ford; P. F. Donovan; Jing Li (Biological Invasions, 2017)

Mate quality and the temporal dynamics of breeding in a sex-role-reversed pipefish, S. typhle - Sarah P. Flanagan; Gunilla Rosenqvist; Adam G. Jones (Behavioral Ecology and Sociobiology, 2017)

Louis M. Herman 1930–2016 - Adam A. Pack; Elia Y. K. Herman; C. Scott Baker; Gordon B. Bauer; Phillip J. Clapham; Richard C. Connor; Alison S. Craig; Paul H. Forestell; Adam S. Frankel; Giuseppe Notarbartolo di Sciara; Matthias Hoffmann‐Kuhnt; Eduardo Mercado; et al. (Marine Mammal Science, 2017)

Quantitative magnetic resonance imaging in patients with cirrhosis: a cross-sectional study - Vijay P. B. Grover; Mary M. E. Crossey; Julie A. Fitzpatrick; Brian K. Saxby; Roberta Shaw; Adam D. Waldman; Marsha Y. Morgan; Simon D. Taylor-Robinson (Metabolic Brain Disease, 2016)

Morphological, ecological and behavioural differentiation of sympatric profundal and pelagic Arctic charr (Salvelinus alpinus) in Loch Dughaill Scotland - O. E. Hooker; J. Barry; T. E. Van Leeuwen; A. Lyle; J. Newton; P. Cunningham; C. E. Adams (Hydrobiologia, 2016)

Resistance exercise increases intramuscular NF-κb signaling in untrained males - Jeremy R. Townsend; Jeffrey R. Stout; Adam R. Jajtner; David D. Church; Kyle S. Beyer; Leonardo P. Oliveira; Michael B. La Monica; Joshua J. Riffe; Tyler W. D. Muddle; Kayla M. Baker; David H. Fukuda; Michael D. Roberts; et al. (European Journal of Applied Physiology, 2016)

Range-wide fragmentation in a threatened fish associated with post-European settlement modification in the Murray–Darling Basin, Australia - Theresa L. Cole; Michael P. Hammer; Peter J. Unmack; Peter R. Teske; Chris J. Brauer; Mark Adams; Luciano B. Beheregaray (Conservation Genetics, 2016)

Modelling of Brain Deformation After Decompressive Craniectomy - Tim L. Fletcher; Barbara Wirthl; Angelos G. Kolias; Hadie Adams; Peter J. A. Hutchinson; Michael P. F. Sutcliffe (Annals of Biomedical Engineering, 2016)

Turnover of hydrogen isotopes in lake sturgeon blood: implications for tracking movements of wild populations - Natasha M. Kreitals; Keith A. Hobson; Brittney M. Hoemsen; Adam L. Crane; Van Wishingrad; Janelle Sloychuk; Michael S. Pollock; Douglas P. Chivers; Iain D. Phillips (Isotopes in Environmental and Health Studies, 2016)

Tracking the long-term responses of diatoms and cladocerans to climate warming and human influences across lakes of the Ring of Fire in the Far North of Ontario, Canada - Kathryn E. Hargan; Clare Nelligan; Adam Jeziorski; Kathleen M. Rühland; Andrew M. Paterson; Wendel Keller; John P. Smol (Journal of Paleolimnology, 2016)

Late Pleistocene climate inferences from a water balance model of Jakes Valley, Nevada (USA) - Cornelia Barth; Douglas P. Boyle; Benjamin J. Hatchett; Scott D. Bassett; Christopher B. Garner; Kenneth D. Adams (Journal of Paleolimnology, 2016)

An Experimental and Numerical Investigation of CO2 Distribution in the Upper Airways During Nasal High Flow Therapy - S. C. Van Hove; J. Storey; C. Adams; K. Dey; P. H. Geoghegan; N. Kabaliuk; S. D. Oldfield; C. J. T. Spence; M. C. Jermy; V. Suresh; J. E. Cater (Annals of Biomedical Engineering, 2016)

Population genomics reveals multiple drivers of population differentiation in a sex‐role‐reversed pipefish - Sarah P. Flanagan; Emily Rose; Adam G. Jones (Molecular Ecology, 2016)
A major goal of molecular ecology is to identify the causes of genetic and phenotypic differentiation among populations. Population genomics is suitably poised to tackle these key questions by diagnosing the evolutionary mechanisms driving divergence in nature. Here, we set out to investigate the evolutionary processes underlying population differentiation in the Gulf pipefish, Syngnathus scovelli . We sampled approximately 50 fish from each of 12 populations distributed from the Gulf coast of Texas to the Atlantic coast of Florida and performed restriction‐site‐associated DNA sequencing to identify SNP s throughout the genome. After imposing quality and stringency filters, we selected a panel of 6348 SNP s present in all 12 populations, 1753 of which were not physically linked. We identified a genome‐wide pattern of isolation by distance, in addition to a more substantial genetic break separating populations in the Gulf of Mexico from those in the Atlantic. We also used several divergence outlier approaches and tests for genotype–environment correlations to identify 400 SNP s putatively involved in local adaptation. Patterns of phenotypic differentiation and variation diverged from the overall genomic pattern, suggesting that selection, phenotypic plasticity or demographic factors may be shaping phenotypes in distinct populations. Overall, our results suggest that population divergence is driven by a variety of factors in S. scovelli , including neutral processes and selection on multiple traits.

Long term effects of reduced fertilizer rates on millet yields and soil properties in the West-African Sahel - Alexis M. Adams; Adam W. Gillespie; Gourango Kar; Saidou Koala; Badiori Ouattara; Anthony A. Kimaro; Andre Bationo; P. B. Irenikatche Akponikpe; Jeff J. Schoenau; Derek Peak (Nutrient Cycling in Agroecosystems, 2016)

African American Patients’ Psychosocial Support Needs and Barriers to Treatment: Patient Needs Assessment - Maureen P. Davey; Brianna Bilkins; Guy Diamond; Alliric I. Willis; Edith P. Mitchell; Adam Davey; Faith M. Young (Journal of Cancer Education, 2016)

Potential effect of atmospheric warming on grapevine phenology and post-harvest heat accumulation across a range of climates - Andrew Hall; Adam J. Mathews; Bruno P. Holzapfel (International Journal of Biometeorology, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Does size matter? A test of size‐specific mortality in Atlantic salmon Salmo salar smolts tagged with acoustic transmitters - M. Newton; J. Barry; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
Mortality rates of wild Atlantic salmon Salmo salar smolts implanted with acoustic transmitters were assessed to determine if mortality was size dependent. The routinely accepted, but widely debated, ‘2% transmitter mass: body mass’ rule in biotelemetry was tested by extending the transmitter burden up to 12·7% of body mass in small [mean fork length ( L F ) 138·3 mm, range 115–168 mm] downstream migrating S. salar smolts. Over the short timescale of emigration (range 11·9–44·5 days) through the lower river and estuary, mortality was not related to S. salar size, nor was a relationship found between mortality probability and transmitter mass: body mass or transmitter length: L F ratios. This study provides further evidence that smolt migration studies can deviate from the ‘2% rule’ of thumb, to more appropriate study‐specific measures, which enables the use of fishes representative of the body size in natural populations without undue effects.

Temporal changes in cladoceran assemblages subjected to a low calcium environment: combining the sediment record with long-term monitoring data - Laura E. Redmond; Adam Jeziorski; Andrew M. Paterson; James A. Rusak; John P. Smol (Hydrobiologia, 2016)

Social structure and landscape genetics of the endemic New Caledonian ant Leptomyrmex pallens Emery, 1883 (Hymenoptera: Formicidae: Dolichoderinae), in the context of fire-induced rainforest fragmentation - Maïa Berman; Christopher M. Austin; Christopher P. Burridge; Adam D. Miller (Conservation Genetics, 2016)

Population genetics of a widely distributed small freshwater fish with varying conservation concerns: the southern purple-spotted gudgeon, Mogurnda adspersa - Minami Sasaki; Michael P. Hammer; Peter J. Unmack; Mark Adams; Luciano B. Beheregaray (Conservation Genetics, 2016)

Determinants of cancer screening in Asian-Americans - Quoc-Dien Trinh; Hanhan Li; Christian P. Meyer; Julian Hanske; Toni K. Choueiri; Gally Reznor; Stuart R. Lipsitz; Adam S. Kibel; Paul K. Han; Paul L. Nguyen; Mani Menon; Jesse D. Sammon (Cancer Causes & Control, 2016)

Tests of ecogeographical relationships in a non-native species: what rules avian morphology? - Adam P. A. Cardilini; Katherine L. Buchanan; Craig D. H. Sherman; Phillip Cassey; Matthew R. E. Symonds (Oecologia, 2016)

Dactylogyrus olfactorius n. sp. (Monogenea, Dactylogyridae) from the olfactory chamber of the fathead minnow, Pimephales promelas Rafinesque (Cyprinidae) - Ebrahim Lari; Rachael V. Adams; David K. Cone; Cameron P. Goater; Greg G. Pyle (Systematic Parasitology, 2016)

Novel genetic risk factors for asthma in African American children: Precision Medicine and the SAGE II Study - Marquitta J. White; O. Risse-Adams; P. Goddard; M. G. Contreras; J. Adams; D. Hu; C. Eng; S. S. Oh; A. Davis; K. Meade; E. Brigino-Buenaventura; M. A. LeNoir; et al. (Immunogenetics, 2016)

Effect of Dynamic Culture and Periodic Compression on Human Mesenchymal Stem Cell Proliferation and Chondrogenesis - Ting Guo; Li Yu; Casey G. Lim; Addison S. Goodley; Xuan Xiao; Jesse K. Placone; Kimberly M. Ferlin; Bao-Ngoc B. Nguyen; Adam H. Hsieh; John P. Fisher (Annals of Biomedical Engineering, 2016)

The role of race and ethnicity in climate change polarization: evidence from a U.S. national survey experiment - Jonathon P. Schuldt; Adam R. Pearson (Climatic Change, 2016)

Testosterone enables growth and hypertrophy in fusion impaired myoblasts that display myotube atrophy: deciphering the role of androgen and IGF-I receptors - David C. Hughes; Claire E. Stewart; Nicholas Sculthorpe; Hannah F. Dugdale; Farzad Yousefian; Mark P. Lewis; Adam P. Sharples (Biogerontology, 2016)

Skeletal muscle cells possess a ‘memory’ of acute early life TNF-α exposure: role of epigenetic adaptation - Adam P. Sharples; Ioanna Polydorou; David C. Hughes; Daniel J. Owens; Thomas M. Hughes; Claire E. Stewart (Biogerontology, 2016)

On the importance of training methods and ensemble aggregation for runoff prediction by means of artificial neural networks - Adam P. Piotrowski; Jaroslaw J. Napiorkowski; Marzena Osuch; Maciej J. Napiorkowski (Hydrological Sciences Journal, 2016)

Evaluation of the onset and length of growing season to define planting date—‘a case study for Mali (West Africa)’ - F. M. Akinseye; S. O. Agele; P. C. S. Traore; M. Adam; A. M. Whitbread (Theoretical and Applied Climatology, 2016)

The impact of tropical forest logging and oil palm agriculture on the soil microbiome - Binu M. Tripathi; David P. Edwards; Lucas William Mendes; Mincheol Kim; Ke Dong; Hyoki Kim; Jonathan M. Adams (Molecular Ecology, 2016)
Selective logging and forest conversion to oil palm agriculture are rapidly altering tropical forests. However, functional responses of the soil microbiome to these land‐use changes are poorly understood. Using 16S rRNA gene and shotgun metagenomic sequencing, we compared composition and functional attributes of soil biota between unlogged, once‐logged and twice‐logged rainforest, and areas converted to oil palm plantations in Sabah, Borneo. Although there was no significant effect of logging history, we found a significant difference between the taxonomic and functional composition of both primary and logged forests and oil palm. Oil palm had greater abundances of genes associated with DNA , RNA , protein metabolism and other core metabolic functions, but conversely, lower abundance of genes associated with secondary metabolism and cell–cell interactions, indicating less importance of antagonism or mutualism in the more oligotrophic oil palm environment. Overall, these results show a striking difference in taxonomic composition and functional gene diversity of soil microorganisms between oil palm and forest, but no significant difference between primary forest and forest areas with differing logging history. This reinforces the view that logged forest retains most features and functions of the original soil community. However, networks based on strong correlations between taxonomy and functions showed that network complexity is unexpectedly increased due to both logging and oil palm agriculture, which suggests a pervasive effect of both land‐use changes on the interaction of soil microbes.

What, if anything, is a social niche? - Julia B. Saltz; Adam P. Geiger; Raleigh Anderson; Benjamin Johnson; Rachel Marren (Evolutionary Ecology, 2016)

History of uterine leiomyoma and risk of endometrial cancer in black women - Lauren A. Wise; Todd R. Sponholtz; Lynn Rosenberg; Lucile L. Adams-Campbell; Wendy Kuohung; Michael P. LaValley; Julie R. Palmer (Cancer Causes & Control, 2016)

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis - Isabel Spier; Martin Kerick; Dmitriy Drichel; Sukanya Horpaopan; Janine Altmüller; Andreas Laner; Stefanie Holzapfel; Sophia Peters; Ronja Adam; Bixiao Zhao; Tim Becker; Richard P. Lifton; et al. (Familial Cancer, 2016)

Lake bathymetry and species occurrence predict the distribution of a lacustrine apex predator - M. R. Hughes; J. A. Dodd; P. S. Maitland; C. E. Adams (Journal of Fish Biology, 2016)
This study examined the abiotic and biotic characteristics of ecosystems that allow expression of a life history called ferox trout, the colloquial name given to brown trout Salmo trutta adopting a piscivorous life history strategy, an apex predator in post‐glacial lakes in northern Europe. One hundred and ninety‐two lakes in Scotland show evidence of currently, or historically, supporting ferox S. trutta ; their presence was predicted in logistic models by larger and deeper lakes with a large catchment that also support populations of Arctic charr Salvelinus alpinus .

Thermal adaptation and phosphorus shape thermal performance in an assemblage of rainforest ants - Michael Kaspari; Natalie A. Clay; Jane Lucas; Shai Revzen; Adam Kay; Stephen P. Yanoviak (Ecology, 2016)
We studied the Thermal Performance Curves ( TPC s) of 87 species of rainforest ants and found support for both the Thermal Adaptation and Phosphorus‐Tolerance hypotheses. TPC s relate a fitness proxy (here, worker speed) to environmental temperature. Thermal Adaptation posits that thermal generalists (ants with flatter, broader TPC s) are favored in the hotter, more variable tropical canopy compared to the cooler, less variable litter below. As predicted, species nesting in the forest canopy 1) had running speeds less sensitive to temperature; 2) ran over a greater range of temperatures; and 3) ran at lower maximum speeds. Tradeoffs between tolerance and maximum performance are often invoked for constraining the evolution of thermal generalists. There was no evidence that ant species traded off thermal tolerance for maximum speed, however. Phosphorus‐Tolerance is a second mechanism for generating ectotherms able to tolerate thermal extremes. It posits that ants active at high temperatures invest in P‐rich machinery to buffer their metabolism against thermal extremes. Phosphorus content in ant tissue varied three‐fold, and as predicted, temperature sensitivity was lower and thermal range was higher in P‐rich species. Combined, we show how the vertical distribution of hot and variable vs. cooler and stable microclimates in a single forest contribute to a diversity of TPC s and suggest that a widely varying P stoichiometry among these ants may drive some of these differences.

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

The energetic contributions of aquatic primary producers to terrestrial food webs in a mid‐size river system - Adam Kautza; S. Mažeika P. Sullivan (Ecology, 2016)
Rivers are increasingly recognized as providing nutritional subsidies (i.e., energy and nutrients) to adjacent terrestrial food webs via depredation of aquatic organisms (e.g., emergent aquatic insects, crayfish, fish) by terrestrial consumers. However, because these prey organisms assimilate energy from both aquatic (e.g., benthic algae, phytoplankton, aquatic macrophytes) and terrestrial (e.g., riparian leaf detritus) primary producers, river subsidies to terrestrial consumers represent a combination of aquatically and terrestrially derived energy. To date, the explicit contribution of energy derived from aquatic primary producers to terrestrial consumers has not been fully explored yet might be expected to be quantitatively important to terrestrial food webs. At 12 reaches along a 185‐km segment of the sixth‐order Scioto River system (Ohio, USA), we quantified the relative contribution of energy derived from aquatic primary producers to a suite of terrestrial riparian consumers that integrate the adjacent landscape across multiple spatial scales through their foraging activities (tetragnathid spiders, rove beetles, adult coenagrionid damselflies, riparian swallows, and raccoons). We used naturally abundant stable isotopes ( 13 C and 15 N) of periphyton, phytoplankton, macrophytes, and terrestrial vegetation to evaluate the energetic contribution of aquatic primary producers to terrestrial food webs. Shoreline tetragnathid spiders were most reliant on aquatic primary producers (50%), followed by wider‐ranging raccoons (48%), damselflies (44%), and riparian swallows (41%). Of the primary producers, phytoplankton (19%) provisioned the greatest nutritional contribution to terrestrial consumers (considered collectively), followed by periphyton (14%) and macrophytes (11%). Our findings provide empirical evidence that aquatic primary producers of large streams and rivers can be a critical nutritional resource for terrestrial food webs. We also show that aquatically derived nutrition contributes to both shoreline and broader‐ranging terrestrial consumers and thus may be an important landscape‐scale energetic linkage between rivers and upland habitats.

Are Evolutionary Algorithms Effective in Calibrating Different Artificial Neural Network Types for Streamwater Temperature Prediction? - Adam P. Piotrowski; Maciej J. Napiorkowski; Monika Kalinowska; Jaroslaw J. Napiorkowski; Marzena Osuch (Water Resources Management, 2016)

Foraging specialisms influence space use and movement patterns of the European eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; O. E. Hooker; P. Boylan; M. C. Lucas; C. E. Adams (Hydrobiologia, 2016)

Light history-dependent respiration explains the hysteresis in the daily ecosystem metabolism of seagrass - Matthew P. Adams; Angus J. P. Ferguson; Paul S. Maxwell; Brodie A. J. Lawson; Jimena Samper-Villarreal; Katherine R. O’Brien (Hydrobiologia, 2016)

Freshwater and coastal migration patterns in the silver‐stage eel Anguilla anguilla - J. Barry; M. Newton; J. A. Dodd; M. C. Lucas; P. Boylan; C. E. Adams (Journal of Fish Biology, 2016)
The unimpeded downstream movement patterns and migration success of small female and male Anguilla anguilla through a catchment in north‐west Europe were studied using an acoustic hydrophone array along the River Finn and into the Foyle Estuary in Ireland. Twenty silver‐stage A. anguilla (total length, L T , range: 332–520 mm) were trapped 152 km upstream from a coastal marine sea‐lough outlet and internally tagged with acoustic transmitters of which 19 initiated downstream migration. Migration speed was highly influenced by river flow within the freshwater ( FW ) compartment. Anguilla anguilla activity patterns were correlated with environmental influences; light, tidal direction and lunar phase all influenced the initiation of migration of tagged individuals. Migration speed varied significantly between upstream and lower river compartments. Individuals migrated at a slower speed in transitional water and sea‐lough compartments compared with the FW compartment. While 88·5% survival was recorded during migration through the upper 121 km of the river and estuary, only 26% of A. anguilla which initiated downstream migration were detected at the outermost end of the acoustic array. Telemetry equipment functioned efficiently, including in the sea‐lough, so this suggests high levels of mortality during sea‐lough migration, or less likely, long‐term sea‐lough residence by silver A. anguilla emigrants. This has important implications for eel management plans.

What do metabolic rates tell us about thermal niches? Mechanisms driving crayfish distributions along an altitudinal gradient - Rick J. Stoffels; Adam J. Richardson; Matthew T. Vogel; Simon P. Coates; Warren J. Müller (Oecologia, 2016)

The OPAL bugs count survey: exploring the effects of urbanisation and habitat characteristics using citizen science - Adam J. Bates; Poppy Lakeman Fraser; Lucy Robinson; John C. Tweddle; Jon P. Sadler; Sarah E. West; Simon Norman; Martin Batson; Linda Davies (Urban Ecosystems, 2015)

Sarcoplasmic Reticulum Phospholipid Fatty Acid Composition and Sarcolipin Content in Rat Skeletal Muscle - Val Andrew Fajardo; Eric Bombardier; Khanh Tran; Adam H. Metherel; Thomas Irvine; Graham P. Holloway; Howard J. Green; Ken D. Stark; A. Russell Tupling (The Journal of Membrane Biology, 2015)

The Pharmacokinetics of the CYP3A Substrate Midazolam in Morbidly Obese Patients Before and One Year After Bariatric Surgery - Margreke J. Brill; Anne van Rongen; Eric P. van Dongen; Bert van Ramshorst; Eric J. Hazebroek; Adam S. Darwich; Amin Rostami-Hodjegan; Catherijne A. Knibbe (Pharmaceutical Research, 2015)

Multitrophic enemy escape of invasive Phragmites australis and its introduced herbivores in North America - Warwick J. Allen; Randee E. Young; Ganesh P. Bhattarai; Jordan R. Croy; Adam M. Lambert; Laura A. Meyerson; James T. Cronin (Biological Invasions, 2015)

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Layer- and Direction-Specific Material Properties, Extreme Extensibility and Ultimate Material Strength of Human Abdominal Aorta and Aneurysm: A Uniaxial Extension Study - Zhongzhao Teng; Jiaxuan Feng; Yongxue Zhang; Yuan Huang; Michael P. F. Sutcliffe; Adam J. Brown; Zaiping Jing; Jonathan H. Gillard; Qingsheng Lu (Annals of Biomedical Engineering, 2015)

Shifts in microbial food web structure and productivity after additions of naturally occurring dissolved organic matter: Results from large‐scale lacustrine mesocosms - Robert W. Sanders; Sandra L. Cooke; Janet M. Fischer; Samuel B. Fey; Adam W. Heinze; Wade H. Jeffrey; Amy L. Macaluso; Robert E. Moeller; Donald P. Morris; Patrick J. Neale; Mark H. Olson; J. Dean Pakulski; et al. (Limnology and Oceanography, 2015)
Predicting the effects of dissolved organic matter (DOM) on pelagic food webs can be difficult because DOM modifies water column optics and can have contrasting effects on species across trophic levels. We combined large mesocosm, smaller‐scale experiments and autoregressive modeling driven bu DOC concentration or DOM optical quality (colored DOM, or CDOM, measured as DOC‐specific absorbance at 320 nm, SUVA 320 ) to assess how heterotrophic and phototrophic microbial populations were altered in a temperate oligotrophic lake. DOM additions yielded DOC concentrations of 1.6 mg L −1 (control) 2.5 mg L −1 , 3.0 mg L −1 , and 4.3 mg L −1 . Primary (PP) and bacterial (BP) production as well as heterotrophic and autotrophic protist abundances were stimulated in the higher DOM additions. BP responded rapidly to DOM additions, but unlike PP, returned to the level of controls within 2–7 d. A bioassay showed that the DOM was a nitrogen source for phytoplankton. The two models revealed that BP and edible phytoplankton were stimulated by CDOM (SUVA 320 ), but only BP was stimulated by DOC concentration. Ultraviolet radiation (UV) inhibited protists in both models, but stimulated edible phytoplankton only in the SUVA 320 model runs. These results suggest that in transparent oligotrophic lakes large influxes of terrestrial (high SUVA 320 ) DOM will stimulate the microbial food web by providing a nutrient subsidy to bacteria and reducing exposure of protists to damaging UV. Nutrients associated with moderate DOM input may also stimulate PP relative to BP, as was observed in these and other experiments, rather than causing an overall system shift toward heterotrophy.

Experimental drought and heat can delay phenological development and reduce foliar and shoot growth in semiarid trees - Henry D. Adams; Adam D. Collins; Samuel P. Briggs; Michel Vennetier; L. Turin Dickman; Sanna A. Sevanto; Núria Garcia‐Forner; Heath H. Powers; Nate G. McDowell (Global Change Biology, 2015)
Higher temperatures associated with climate change are anticipated to trigger an earlier start to the growing season, which could increase the terrestrial C sink strength. Greater variability in the amount and timing of precipitation is also expected with higher temperatures, bringing increased drought stress to many ecosystems. We experimentally assessed the effects of higher temperature and drought on the foliar phenology and shoot growth of mature trees of two semiarid conifer species. We exposed field‐grown trees to a ~45% reduction in precipitation with a rain‐out structure (‘drought’), a ~4.8 °C temperature increase with open‐top chambers (‘heat’), and a combination of both simultaneously (‘drought + heat’). Over the 2013 growing season, drought, heat, and drought + heat treatments reduced shoot and needle growth in piñon pine ( Pinus edulis ) by ≥39%, while juniper ( Juniperus monosperma ) had low growth and little response to these treatments. Needle emergence on primary axis branches of piñon pine was delayed in heat, drought, and drought + heat treatments by 19–57 days, while secondary axis branches were less likely to produce needles in the heat treatment, and produced no needles at all in the drought + heat treatment. Growth of shoots and needles, and the timing of needle emergence correlated inversely with xylem water tension and positively with nonstructural carbohydrate concentrations. Our findings demonstrate the potential for delayed phenological development and reduced growth with higher temperatures and drought in tree species that are vulnerable to drought and reveal potential mechanistic links to physiological stress responses. Climate change projections of an earlier and longer growing season with higher temperatures, and consequent increases in terrestrial C sink strength, may be incorrect for regions where plants will face increased drought stress with climate change.

Two nights of sleep deprivation with or without energy restriction does not impair the thermal response to cold - Samuel J. Oliver; Adam D. Harper Smith; Ricardo J. S. Costa; Norbert Maassen; James L. J. Bilzon; Neil P. Walsh (European Journal of Applied Physiology, 2015)

Production and characterisation of Epstein–Barr virus helicase–primase complex and its accessory protein BBLF2/3 - Eric Thierry; Martha Brennich; Adam Round; Marlyse Buisson; Wim P. Burmeister; Stephanie Hutin (Virus Genes, 2015)

Leaching of copper and nickel in soil-water systems contaminated by bauxite residue (red mud) from Ajka, Hungary: the importance of soil organic matter - Cindy L. Lockwood; Douglas I. Stewart; Robert J. G. Mortimer; William M. Mayes; Adam P. Jarvis; Katalin Gruiz; Ian T. Burke (Environmental Science and Pollution Research, 2015)

A framework for modeling uncertainty in regional climate change - Erwan Monier; Xiang Gao; Jeffery R. Scott; Andrei P. Sokolov; C. Adam Schlosser (Climatic Change, 2015)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

A novel cisplatin mediated apoptosis pathway is associated with acid sphingomyelinase and FAS proapoptotic protein activation in ovarian cancer - L. Maurmann; L. Belkacemi; N. R. Adams; P. M. Majmudar; S. Moghaddas; R. N. Bose (Apoptosis, 2015)

Harnessing the climate mitigation, conservation and poverty alleviation potential of seagrasses: prospects for developing blue carbon initiatives and payment for ecosystem service programmes - Adam P. Hejnowicz; Hilary Kennedy; Murray A. Rudd; Mark R. Huxham (Frontiers in Marine Science, 2015)

Patterns of herbivory-induced mortality of a dominant non-native tree/shrub (Tamarix spp.) in a southwestern US watershed - Kevin R. Hultine; Tom L. Dudley; Dan F. Koepke; Daniel W. Bean; Ed P. Glenn; Adam M. Lambert (Biological Invasions, 2015)

Nutrient uptake and primary productivity in an urban estuary: using rate measurements to evaluate phytoplankton response to different hydrological and nutrient conditions - Frances P. Wilkerson; Richard C. Dugdale; Alexander E. Parker; Sarah B. Blaser; Adam Pimenta (Aquatic Ecology, 2015)

International Guidelines for Bioequivalence of Locally Acting Orally Inhaled Drug Products: Similarities and Differences - Dongmei Lu; Sau L. Lee; Robert A. Lionberger; Stephanie Choi; Wallace Adams; Hoainhon N. Caramenico; Badrul A. Chowdhury; Dale P. Conner; Rohit Katial; Susan Limb; John R. Peters; Lawrence Yu; et al. (The AAPS Journal, 2015)

Non-invasive estimation of hydration status changes through tear fluid osmolarity during exercise and post-exercise rehydration - Corey T. Ungaro; Adam J. Reimel; Ryan P. Nuccio; Kelly A. Barnes; Matthew D. Pahnke; Lindsay B. Baker (European Journal of Applied Physiology, 2015)

Light acclimation optimizes leaf functional traits despite height-related constraints in a canopy shading experiment - Adam P. Coble; Molly A. Cavaleri (Oecologia, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Overuse Activity in the Presence of Scapular Dyskinesis Leads to Shoulder Tendon Damage in a Rat Model - Katherine E. Reuther; Stephen J. Thomas; Jennica J. Tucker; Rameen P. Vafa; Joshua A. Gordon; Stephen S. Liu; Adam C. Caro; Sarah M. Yannascoli; Andrew F. Kuntz; Louis J. Soslowsky (Annals of Biomedical Engineering, 2015)

Role of SIRT1 in autoimmune demyelination and neurodegeneration - Alvaro Martin; Cosmin A. Tegla; Cornelia D. Cudrici; Adam M. Kruszewski; Philippe Azimzadeh; Dallas Boodhoo; Armugam P. Mekala; Violeta Rus; Horea Rus (Immunologic Research, 2015)

Songbirds as sentinels of mercury in terrestrial habitats of eastern North America - Allyson K. Jackson; David C. Evers; Evan M. Adams; Daniel A. Cristol; Collin Eagles-Smith; Samuel T. Edmonds; Carrie E. Gray; Bart Hoskins; Oksana P. Lane; Amy Sauer; Timothy Tear (Ecotoxicology, 2015)

Thermal adaptation generates a diversity of thermal limits in a rainforest ant community - Michael Kaspari; Natalie A. Clay; Jane Lucas; Stephen P Yanoviak; Adam Kay (Global Change Biology, 2015)
The Thermal Adaptation Hypothesis posits that the warmer, aseasonal tropics generates populations with higher and narrower thermal limits. It has largely been tested among populations across latitudes. However, considerable thermal heterogeneity exists within ecosystems: across 31 trees in a Panama rainforest, surfaces exposed to sun were 8 °C warmer and varied more in temperature than surfaces in the litter below. Tiny ectotherms are confined to surfaces and are variously submerged in these superheated boundary layer environments. We quantified the surface CT min and CT max s (surface temperatures at which individuals grew torpid and lost motor control, respectively) of 88 ant species from this forest; they ranged in average mass from 0.01 to 57 mg. Larger ants had broader thermal tolerances. Then, for 26 of these species we again tested body CT max s using a thermal dry bath to eliminate boundary layer effects: body size correlations observed previously disappeared. In both experiments, consistent with Thermal Adaptation, CT max s of canopy ants averaged 3.5–5 °C higher than populations that nested in the shade of the understory. We impaled thermocouples in taxidermy mounts to further quantify the factors shaping operative temperatures for four ant species representing the top third (1–30 mg) of the size distribution. Extrapolations suggest the smallest 2/3rds of species reach thermal equilibrium in CT max subsuming 74% of those previously recorded for ant populations worldwide. The Thermal Adaptation Hypothesis can be a powerful tool in predicting diversity of thermal limits within communities. Boundary layer temperatures are likely key to predicting the future of Earth's tiny terrestrial ectotherm populations.

Stochastic Modelling of Reservoir Sedimentation in a Semi-Arid Watershed - N. Adam; S. Erpicum; P. Archambeau; M. Pirotton; B. Dewals (Water Resources Management, 2015)

European newts establish in Australia, marking the arrival of a new amphibian order - Reid Tingley; Andrew R. Weeks; Adam S. Smart; Anthony R. van Rooyen; Andrew P. Woolnough; Michael A. McCarthy (Biological Invasions, 2015)

Decreased expression of HLA-DQ and HLA-DR on cells of the monocytic lineage in cystic fibrosis - Thomas P. Hofer; Marion Frankenberger; Irene Heimbeck; Dorothe Burggraf; Matthias Wjst; Adam K. A. Wright; Maria Kerscher; Susanne Nährig; Rudolf M. Huber; Rainald Fischer; Loems Ziegler- Heitbrock (Journal of Molecular Medicine, 2014)

Molecular species identification for multiple carnivores - Marta De Barba; Jennifer R. Adams; Caren S. Goldberg; Carisa R. Stansbury; Daniela Arias; Rodrigo Cisneros; Lisette P. Waits (Conservation Genetics Resources, 2014)

Genome sequence of vanilla distortion mosaic virus infecting Coriandrum sativum - I. P. Adams; S. Rai; M. Deka; V. Harju; T. Hodges; G. Hayward; A. Skelton; A. Fox; N. Boonham (Archives of Virology, 2014)

Common vitamin D pathway gene variants reveal contrasting effects on serum vitamin D levels in African Americans and European Americans - Ken Batai; Adam B. Murphy; Ebony Shah; Maria Ruden; Jennifer Newsome; Sara Agate; Michael A. Dixon; Hua Yun Chen; Leslie A. Deane; Courtney M. P. Hollowell; Chiledum Ahaghotu; Rick A. Kittles (Human Genetics, 2014)

The energy‐conserving electron transfer system used by D esulfovibrio alaskensis strain G 20 during pyruvate fermentation involves reduction of endogenously formed fumarate and cytoplasmic and membrane‐bound complexes, Hdr‐Flox and Rnf - Birte Meyer; Jennifer V. Kuehl; Morgan N. Price; Jayashree Ray; Adam M. Deutschbauer; Adam P. Arkin; David A. Stahl (Environmental Microbiology, 2014)
Summary The adaptation capability of D esulfovibrio to natural fluctuations in electron acceptor availability was evaluated by studying D esulfovibrio alaskensis strain G 20 under varying respiratory, fermentative and methanogenic coculture conditions in chemostats. Transition from lactate to pyruvate in coculture resulted in a dramatic shift in the population structure and closer interspecies cell‐to‐cell interactions. Lower methane production rates in coculture than predicted from pyruvate input was attributed to redirection of electron flow to fumarate reduction. Without a methanogenic partner, accumulation of H 2 and formate resulted in greater succinate production. Comparative transcript and gene fitness analysis in concert with physiological data of G 20 wildtype and mutants demonstrated that pyruvate fermentation involves respiration of cytoplasmically formed fumarate using cytoplasmic and membrane‐bound energy‐conserving complexes, Rnf , Hdr‐Flox ‐1 and Hmc. At the low H 2 /formate levels maintained in coculture, Rnf likely functions as proton‐pumping ferredoxin (Fd) : type‐I cytochrome c oxidoreductase, which transitions to a proton‐pumping Fd red : nicotinamide adenine dinucleotide ( NAD + ) oxidoreductase at high H 2 /formate levels during fermentation in monoculture. Hdr‐Flox ‐1 is postulated to recycle Fd red via a flavin‐based electron bifurcation involving NADH , Fd ox and the thiol/disulphide‐containing DsrC . In a menaquinone ( MQ )‐based electron confurcation reaction, the high‐molecular‐weight cytochrome‐c 3 complex, Hmc , is proposed to then couple DsrC red and periplasmic H 2 /formate oxidation using the MQ pool to fuel a membrane‐bound fumarate reductase.

Reproductive morphology of the deep-sea protobranch bivalves Yoldiella ecaudata, Yoldiella sabrina, and Yoldiella valettei (Yoldiidae) from the Southern Ocean - Adam J. Reed; James P. Morris; Katrin Linse; Sven Thatje (Polar Biology, 2014)

Aspirated bile: a major host trigger modulating respiratory pathogen colonisation in cystic fibrosis patients - F. J. Reen; D. F. Woods; M. J. Mooij; M. N. Chróinín; D. Mullane; L. Zhou; J. Quille; D. Fitzpatrick; J. D. Glennon; G. P. McGlacken; C. Adams; F. O’Gara (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Introduced parasite Anguillicola crassus infection significantly impedes swim bladder function in the European eel Anguilla anguilla (L.) - J Barry; J McLeish; J A Dodd; J F Turnbull; P Boylan; C E Adams (Journal of Fish Diseases, 2014)

A flexible spatio-temporal model for air pollution with spatial and spatio-temporal covariates - Johan Lindström; Adam A. Szpiro; Paul D. Sampson; Assaf P. Oron; Mark Richards; Tim V. Larson; Lianne Sheppard (Environmental and Ecological Statistics, 2014)

Nucleotide variants of the cancer predisposing gene CDH1 and the risk of non-syndromic cleft lip with or without cleft palate - Kamil K. Hozyasz; Adrianna Mostowska; Piotr Wójcicki; Agnieszka Lasota; Barbara Offert; Adam Balcerek; Izabella Dunin-Wilczyńska; Paweł P. Jagodziński (Familial Cancer, 2014)

Quantifying targets to manage invasion risk: light gradients dominate the early regeneration niche of naturalized and pre-commercial Miscanthus populations - Natalie M. West; David P. Matlaga; Adam S. Davis (Biological Invasions, 2014)

Beyond a warming fingerprint: individualistic biogeographic responses to heterogeneous climate change in California - Giovanni Rapacciuolo; Sean P. Maher; Adam C. Schneider; Talisin T. Hammond; Meredith D. Jabis; Rachel E. Walsh; Kelly J. Iknayan; Genevieve K. Walden; Meagan F. Oldfather; David D. Ackerly; Steven R. Beissinger (Global Change Biology, 2014)
Understanding recent biogeographic responses to climate change is fundamental for improving our predictions of likely future responses and guiding conservation planning at both local and global scales. Studies of observed biogeographic responses to 20th century climate change have principally examined effects related to ubiquitous increases in temperature – collectively termed a warming fingerprint. Although the importance of changes in other aspects of climate – particularly precipitation and water availability – is widely acknowledged from a theoretical standpoint and supported by paleontological evidence, we lack a practical understanding of how these changes interact with temperature to drive biogeographic responses. Further complicating matters, differences in life history and ecological attributes may lead species to respond differently to the same changes in climate. Here, we examine whether recent biogeographic patterns across California are consistent with a warming fingerprint. We describe how various components of climate have changed regionally in California during the 20th century and review empirical evidence of biogeographic responses to these changes, particularly elevational range shifts. Many responses to climate change do not appear to be consistent with a warming fingerprint, with downslope shifts in elevation being as common as upslope shifts across a number of taxa and many demographic and community responses being inconsistent with upslope shifts. We identify a number of potential direct and indirect mechanisms for these responses, including the influence of aspects of climate change other than temperature (e.g., the shifting seasonal balance of energy and water availability), differences in each taxon's sensitivity to climate change, trophic interactions, and land‐use change. Finally, we highlight the need to move beyond a warming fingerprint in studies of biogeographic responses by considering a more multifaceted view of climate, emphasizing local‐scale effects, and including a priori knowledge of relevant natural history for the taxa and regions under study.

Diatoms indicate that calcium decline, not acidification, explains recent cladoceran assemblage changes in south-central Ontario softwater lakes - Jennifer L. Barrow; Adam Jeziorski; Kathleen M. Rühland; Kristopher R. Hadley; John P. Smol (Journal of Paleolimnology, 2014)

Prolonged infrapatellar tendon vibration does not influence quadriceps maximal or explosive isometric force production in man - Adam Fry; Jonathan P. Folland (European Journal of Applied Physiology, 2014)

Hebbian learning from higher-order correlations requires crosstalk minimization - K. J. A. Cox; P. R. Adams (Biological Cybernetics, 2014)

Acute toxicity of copper, lead, cadmium, and zinc to early life stages of white sturgeon (Acipenser transmontanus) in laboratory and Columbia River water - David W. Vardy; Robert Santore; Adam Ryan; John P. Giesy; Markus Hecker (Environmental Science and Pollution Research, 2014)

Hydraulic Performance and Iron Removal in Wetlands and Lagoons Treating Ferruginous Coal Mine Waters - Faradiella M. Kusin; Adam P. Jarvis; Catherine J. Gandy (Wetlands, 2014)

Providing patient education: impact on quantity and quality of family health history collection - Chris A. Beadles; R. Ryanne Wu; Tiffany Himmel; Adam H. Buchanan; Karen P. Powell; Elizabeth Hauser; Vincent C. Henrich; Geoffrey S. Ginsburg; Lori A. Orlando (Familial Cancer, 2014)

Assessing Risk to Birds from Industrial Wind Energy Development via Paired Resource Selection Models - TRICIA A. MILLER; ROBERT P. BROOKS; MICHAEL LANZONE; DAVID BRANDES; JEFF COOPER; KIERAN O'MALLEY; CHARLES MAISONNEUVE; JUNIOR TREMBLAY; ADAM DUERR; TODD KATZNER (Conservation Biology, 2014)
When wildlife habitat overlaps with industrial development animals may be harmed. Because wildlife and people select resources to maximize biological fitness and economic return, respectively, we estimated risk, the probability of eagles encountering and being affected by turbines, by overlaying models of resource selection for each entity. This conceptual framework can be applied across multiple spatial scales to understand and mitigate impacts of industry on wildlife. We estimated risk to Golden Eagles (Aquila chrysaetos) from wind energy development in 3 topographically distinct regions of the central Appalachian Mountains of Pennsylvania (United States) based on models of resource selection of wind facilities (n = 43) and of northbound migrating eagles (n = 30). Risk to eagles from wind energy was greatest in the Ridge and Valley region; all 24 eagles that passed through that region used the highest risk landscapes at least once during low altitude flight. In contrast, only half of the birds that entered the Allegheny Plateau region used highest risk landscapes and none did in the Allegheny Mountains. Likewise, in the Allegheny Mountains, the majority of wind turbines (56%) were situated in poor eagle habitat; thus, risk to eagles is lower there than in the Ridge and Valley, where only 1% of turbines are in poor eagle habitat. Risk within individual facilities was extremely variable; on average, facilities had 11% (SD 23; range = 0–100%) of turbines in highest risk landscapes and 26% (SD 30; range = 0–85%) of turbines in the lowest risk landscapes. Our results provide a mechanism for relocating high‐risk turbines, and they show the feasibility of this novel and highly adaptable framework for managing risk of harm to wildlife from industrial development. Evaluación del Riesgo para las Aves por el Desarrollo de Energía Eólica Industrial Mediante Modelos de Selección de Recursos Pareados.

Genetic Diversity and Conservation Implications of Four Cupressus Species in China as Revealed by Microsatellite Markers - Xu Lu; Haiyan Xu; Zhonghu Li; Huiying Shang; Robert P. Adams; Kangshan Mao (Biochemical Genetics, 2014)

The complete genome sequences of two isolates of potato black ringspot virus and their relationship to other isolates and nepoviruses - R. Souza Richards; I. P. Adams; J. F. Kreuze; J. De Souza; W. Cuellar; A. M. Dullemans; R. A. A. Van Der Vlugt; R. Glover; U. Hany; M. Dickinson; N. Boonham (Archives of Virology, 2014)

Evaluating diatom‐derived Holocene pH reconstructions for Arctic lakes using an expanded 171‐lake training set - SARAH A. FINKELSTEIN; JOAN BUNBURY; KONRAD GAJEWSKI; ALEXANDER P. WOLFE; JENNIFER K. ADAMS; JANE E. DEVLIN (Journal of Quaternary Science, 2014)
Inference models from diatoms preserved in lake sediments can be used to reconstruct long‐term pH changes to better understand the process of lake ontogeny. An expanded diatom training set was developed using taxonomically harmonized modern assemblages in surface sediments of 171 lakes spanning a variety of geological and climatic settings across the Canadian Arctic. Lake‐water pH emerged as a significant variable and the most influential in structuring diatom assemblages. The resulting two‐component weighted‐averaging partial least squares pH inference model performs strongly, even after identifying effects of spatial autocorrelation at distances

Long-term Trends in Cladoceran Assemblages Related to Acidification and Subsequent Liming of Middle Lake (Sudbury, Canada) - Andrew L. Labaj; Adam Jeziorski; Joshua Kurek; John P. Smol (Water, Air, & Soil Pollution, 2014)

Antiangiogenic Effect of Docetaxel and Everolimus as Individual and Dual-Drug-Loaded Micellar Nanocarriers - Gyan P. Mishra; Bhuvana Shyam Doddapaneni; Duc Nguyen; Adam W. G. Alani (Pharmaceutical Research, 2014)

The Tendon Injury Response is Influenced by Decorin and Biglycan - Andrew A. Dunkman; Mark R. Buckley; Michael J. Mienaltowski; Sheila M. Adams; Stephen J. Thomas; Lauren Satchell; Akash Kumar; Lydia Pathmanathan; David P. Beason; Renato V. Iozzo; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2014)

Converging patterns of vertical variability in leaf morphology and nitrogen across seven Eucalyptus plantations in Brazil and Hawaii, USA - Adam P. Coble; Alisha Autio; Molly A. Cavaleri; Dan Binkley; Michael G. Ryan (Trees, 2014)

Farmer Participation in U.S. Farm Bill Conservation Programs - Adam P. Reimer; Linda S. Prokopy (Environmental Management, 2014)

The complete genome sequence of Piper yellow mottle virus (PYMoV) - U. Hany; I. P. Adams; R. Glover; A. I. Bhat; N. Boonham (Archives of Virology, 2014)

Reduction of Baltic Sea Nutrient Inputs and Allocation of Abatement Costs Within the Baltic Sea Catchment - Fredrik Wulff; Christoph Humborg; Hans Estrup Andersen; Gitte Blicher-Mathiesen; Mikołaj Czajkowski; Katarina Elofsson; Anders Fonnesbech-Wulff; Berit Hasler; Bongghi Hong; Viesturs Jansons; Carl-Magnus Mörth; James C. R. Smart; et al. (Ambio, 2014)

The influence of calcium decline and climate change on the cladocerans within low calcium, circumneutral lakes of the Experimental Lakes Area - Adam Jeziorski; Andrew M. Paterson; Ian Watson; Brian F. Cumming; John P. Smol (Hydrobiologia, 2014)

Control of methionine metabolism by the SahR transcriptional regulator in P roteobacteria - Pavel S. Novichkov; Xiaoqing Li; Jennifer V. Kuehl; Adam M. Deutschbauer; Adam P. Arkin; Morgan N. Price; Dmitry A. Rodionov (Environmental Microbiology, 2014)
Summary Sulphur is an essential element in the metabolism. The sulphur‐containing amino acid methionine is a metabolic precursor for S ‐adenosylmethionine ( SAM ), which serves as a coenzyme for ubiquitous methyltrtansferases. Recycling of organic sulphur compounds, e.g. via the SAM cycle, is an important metabolic process that needs to be tightly regulated. Knowledge about transcriptional regulation of these processes is still limited for many free‐living bacteria. We identified a novel transcription factor SahR from the ArsR family that controls the SAM cycle genes in diverse microorganisms from soil and aquatic ecosystems. By using comparative genomics, we predicted SahR ‐binding DNA motifs and reconstructed SahR regulons in the genomes of 62 P roteobacteria. The conserved core of SahR regulons includes all enzymes required for the SAM cycle: the SAH hydrolase AhcY , the methionine biosynthesis enzymes MetE / MetH and MetF , and the SAM synthetase MetK . By using a combination of experimental techniques, we validated the SahR regulon in the sulphate‐reducing D eltaproteobacterium D esulfovibrio alaskensis . SahR functions as a negative regulator that responds to the S ‐adenosylhomocysteine ( SAH ). The elevated SAH level in the cell dissociates SahR from its DNA operators and induces the expression of SAM cycle genes. The effector‐sensing domain in SahR is related to SAM ‐dependent methylases that are able to tightly bind SAH . SahR represents a novel type of transcriptional regulators for the control of sulphur amino acid metabolism.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

On the growth of locally interacting plants: differential equations for the dynamics of spatial moments - Thomas P. Adams; E. Penelope Holland; Richard Law; Michael J. Plank; Michael Raghib (Ecology, 2013)
Ecologists are faced with the challenge of how to scale up from the activities of individual plants and animals to the macroscopic dynamics of populations and communities. It is especially difficult to do this in communities of plants where the fate of individuals depends on their immediate neighbors rather than an average over a larger region. This has meant that algorithmic, agent‐based models are typically used to understand their dynamics, although certain macroscopic models have been developed for neighbor‐dependent, birth–death processes. Here we present a macroscopic model that, for the first time, incorporates explicit, gradual, neighbor‐dependent plant growth, as a third fundamental process of plant communities. The model is derived from a stochastic, agent‐based model, and describes the dynamics of the first and second spatial moments of a multispecies, spatially structured plant community with neighbor‐dependent growth, births, and deaths. A simple example shows that strong neighborhood space‐filling during tree growth in an even‐aged stand of Scots pine is well captured by the spatial‐moment model. The space‐filling has a spatial signature consistent with that observed in several field studies of forests. Small neighborhoods of interaction, nonuniform spacing of trees, and asymmetric competition all contribute to the buildup of a wide range of tree sizes with some large dominant individuals and many smaller ones.

Roles of Patch Characteristics, Drought Frequency, and Restoration in Long‐Term Trends of a Widespread Amphibian - BLAKE R. HOSSACK; MICHAEL J. ADAMS; CHRISTOPHER A. PEARL; KRISTINE W. WILSON; EVELYN L. BULL; KRISTIN LOHR; DEBRA PATLA; DAVID S. PILLIOD; JASON M. JONES; KEVIN K. WHEELER; SAMUEL P. MCKAY; PAUL STEPHEN CORN (Conservation Biology, 2013)
Despite the high profile of amphibian declines and the increasing threat of drought and fragmentation to aquatic ecosystems, few studies have examined long‐term rates of change for a single species across a large geographic area. We analyzed growth in annual egg‐mass counts of the Columbia spotted frog ( Rana luteiventris ) across the northwestern United States, an area encompassing 3 genetic clades. On the basis of data collected by multiple partners from 98 water bodies between 1991 and 2011, we used state‐space and linear‐regression models to measure effects of patch characteristics, frequency of summer drought, and wetland restoration on population growth. Abundance increased in the 2 clades with greatest decline history, but declined where populations are considered most secure. Population growth was negatively associated with temporary hydroperiods and landscape modification (measured by the human footprint index), but was similar in modified and natural water bodies. The effect of drought was mediated by the size of the water body: populations in large water bodies maintained positive growth despite drought, whereas drought magnified declines in small water bodies. Rapid growth in restored wetlands in areas of historical population declines provided strong evidence of successful management. Our results highlight the importance of maintaining large areas of habitat and underscore the greater vulnerability of small areas of habitat to environmental stochasticity. Similar long‐term growth rates in modified and natural water bodies and rapid, positive responses to restoration suggest pond construction and other forms of management can effectively increase population growth. These tools are likely to become increasingly important to mitigate effects of increased drought expected from global climate change . Papeles de las Características del Fragmento, Frecuencia de Sequía y Restauración en las Tendencias a Largo Plazo de un Anfibio Ampliamente Distribuido

Responses of the Salt Marsh Succulent Bassia diffusa (Thunb.) Kuntze to Salinity and Inundation - P. T. Tabot; J. B. Adams (Wetlands, 2013)

Foraging ants trade off further for faster: use of natural bridges and trunk trail permanency in carpenter ants - Raquel G. Loreto; Adam G. Hart; Thairine M. Pereira; Mayara L. R. Freitas; David P. Hughes; Simon L. Elliot (The Science of Nature, 2013)

Human-mediated drivers of change — impacts on coastal ecosystems and marine biota of South Africa - A Mead; C L Griffiths; G M Branch; C D McQuaid; L K Blamey; J J Bolton; R J Anderson; F Dufois; M Rouault; P W Froneman; A K Whitfield; L R Harris; et al. (African Journal of Marine Science, 2013)

Three nights of sleep deprivation does not alter thermal strain during exercise in the heat - Jonathan P. Moore; Adam D. Harper Smith; Umberto Di Felice; Neil P. Walsh (European Journal of Applied Physiology, 2013)

LC–DAD–MS-based metabolite profiling of three species of Justicia (Acanthaceae) - Angela I. Calderón; Adam Hodel; Jean-Luc Wolfender; Mahabir P. Gupta; Mireya Correa; Kurt Hostettmann (Natural Product Research, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A new quantitative real-time PCR assay for Rhizoctonia solani AG3-PT and the detection of AGs of Rhizoctonia solani associated with potato in soil and tuber samples in Great Britain - James W. Woodhall; Ian P. Adams; Jeff C. Peters; Glyn Harper; Neil Boonham (European Journal of Plant Pathology, 2013)

Phylogenetic Patterns of Sexual Size Dimorphism in Turtles and Their Implications for Rensch’s Rule - Claudia P. Ceballos; Dean C. Adams; John B. Iverson; Nicole Valenzuela (Evolutionary Biology, 2013)

Evidence of a recent decline in river lamprey Lampetra fluviatilis parasitism of a nationally rare whitefish Coregonus lavaretus : is there a diamond in the ruffe Gymnocephalus cernuus ? - J. B. Hume; C. E. Adams; C. W. Bean; P. S. Maitland (Journal of Fish Biology, 2013)
Lamprey‐induced scarring of the nationally rare Coregonus lavaretus , a known host of a freshwater‐resident population of European river lamprey Lampetra fluviatilis , was found to have declined precipitously since the establishment of several non‐native fishes in Loch Lomond. Evidence presented in this study points to the possibility that L. fluviatilis in this lake may have altered its trophic ecology in response to the negative impact that non‐native species, in particular ruffe Gymnocephalus cernuus , have had on their favoured host.

Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches - A. R. Sheik; C. P. D. Brussaard; G. Lavik; R. A. Foster; N. Musat; B. Adam; M. M. M. Kuypers (Environmental Microbiology, 2013)
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l −1 ). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l −1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.

Pharmacokinetics and Metabolism of 2-Aminothiazoles with Antiprion Activity in Mice - B. Michael Silber; Satish Rao; Kimberly L. Fife; Alejandra Gallardo-Godoy; Adam R. Renslo; Deepak K. Dalvie; Kurt Giles; Yevgeniy Freyman; Manuel Elepano; Joel R. Gever; Zhe Li; Matthew P. Jacobson; et al. (Pharmaceutical Research, 2013)

Complete genome sequence of arracacha virus B: a novel cheravirus - I. P. Adams; R. Glover; R. Souza-Richards; S. Bennett; U. Hany; N. Boonham (Archives of Virology, 2013)

Fentanyl-associated Fatalities Among Illicit Drug Users in Wayne County, Michigan (July 2005–May 2006) - D. Adam Algren; Carolyn P. Monteilh; Mohan Punja; Joshua G. Schier; Martin Belson; Bradford R. Hepler; Carl J. Schmidt; Corinne E. Miller; Manish Patel; Leonard J. Paulozzi; Masja Straetemans; Carol Rubin (Journal of Medical Toxicology, 2013)

Aquatic Ecosystem Responses to Rapid Recovery from Extreme Acidification and Metal Contamination in Lakes Near Wawa, Ontario - Adam Jeziorski; Bill Keller; Andrew M. Paterson; Christine M. Greenaway; John P. Smol (Ecosystems, 2013)

The role of continental shelf width in determining freshwater phylogeographic patterns in south‐eastern A ustralian pygmy perches ( T eleostei: P ercichthyidae) - Peter J. Unmack; Michael P. Hammer; Mark Adams; Jerald B. Johnson; Thomas E. Dowling (Molecular Ecology, 2013)
Biogeographic patterns displayed by obligate freshwater organisms are intimately related to the nature and extent of connectivity between suitable habitats. Two of the more significant barriers to freshwater connections are seawater and major drainage divides. South‐eastern A ustralia provides a contrast between these barriers as it has discrete areas that are likely influenced to a greater or lesser extent by each barrier type. We use continental shelf width as a proxy for the potential degree of river coalescence during low sea levels. Our specific hypothesis is that the degree of phylogeographic divergence between coastal river basins should correspond to the continental shelf width of each region. This predicts that genetic divergences between river basins should be lowest in regions with a wider continental shelf and that regions with similar continental shelf width should have similar genetic divergences. Pygmy perches ( N annoperca australis and N annoperca ‘flindersi’) in south‐eastern A ustralia provide an ideal opportunity to test these biogeographic hypotheses. Phylogeographic patterns were examined based on range‐wide sampling of 82 populations for cytochrome b and 23 polymorphic allozyme loci. Our results recovered only limited support for our continental shelf width hypothesis, although patterns within Bass clade were largely congruent with reconstructed low sea‐level drainage patterns. In addition, we identified several instances of drainage divide crossings, typically associated with low elevational differences. Our results demonstrate high levels of genetic heterogeneity with important conservation implications, especially for declining populations in the M urray– D arling B asin and a highly restricted disjunct population in A nsons R iver, T asmania.

Racial disparities in colorectal cancer incidence by type 2 diabetes mellitus status - Philip P. Cavicchia; Swann Arp Adams; Susan E. Steck; James R. Hussey; Jihong Liu; Virginie G. Daguisé; James R. Hebert (Cancer Causes & Control, 2013)

Phylogenetics of Stelis and closely related genera (Orchidaceae: Pleurothallidinae) - Adam P. Karremans; Freek T. Bakker; Franco Pupulin; Rodolfo Solano-Gómez; Marinus J. M. Smulders (Plant Systematics and Evolution, 2013)

Evaluating the ability of Bayesian clustering methods to detect hybridization and introgression using an empirical red wolf data set - Justin H. Bohling; Jennifer R. Adams; Lisette P. Waits (Molecular Ecology, 2013)
Bayesian clustering methods have emerged as a popular tool for assessing hybridization using genetic markers. Simulation studies have shown these methods perform well under certain conditions; however, these methods have not been evaluated using empirical data sets with individuals of known ancestry. We evaluated the performance of two clustering programs, baps and structure , with genetic data from a reintroduced red wolf ( Canis rufus ) population in North Carolina, USA. Red wolves hybridize with coyotes ( C. latrans ), and a single hybridization event resulted in introgression of coyote genes into the red wolf population. A detailed pedigree has been reconstructed for the wild red wolf population that includes individuals of 50–100% red wolf ancestry, providing an ideal case study for evaluating the ability of these methods to estimate admixture. Using 17 microsatellite loci, we tested the programs using different training set compositions and varying numbers of loci. structure was more likely than baps to detect an admixed genotype and correctly estimate an individual's true ancestry composition. However, structure was more likely to misclassify a pure individual as a hybrid. Both programs were outperformed by a maximum‐likelihood‐based test designed specifically for this system, which never misclassified a hybrid (50–75% red wolf) as a red wolf or vice versa. Training set composition and the number of loci both had an impact on accuracy but their relative importance varied depending on the program. Our findings demonstrate the importance of evaluating methods used for detecting admixture in the context of endangered species management.

Phylogenetic relationships among the New World cypresses (Hesperocyparis; Cupressaceae): evidence from noncoding chloroplast DNA sequences - Randall G. Terry; Jim A. Bartel; Robert P. Adams (Plant Systematics and Evolution, 2012)

Exposure to particulate matter and adverse birth outcomes: a comprehensive review and meta-analysis - Amir Sapkota; Adam P. Chelikowsky; Keeve E. Nachman; Aaron J. Cohen; Beate Ritz (Air Quality, Atmosphere & Health, 2012)

Measurement of Drug in Small Particles from Aqueous Nasal Sprays by Andersen Cascade Impactor - William H. Doub; Wallace P. Adams; Anna M. Wokovich; John C. Black; Meiyu Shen; Lucinda F. Buhse (Pharmaceutical Research, 2012)

A new large scale soil DNA extraction procedure and real-time PCR assay for the detection of Sclerotium cepivorum in soil - James W. Woodhall; Kathryn M. Webb; Patricia M. Giltrap; Ian P. Adams; Jeff C. Peters; Giles E. Budge; Neil Boonham (European Journal of Plant Pathology, 2012)

Preliminary success using hydrogen peroxide to treat A tlantic salmon, S almo salar L. , affected with experimentally induced amoebic gill disease ( AGD ) - M B Adams; P B B Crosbie; B F Nowak (Journal of Fish Diseases, 2012)
Currently, the only effective and commercially used treatment for amoebic gill disease ( AGD ) in farmed T asmanian A tlantic salmon is freshwater bathing. H ydrogen peroxide ( H 2 O 2 ), commonly used throughout the aquaculture industry for a range of topical skin and gill infections, was trialled in vitro and in vivo to ascertain its potential as an alternative treatment against AGD . Under in vitro conditions, trophozoites of N eoparamoeba perurans were exposed to three concentrations of H 2 O 2 in sea water (500, 1000 and 1500 mg L −1 ) over four durations (10, 20, 30 and 60 min) each at two temperatures (12 and 18 °C). Trophozoite viability was assessed immediately post‐exposure and after 24 h. A concentration/duration combination of 1000 mg L −1 for >10 min demonstrated potent amoebicidal activity. Subsequently, A tlantic salmon mildly affected with experimentally induced AGD were treated with H 2 O 2 at 12 and 18 °C for 15 min at 1250 mg L −1 and their re‐infection rate was compared to freshwater‐treated fish over 21 days. Significant differences in the percentage of filaments affected with hyperplastic lesions (in association with amoebae) and plasma osmolality were noted between treatment groups immediately post‐bath. However, the results were largely equivocal in terms of disease resolution over a 3‐week period following treatment. These data suggest that H 2 O 2 treatment in sea water successfully ameliorated a clinically light case of AGD under laboratory conditions.

Morphological and physiological responses of Triglochin buchenaui Köcke, Mering & Kadereit to various combinations of water and salinity: implications for resilience to climate change - P. T. Tabot; J. B. Adams (Wetlands Ecology and Management, 2012)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Carbachol-Induced Volume Adaptation in Mouse Bladder and Length Adaptation via Rhythmic Contraction in Rabbit Detrusor - John E. Speich; Cameron W. Wilson; Atheer M. Almasri; Jordan B. Southern; Adam P. Klausner; Paul H. Ratz (Annals of Biomedical Engineering, 2012)

Effects of Device and Formulation on In Vitro Performance of Dry Powder Inhalers - Wallace P. Adams; Sau L. Lee; Robert Plourde; Robert A. Lionberger; Craig M. Bertha; William H. Doub; Jean-Marc Bovet; Anthony J. Hickey (The AAPS Journal, 2012)

Cognition in Obstructive Sleep Apnea-Hypopnea Syndrome (OSAS): Current Clinical Knowledge and the Impact of Treatment - Stephanie A. Kielb; Sonia Ancoli-Israel; George W. Rebok; Adam P. Spira (NeuroMolecular Medicine, 2012)

Erratum to: Contemporary Reviews of Mine Water Studies in Europe, Part 1 - Christian Wolkersdorfer; Rob Bowell; Jaime M. Amezaga; Adeline Kroll; Adam P. Jarvis; Ben Rees; Erik Puura; Wiel M. H. Miseré; Roy W. M. G. Wings; Peter Bajtoš; Leopold Weber; Blanka Sárváryné-Szentkatolnay; et al. (Mine Water and the Environment, 2012)

Changes since the onset of acid deposition among calcium-sensitive cladoceran taxa within softwater lakes of Ontario, Canada - Adam Jeziorski; Andrew M. Paterson; John P. Smol (Journal of Paleolimnology, 2012)

Cladoceran Response to Calcium Decline and the Subsequent Inadvertent Liming of a Softwater Canadian Lake - Melanie Shapiera; Adam Jeziorski; Andrew M. Paterson; John P. Smol (Water, Air, & Soil Pollution, 2012)

Creating a Cadre of Junior Investigators to Address the Challenges of Cancer-Related Health Disparities: Lessons Learned from the Community Networks Program - Tisha M. Felder; Heather M. Brandt; Cheryl A. Armstead; Philip P. Cavicchia; Kathryn L. Braun; Swann A. Adams; Daniela B. Friedman; Sora Tanjasiri; Susan E. Steck; Emily R. Smith; Virginie G. Daguisé; James R. Hébert (Journal of Cancer Education, 2012)

Analysis of climate policy targets under uncertainty - Mort Webster; Andrei P. Sokolov; John M. Reilly; Chris E. Forest; Sergey Paltsev; Adam Schlosser; Chien Wang; David Kicklighter; Marcus Sarofim; Jerry Melillo; Ronald G. Prinn; Henry D. Jacoby (Climatic Change, 2012)

The Influence of Engineering Scale and Environmental Conditions on the Performance of Compost Bioreactors for the Remediation of Zinc in Mine Water Discharges - Catherine J. Gandy; Adam P. Jarvis (Mine Water and the Environment, 2012)

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

Climate change projections and stratosphere–troposphere interaction - Adam A. Scaife; Thomas Spangehl; David R. Fereday; Ulrich Cubasch; Ulrike Langematz; Hideharu Akiyoshi; Slimane Bekki; Peter Braesicke; Neal Butchart; Martyn P. Chipperfield; Andrew Gettelman; Steven C. Hardiman; et al. (Climate Dynamics, 2012)

Report on the 31st Southern Forest Tree Improvement Conference (SFTIC) - C. Dana Nelson; Randall J. Rousseau; Joshua P. Adams; M. Cetin Yuceer (Tree Genetics & Genomes, 2012)

Temperature sensitivity of soil enzyme kinetics under N ‐fertilization in two temperate forests - Madeleine M. Stone; Marissa S. Weiss; Christine L. Goodale; Mary Beth Adams; Ivan J. Fernandez; Donovan P. German; Steven D. Allison (Global Change Biology, 2012)
Soil microbes produce extracellular enzymes that degrade carbon ( C )‐containing polymers in soil organic matter. Because extracellular enzyme activities may be sensitive to both increased nitrogen ( N ) and temperature change, we measured the effect of long‐term N addition and short‐term temperature variation on enzyme kinetics in soils from hardwood forests at B ear B rook, M aine, and F ernow F orest, W est V irginia. We determined the V max and K m parameters for five hydrolytic enzymes: α ‐glucosidase, β ‐glucosidase, β ‐xylosidase, cellobiohydrolase, and N ‐ acetyl‐glucosaminidase. Temperature sensitivities of V max and K m were assessed within soil samples subjected to a range of temperatures. We hypothesized that (1) N additions would cause microbial C limitation, leading to higher enzyme V max values and lower K m values; and (2) both V max and K m would increase at higher temperatures. Finally, we tested whether or not temperature sensitivity of enzyme kinetics is mediated by N addition. Nitrogen addition significantly or marginally significantly increased V max values for all enzymes, particularly at F ernow. Nitrogen fertilization led to significantly lower K m values for all enzymes at B ear B rook, but variable K m responses at F ernow F orest. Both V max and K m were temperature sensitive, with Q 10 values ranging from 1.64–2.27 for enzyme V max and 1.04–1.93 for enzyme K m . No enzyme showed a significant interaction between N and temperature sensitivity for V max , and only β ‐xylosidase showed a significant interaction between N and temperature sensitivity for K m . Our study is the first to experimentally demonstrate a positive relationship between K m and temperature for soil enzymes. Higher temperature sensitivities for V max relative to K m imply that substrate degradation will increase with temperature. In addition, the V max and K m responses to N indicate greater substrate degradation under N addition. Our results suggest that increasing temperatures and N availability in forests of the northeastern US will lead to increased hydrolytic enzyme activity, despite the positive temperature sensitivity of K m .

Are phenotypic traits useful for differentiating among a priori Coregonus taxa? - E. C. Etheridge; C. E. Adams; C. W. Bean; N. C. Durie; A. R. D. Gowans; C. Harrod; A. A. Lyle; P. S. Maitland; I. J. Winfield (Journal of Fish Biology, 2012)
A key for three putative species apparently found in three geographic areas, i.e. Coregonus clupeoides (in Scotland), Coregonus stigmaticus (in England), and Coregonus pennantii (in Wales) given in a recent review was tested quantitatively using 544 individuals from nine populations. The classification success of the key was very low (27%). It was concluded that there is currently no robust evidence for the recognition of the three putative species. Furthermore, the use of phenotypic characters alone to distinguish putative species in postglacial fish species such as those of the genus Coregonus that show homoplasy in many of these traits is questioned. In the absence of further evidence, it was concluded that a single highly variable species best describes the pattern of phenotypic variation in these U.K. populations. On this basis it is argued that taxonomic subdivision of U.K. European coregonids is inappropriate and that Coregonus lavaretus should prevail as the species name applicable to all populations.

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

When three per cent may not be three per cent; device-equipped seabirds experience variable flight constraints - Sylvie P. Vandenabeele; Emily L. Shepard; Adam Grogan; Rory P. Wilson (Marine Biology, 2012)

Crustacean zooplankton sedimentary remains from calcium-poor lakes: complex responses to threshold concentrations - Adam Jeziorski; Andrew M. Paterson; John P. Smol (Aquatic Sciences, 2012)

Calcium content of littoral Cladocera in three softwater lakes of the Canadian Shield - Melanie Shapiera; Adam Jeziorski; Norman D. Yan; John P. Smol (Hydrobiologia, 2011)

Behavioral Variant Frontotemporal Dementia with Corticobasal Degeneration Pathology: Phenotypic Comparison to bvFTD with Pick’s Disease - Katherine P. Rankin; Mary Catherine Mayo; William W. Seeley; Suzee Lee; Gil Rabinovici; Maria Luisa Gorno-Tempini; Adam L. Boxer; Michael W. Weiner; John Q. Trojanowski; Stephen J. DeArmond; Bruce L. Miller (Journal of Molecular Neuroscience, 2011)

Using morphological characters of subfossil daphniid postabdominal claws to improve taxonomic resolution within species complexes - Jennifer B. Korosi; Adam Jeziorski; John P. Smol (Hydrobiologia, 2011)

Pre-clinical characterization of CX-4945, a potent and selective small molecule inhibitor of CK2 for the treatment of cancer - Fabrice Pierre; Peter C. Chua; Sean E. O’Brien; Adam Siddiqui-Jain; Pauline Bourbon; Mustapha Haddach; Jerome Michaux; Johnny Nagasawa; Michael K. Schwaebe; Eric Stefan; Anne Vialettes; Jeffrey P. Whitten; et al. (Molecular and Cellular Biochemistry, 2011)

Investigating the effect of a single glycine to alanine substitution on interactions of antimicrobial peptide latarcin 2a with a lipid membrane - Grace Idiong; Amy Won; Annamaria Ruscito; Bonnie O. Leung; Adam P. Hitchcock; Anatoli Ianoul (European Biophysics Journal, 2011)

What is return to work? An investigation into the quantification of return to work - Adam P. Vogel; Samantha J. Barker; Amanda E. Young; Rasa Ruseckaite; Alex Collie (International Archives of Occupational and Environmental Health, 2011)

Hemodynamic Changes Quantified in Abdominal Aortic Aneurysms with Increasing Exercise Intensity Using MR Exercise Imaging and Image-Based Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Use of Congeneric Assessment to Reveal the Linked Genetic Histories of Two Threatened Fishes in the Murray‐Darling Basin, Australia - M. ADAMS; S. D. WEDDERBURN; P. J. UNMACK; M. P. HAMMER; J. B. JOHNSON (Conservation Biology, 2011)
The intensely regulated Murray‐Darling Basin in southeastern Australia is the nation's most extensive and economically important river system, and it contains fragmented populations of numerous fish species. Among these is the Murray hardyhead (Craterocephalus fluviatilis), a species listed as endangered (International Union for Conservation of Nature Red List) in the mid‐1990s prior to its acute decline with the progression of a severe drought that began in 1997. We compared the genetic structure of Murray hardyhead with 4 congeneric species (Darling hardyhead [C. amniculus], Finke hardyhead [C. centralis], Lake Eyre hardyhead [C. eyresii], and unspecked hardyhead [C. stercusmuscarum]), selected on the basis of their taxonomic or biological similarity to Murray hardyhead, in order to affirm species boundaries and test for instances of introgressive hybridization, which may influence species ecology and conservation prospects. We used allozyme (52 loci) and mtDNA markers (1999 bp of ATPase and cytochrome b) to provide a comparative genetic assessment of 139 Murray hardyhead, which represented all extant and some recently extirpated populations, and 71 congeneric specimens from 12 populations. We confirmed that Murray hardyhead and Darling hardyhead are taxonomically distinct and identified a number of potential conservation units, defined with genetic criteria, in both species. We also found allozyme and mtDNA evidence of historic genetic exchange between these 2 allopatric species, apparently involving one population of each species at the geographic edge of the species’ ranges, not in the most proximate populations sampled. Our results provide information on species boundaries and offer insight into the likely causes of high genetic diversity in certain populations, results which are already being used to guide national recovery planning and local action. Given the prevalence of incorrect taxonomies and introgression in many organismal groups, we believe these data point to the need to commence genetic investigations of any threatened species from an initially broad taxonomic focus.

Evaluation of temporal concentration profiles for ungauged rivers following pollution incidents - Adam P. Piotrowski; Jaroslaw J. Napiorkowski; Pawel M. Rowinski; Steve G. Wallis (Hydrological Sciences Journal, 2011)

Imaging interactions of cationic antimicrobial peptides with model lipid monolayers using X-ray spectromicroscopy - Bonnie O. Leung; Adam P. Hitchcock; Amy Won; Anatoli Ianoul; Andreas Scholl (European Biophysics Journal, 2011)

Support for maternal manipulation of developmental nutrition in a facultatively eusocial bee, Megalopta genalis (Halictidae) - Karen M. Kapheim; Sandra P. Bernal; Adam R. Smith; Peter Nonacs; William T. Wcislo (Behavioral Ecology and Sociobiology, 2011)

Genomic variations define divergence of water/wildlife‐associated Campylobacter jejuni niche specialists from common clonal complexes - Philip J. Hepworth; Kevin E. Ashelford; Jason Hinds; Katherine A. Gould; Adam A. Witney; Nicola J. Williams; Howard Leatherbarrow; Nigel P. French; Richard J. Birtles; Chriselle Mendonca; Nick Dorrell; Brendan W. Wren; et al. (Environmental Microbiology, 2011)
Summary Although the major food‐borne pathogen Campylobacter jejuni has been isolated from diverse animal, human and environmental sources, our knowledge of genomic diversity in C. jejuni is based exclusively on human or human food‐chain‐associated isolates. Studies employing multilocus sequence typing have indicated that some clonal complexes are more commonly associated with particular sources. Using comparative genomic hybridization on a collection of 80 isolates representing diverse sources and clonal complexes, we identified a separate clade comprising a group of water/wildlife isolates of C. jejuni with multilocus sequence types uncharacteristic of human food‐chain‐associated isolates. By genome sequencing one representative of this diverse group ( C. jejuni 1336), and a representative of the bank‐vole niche specialist ST‐3704 ( C. jejuni 414), we identified deletions of genomic regions normally carried by human food‐chain‐associated C. jejuni . Several of the deleted regions included genes implicated in chicken colonization or in virulence. Novel genomic insertions contributing to the accessory genomes of strains 1336 and 414 were identified. Comparative analysis using PCR assays indicated that novel regions were common but not ubiquitous among the water/wildlife group of isolates, indicating further genomic diversity among this group, whereas all ST‐3704 isolates carried the same novel accessory regions. While strain 1336 was able to colonize chicks, strain 414 was not, suggesting that regions specifically absent from the genome of strain 414 may play an important role in this common route of Campylobacter infection of humans. We suggest that the genomic divergence observed constitutes evidence of adaptation leading to niche specialization.

Inhibitory effects of alcohol on glucose transport across the blood–brain barrier leads to neurodegeneration: preventive role of acetyl-l-carnitine - P. M. Abdul Muneer; Saleena Alikunju; Adam M. Szlachetka; James Haorah (Psychopharmacology, 2011)

Erratum to: In Vitro Considerations to Support Bioequivalence of Locally Acting Drugs in Dry Powder Inhalers for Lung Diseases - S. L. Lee; W. P. Adams; B. V. Li; D. P. Conner; B. A. Chowdhury; L. X. Yu (The AAPS Journal, 2011)

An improved curvilinear gradient method for parameter optimization in complex biological models - David Szekely; Jamie I. Vandenberg; Socrates Dokos; Adam P. Hill (Medical & Biological Engineering & Computing, 2011)

Efficiency of ASTM Method D4994-89 for Recovery of Enteric Viruses from Biosolids - Charles P. Gerba; Adam Ross; Kazue Takizawa; Ian L. Pepper (Food and Environmental Virology, 2011)

Culturable Rhodobacter and Shewanella species are abundant in estuarine turbidity maxima of the Columbia River - S. L. Bräuer; C. Adams; K. Kranzler; D. Murphy; M. Xu; P. Zuber; H. M. Simon; A. M. Baptista; B. M. Tebo (Environmental Microbiology, 2011)
Summary Measurements of dissolved, ascorbate‐reducible and total Mn by ICP‐OES revealed significantly higher concentrations during estuarine turbidity maxima (ETM) events, compared with non‐events in the Columbia River. Most probable number (MPN) counts of Mn‐oxidizing or Mn‐reducing heterotrophs were not statistically different from that of other heterotrophs (10 3 –10 4 cells ml −1 ) when grown in defined media, but counts of Mn oxidizers were significantly lower in nutrient‐rich medium (13 cells ml −1 ). MPN counts of Mn oxidizers were also significantly lower on Mn(III)‐pyrophosphate and glycerol (21 cells ml −1 ). Large numbers of Rhodobacter spp. were cultured from dilutions of 10 −2 to 10 −5 , and many of these were capable of Mn(III) oxidation. Up to c . 30% of the colonies tested LBB positive, and all 77 of the successfully sequenced LBB positive colonies (of varying morphology) yielded sequences related to Rhodobacter spp. qPCR indicated that a cluster of Rhodobacter isolates and closely related strains (95–99% identity) represented approximately 1–3% of the total Bacteria , consistent with clone library results. Copy numbers of SSU rRNA genes for either Rhodobacter spp. or Bacteria were four to eightfold greater during ETM events compared with non‐events. Strains of a Shewanella sp. were retrieved from the highest dilutions (10 −5 ) of Mn reducers, and were also capable of Mn oxidation. The SSU rRNA gene sequences from these strains shared a high identity score (98%) with sequences obtained in clone libraries. Our results support previous findings that ETMs are zones with high microbial activity. Results indicated that Shewanella and Rhodobacter species were present in environmentally relevant concentrations, and further demonstrated that a large proportion of culturable bacteria, including Shewanella and Rhodobacter spp., were capable of Mn cycling in vitro .

Holocene climate and environmental change in central New York (USA) - Henry T. Mullins; William P. Patterson; Mark A. Teece; Adam W. Burnett (Journal of Paleolimnology, 2011)

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Intra-seasonal variation in foraging behavior among Adélie penguins (Pygocelis adeliae) breeding at Cape Hallett, Ross Sea, Antarctica - P. O’B. Lyver; C. J. MacLeod; G. Ballard; B. J. Karl; K. J. Barton; J. Adams; D. G. Ainley; P. R. Wilson (Polar Biology, 2011)

Heterogenic expression of genes encoding secreted proteins at the periphery of Aspergillus niger colonies - Arman Vinck; Charissa de Bekker; Adam Ossin; Robin A. Ohm; Ronald P. de Vries; Han A. B. Wösten (Environmental Microbiology, 2011)
Summary Colonization of a substrate by fungi starts with the invasion of exploring hyphae. These hyphae secrete enzymes that degrade the organic material into small molecules that can be taken up by the fungus to serve as nutrients. We previously showed that only part of the exploring hyphae of Aspergillus niger highly express the glucoamylase gene glaA . This was an unexpected finding since all exploring hyphae are exposed to the same environmental conditions. Using GFP as a reporter, we here demonstrate that the acid amylase gene aamA , the α‐glucuronidase gene aguA , and the feruloyl esterase gene faeA of A. niger are also subject to heterogenic expression within the exploring mycelium. Coexpression studies using GFP and dTomato as reporters showed that hyphae that highly express one of these genes also highly express the other genes encoding secreted proteins. Moreover, these hyphae also highly express the amylolytic regulatory gene amyR , and the glyceraldehyde‐3‐phosphate dehydrogenase gene gpdA. In situ hybridization demonstrated that the high expressers are characterized by a high 18S rRNA content. Taken together, it is concluded that two subpopulations of hyphae can be distinguished within the exploring mycelium of A. niger . The experimental data indicate that these subpopulations differ in their transcriptional and translational activity.

Ecological boundary detection using Bayesian areal wombling - Matthew C. Fitzpatrick; Evan L. Preisser; Adam Porter; Joseph Elkinton; Lance A. Waller; Bradley P. Carlin; Aaron M. Ellison (Ecology, 2010)
The study of ecological boundaries and their dynamics is of fundamental importance to much of ecology, biogeography, and evolution. Over the past two decades, boundary analysis (of which wombling is a subfield) has received considerable research attention, resulting in multiple approaches for the quantification of ecological boundaries. Nonetheless, few methods have been developed that can simultaneously (1) analyze spatially homogenized data sets (i.e., areal data in the form of polygons rather than point‐reference data); (2) account for spatial structure in these data and uncertainty associated with them; and (3) objectively assign probabilities to boundaries once detected. Here we describe the application of a Bayesian hierarchical framework for boundary detection developed in public health, which addresses these issues but which has seen limited application in ecology. As examples, we analyze simulated spread data and the historic pattern of spread of an invasive species, the hemlock woolly adelgid ( Adelges tsugae ), using county‐level summaries of the year of first reported infestation and several covariates potentially important to influencing the observed spread dynamics. Bayesian areal wombling is a promising approach for analyzing ecological boundaries and dynamics related to changes in the distributions of native and invasive species.

Validity of the Prey‐Trap Hypothesis for Carnivore‐Ungulate Interactions at Wildlife‐Crossing Structures - ADAM T. FORD; ANTHONY P. CLEVENGER (Conservation Biology, 2010)
Wildlife‐exclusion fencing and wildlife‐crossing structures (e.g., underpasses and overpasses) are becoming increasingly common features of highway projects around the world. The prey‐trap hypothesis posits that predators exploit crossing structures to detect and capture prey. The hypothesis predicts that predation events occur closer to a highway after the construction of fences and crossing structures and that prey species’ use of crossings increases the probability that predators will attack prey. We examined interactions between ungulates and large carnivores at 28 wildlife crossing structures along 45 km of the Trans‐Canada Highway in Banff National Park, Alberta. We obtained long‐term records of locations where ungulates were killed (kill sites) before and after crossing structures were built. We also placed remote, motion‐triggered cameras at two crossing structures to monitor predator behavior following ungulate passage through the structure. The proximity of ungulate kill sites to the highway was similar before and after construction of fencing and crossing structures. We found only five kill sites near crossing structures after more than 32,000 visits over 13 years. We found no evidence that predator behavior at crossing structures is affected by prey movement. Our results suggest that interactions between large mammals and their prey at wildlife‐crossing structures in Banff National Park are not explained by the prey‐trap hypothesis.

Species-specific difference in expression and splice-site choice in Inpp5b, an inositol polyphosphate 5-phosphatase paralogous to the enzyme deficient in Lowe Syndrome - Susan P. Bothwell; Leslie W. Farber; Adam Hoagland; Robert L. Nussbaum (Mammalian Genome, 2010)

Association of red‐mark syndrome with a Rickettsia ‐like organism and its connection with strawberry disease in the USA - M Metselaar; K D Thompson; R M L Gratacap; M J L Kik; S E LaPatra; S J Lloyd; D R Call; P D Smith; A Adams (Journal of Fish Diseases, 2010)
Red‐mark syndrome (RMS), a disease seen mostly in rainbow trout, Oncorhynchus mykiss , is of unknown aetiology. The research presented here indicates the presence of an intracellular bacterium in RMS‐affected fish. A positive reaction was observed using immunohistochemistry (IHC) with skin lesions, liver, kidney and spleen of affected fish sampled from several locations within the United Kingdom using two different polyclonal antisera raised against Piscirickettsia salmonis . The same reaction was also seen with a number of different anti‐ P. salmonis monoclonal antibodies (MAbs). A disease with similar clinical signs to RMS, referred to as strawberry disease (SD), has been reported in the USA. A Rickettsia ‐like organism (RLO) has recently been associated with SD based on analysis of 16S rDNA sequences. Using the same panel of anti‐ P. salmonis antibodies used to screen the RMS samples, similar staining was obtained in tissue of SD‐affected fish by IHC. A polymerase chain reaction (PCR) using RLO‐specific primers was also performed on RMS‐affected fish from the United Kingdom, and the samples were positive for the RLO 16S rRNA sequence. These findings suggest that the same aetiological agent may be responsible for RMS in the United Kingdom and SD in the USA.

Hydrogen peroxide‐induced oxidative stress responses in Desulfovibrio vulgaris Hildenborough - Aifen Zhou; Zhili He; Alyssa M. Redding‐Johanson; Aindrila Mukhopadhyay; Christopher L. Hemme; Marcin P. Joachimiak; Feng Luo; Ye Deng; Kelly S. Bender; Qiang He; Jay D. Keasling; David A. Stahl; et al. (Environmental Microbiology, 2010)
Summary To understand how sulphate‐reducing bacteria respond to oxidative stresses, the responses of Desulfovibrio vulgaris Hildenborough to H 2 O 2 ‐induced stresses were investigated with transcriptomic, proteomic and genetic approaches. H 2 O 2 and induced chemical species (e.g. polysulfide, ROS) and redox potential shift increased the expressions of the genes involved in detoxification, thioredoxin‐dependent reduction system, protein and DNA repair, and decreased those involved in sulfate reduction, lactate oxidation and protein synthesis. A gene coexpression network analysis revealed complicated network interactions among differentially expressed genes, and suggested possible importance of several hypothetical genes in H 2 O 2 stress. Also, most of the genes in PerR and Fur regulons were highly induced, and the abundance of a Fur regulon protein increased. Mutant analysis suggested that PerR and Fur are functionally overlapped in response to stresses induced by H 2 O 2 and reaction products, and the upregulation of thioredoxin‐dependent reduction genes was independent of PerR or Fur. It appears that induction of those stress response genes could contribute to the increased resistance of deletion mutants to H 2 O 2 ‐induced stresses. In addition, a conceptual cellular model of D. vulgaris responses to H 2 O 2 stress was constructed to illustrate that this bacterium may employ a complicated molecular mechanism to defend against the H 2 O 2 ‐induced stresses.

Brevetoxins in sharks and rays (Chondrichthyes, Elasmobranchii) from Florida coastal waters - Leanne J. Flewelling; Douglas H. Adams; Jerome P. Naar; Karen E. Atwood; April A. Granholm; Sheila N. O’Dea; Jan H. Landsberg (Marine Biology, 2010)

Functional traits as indicators of biodiversity response to land use changes across ecosystems and organisms - Marie Vandewalle; Francesco de Bello; Matty P. Berg; Thomas Bolger; Sylvain Dolédec; Florence Dubs; Christian K. Feld; Richard Harrington; Paula A. Harrison; Sandra Lavorel; Pedro Martins da Silva; Marco Moretti; et al. (Biodiversity and Conservation, 2010)

The complete genome sequence of Canna yellow streak virus - W. A. Monger; I. P. Adams; R. H. Glover; B. Barrett (Archives of Virology, 2010)

Establishing reliable minimum count sizes for cladoceran subfossils sampled from lake sediments - Joshua Kurek; Jennifer B. Korosi; Adam Jeziorski; John P. Smol (Journal of Paleolimnology, 2010)

The contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M.W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. VAN VUUREN; ADAM POSTHUMA (Global Change Biology, 2010)

Ecological effects of longline fishing and climate change on the pelagic ecosystem off eastern Australia - Shane P. Griffiths; Jock W. Young; Matt J. Lansdell; Robert A. Campbell; John Hampton; Simon D. Hoyle; Adam Langley; Donald Bromhead; Michael G. Hinton (Reviews in Fish Biology and Fisheries, 2010)

An evaluation of the usefulness of Staphylococcus aureus serodiagnosis in clinical practice - J. Elston; M. Ling; B. Jeffs; K. Adams; H. Thaker; P. Moss; R. Meigh; G. Barlow (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Geochronology of Mount Morning, Antarctica: two-phase evolution of a long-lived trachyte-basanite-phonolite eruptive center - Adam P. Martin; Alan F. Cooper; W. James Dunlap (Bulletin of Volcanology, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

The complete genome sequence of the Tanzanian strain of Cassava brown streak virus and comparison with the Ugandan strain sequence - Wendy A. Monger; T. Alicai; J. Ndunguru; Z. M. Kinyua; M. Potts; R. H. Reeder; D. W. Miano; I. P. Adams; N. Boonham; R. H. Glover; J. Smith (Archives of Virology, 2010)

The clearwater consensus: the estimation of metal hazard in fresh water - Miriam L. Diamond; Nilima Gandhi; William J. Adams; John Atherton; Satyendra P. Bhavsar; Cécile Bulle; Peter G. C. Campbell; Alain Dubreuil; Anne Fairbrother; Kevin Farley; Andrew Green; Jeroen Guinee; et al. (The International Journal of Life Cycle Assessment, 2010)

Phylogeographic structure in the threatened Yarra pygmy perch Nannoperca obscura (Teleostei: Percichthyidae) has major implications for declining populations - Michael P. Hammer; Peter J. Unmack; Mark Adams; Jerald B. Johnson; Keith F. Walker (Conservation Genetics, 2010)

Stratospheric temperature trends: impact of ozone variability and the QBO - Mauro Dall’Amico; Lesley J. Gray; Karen H. Rosenlof; Adam A. Scaife; Keith P. Shine; Peter A. Stott (Climate Dynamics, 2010)

No Differences in Soil Carbon Stocks Across the Tree Line in the Peruvian Andes - Michael Zimmermann; Patrick Meir; Miles R. Silman; Anna Fedders; Adam Gibbon; Yadvinder Malhi; Dunia H. Urrego; Mark B. Bush; Kenneth J. Feeley; Karina C. Garcia; Greta C. Dargie; Wiliam R. Farfan; et al. (Ecosystems, 2010)

Pervasive interactions between ungulate browsers and disturbance regimes promote temperate forest herbaceous diversity - Alejandro A. Royo; Rachel Collins; Mary Beth Adams; Chad Kirschbaum; Walter P. Carson (Ecology, 2010)
Disruptions to historic disturbance and herbivory regimes have altered plant assemblages in forests worldwide. An emerging consensus suggests that these disruptions often result in impoverished forest biotas. This is particularly true for eastern U.S. deciduous forests where large gaps and understory fires were once relatively common and browsers were far less abundant. Although much research has focused on how disturbance and browsers affect tree diversity, far less attention has been devoted to forest understories where the vast majority (>75%) of the vascular species reside. Here we test the hypothesis that the reintroduction of disturbances resembling historic disturbance regimes and moderate levels of ungulate browsing enhance plant diversity. We explore whether once‐common disturbances and their interaction with the top‐down influence of browsers can create conditions favorable for the maintenance of a rich herbaceous layer in a region recognized as a temperate biodiversity hotspot in West Virginia, USA. We tested this hypothesis via a factorial experiment whereby we manipulated canopy gaps (presence/absence) of a size typically found in old‐growth stands, low‐intensity understory fire (burned/unburned), and deer browsing (fenced/unfenced). We tracked the abundance and diversity of more than 140 herb species for six years. Interactions among our treatments were pervasive. The combination of canopy gaps and understory fire increased herbaceous layer richness, cover, and diversity well beyond either disturbance alone. Furthermore, we documented evidence that deer at moderate levels of abundance promote herbaceous richness and abundance by preferentially browsing fast‐growing pioneer species that thrive following co‐occurring disturbances (i.e., fire and gaps). This finding sharply contrasts with the negative impact browsers have when their populations reach levels well beyond those that occurred for centuries. Although speculative, our results suggest that interactions among fire, canopy gaps, and browsing provided a variable set of habitats and conditions across the landscape that was potentially capable of maintaining much of the plant diversity found in temperate forests.

SWITCH in Birmingham, UK: experimental investigation of the ecological and hydrological performance of extensive green roofs - Adam J. Bates; Rae Mackay; Richard B. Greswell; Jon P. Sadler (Reviews in Environmental Science and Bio/Technology, 2009)

Cryptococcal meningitis — a follow-up study of a serious clinical entity: quick cytological and microbiological diagnostics using a special staining procedure in cerebrospinal fluid specimens - P. Adam; O. Sobek; D. Doležil; Z. Lodin; J. Kasík; L. Hajduková; Š. Cihelková; J. Svatoňová; M. Hybeľová; D. Adam; V. Melezinková (Folia Microbiologica, 2009)

Heterogeneous response of circumboreal wildfire risk to climate change since the early 1900s - MARTIN P. GIRARDIN; ADAM A. ALI; CHRISTOPHER CARCAILLET; MANFRED MUDELSEE; IGOR DROBYSHEV; CHRISTELLE HÉLY; YVES BERGERON (Global Change Biology, 2009)
We investigated changes in wildfire risk over the 1901−2002 ( ad ) period with an analysis of broad‐scale patterns of July monthly drought code (MDC) variability on 28 forested ecoregions of the North American and Eurasian continents. The MDC is an estimate of the net effect of changes in evapotranspiration and precipitation on cumulative moisture depletion in soils, and is well correlated with annual fire statistics across the circumboreal (explaining 25–61% of the variance in regional area burned). We used linear trend and regime shift analyses to investigate (multi‐) decadal changes in MDC and percentage area affected by drought, and kernel function for analysis of temporal changes in the occurrence rates of extreme drought years. Our analyses did not reveal widespread patterns of linear increases in dryness through time as a response to rising Northern Hemisphere land temperatures. Instead, we found heterogeneous patterns of drought severity changes that were inherent to the nonuniformly distributed impacts of climate change on dryness. Notably, significant trends toward increasing summer moisture in southeastern and southwestern boreal Canada were detected. The diminishing wildfire risk in these regions is coherent with widely reported decreases in area burned since about 1850, as reconstructed by dendrochronological dating of forest stands. Conversely, we found evidence for increasing percentage area affected by extreme droughts in Eurasia (+0.57% per decade; P P =0.07). Although not statistically significant, temporal changes in occurrence rates are sufficiently important spatially to be paid further attention. The absence of a linear trend in MDC severity, in conjunction with the presence of an increase in the occurrence rate of extreme drought years, suggest that fire disturbance regimes in the Eurasian taiga could be shifting toward being increasingly pulse dependent.

Response of the hammerhead shark olfactory epithelium to amino acid stimuli - Timothy C. Tricas; Stephen M. Kajiura; Adam P. Summers (Journal of Comparative Physiology A, 2009)

A Bayesian approach to estimating Atlantic salmon fry densities using a rapid sampling technique - G. DAUPHIN; E. PREVOST; C. E. ADAMS; P. BOYLAN (Fisheries Management and Ecology, 2009)
Removal sampling by electric fishing is widely used for assessing fish population size. As it is manpower consuming, less‐demanding techniques have been proposed to increase the number of sites covered with the same human resources. These techniques essentially provide relative abundance measures. To be used for absolute abundance estimation, they need to be inter‐calibrated with another method such as removal sampling. Here, hierarchical Bayesian modelling framework is used for this inter‐calibration because it allows an estimate of absolute abundance from abundance index data alone while accounting for the main sources of uncertainty. It is applied to a 0+ juvenile Atlantic salmon, Salmo salar L. data set from 21 sites on the River Faughan, Northern Ireland. A positive relationship was found between the abundance index (number of fish caught in 5 min of actual electric fishing) and the density. The estimates from the index of abundance alone are fairly imprecise, but still allow differentiation of contrasting levels of fish density.

In Vitro Considerations to Support Bioequivalence of Locally Acting Drugs in Dry Powder Inhalers for Lung Diseases - Sau Lawrence Lee; Wallace P. Adams; Bing V. Li; Dale P. Conner; Badrul A. Chowdhury; Lawrence X. Yu (The AAPS Journal, 2009)

Contribution of mobile genetic elements to Desulfovibrio vulgaris genome plasticity - Christopher B. Walker; Sergey Stolyar; Dylan Chivian; Nicolas Pinel; Jeffrey A. Gabster; Paramvir S. Dehal; Zhili He; Zamin Koo Yang; Huei‐Che B. Yen; Jizhong Zhou; Judy D. Wall; Terry C. Hazen; et al. (Environmental Microbiology, 2009)
Summary The genome of Desulfovibrio vulgaris strain DePue, a sulfate‐reducing Deltaproteobacterium isolated from heavy metal‐impacted lake sediment, was completely sequenced and compared with the type strain D. vulgaris Hildenborough. The two genomes share a high degree of relatedness and synteny, but harbour distinct prophage and signatures of past phage encounters. In addition to a highly variable phage contribution, the genome of strain DePue contains a cluster of open‐reading frames not found in strain Hildenborough coding for the production and export of a capsule exopolysaccharide, possibly of relevance to heavy metal resistance. Comparative whole‐genome microarray analysis on four additional D. vulgaris strains established greater interstrain variation within regions associated with phage insertion and exopolysaccharide biosynthesis.

Label-free in situ imaging of lignification in the cell wall of low lignin transgenic Populus trichocarpa - M. Schmidt; A. M. Schwartzberg; P. N. Perera; A. Weber-Bargioni; A. Carroll; P. Sarkar; E. Bosneaga; J. J. Urban; J. Song; M. Y. Balakshin; E. A. Capanema; M. Auer; et al. (Planta, 2009)

Fatigue-induced early onset of anticipatory postural adjustments in non-fatigued muscles: support for a centrally mediated adaptation - Adam J. Strang; William P. Berg; Mathias Hieronymus (Experimental Brain Research, 2009)

A Comparison of Data Sets Varying in Spatial Accuracy Used to Predict the Occurrence of Wildlife-Vehicle Collisions - Kari E. Gunson; Anthony P. Clevenger; Adam T. Ford; John A. Bissonette; Amanda Hardy (Environmental Management, 2009)

Molecular characterization of a new macluravirus from yam in Yunnan, China - J.-G. Wang; X.-J. Zou; H.-Y. Zheng; Michael J. Adams; H.-R. Chen; J.-P. Chen (Archives of Virology, 2009)

Geochronology and provenance of the Late Paleozoic accretionary wedge and Gympie Terrane, New England Orogen, eastern Australia∗ - R. J. Korsch; C. J. Adams; L. P. Black; D. A. Foster; G. L. Fraser; C. G. Murray; C. Foudoulis; W. L. Griffin (Australian Journal of Earth Sciences, 2009)

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Validation of a wetland Rapid Assessment Method: Use of EPA’s level 1-2-3 framework for method testing and refinement - Eric D. Stein; A. Elizabeth Fetscher; Ross P. Clark; Adam Wiskind; J. Letitia Grenier; Martha Sutula; Joshua N. Collins; Cristina Grosso (Wetlands, 2009)

CCC and Prohexadione-Ca Enhance Rhizome Growth and Lateral Bud Production in Rhubarb (Rheum rhabarbarum L.) - Usha P. Rayirath; Rajasekaran R. Lada; Claude D. Caldwell; Samuel K. Asiedu; Kevin J. Sibley; Azure D. Adams (Journal of Plant Growth Regulation, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Eosinophilic meningitis — an immunophenotyping recording of a very rare clinical entity — Brief Report - P. Adam; O. Sobek; M. Hybel’ová; D. Doležil; J. Kasík; L. Hajduková; D. Adam; J. Svatoňová (Folia Microbiologica, 2009)

Landscape genetics of California mule deer ( Odocoileus hemionus ): the roles of ecological and historical factors in generating differentiation - KATHERINE M. PEASE; ADAM H. FREEDMAN; JOHN P. POLLINGER; JOHN E. MCCORMACK; WOLFGANG BUERMANN; JEFF RODZEN; JIM BANKS; ERIN MEREDITH; VERNON C. BLEICH; ROBERT J. SCHAEFER; KEN JONES; ROBERT K. WAYNE (Molecular Ecology, 2009)
Landscape genetics is an emerging discipline that utilizes environmental and historical data to understand geographic patterns of genetic diversity. Niche modelling has added a new dimension to such efforts by allowing species–environmental associations to be projected into the past so that hypotheses about historical vicariance can be generated and tested independently with genetic data. However, previous approaches have primarily utilized DNA sequence data to test inferences about historical isolation and may have missed very recent episodes of environmentally mediated divergence. We type 15 microsatellite loci in California mule deer and identify five genetic groupings through a Structure analysis that are also well predicted by environmental data. We project the niches of these five deer ecotypes to the last glacial maximum (LGM) and show they overlap to a much greater extent than today, suggesting that vicariance associated with the LGM cannot explain the present‐day genetic patterns. Further, we analyse mitochondrial DNA (mtDNA) sequence trees to search for evidence of historical vicariance and find only two well‐supported clades. A coalescence‐based analysis of mtDNA data shows that the genetic divergence of the mule deer genetic clusters in California is recent and appears to be mediated by ecological factors. The importance of environmental factors in explaining the genetic diversity of California mule deer is unexpected given that they are highly mobile species and have a broad habitat distribution. Geographic differences in the timing of reproduction and peak vegetation as well as habitat choice reflecting natal origin may explain the persistence of genetic subdivision.

Taxonomic resolution, ecotypes and the biogeography of Prochlorococcus - Adam C. Martiny; Amos P. K. Tai; Daniele Veneziano; François Primeau; Sallie W. Chisholm (Environmental Microbiology, 2009)
Summary In order to expand our understanding of the diversity and biogeography of Prochlorococcus ribotypes, we PCR‐amplified, cloned and sequenced the 16S/23S rRNA ITS region from sites in the Atlantic and Pacific oceans. Ninety‐three per cent of the ITS sequences could be assigned to existing Prochlorococcus clades, although many novel subclades were detected. We assigned the sequences to operational taxonomic units using a graduated scale of sequence identity from 80% to 99.5% and correlated Prochlorococcus diversity with respect to environmental variables and dispersal time between the sites. Dispersal time was estimated using a global ocean circulation model. The significance of specific environmental variables was dependent on the degree of sequence identity used to define a taxon: light correlates with broad‐scale diversity (90% cut‐off), temperature with intermediate scale (95%) whereas no correlation with phosphate was observed. Community structure was correlated with dispersal time between sample sites only when taxa were defined using the finest sequence similarity cut‐off. Surprisingly, the concentration of nitrate, which cannot be used as N source by the Prochlorococcus strains in culture, explains some variation in community structure for some definitions of taxa. This study suggests that the spatial distribution of Prochlorococcus ecotypes is shaped by a hierarchy of environmental factors as well dispersal limitation.

Cerebrospinal fluid and serum prealbumin (transthyretin) in patients with multiple sclerosis (MS): Comparison of particular subgroups of MS patients - M. Hybeľová; J. Svatoňová; O. Sobek; P. Adam; D. Doležil; D. Adam (Folia Microbiologica, 2009)

Historic magmatism on the Reykjanes Peninsula, Iceland: a snap-shot of melt generation at a ridge segment - David W. Peate; Joel A. Baker; Sveinn P. Jakobsson; Tod E. Waight; Adam J. R. Kent; Nathalie V. Grassineau; Anna Cecile Skovgaard (Contributions to Mineralogy and Petrology, 2009)

Contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M. W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. Van VUUREN; ADAM POSTHUMA (Global Change Biology, 2009)

Preparation and characterization of the conjugated Fusarium mycotoxins zearalenone-4 O -β-D-glucopyranoside, α-zearalenol-4 O -β-D-glucopyranoside and β-zearalenol-4 O -β-D-glucopyranoside by MS/MS and two-dimensional NMR - F. Berthiller; C. Hametner; P. Krenn; W. Schweiger; R. Ludwig; G. Adam; R. Krska; R. Schuhmacher (Food Additives & Contaminants: Part A, 2009)

A Mass Balance Mercury Budget for a Mine-Dominated Lake: Clear Lake, California - Thomas H. Suchanek; Janis Cooke; Kaylene Keller; Salvador Jorgensen; Peter J. Richerson; Collin A. Eagles-Smith; E. James Harner; David P. Adam (Water, Air, & Soil Pollution, 2009)

Extensive pollen flow in two ecologically contrasting populations of Populus trichocarpa - G. T. SLAVOV; S. LEONARDI; J. BURCZYK; W. T. ADAMS; S. H. STRAUSS; S. P. DIFAZIO (Molecular Ecology, 2009)
Pollen‐mediated gene flow was measured in two populations of black cottonwood using direct (paternity analysis) and indirect (correlated paternity) methods. The Marchel site was an area with an approximate radius of 250 m in a large continuous stand growing in a mesic habitat in western Oregon. In contrast, the Vinson site was an area with a radius of approximately 10 km and consisted of small, disjunct and isolated stands in the high desert of eastern Oregon. Pollen immigration was extensive in both populations, and was higher in the Marchel site (0.54 ± 0.02) than in the substantially larger and more isolated Vinson site (0.32 ± 0.02). Pollen pool differentiation among mothers was approximately five times stronger in the Vinson population (Φ FT = 0.253, N = 27 mothers) than in the Marchel population (Φ FT = 0.052, N = 5 mothers). Pollen dispersal was modelled using a mixed dispersal curve that incorporated pollen immigration. Predicted pollination frequencies generated based on this curve were substantially more accurate than those based on the widely used exponential power dispersal curve. Male neighbourhood sizes ( sensu Wright 1946 ) estimated using paternity analysis and pollen pool differentiation were remarkably similar. They were three to five times smaller in the Vinson population, which reflected the substantial ecological and demographic differences between the two populations. When the same mathematical function was used, applying direct and indirect methods resulted in similar pollen dispersal curves, thus confirming the value of indirect methods as a viable lower‐cost alternative to paternity analysis.

Independent colonization and extensive cryptic speciation of freshwater amphipods in the isolated groundwater springs of Australia's Great Artesian Basin - NICHOLAS P. MURPHY; MARK ADAMS; ANDREW D. AUSTIN (Molecular Ecology, 2009)
The groundwater‐dependent springs of the Great Artesian Basin (GAB) in arid inland Australia represent a unique and threatened ecosystem. These incredibly isolated springs support a diverse array of endemic flora and fauna. One of the common faunal groups in the GAB springs is the freshwater amphipods of the family Chiltoniidae. The morphological conservatism and taxonomic uncertainty associated with these amphipods has ensured their true biodiversity, phylogeographical history and evolutionary affinities have remained unknown. We have used mitochondrial DNA and allozyme data to unravel a complicated history of isolation, extinction and dispersal among spring amphipod populations across the GAB. The results provide evidence for multiple independent colonizations in the GAB springs, particularly within the Lake Eyre group of springs. The inclusion of a group of Western Australian (WA) stygobitic amphipods from populations up to 1500 km away found surprising evidence for a shared evolutionary history between stygobitic and GAB spring amphipods. Approximate dating of the diversity found between major clades suggests the majority of lineages originated in the late Miocene, around the time of the aridification of inland Australia. The large number of independent lineages and the close connection between GAB spring and WA stygobitic amphipods suggest that a significantly rich amphipod fauna existed in the much wetter environment that once existed in inland Australia. The results also provide evidence for a gross underestimation of the species diversity within the springs, with 12 putative species identified, a conclusion with significant implications for the ongoing conservation of the GAB springs.

Contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M. W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. Van VUUREN; ADAM POSTHUMA (Global Change Biology, 2009)
In this study, we analyze the impact of fertilizer‐ and manure‐induced N 2 O emissions due to energy crop production on the reduction of greenhouse gas (GHG) emissions when conventional transportation fuels are replaced by first‐generation biofuels (also taking account of other GHG emissions during the entire life cycle). We calculate the nitrous oxide (N 2 O) emissions by applying a statistical model that uses spatial data on climate and soil. For the land use that is assumed to be replaced by energy crop production (the ‘reference land‐use system’), we explore a variety of options, the most important of which are cropland for food production, grassland, and natural vegetation. Calculations are also done in the case that emissions due to energy crop production are fully additional and thus no reference is considered. The results are combined with data on other emissions due to biofuels production that are derived from existing studies, resulting in total GHG emission reduction potentials for major biofuels compared with conventional fuels. The results show that N 2 O emissions can have an important impact on the overall GHG balance of biofuels, though there are large uncertainties. The most important ones are those in the statistical model and the GHG emissions not related to land use. Ethanol produced from sugar cane and sugar beet are relatively robust GHG savers: these biofuels change the GHG emissions by −103% to −60% (sugar cane) and −58% to −17% (sugar beet), compared with conventional transportation fuels and depending on the reference land‐use system that is considered. The use of diesel from palm fruit also results in a relatively constant and substantial change of the GHG emissions by −75% to −39%. For corn and wheat ethanol, the figures are −38% to 11% and −107% to 53%, respectively. Rapeseed diesel changes the GHG emissions by −81% to 72% and soybean diesel by −111% to 44%. Optimized crop management, which involves the use of state‐of‐the‐art agricultural technologies combined with an optimized fertilization regime and the use of nitrification inhibitors, can reduce N 2 O emissions substantially and change the GHG emissions by up to −135 percent points (pp) compared with conventional management. However, the uncertainties in the statistical N 2 O emission model and in the data on non‐land‐use GHG emissions due to biofuels production are large; they can change the GHG emission reduction by between −152 and 87 pp.

The Nuclear Factor Y subunits NF-YB2 and NF-YB3 play additive roles in the promotion of flowering by inductive long-day photoperiods in Arabidopsis - Roderick W. Kumimoto; Luc Adam; Graham J. Hymus; Peter P. Repetti; T. Lynne Reuber; Colleen M. Marion; Frederick D. Hempel; Oliver J. Ratcliffe (Planta, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

B-type natriuretic peptide and wall stress in dilated human heart - P. Alter; H. Rupp; M. B. Rominger; A. Vollrath; F. Czerny; J. H. Figiel; P. Adams; F. Stoll; K. J. Klose; B. Maisch (Molecular and Cellular Biochemistry, 2008)

Alternative migration and host parasitism strategies and their long‐term stability in river lampreys from the River Endrick, Scotland - C. E. Adams; N. Bissett; J. Newton; P. S. Maitland (Journal of Fish Biology, 2008)
The stability of a discrete body size dimorphism of sexually mature river lamprey Lampetra fluviatilis from the River Endrick, Scotland, was examined over a 21 year period. Stable isotope analysis was used to test the hypothesis that the two size forms comprise individuals with differing migration and parasitic foraging strategies. Maturing river lamprey and the brook lamprey Lampetra planeri were trapped over 3 months each year in the periods 1983–1984 and 2004–2005. Brook lamprey catches and catches of both species combined showed no significant trend in catch rate with time. The catch rate of small body size river lamprey declined between 1983–1984 and 2004–2005 (although the difference did not reach statistical significance; P = 0·055). In contrast, there was a significant increase in the catch rate of the large body size river lamprey and as a consequence, a significant change in the relative proportion of each of the two river lamprey morphs over the study period. Analysis of the stable isotopes of C and N in muscle tissue showed that brook lamprey tissue derived its carbon from a freshwater source and had a δ 13 C more consistent with that of the River Endrick than with Loch Lomond. δ 15 N values for this species showed it to be feeding at the base of the food chain, consistent with filter feeding as an ammocoete. The large body size and the small body size river lamprey adults differed substantially in their δ 13 C values, with the small body size δ 13 C signature indicative of a freshwater carbon source and the large body size morph of a marine source. The small body size morph had a δ 13 C signature that was consistent with that of Loch Lomond powan Coregonus lavaretus suggesting that they share a common carbon source. The large body size morph was clearly feeding at a higher trophic level than the small body size morph. A single small body size river lamprey individual with typical morphology for that group, however, had C and N signatures that clustered with those of the large body size morphs. This individual had either migrated to sea to forage, as is typical for the species, or had been feeding on an anadromous fish with a strong marine C signature in fresh water. It is concluded that the body size dimorphism is indicative of a differential migration and foraging strategy in the parasitic phase of the life cycle of river lamprey at this site.

Gene transcript analysis of assimilatory iron limitation in Geobacteraceae during groundwater bioremediation - Regina A. O'Neil; Dawn E. Holmes; Maddalena V. Coppi; Lorrie A. Adams; M. Juliana Larrahondo; Joy E. Ward; Kelly P. Nevin; Trevor L. Woodard; Helen A. Vrionis; A. Lucie N'Guessan; Derek R. Lovley (Environmental Microbiology, 2008)
Summary Limitations on the availability of Fe(III) as an electron acceptor are thought to play an important role in restricting the growth and activity of Geobacter species during bioremediation of contaminated subsurface environments, but the possibility that these organisms might also be limited in the subsurface by the availability of iron for assimilatory purposes was not previously considered because copious quantities of Fe(II) are produced as the result of Fe(III) reduction. Analysis of multiple Geobacteraceae genomes revealed the presence of a three‐gene cluster consisting of homologues of two iron‐dependent regulators, fur and dtxR ( ideR ), separated by a homologue of feoB , which encodes an Fe(II) uptake protein. This cluster appears to be conserved among members of the Geobacteraceae and was detected in several environments. Expression of the fur‐feoB‐ideR cluster decreased as Fe(II) concentrations increased in chemostat cultures. The number of Geobacteraceae feoB transcripts in groundwater samples from a site undergoing in situ uranium bioremediation was relatively high until the concentration of dissolved Fe(II) increased near the end of the field experiment. These results suggest that, because much of the Fe(II) is sequestered in solid phases, Geobacter species, which have a high requirement for iron for iron‐sulfur proteins, may be limited by the amount of iron available for assimilatory purposes. These results demonstrate the ability of transcript analysis to reveal previously unsuspected aspects of the in situ physiology of microorganisms in subsurface environments.

Calcium levels in Daphnia ephippia cannot provide a useful paleolimnological indicator of historical lakewater Ca concentrations - Adam Jeziorski; Andrew M. Paterson; Norman D. Yan; John P. Smol (Journal of Paleolimnology, 2008)

Phylogenetic relationships among North American Alosa species (Clupeidae) - B. R. Bowen; B. R. Kreiser; P. F. Mickle; J. F. Schaefer; S. B. Adams (Journal of Fish Biology, 2008)
A phylogeny of the six North American species in the genus Alosa , with representatives of three Eurasian species, was generated using mtDNA sequences. This was accomplished by obtaining sequences for three North American species and additional geographical sampling of the other three species. The subgenus Alosa , including the formerly recognized subgenus Caspialosa , formed a strongly supported monophyletic group. Alosa alabamae was part of a polytomy with Alosa sapidissima , which was interpreted to support the recognition of A. alabamae as an incipient, yet distinct, species. The subgenus Pomolobus was not recovered as a monophyletic group. Alosa chrysochloris was basal to all other Alosa , although this position was only weakly supported. Previous work had indicated that Alosa pseudoharengus and Alosa aestivalis are not reciprocally monophyletic, but additional sampling in this study did not detect any further cases of shared haplotypes between the two species. The phylogeny supports previous hypotheses that the evolution of North American Alosa species in the Gulf of Mexico ( A. chrysochloris and A. alabamae ) was the result of two independent events. First, the ancestor of A. chrysochloris was isolated in the Gulf of Mexico, likely by the close of the Suwannee Straits, and this was followed later by dispersal of the ancestor of A. alabamae around the Florida peninsula into the Gulf of Mexico sometime during or after the Pleistocene.

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

A new potyvirus from butterfly flower (Iris japonica Thunb.) in Zhejiang, China - J. Chen; Y.-H. Shi; M.-Y. Li; M. J. Adams; J.-P. Chen (Archives of Virology, 2008)

Determination of Iodine in Low Mass Human Hair Samples by Inductively Coupled Plasma Mass Spectrometry - K. E. Levine; A. S. Essader; F. X. Weber; J. M. Perlmutter; L. S. Milstein; R. A. Fernando; M. A. Levine; B. J. Collins; J. B. Adams; P. M. Grohse (Bulletin of Environmental Contamination and Toxicology, 2007)

Genomic analysis of rice stripe virus Zhejiang isolate shows the presence of an OTU-like domain in the RNA1 protein and a novel sequence motif conserved within the intergenic regions of ambisense segments of tenuiviruses - H.-M. Zhang; J. Yang; H.-R. Sun; X. Xin; H.-D. Wang; J.-P. Chen; M. J. Adams (Archives of Virology, 2007)

Molecular characterization of the genome segments S4, S6 and S7 of rice gall dwarf virus - H. M. Zhang; J. Yang; X. Xin; J. P. Chen; M. J. Adams (Archives of Virology, 2007)

Analysis of cerebrospinal fluid cell populations with monoclonal antibodies - P. Adam; O. Sobek; C. S. Scott (Folia Microbiologica, 2007)

GnRH-Mediated DAN Production Regulates the Transcription of the GnRH Receptor in Gonadotrope Cells - Rakel López de Maturana; Bronwen Martin; Robert P. Millar; Pamela Brown; Lindsay Davidson; Adam J. Pawson; Moira R. Nicol; J. Ian Mason; Perdita Barran; Zvi Naor; Stuart Maudsley (NeuroMolecular Medicine, 2007)

Morphology, cytoskeletal organization, and myosin dynamics of mouse embryonic fibroblasts cultured on nanofibrillar surfaces - Ijaz Ahmed; Abdul S. Ponery; Alam Nur-E-Kamal; Jabeen Kamal; Adam S. Meshel; Michael P. Sheetz; Melvin Schindler; Sally Meiners (Molecular and Cellular Biochemistry, 2007)

Forest Measurement and Biometrics in Forest Management: Status and Future Needs of the Pacific Northwest USA - Hailemariam Temesgen; Michael E. Goerndt; Greg P. Johnson; Darius M. Adams; Robert A. Monserud (Journal of Forestry, 2007)
Forest measurement and biometrics (FMB) programs have been at the heart of forestry education in North America since its beginnings at the Biltmore Forest School more than 100 years ago. Over the intervening period, the field of forestry has changed in critical ways. There are manyforest management and policy issues that, at first glance, do not appear to involve FMB but which, on further examination, are found to be closely linked. In this regard, FMB has both an “inside„ and “outside.„ The outside part faces interactions with its clients andfront-line sciences (e.g., forest ecology, silviculture, etc.) which bring new data-analytic ideas to FMB. The clients and professionals in these allied sciences need solutions to pressing quantitative questions. The inside face relates to the need to extend the structure of statistical inference,integrate emerging technologies, and adapt mathematical and statistical precepts to FMB needs. In this essay, we provide a brief overview of the current diversity of FMB applications using examples from business, policy analysis, and ecosystem and landscape analysis; offer our views on themost critical challenges facing FMB researchers and practitioners in the 21st Century; and outline ways how FMB professionals and academic forestry programs might cooperate to meet these challenges. We assert that FMB needs to be responsive to contemporary resource management challenges andaddress the many land management challenges in the Pacific Northwest and around the world.

Identification of Pratylenchus thornei, the cereal and legume root-lesion nematode, based on SCAR-PCR and satellite DNA - S. Carrasco-Ballesteros; P. Castillo; B. J. Adams; E. Pérez-Artés (European Journal of Plant Pathology, 2007)

Feeding Selectivity by Mantled Howler Monkeys (Alouatta palliata) in Relation to Leaf Secondary Chemistry in Hymenaea courbaril - B. J. Welker; W. König; M. Pietsch; R. P. Adams (Journal of Chemical Ecology, 2007)

Raman Chemical Imaging for Ingredient-specific Particle Size Characterization of Aqueous Suspension Nasal Spray Formulations: A Progress Report - William H. Doub; Wallace P. Adams; John A Spencer; Lucinda F. Buhse; Matthew P. Nelson; Patrick J. Treado (Pharmaceutical Research, 2007)

Identification of putative ancestors of the multidrug-resistant Salmonella enterica serovar typhimurium DT104 clone harboring the Salmonella genomic island 1 - J. Matiasovicova; P. Adams; P. A. Barrow; H. Hradecka; M. Malcova; R. Karpiskova; E. Budinska; L. Pilousova; I. Rychlik (Archives of Microbiology, 2007)

Locating hybrid individuals in the red wolf (Canis rufus) experimental population area using a spatially targeted sampling strategy and faecal DNA genotyping - JENNIFER R. ADAMS; CHRIS LUCASH; LESLIE SCHUTTE; LISETTE P. WAITS (Molecular Ecology, 2007)
Hybridization with coyotes (Canis latrans) continues to threaten the recovery of endangered red wolves (Canis rufus) in North Carolina and requires the development of new strategies to detect and remove coyotes and hybrids. Here, we combine a spatially targeted faecal collection strategy with a previously published reference genotype data filtering method and a genetic test for coyote ancestry to screen portions of the red wolf experimental population area for the presence of nonred wolf canids. We also test the accuracy of our maximum‐likelihood assignment test for identifying hybrid individuals using eight microsatellite loci instead of the original 18 loci and compare its performance to the Bayesian approach implemented in newhybrids . We obtained faecal DNA genotypes for 89 samples, 73 of which were matched to 23 known individuals. The performance of two sampling strategies — comprehensive sweep and opportunistic spot‐check was evaluated. The opportunistic spot‐check sampling strategy required less effort than the comprehensive sweep sampling strategy but identified fewer individuals. Six hybrids or coyotes were detected and five of these individuals were subsequently captured and removed from the population. The accuracy and power of the genetic test for coyote ancestry is decreased when using eight loci; however, nonred wolf canids are identified with high frequency. This combination of molecular and traditional field‐based approaches has great potential for addressing the challenge of hybridization in other species and ecosystems.

Livestock Trampling Reduces the Conservation Value of Beetle Communities on High Quality Exposed Riverine Sediments - Adam J. Bates; Jon P. Sadler; Adrian P. Fowles (Biodiversity and Conservation, 2007)

ULTRASONOGRAPHIC CHARACTERIZATION OF REPRODUCTIVE ANATOMY AND EARLY EMBRYONIC DETECTION IN THE NORTHERN FUR SEAL ( CALLORHINUS URSINUS ) IN THE FIELD - Gregg P. Adams; J. Ward Testa; Caroline E. C. Goertz; Rolf R. Ream; Jeremy T. Sterling (Marine Mammal Science, 2007)

Pollination and other ecosystem services produced by mobile organisms: a conceptual framework for the effects of land‐use change - Claire Kremen; Neal M. Williams; Marcelo A. Aizen; Barbara Gemmill‐Herren; Gretchen LeBuhn; Robert Minckley; Laurence Packer; Simon G. Potts; T'ai Roulston; Ingolf Steffan‐Dewenter; Diego P. Vázquez; Rachael Winfree; et al. (Ecology Letters, 2007)
Many ecosystem services are delivered by organisms that depend on habitats that are segregated spatially or temporally from the location where services are provided. Management of mobile organisms contributing to ecosystem services requires consideration not only of the local scale where services are delivered, but also the distribution of resources at the landscape scale, and the foraging ranges and dispersal movements of the mobile agents. We develop a conceptual model for exploring how one such mobile‐agent‐based ecosystem service (MABES), pollination, is affected by land‐use change, and then generalize the model to other MABES. The model includes interactions and feedbacks among policies affecting land use, market forces and the biology of the organisms involved. Animal‐mediated pollination contributes to the production of goods of value to humans such as crops; it also bolsters reproduction of wild plants on which other services or service‐providing organisms depend. About one‐third of crop production depends on animal pollinators, while 60–90% of plant species require an animal pollinator. The sensitivity of mobile organisms to ecological factors that operate across spatial scales makes the services provided by a given community of mobile agents highly contextual. Services vary, depending on the spatial and temporal distribution of resources surrounding the site, and on biotic interactions occurring locally, such as competition among pollinators for resources, and among plants for pollinators. The value of the resulting goods or services may feed back via market‐based forces to influence land‐use policies, which in turn influence land management practices that alter local habitat conditions and landscape structure. Developing conceptual models for MABES aids in identifying knowledge gaps, determining research priorities, and targeting interventions that can be applied in an adaptive management context.

Fatigue-induced adaptive changes of anticipatory postural adjustments - Adam J. Strang; William P. Berg (Experimental Brain Research, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols: Part 2—Evaluation of a method for determining equivalence - David Christopher; Wallace P. Adams; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Product Quality Research Institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 1: Background for a statistical method - Wallace P. Adams; David Christopher; Douglas S. Lee; Beth Morgan; Ziqing Pan; Gur Jai Pal Singh; Yi Tsong; Svetlana Lyapustina (AAPS PharmSciTech, 2007)

Development of an in vivo assay to assess attachment of Neoparamoeba sp. (an amphizoic gymnamoeba) to the gills of Atlantic salmon, Salmo salar L. - P B B Crosbie; M B Adams; M G Attard; B F Nowak (Journal of Fish Diseases, 2007)

Characterisation of an isolate of Narcissus degeneration virus from Chinese narcissus (Narcissus tazetta var. chinensis) - J. Chen; Y.-H. Shi; M. J. Adams; H.-Y. Zheng; B.-X. Qin; J.-P. Chen (Archives of Virology, 2007)

The Granites gold deposits, Northern Territory, Australia: evidence for an early syn-tectonic ore genesis - G. J. Adams; R. A. Both; P. James (Mineralium Deposita, 2007)

An efficient method for screening faecal DNA genotypes and detecting new individuals and hybrids in the red wolf (Canis rufus) experimental population area - Jennifer R. Adams; Lisette P. Waits (Conservation Genetics, 2006)

The disruption and recovery of fish communities in the Indian River Lagoon, Florida, following two hurricanes in 2004 - R. Paperno; D. M. Tremain; D. H. Adams; A. P. Sebastian; J. T. Sauer; J. Dutka-Gianelli (Estuaries and Coasts, 2006)

Ex situ bioremediation of phenol contaminated soil using polymer beads - George P. Prpich; Rachel L. Adams; Andrew J. Daugulis (Biotechnology Letters, 2006)

Narcissus symptomless virus: a new carlavirus of daffodils - J. Chen; Y.-H. Shi; Y.-W. Lu; M. J. Adams; J.-P. Chen (Archives of Virology, 2006)

Condition-dependent dispersal of a patchily distributed riparian ground beetle in response to disturbance - Adam J. Bates; Jon P. Sadler; Adrian P. Fowles (Oecologia, 2006)

Selectivity at a three-base bulge site in the DNA binding of ΔΔ-[{Ru(phen)2}2(μ-dppm)]4+ [dppm is 4,6-bis(2-pyridyl)pyrimidine; phen is 1,10-phenanthroline] - Joy L. Morgan; Damian P. Buck; Adam G. Turley; J. Grant Collins; F. Richard Keene (JBIC Journal of Biological Inorganic Chemistry, 2006)

An integrated SSR map of grapevine based on five mapping populations - A. Doligez; A. F. Adam-Blondon; G. Cipriani; G. Di Gaspero; V. Laucou; D. Merdinoglu; C. P. Meredith; S. Riaz; C. Roux; P. This (Theoretical and Applied Genetics, 2006)

Systematic analysis of Dendrobium Swartz section Dendrocoryne in the Australian region - P. B. Adams; J. M. Burke; S. D. Lawson (Plant Systematics and Evolution, 2006)

Complete nucleotide sequence of the genomic RNA of Narcissus yellow stripe virus from Chinese narcissus in Zhangzhou city, China - J. Chen; Y.-W. Lu; Y.-H. Shi; M. J. Adams; J.-P. Chen (Archives of Virology, 2006)

Complete nucleotide sequence and affinities of the genomic RNA of Narcissus common latent virus (genus Carlavirus) - H.-Y. Zheng; J. Chen; M. J. Adams; J.-P. Chen (Archives of Virology, 2006)

The Histidine Operon Is Ancient - Morgan N. Price; Eric J. Alm; Adam P. Arkin (Journal of Molecular Evolution, 2006)

The phylogenetic structure of the cluster of tobamovirus species serologically related to ribgrass mosaic virus (RMV) and the sequence of streptocarpus flower break virus (SFBV) - C. Heinze; D.-E. Lesemann; N. Ilmberger; P. Willingmann; G. Adam (Archives of Virology, 2006)

Gene expression profiling of human alveolar macrophages of phenotypically normal smokers and nonsmokers reveals a previously unrecognized subset of genes modulated by cigarette smoking - Adriana Heguy; Timothy P. O’Connor; Karsta Luettich; Stefan Worgall; Adam Cieciuch; Ben-Gary Harvey; Neil R. Hackett; Ronald G. Crystal (Journal of Molecular Medicine, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Absolute Measurements of Photoluminescence Quantum Yields of Solutions Using an Integrating Sphere - Laurent Porrès; Adam Holland; Lars-Olof Pålsson; Andrew P. Monkman; Chris Kemp; Andrew Beeby (Journal of Fluorescence, 2006)

Current issues in fish welfare - F. A. Huntingford; C. Adams; V. A. Braithwaite; S. Kadri; T. G. Pottinger; P. Sandøe; J. F. Turnbull (Journal of Fish Biology, 2006)
Human beings may affect the welfare of fish through fisheries, aquaculture and a number of other activities. There is no agreement on just how to weigh the concern for welfare of fish against the human interests involved, but ethical frameworks exist that suggest how this might be approached. Different definitions of animal welfare focus on an animal's condition, on its subjective experience of that condition and/or on whether it can lead a natural life. These provide different, legitimate, perspectives, but the approach taken in this paper is to focus on welfare as the absence of suffering. An unresolved and controversial issue in discussions about animal welfare is whether non‐human animals exposed to adverse experiences such as physical injury or confinement experience what humans would call suffering. The neocortex, which in humans is an important part of the neural mechanism that generates the subjective experience of suffering, is lacking in fish and non‐mammalian animals, and it has been argued that its absence in fish indicates that fish cannot suffer. A strong alternative view, however, is that complex animals with sophisticated behaviour, such as fish, probably have the capacity for suffering, though this may be different in degree and kind from the human experience of this state. Recent empirical studies support this view and show that painful stimuli are, at least, strongly aversive to fish. Consequently, injury or experience of other harmful conditions is a cause for concern in terms of welfare of individual fish. There is also growing evidence that fish can experience fear‐like states and that they avoid situations in which they have experienced adverse conditions. Human activities that potentially compromise fish welfare include anthropogenic changes to the environment, commercial fisheries, recreational angling, aquaculture, ornamental fish keeping and scientific research. The resulting harm to fish welfare is a cost that must be minimized and weighed against the benefits of the activity concerned. Wild fish naturally experience a variety of adverse conditions, from attack by predators or conspecifics to starvation or exposure to poor environmental conditions. This does not make it acceptable for humans to impose such conditions on fish, but it does suggest that fish will have mechanisms to cope with these conditions and reminds us that pain responses are in some cases adaptive (for example, suppressing feeding when injured). In common with all vertebrates, fish respond to environmental challenges with a series of adaptive neuro‐endocrine adjustments that are collectively termed the stress response. These in turn induce reversible metabolic and behavioural changes that make the fish better able to overcome or avoid the challenge and are undoubtedly beneficial, in the short‐term at least. In contrast, prolonged activation of the stress response is damaging and leads to immuno‐suppression, reduced growth and reproductive dysfunction. Indicators associated with the response to chronic stress (physiological endpoints, disease status and behaviour) provide a potential source of information on the welfare status of a fish. The most reliable assessment of well‐being will be obtained by examining a range of informative measures and statistical techniques are available that enable several such measures to be combined objectively. A growing body of evidence tells us that many human activities can harm fish welfare, but that the effects depend on the species and life‐history stage concerned and are also context‐dependent. For example, in aquaculture, adverse effects related to stocking density may be eliminated if good water quality is maintained. At low densities, bad water quality may be less likely to arise whereas social interactions may cause greater welfare problems. A number of key differences between fish and birds and mammals have important implications for their welfare. Fish do not need to fuel a high body temperature, so the effects of food deprivation on welfare are not so marked. For species that live naturally in large shoals, low rather than high densities may be harmful. On the other hand, fish are in intimate contact with their environment through the huge surface area of their gills, so they are vulnerable to poor water quality and water borne pollutants. Extrapolation between taxa is dangerous and general frameworks for ensuring welfare in other vertebrate animals need to be modified before they can be usefully applied to fish. The scientific study of fish welfare is at an early stage compared with work on other vertebrates and a great deal of what we need to know is yet to be discovered. It is clearly the case that fish, though different from birds and mammals, however, are sophisticated animals, far removed from unfeeling creatures with a 15 s memory of popular misconception. A heightened appreciation of these points in those who exploit fish and in those who seek to protect them would go a long way towards improving fish welfare.

LST1 and NCR3 expression in autoimmune inflammation and in response to IFN-γ, LPS and microbial infection - H. Mulcahy; K. P. O'Rourke; C. Adams; M. G. Molloy; F. O'Gara (Immunogenetics, 2006)

The influence of broad scale climatic phenomena on long term trends in Atlantic salmon population size: an example from the River Foyle, Ireland - P. Boylan; C. E. Adams (Journal of Fish Biology, 2006)
The effect of marine climatic conditions in the North Atlantic on the abundance of returning migrant Atlantic salmon Salmo salar in the River Foyle, Ireland was examined. Catches of Atlantic salmon from commercial netting stations significantly predicted a measure of population size independent of catches over a 48 year period, thus commercial net catches were used as a measure of relative population size over a longer period in this study. The North Atlantic Oscillation index in winter (wNAOI) provides a generalized measure of climate variation for the northern hemisphere and between 1875 and 2001, the wNAOI was a highly significant predictor of the 5 year running mean of catches of migrant Atlantic salmon returning to the River Foyle. When the index was 0·151, however, this relationship uncoupled. The probability of catches exceeding the long‐term median was 2·34 times lower in years where the wNAOI was above the 0·151 breakpoint than for years when it was

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Complete Mitochondrial DNA Sequences of the Decapod Crustaceans Pseudocarcinus gigas (Menippidae) and Macrobrachium rosenbergii (Palaemonidae) - Adam D. Miller; Nicholas P. Murphy; Christopher P. Burridge; Christopher M. Austin (Marine Biotechnology, 2005)

Estimated Ultraviolet Radiation Doses in Wetlands in Six National Parks - Stephen A. Diamond; Peter C. Trenham; Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Stacey L. Stark; David Bradford; P. Stephen Corn; Ken Czarnowski; Paul D. Brooks; Dan Fagre; Bob Breen; et al. (Ecosystems, 2005)

Hydroxamic Acid Content and Toxicity of Rye at Selected Growth Stages - Clifford P. Rice; Yong Bong Park; Frédérick Adam; Aref A. Abdul-Baki; John R. Teasdale (Journal of Chemical Ecology, 2005)

A potential role for the endothelin ETA receptor in salt-sensitive hypertension of the proANP gene-disrupted mouse - P. F. O’Tierney; E. Angelis; M. Y. Tse; J. J. Pang; M. A. Adams; S. C. Pang (Molecular and Cellular Biochemistry, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

The Development of Marine Toxicity Identification Evaluation (TIE) Procedures Using the Unicellular Alga Nitzschia closterium - A. C. Hogan; J. L. Stauber; F. Pablo; M. S. Adams; R. P. Lim (Archives of Environmental Contamination and Toxicology, 2005)

The complete sequence of the genomic RNA of an isolate of Lily virus X (genus Potexvirus) - J. Chen; Y.-H. Shi; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Hierarchical change in antioxidant enzyme gene expression and activity in acute cardiac rejection: Role of inducible nitric oxide synthase - Vani Nilakantan; XiangHua Zhou; Gail Hilton; Allan M. Roza; Mark B. Adams; Christopher P. Johnson; Galen M. Pieper (Molecular and Cellular Biochemistry, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Neoparamoeba branchiphila n. sp., and related species of the genus Neoparamoeba Page, 1987: morphological and molecular characterization of selected strains - I Dyková; B F Nowak; P B B Crosbie; I Fiala; H Pecková; M B Adams; B Macháčková; H Dvořáková (Journal of Fish Diseases, 2005)
A total of 18 Neoparamoeba strains were characterized both morphologically and using the SSU rRNA gene sequences as molecular markers. Nine were isolated from gills of farmed Atlantic salmon, Salmo salar L., six from sediments sampled in areas of sea‐cage farms and three from net material of sea‐cages. The newly obtained sequences extended substantially the dataset of Neoparamoeba strains available for phylogenetic analyses, which were used to infer taxonomic relatedness among 32 strains morphologically assigned to this genus. In addition to the N. pemaquidensis and N. aestuarina clades, phylogenetic analyses clearly distinguished a third clade with sequences from six strains. Members of this clade are characterized as representatives of a new species, N. branchiphila n. sp. The diagnostic primers for the identification of this species are introduced.

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

Mapping 245 SSR markers on the Vitis vinifera genome: a tool for grape genetics - A. -F. Adam-Blondon; C. Roux; D. Claux; G. Butterlin; D. Merdinoglu; P. This (Theoretical and Applied Genetics, 2004)

The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; S. K. Zavriev; C. M. Fauquet (Archives of Virology, 2004)

Pelargonium necrotic spot virus: a new member of the genus Tombusvirus - C. Heinze; V. Wobbe; D.-E. Lesemann; D. Y. Zhang; P. Willingmann; G. Adam (Archives of Virology, 2004)

Genetic evaluation of a proposed introduction: the case of the greater prairie chicken and the extinct heath hen - Eric P. Palkovacs; Adam J. Oppenheimer; Eugene Gladyshev; John E. Toepfer; George Amato; Thomas Chase; Adalgisa Caccone (Molecular Ecology, 2004)
Population introduction is an important tool for ecosystem restoration. However, before introductions should be conducted, it is important to evaluate the genetic, phenotypic and ecological suitability of possible replacement populations. Careful genetic analysis is particularly important if it is suspected that the extirpated population was unique or genetically divergent. On the island of Martha's Vineyard, Massachusetts, the introduction of greater prairie chickens ( Tympanuchus cupido pinnatus ) to replace the extinct heath hen ( T. cupido cupido ) is being considered as part of an ecosystem restoration project. Martha's Vineyard was home to the last remaining heath hen population until its extinction in 1932. We conducted this study to aid in determining the suitability of greater prairie chickens as a possible replacement for the heath hen. We examined mitochondrial control region sequences from extant populations of all prairie grouse species ( Tympanuchus ) and from museum skin heath hen specimens. Our data suggest that the Martha's Vineyard heath hen population represents a divergent mitochondrial lineage. This result is attributable either to a long period of geographical isolation from other prairie grouse populations or to a population bottleneck resulting from human disturbance. The mtDNA diagnosability of the heath hen contrasts with the network of mtDNA haplotypes of other prairie grouse ( T. cupido attwateri, T. pallidicinctus and T. phasianellus ), which do not form distinguishable mtDNA groupings. Our findings suggest that the Martha's Vineyard heath hen was more genetically isolated than are current populations of prairie grouse and place the emphasis for future research on examining prairie grouse adaptations to different habitat types to assess ecological exchangeability between heath hens and greater prairie chickens.

Storm Surges from Extra-Tropical Cyclones - M. B. Danard; S. K. Dube; G. Gönnert; Adam Munroe; T. S. Murty; P. Chittibabu; A. D. Rao; P. C. Sinha (Natural Hazards, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Morphological and genetic variation within Metrosideros polymorpha (Myrtaceae) on Hawai'i - Shelley A. James; Christopher F. Puttock; Susan Cordell; Robert P. Adams (New Zealand Journal of Botany, 2004)
The highly polymorphic taxon Metrosideros polymorpha ('ohi'a) is the most abundant endemic tree in Hawai'i, occupying a wide but fragmented range of habitats across Federal, State, and privately managed lands. Morphological character states of 342 herbarium specimens from the island of Hawai'i distributed the five recognised varieties in ordinal space, but intermediate pheno‐types were prevalent. Morphological and random amplified polymorphic DNA (RAPD) analyses were undertaken for 10 individuals at 3 sites on Hawai'i. Individuals at a high‐elevation dry site and mid‐elevation dry site had smaller, pubescent leaves with a higher leaf mass per area and nitrogen content than individuals at a moist mid‐elevation site. While the populations were separated in ordinal space, taxo‐nomic varieties overlapped. The high degree of overlap between the taxonomic varieties, based on genetic and morphological characteristics, does not support the current varietal subdivision of Metrosideros polymorpha on Hawai'i.

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Virology Division News: The new plant virus family Flexiviridae and assessment of molecular criteria for species demarcation - M. J. Adams; J. F. Antoniw; M. Bar-Joseph; A. A. Brunt; T. Candresse; G. D. Foster; G. P. Martelli; R. G. Milne; C. M. Fauquet (Archives of Virology, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

Late Pleistocene Vegetation and Climate in the Southern Cascade Range and the Modoc Plateau Region - Katharine J. Hakala; David P. Adam (Journal of Paleolimnology, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

Levels of apolipoprotein A-II in cerebrospinal fluid in patients with neuroborreliosis are associated with lipophagocytosis - L. Táborský; P. Adam; O. Sobek; M. Dostál; J. Dvořáková; L. Dubská (Folia Microbiologica, 2003)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Pedigree‐based assignment tests for reversing coyote ( Canis latrans ) introgression into the wild red wolf ( Canis rufus ) population - Craig R. Miller; Jennifer R. Adams; Lisette P. Waits (Molecular Ecology, 2003)
The principal threat to the persistence of the endangered red wolf ( Canis rufus ) in the wild is hybridization with the coyote ( Canis latrans ). To facilitate idengification and removal of hybrids, assignment tests are developed which use genotype data to estimate identity as coyote, 1 / 4 , 1 / 2 , 3 / 4 or full red wolf. The tests use genotypes from the red wolves that founded the surviving population and the resulting pedigree, rather than a contemporary red wolf sample. The tests are evaluated by analysing both captive red wolves at 18 microsatellite loci, and data simulated under a highly parameterized, biologically reasonable model. The accuracy of assignment rates are generally high, with over 95% of known red wolves idengified correctly. There are, however, tradeoffs between ambiguous assignments and misassignments, and between misidengifying red wolves as hybrids and hybrids as red wolves. These result in a compromise between limiting introgression and avoiding demographic losses. The management priorities and level of introgression determine the combination of test and removal strategy that best balances these tradeoffs. Ultimately, we conclude that the use of the assignment tests has the capacity to arrest and reverse introgression. To our knowledge, the presented approach is novel in that it accounts for genetic drift when the genotypes under analysis are temporally separated from the reference populations to which they are being assigned. These methods may be valuable in cases where reference databases for small populations have aged substantially, pedigree information is available or data are generated from historical samples.

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Source monitoring improvement in patients with schizophrenia receiving antipsychotic medications - Richard S. E. Keefe; Margaret P. Poe; Joseph P. McEvoy; Adam Vaughan (Psychopharmacology, 2003)

Predicting Oral Absorption of Drugs: A Case Study with a Novel Class of Antimicrobial Agents - Allen R. Hilgers; Donald P. Smith; John J. Biermacher; Jeffrey S. Day; Jana L. Jensen; Sandra M. Sims; Wade J. Adams; Janice M. Friis; Joe Palandra; John D. Hosley; Eric M. Shobe; Philip S. Burton (Pharmaceutical Research, 2003)

Using faecal DNA sampling and GIS to monitor hybridization between red wolves ( Canis rufus ) and coyotes ( Canis latrans ) - J. R. Adams; B. T. Kelly; L. P. Waits (Molecular Ecology, 2003)
The US Fish and Wildlife Service's (USFWS) Red Wolf Recovery Program recognizes hybridization with coyotes as the primary threat to red wolf recovery. Efforts to curb or stop hybridization are hampered in two ways. First, hybrid individuals are difficult to identify based solely on morphology. Second, managers need to effectively search 6000 km 2 for the presence of coyotes and hybrids. We develop a noninvasive method to screen large geographical areas for coyotes and hybrids with maternal coyote ancestry by combining mitochondrial DNA sequence analysis of faeces (scat) and geographic information system (GIS) technology. This method was implemented on the Alligator River National Wildlife Refuge (1000 km 2 ) in northeastern North Carolina. A total of 956 scats were collected in the spring of 2000 and 2001 and global positioning system (GPS) coordinates were recorded. Seventy‐five percent of the scats were assigned to species and five coyote/hybrid scats were detected. Placement of scat location coordinates on a map of the experimental population area revealed that four of the coyote/hybrid scats were detected within the home ranges of sterilized hybrids. The other coyote/hybrid scat indicated the presence of a previously unknown individual. We suggest this method be expanded to include more of the experimental population area and be optimized for use with nuclear markers to improve detection of hybrid and back‐crossed individuals.

Diadema antillarum 17 years after mass mortality: is recovery beginning on St. Croix? - R. J. Miller; A. J. Adams; N. B. Ogden; J. C. Ogden; J. P. Ebersole (Coral Reefs, 2003)

Lack of genetic divergence found with microsatellite DNA markers in the tarakihi Nemadactylus macropterus - Christopher P. Burridge; Adam J. Smolenski (New Zealand Journal of Marine and Freshwater Research, 2003)
Three classes of molecular markers are commonly employed during population genetic studies of marine taxa: allozymes, mitochondrial DNA (mtDNA), and microsatellite DNA. These markers differ in their levels of polymorphism, and the ease and cost of their application. Nemadactylus macropterus is a commercially important marine fish from New Zealand and southern Australia that has been the subject of genetic (allozyme, mtDNA) and non‐genetic (otolith microchemistry, larval advection) studies of stock structure. We collected microsatellite DNA data from this species to compare the utility of these molecular markers with those genetic methods previously applied to N. macropterus . Microsatellites did not indicate significant divergence among Australian samples, or between Australian and New Zealand samples. The latter is incongruent with the allozyme and mtDNA studies, and it is suggested that allelic homoplasy has hindered the resolution of population structure when using microsatellites.

A novel fibrocartilaginous tendon from an elasmobranch fish (Rhinoptera bonasus) - Adam P. Summers; Magdalena M. Koob-Emunds; Stephen M. Kajiura; Thomas J. Koob (Cell and Tissue Research, 2003)

Sequence analysis demonstrates that Onion yellow dwarf virus isolates from China contain a P3 region much larger than other potyviruses - J. Chen; M. J. Adams; H.-Y. Zheng; J.-P. Chen (Archives of Virology, 2003)

Scientific Considerations of Pharmaceutical Solid Polymorphism in Abbreviated New Drug Applications - Lawrence X. Yu; M. Scott Furness; Andre Raw; Kathy P. Woodland Outlaw; Nashed E. Nashed; Edwin Ramos; Stephen P. F. Miller; Richard C. Adams; Florence Fang; Rashmikant M. Patel; Frank O. Holcombe; Yuan-yuan Chiu; et al. (Pharmaceutical Research, 2003)

Sphagnum in peatlands of Australasia: Their distribution, utilisation and management - J. Whinam; G.S. Hope; B.R. Clarkson; R.P. Buxton; P.A. Alspach; P. Adam (Wetlands Ecology and Management, 2003)

Widespread occurrence of a domestic dog mitochondrial DNA haplotype in southeastern US coyotes - J. R. Adams; J. A. Leonard; L. P. Waits (Molecular Ecology, 2003)
Sequence analysis of the mitochondrial DNA control region from 112 southeastern US coyotes ( Canis latrans ) revealed 12 individuals with a haplotype closely related to those in domestic dogs. Phylogenetic analyses grouped this new haplotype in the dog/grey wolf ( Canis familiaris / Canis lupus ) clade with 98% bootstrap support. These results demonstrate that a male coyote hybridized with a female dog, and female hybrid offspring successfully integrated into the coyote population. The widespread distribution of this haplotype from Florida to West Virginia suggests that the hybridization event occurred long ago before the southeastern USA was colonized by coyotes. However, it could have occurred in the southeastern USA before the main front of coyotes arrived in the area between male coyotes released for sport and a local domestic dog. The introgression of domestic dog genes into the southeastern coyote population does not appear to have substantially affected the coyote's genetic, morphological, or behavioural integrity. However, our results suggest that, contrary to previous reports, hybridization can occur between domestic and wild canids, even when the latter is relatively abundant. Therefore, hybridization may be a greater threat to the persistence of wild canid populations than previously thought.

Effect of the proteasome inhibitor MLN519 on the expression of inflammatory molecules following middle cerebral artery occlusion and reperfusion in the rat - R. Berti; A. J. Williams; L. C. Velarde; J. R. Moffett; P. J. Elliott; J. Adams; C. Yao; J. R. Dave; F. C. Tortella (Neurotoxicity Research, 2003)

An unusual large intergenic region in the S-RNA of a Bulgarian tomato spotted wilt virus isolate - C. Heinze; P. Willingmann; F. Schwach; G. Adam (Archives of Virology, 2003)

The dynamics and ecology of exotic tropical species in floating plant mats: Lake Naivasha, Kenya - C. S. Adams; R. R. Boar; D. S. Hubble; M. Gikungu; D. M. Harper; P. Hickley; N. Tarras-Wahlberg (Hydrobiologia, 2002)

Identification of a role for actin in translational fidelity in yeast - K. Kandl; R. Munshi; P. Ortiz; G. Andersen; T. Kinzy; A. Adams (Molecular Genetics and Genomics, 2002)

Estimated migration rates under scenarios of global climate change - Jay R. Malcolm; Adam Markham; Ronald P. Neilson; Michael Garaci (Journal of Biogeography, 2002)
Aim Greenhouse‐induced warming and resulting shifts in climatic zones may exceed the migration capabilities of some species. We used fourteen combinations of General Circulation Models (GCMs) and Global Vegetation Models (GVMs) to investigate possible migration rates required under CO 2 ‐doubled climatic forcing. Location Global. Methods Migration distances were calculated between grid cells of future biome type x and nearest same‐biome‐type cells in the current climate. In `base‐case' calculations, we assumed that 2 × CO 2 climate forcing would occur in 100 years, we used ten biome types and we measured migration distances as straight‐line distances ignoring water barriers and human development. In sensitivity analyses, we investigated different time periods of 2 × CO 2 climate forcing, more narrowly defined biomes and barriers because of water bodies and human development. Results In the base‐case calculations, average migration rates varied significantly according to the GVM used (BIOME3 vs. MAPSS), the age of the GCM (older‐ vs. newer‐generation GCMs), and whether or not GCMs included sulphate cooling or CO 2 fertilization effects. However, high migration rates (≥ 1000 m year −1 ) were relatively common in all models, consisting on average of 17% grid cells for BIOME3 and 21% for MAPSS. Migration rates were much higher in boreal and temperate biomes than in tropical biomes. Doubling of the time period of 2 × CO 2 forcing reduced these areas of high migration rates to c . 12% of grid cells for both BIOME3 and MAPSS. However, to obtain migration rates in the Boreal biome that were similar in magnitude to those observed for spruce when it followed the retreating North American Glacier, a radical increase in the period of warming was required, from 100 to >1000 years. A reduction in biome area by an order of magnitude increased migration rates by one to three orders of magnitude, depending on the GVM. Large water bodies and human development had regionally important effects in increasing migration rates. Main conclusions In conclusion, evidence from coupled GCMs and GVMs suggests that global warming may require migration rates much faster than those observed during post‐glacial times and hence has the potential to reduce biodiversity by selecting for highly mobile and opportunistic species. Several poorly understood factors that are expected to influence the magnitude of any such reduction are discussed, including intrinsic migrational capabilities, barriers to migration, the role of outlier populations in increasing migration rates, the role of climate in setting range limits and variation in species range sizes.

Bioaccumulation of 110mAg, 60Co, 137Cs and 54Mn by the Freshwater Crustacean Daphnia magna from Dietary sources (Scenedesmus obliquus and Cyclotella meneghiana) - C. Adam; J. Garnier-Laplace; J. P. Baudin (Water, Air, & Soil Pollution, 2002)

Content Uniformity and Dose Uniformity: Current Approaches, Statistical Analyses, and Presentation of an Alternative Approach, with Special Reference to Oral Inhalation and Nasal Drug Products - Roger L. Williams; Wallace P. Adams; Guirag Poochikian; Walter W. Hauck (Pharmaceutical Research, 2002)

Characterisation of a potyvirus and a potexvirus from Chinese scallion - J. Chen; H. Y. Zheng; J. P. Chen; M. J. Adams (Archives of Virology, 2002)

Mapping QTLs associated with drought avoidance in upland rice grown in the Philippines and West Africa - Adam H. Price; John Townend; Monty P. Jones; Alain Audebert; Brigitte Courtois (Plant Molecular Biology, 2002)

Impact of Cadmium and Zinc Prior Exposure on 110m Silver, 58+60 Cobalt and 137 Cesium Uptake by Two Freshwater Bivalves During a Brief Field Experiment - C. Adam; B. Fraysse; J. Garnier-Laplace; J. P. Baudin; A. Boudou (Bulletin of Environmental Contamination and Toxicology, 2002)

The population genetics of host specificity: genetic differentiation in dove lice (Insecta: Phthiraptera) - Kevin P Johnson; Barry L Williams; Devin M Drown; Richard J Adams; Dale H Clayton (Molecular Ecology, 2002)
Some species of parasites occur on a wide range of hosts while others are restricted to one or a few host species. The host specificity of a parasite species is determined, in part, by its ability to disperse between host species. Dispersal limitations can be studied by exploring the genetic structure of parasite populations both within a single species of host and across multiple host species. In this study we examined the genetic structure in the mitochondrial cytochrome oxidase I (COI) gene of two genera of lice (Insecta: Phthiraptera) occurring on multiple sympatric species of doves in southern North and Central America. One genus, Columbicola , is generally less host‐specific than the other, Physconelloides . For both genera we identified substantial genetic differentiation between populations of conspecific lice on different host species, generally 10–20% sequence divergence. This level of divergence is in the range of that often observed between species of these two genera. We used nested clade analysis to explore fine scale genetic structure within species of these feather lice. We found that species of Physconelloides exhibited more genetic structure, both among hosts and among geographical localities, than did species of Columbicola . In many cases, single haplotypes within species of Columbicola are distributed on multiple host species. Thus, the population genetic structure of species of Physconelloides reveals evidence of geographical differentiation on top of high host species specificity. Underlying differences in dispersal biology probably explain the differences in population genetic structure that we observed between Columbicola and Physconelloides .

Establishment of a local map of AFLP markers around the powdery mildew resistance gene Run1 in grapevine and assessment of their usefulness for marker assisted selection - J. Pauquet; A. Bouquet; P. This; A.-F. Adam-Blondon (Theoretical and Applied Genetics, 2001)

Molecular characterisation of segments 1 to 6 of Rice black-streaked dwarf virus from China provides the complete genome - H. M. Zhang; J. P. Chen; M. J. Adams (Archives of Virology, 2001)

Incidence of squamous neoplasia of the cervix and vagina in women exposed prenatally to diethylstilbestrol (United States) - E. E. Hatch; A. L. Herbst; R. N. Hoover; K. L. Noller; E. Adam; R. H. Kaufman; J. R. Palmer; L. Titus-Ernstoff; M. Hyer; P. Hartge; S. J. Robboy (Cancer Causes & Control, 2001)

Genomic analysis of common chimpanzee major histocompatibility complex class I genes - E.J. Adams; P. Parham (Immunogenetics, 2001)

Mean Annual Temperature and Total Annual Precipitation Trends at Canadian Biosphere Reserves - James P. Hamilton; Graham S. Whitelaw; Adam Fenech (Environmental Monitoring and Assessment, 2001)

Kinetics of 110mAg, 60Co, 137Cs and 54Mn Bioaccumulation from Water and Depuration by the Crustacean Daphnia Magna - C. Adam; J. P. Baudin; J. Garnier-Laplace (Water, Air, & Soil Pollution, 2001)

Mesophyll-specific, light and metabolic regulation of the C4 PPCZm1 promoter in transgenic maize - Albert P. Kausch; T. Page Owen; Susan J. Zachwieja; Adam R. Flynn; Jen Sheen (Plant Molecular Biology, 2001)

Variation in isomeric products of a phosphodiesterase from the chloroplasts of Phaseolus vulgaris in response to cations - Penny E. Diffley; Alan Geisbrecht; Russell P. Newton; Michael Oliver; Christopher J. Smith; Judith Vaughan; Jan van Cleef; Jan van Geyschem; Terence J. Walton; Mark Bayliss; A. Gareth Brenton; Frank M. Harris; et al. (Plant Biosystems, 2001)

High-throughput synthesis and screening of platinum drug candidates - Christopher J. Ziegler; Adam P. Silverman; Stephen J. Lippard (JBIC Journal of Biological Inorganic Chemistry, 2000)

A Piscirickettsia salmonis ‐like organism in grouper, Epinephelus melanostigma , in Taiwan - S‐C Chen; P‐C Wang; M‐C Tung; K D Thompson; A Adams (Journal of Fish Diseases, 2000)

Evidence for the involvement of dietary lipids on the modulation of transforming growth factor-β1 in the platelets of male rats - Jay M. Adam; Jayadev Raju; Nasreen Khalil; Ranjana P. Bird (Molecular and Cellular Biochemistry, 2000)

Experimental Kinetic Rates of Food-Chain and Waterborne Radionuclide Transfer to Freshwater Fish: A Basis for the Construction of Fish Contamination Charts - J. Garnier-Laplace; C. Adam; J. P. Baudin (Archives of Environmental Contamination and Toxicology, 2000)

Spectroscopic studies of the tungsten-containing formaldehyde ferredoxin oxidoreductase from the hyperthermophilic archaeon Thermococcus litoralis - Ish K. Dhawan; Roopali Roy; Brian P. Koehler; Swaranalatha Mukund; Michael W. W. Adams; Michael K. Johnson (JBIC Journal of Biological Inorganic Chemistry, 2000)

Changes in reproductive strategy in the ruffe during a period of establishment in a new habitat - J. A. Devine; C. E. Adams; P. S. Maitland (Journal of Fish Biology, 2000)
The pattern of maturation, body size and fecundity was examined in a population of ruffe ( Gymnocephalus cernuus L.) three times during a period of rapid growth, and eventual stabilization, following its introduction to a new habitat. When the ruffe were less common, maturing ruffe were relatively large and immature ruffe relatively small, compared with when the ruffe were abundant. Intermediate ruffe population size showed a maturation pattern intermediate between these two extremes. It is suggested that this pattern of maturation is a response of the ruffe population to changing growth opportunity induced by changing intraspecific competition. This fluctuating maturation pattern is interpreted in terms of a threshold‐dependent maturation trigger, operating on the rate of accumulation of energy and a trade‐off between somatic growth and gonad development. When the ruffe population was large, high intraspecific competition resulted in low opportunity for growth; only fish with the highest rate of food acquisition were able to mature in a given year–the investment in gonadal tissue reducing somatic growth. When the ruffe population was low, the high rate of energy acquisition in the population resulted in the triggering of maturation, even at small size, only the very smallest fish remaining immature. High growth opportunity allowed maturing fish to develop gonad and maintain somatic growth. The pattern of size related fecundity also changed over the three periods. When growth opportunity was low, size related fecundity was greater than when opportunity for growth was high. This suggests that maturing females faced with poor growth conditions compensated by increasing egg number for a given body size either by decreasing egg size or by increasing total investment in ovarian tissue.

Common chimpanzees have greater diversity than humans at two of the three highly polymorphic MHC class I genes - E.J. Adams; Stewart Cooper; Glenys Thomson; P. Parham; E. Adams (Immunogenetics, 2000)

Renal effects of cyclooxygenase inhibitors in volume-depleted dogs - David P. Brooks; Jerry Adams; P. Dennis DePalma; Edward F. Webb; Robert H. Palmer; Don E. Griswold (Inflammopharmacology, 2000)

A deletion on Chromosome 4 cosegregates with the whirler deafness mutation: exclusion of Orm1 as a candidate - Adam J.W. Paige; Brent W. Kiernan; Anabel Varela; Michael J.C. Rogers; David Hughes; Karen P. Steel; Steve D.M. Brown (Mammalian Genome, 2000)

Subannual Temporal Variation in Faunal Distributions at the TAG Hydrothermal Mound (26° N, Mid‐Atlantic Ridge) - Jonathan T. P. Copley; Paul A. Tyler; Cindy L. Van Dover; Adam Schultz; Penny Dickson; Sandipa Singh; Margaret Sulanowska (Marine Ecology, 1999)
This paper evaluates the dynamics of two faunal assemblages colonizing high‐ and low‐temperature habitats of the TAG hydrothermal mound on the Mid‐Atlantic Ridge. Timelapse video and photographic transects were used to monitor changes in shrimp and anemone populations from June 1994 to March 1995. During this period, holes were drilled in the vicinity of the target populations by the Ocean Drilling Program (ODP). The a priori expectation of a rapid redistribution of motile alvinocaridid shrimp to occupy the optimal thermal and chemical habitat in response to changes in the pattern of hydrothermal activity was met by the observation of an increase in hydrothermal activity and shrimp population density at the site where a timelapse video system was deployed. The importance of hydrothermal activity as a control on the distribution of vent shrimp is suggested by tidal variations in the distribution of shrimp on a minidiffuser chimney. Sediment deposition during ODP drilling resulted in a temporary disturbance of the shrimp occupying the flat part of the mound surface seen by the timelapse video. In contrast to the changes observed in shrimp distribution, little change was observed in the distribution of anemones across the mound in two photographic transects 10 months apart, with the exception of a localized disturbance where anemones were buried by sediment around an ODP hole. Differences in the response of the shrimp and anemones to changes in the hydrothermal system may result from differences in their motility and rates of biological activity, or reflect a lower trophic position in the case of the shrimp.

Evidence for an HLA-C -like locus in the orangutan Pongo pygmaeus - Glenys Thomson; Erin J. Adams; P. Parham (Immunogenetics, 1999)

Organochlorines in Stranded Pilot Whales ( Globicephala melaena ) from the Coast of Massachusetts - K. L. Tilbury; N. G. Adams; C. A. Krone; J. P. Meador; G. Early; U. Varanasi (Archives of Environmental Contamination and Toxicology, 1999)

Quantitative Determination of Gap Junctional Permeability in the Lens Cortex - R. Eckert; B. Adams; J. Kistler; P. Donaldson (The Journal of Membrane Biology, 1999)

Comparison of the depression of H-reflexes following previous activation in upper and lower limb muscles in human subjects - Christiane Rossi-Durand; Kelvin E. Jones; Simon Adams; P. Bawa (Experimental Brain Research, 1999)

Preservation of DNA in plant specimens: inactivation and re‐activation of Dnases in field specimens - R P. Adams; M. Zhong; Y. Fei (Molecular Ecology, 1999)

Genetic diversity in the moss Hennediella heimii in Miers Valley, southern Victoria Land, Antarctica - T. M. Dale; M. L. Skotnicki; K. D. Adam; P. M. Selkirk (Polar Biology, 1999)

European Surveillance of Infections and Risk Factors in Cancer Patients - D. Buchheidt; W. Hiddemann; X. Schiel; V. Krcmery; M. Karthaus; J. P. Donnelly; M. Wilhelm; G. Maschmeyer; H. Link; D. Adam; M. Helmerking (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Nutrient cycling and growth in forest ecosystems of south western Australia: Relevance to agricultural landscapes - P. F. Grierson; M. A. Adams (Agroforestry Systems, 1999)

Short tandem repeat polymorphic markers for the rat genome from marker-selected libraries - Roxanne Y. Walder; Michael R. Garrett; Ann M. McClain; Gretel E. Beck; Theresa M.H. Brennan; Nancy A. Kramer; Adam B. Kanis; Allyn L. Mark; John P. Rapp (Mammalian Genome, 1998)

Towards an integrated linkage map of common bean. 4. Development of a core linkage map and alignment of RFLP maps - R. Freyre; P. W. Skroch; V. Geffroy; A.-F. Adam-Blondon; A. Shirmohamadali; W. C. Johnson; V. Llaca; R. O. Nodari; P. A. Pereira; S.-M. Tsai; J. Tohme; M. Dron; et al. (Theoretical and Applied Genetics, 1998)

The effects of non-homology in RAPD bands on similarity and multivariate statistical ordination in Brassica and Helianthus - R. P. Adams; L. H. Rieseberg (Theoretical and Applied Genetics, 1998)

DNA fingerprinting reveals clonal nature of Vetiveria zizanioides (L.) Nash, Gramineae and sources of potential new germplasm - R. P. ADAMS; M. ZHONG† Y. TURUSPEKOV; M. R. DAFFORN; J. F. VELDKAMP (Molecular Ecology, 1998)
Random amplified polymorphic DNAs (RAPDs) were used to examine accessions of vetiver ( Vetiveria zizanioides (L.) Nash, Gramineae) from around the world. It appears that only one genotype, ‘Sunshine’, accounts for almost all the germplasm utilized. Screening of numerous accessions of vetiver revealed only a few nonfertile germlines. Analysis of V . zizanioides and other Vetiveria species, Chrysopogon fulvus (Spreng.) Chiov., C . gryllus (L.) Trin., Sorghum bicolour (L.) Moench., and S . halepense (L.) Pers., revealed that Vetiveria and Chrysopogon are not separable by their RAPDs. This lends support to merging the genus Vetiveria with Chrysopogon . The lack of genetic diversity in this important cultivated plant is a critical factor and additional, suitable germplasm must be collected and introduced into erosion control projects around the world.

A family of LRR sequences in the vicinity of the Co-2 locus for anthracnose resistance in Phaseolus vulgaris and its potential use in marker-assisted selection - V. Geffroy; F. Creusot; J. Falquet; M. Sévignac; A.-F. Adam-Blondon; H. Bannerot; P. Gepts; M. Dron (Theoretical and Applied Genetics, 1998)

A major histocompatibility complex class I allele shared by two species of chimpanzee - Stewart Cooper; Erin J. Adams; R. Spencer Wells; Christopher M. Walker; P. Parham (Immunogenetics, 1998)

Sensitivity of isoenzyme analysis for the detection of interspecies cell line cross-contamination - Raymond W. Nims; Adam P. Shoemaker; Marcie A. Bauernschub; Laura J. Rec; John W. Harbell (In Vitro Cellular & Developmental Biology - Animal, 1998)

Anatomical evidence for androdioecy in the clam shrimp Eulimnadia texana - Naida Zucker; Mark Cunningham; Henry P. Adams (Hydrobiologia, 1997)

A Comparison of Female Postcopulatory Behavior in Drosophila melanogaster and Drosophila biarmipes - Scott P. McRobert; Carissa R. Adams; Mark Wuttke; Jennifer Frank; Larry L. Jackson (Journal of Insect Behavior, 1997)

Comparative Bioaccumulation of Chlorinated Hydrocarbons from Sediment by Two Infaunal Invertebrates - J. P. Meador; N. G. Adams; E. Casillas; J. L. Bolton (Archives of Environmental Contamination and Toxicology, 1997)

Genetic variation in Antarctic populations of the moss Sarconeurum glaciale - J. Armstrong; P. M. Selkirk; M. B. Connett; T. W. Joe; M. Skotnicki; K. D. Adam; T. Dale (Polar Biology, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Sex ratios, local fitness enhancement and eusociality in the allodapine bee Exoneura richardsoni - Adam L. Cronin; Michael P. schwarz (Evolutionary Ecology, 1997)

60 Co Transfer from Water to the Rainbow Trout ( Oncorhynchus mikiss Walbaum) - J. P. Baudin; M. P. Véran; C. Adam; J. Garnier-Laplace (Archives of Environmental Contamination and Toxicology, 1997)

The cardiac effects of terfenadine after inhibition of its metabolism by grapefruit juice - C. P. Clifford; D. A. Adams; S. Murray; G. W. Taylor; M. R. Wilkins; A. R. Boobis; D. S. Davies (European Journal of Clinical Pharmacology, 1997)

Clonal Atlantic salmon × brown trout hybrids produced by gynogenesis - P. F. Galbreath; K. J. Adams; P. A. Wheeler; G. H. Thorgaard (Journal of Fish Biology, 1997)
Clonal full‐sib progeny groups of Atlantic salmon Salmo salar × brown trout Salmo trutta hybrids were produced by gynogenesis. Eggs obtained from two 3‐year‐old Atlantic salmon (female) × brown trout (male) F 1 hybrids were activated with UV‐irradiated rainbow trout Oncorhynchus mykiss sperm. Fecundity, percentage egg activation and percentage survival to completion of yolk‐sac absorption were similar for the two females, and averaged 800 eggs kg −1 , 90 and 65%, respectively. Flow cytometric and protein electrophoretic analyses confirmed the progeny to be diploid hybrids. Isogenicity within progeny groups and to the maternal parent was indicated by identical DNA fingerprint patterns detected with multilocus oligonucleotide probes–GATA (5) and ACTG (n) . Isogenicity was also observed in the gynogenetic progeny of a third female spawned the following year. It appeared that a large portion of the oocytes in females of this hybrid underwent a premeiotic chromosome doubling, or possibly a complete suppression of meiosis. The result was ovulation of diploid eggs, each possessing a full set of both Atlantic salmon and brown trout chromosomes identical to those in the maternal somatic cells. Lines of clonal hybrids could therefore be perpetuated by gynogenesis and would have potential both as experimental animals and in commercial aquaculture.

Falsified or forged medical prescriptions as an indicator of pharmacodependence: A pilot study - M. Lapeyre-Mestre; C. Damase-Michel; P. Adams; P. Michaud; J. L. Montastruc (European Journal of Clinical Pharmacology, 1997)

Role of hydrazine in the mechanism of isoniazid hepatotoxicity in rabbits - Troy C. Sarich; Mohammed Youssefi; Ting Zhou; Stephen P. Adams; Richard A. Wall; J. M. Wright (Archives of Toxicology, 1996)

Levels of polyandry and intracolonial genetic relationships in Apis florea - Benjamin P. Oldroyd; Adam J. Smolenski; Jean-Marie Cornuet; Siriwat Wongsiri; Arnaud Estoup; Thomas E. Rinderer; Ross H. Crozier (Behavioral Ecology and Sociobiology, 1995)

Levels of polyandry and intracolonial genetic relationships in Apis florea - B. P. Oldroyd; Adam J. Smolenski; Jean-Marie Cornuet; Siriwat Wongsiri; Arnaud Estoup; Thomas E. Rinderer; Ross H. Crozier (Behavioral Ecology and Sociobiology, 1995)

Equine infectious anemia virus (EIAV) Humoral responses of recipient ponies and antigenic variation during persistent infection - P. M. Rwambo; C. J. Issel; W. V. Adams; K. A. Hussain; M. Miller; R. C. Montelaro (Archives of Virology, 1990)

Validation of a simple potato growth model in the North Central United States - K. B. Johnson; R. L. Conlon; S. S. Adams; D. C. Nelson; D. I. Rouse; P. S. Teng (American Journal of Potato Research, 1988)

Estimating medullary chemoreceptor blood flow from ventilatory-CO2 response transients: Theory and data from anesthetized dogs - J. Milton Adams; William P. Glasheen; Matthew L. Severns (Annals of Biomedical Engineering, 1984)

The effect of venturicidin on light and oxygen-dependent electron transport, proton translocation, membrane potential development and ATP synthesis in intact cells of Rhodopseudomonas capsulata - Nicholas P. J. Cotton; Adam J. Clark; J. Barry Jackson (Archives of Microbiology, 1981)

Inheritance of red cell glucose-phosphate isomerase in the Australian marsupial, Dasyuroides byrnei - M. Adams; P. R. Baverstock; H. J. Aslin (Biochemical Genetics, 1981)

Lead-induced leukocytosis in female mice - G. R. Hogan; D. P. Adams (Archives of Toxicology, 1979)

Soil compaction and potato growth - G. R. Blake; D. H. Bofxter; E. P. Adams; J. K. Aase (American Journal of Potato Research, 1960)

How can we interpret the zero tolerance for bacterial ring rot in certified seed potatoes - C. E. Logsdon; H. W. Poulsen; John J. Adams; J. W. Scannell; C. W. Frutchey; Robert Hickman; T. C. Blackburn; J, L. Robinson; E. L. Newdick; Paul J. Eastman; L. O. Weaver; H. C. Moore; et al. (American Journal of Potato Research, 1957)

Potato foliage development - R. A. Kelley; J. B. Adams; P. H. Baird (American Journal of Potato Research, 1953)